THEORY AND PRACTICE OF LAW LIBRARIANSHIP THROUGH CONTINUING PROFESSIONAL EDUCATION: THE NIGERIAN EXPERIENCE - Jegede, Olugbemiro J. (1997)
The essay is the three parts. The first part deals with issues/indicators for the need of the continuing professional education (CPE) for librarians working in law libraries. The next segment of the essay discusses the introduction of the CPE programme: objectives, whom is it designed for? etc. Reasons for choosing the faculty members are analysed. The changes in the course-content reflect the changing needs of the librarians. The concluding part advocates that the CPE programmes should commensurate with the general level of the practice of librarianship in the individual countries. What is important however is that each CPE programme should be continuously evaluated to make sure its original objectives are achieved. The CPE programme by the Nigerian Institute of Advanced Legal Studies, serves not only the librarians from the law libraries and later on the librarians from other special libraries to up date their knowledge and practice of librarianship; but also serves library users, and policy makers to achieve better library and information services for national development.
openalex: W2485260474 mag: 2485260474
Keywords: openalex:import

CLOSING THE INFORMATION TECHNOLOGY GAP: TYPICAL TRAINING CONCERNS IN A SOUTH AFRICAN UNIVERSITY LIBRARY IN THE 1990s - Walker, Clare M. (1997)
This paper describes approaches to developing and maintaining a staff training and CPE programme in the Library of the University of the Witwatersrand, Johannesburg (Wits Library).
openalex: W2484571110 mag: 2484571110
Keywords: openalex:import

Telling It like It Is about the African-American Students' Plight - Todd, Leon W. (Education 3-13, 1997)
The most segregated time of every week in America, it has been said, eleven o'clock on Sunday mornings. On the Sunday morning of January 12, 1992, Milwaukee School Superintendent J. Howard Fuller made his way to Mount Carmel Lutheran Church, on the Northwest Side, to talk about what he was trying to accomplish in the public schools. As an ongoing part of the Crusade to Save Our Children, Fuller had been doing this pretty much every Sunday, but on this particular one his cool composure finally cracked. It happened during the question-and-answer period that followed his talk and it had to do with Chapter 220, the program that allowed students from city schools to attend suburban ones and vice versa. Since its inception in 1976, the program had been, like so much else that involved the tentacles of race, an intricate flash point of anger, resentment, and opportunity. Many people wanted to see the program abolished altogether. A Teacher Explains Problem In any case, a woman stood up and identified herself as a member of the faculty at Shorewood Middle School. She was concerned, she said, that there wasn't enough money in their budget so that `your kids' could stay around after school to get extra help and still have a bus to take them home. My view, Fuller said, is that when a kid comes into your school district, that your She didn't respond to that. She simply said it was her understanding that nothing could be done about the situation. Fuller didn't agree. The question what do you think ought to be done for those children and what do you do for the children in your district? They Are Suburban Students a Milwaukee kid decides to come to a suburban school, in my opinion that kid now belongs to that suburban district, just like any other kid. If you all think that these kids should all have these experiences, they are your kids, so you should think about how you are going to come up with the resources to be sure that your kids have what they ought to have, because they are your kids. If they are sent to your school district and they are not your kids, then whose kids are they? Fuller Wanted All Children to Come First This was why Fuller took the job of superintendent, to make sure that all children came first, and that their interests were served. To know intellectually that a Shorewood or a Wauwatosa was reluctantly opening its hallowed halls but not allowing Milwaukee kids to feel fully welcome was one thing, but to hear a teacher so openly raise the polarizing issue of whom they belonged to was quite another. It was more than Fuller could stand. Children deserved more, much more, than being caught up in an endless spiral of red tape and bureaucracy, than being viewed as outcasts, surrounded by bickering and hair splitting about who was responsible for them. What galled Fuller about the situation was the overall fact of its inequity: MPS guaranteed that 10% of the spots in their magnet schools be reserved for suburban schools only admitted kids from Milwaukee based upon availability (making it far too easy to say there's no room at the inn). Excuses Instead of Solutions The Catch-22s of race the multitude of ways in which barriers and hurdles, fine print and caveats, rear their sinister beads and scuttle attempts to level the playing field would appear to be limitless. In education, in housing, in employment, in obtaining a loan: someone, somewhere, was always at the ready, it seemed, lurking in the background, in possession of some ingenious scheme that enabled institutional racism to continue. Wasn't it bad enough that a child had to be labeled a 220 kid? But to not have a bus there so that a child could stay later and get extra help especially when blacks had borne so much of the brunt of busing seemed yet one more bitter irony. Was it any wonder that Howard Fuller wanted to ultimately get rid of busing altogether? …
openalex: W339464546 mag: 339464546
Keywords: openalex:import

Boredom Proneness in African-American College Students: A Factor Analytic Perspective - Vodanovich, Stephen J.; Watt, John; Piotrowski, Chris (Education 3-13, 1997)
A review of the research literature points to the unavoidable fact that the majority of African-American college/university students perceive their experience during higher education negatively (Berry & Asamen, 1989; Gardner, Keller, & Piotrowski, 1996; Keller, Piotrowski, & Sherry, 1982). In terms of adjustment these investigations concluded that African-American students perceive greater racial tensions and hostility, express lower levels of satisfaction, experience greater levels of isolation, and feel less identified with institutions of higher education than do their White counterparts (see Thompson & Fretz, 1991 for a review). The problem of adjustment to college/university life for African-American students is frequently attributed to extrinsic factors (e.g., racism, Anglo-European values, poor academic advising.) To date, however, little attention has been given to intrinsic personality factors that may contribute to adaptive capacity in the psychosocial and academic environment of higher education. One personality construct that may shed some light on the poor adjustment of African-American students to college life is boredom proneness. Unfortunately, there is a dearth of research on the relationship of race and boredom proneness, although earlier studies have reported that African-Americans scored lower on the Boredom Susceptibility subscale of the Sensation Seeking Scale (Zuckerman, 1979). More recently, Watt and Vodanovich (1992a) found that African-Americans possessed significantly higher scores on the Boredom Proneness Scale (Farmer & Sundberg, 1986). Greater boredom levels have also been reported among females, younger individuals, and those from less industrialized countries (e.g., Polly, Vodanovich, Watt, & Blanchard, 1993; Sundberg, Latkin, Farmer, & Saoud, 1991; Vodanovich & Kass, 1990b). In essence, researchers speculate that individuals from impoverished or restrictive environments may experience greater boredom. Review of the Boredom Construct Boredom has been identified as a contributing factor in a myriad of health and social problems. For instance, it has been associated with substance abuse (Johnston & O'Malley, 1986; Paulson, Coombs, & Richardson, 1990), eating disorders (e.g., Ganley, 1989), poor academic and work performance, (e.g., Drory, 1982; Maroldo, 1986; O'Hanlon, 1981; Robinson, 1975), and a variety of negative affective states (e.g., Farmer & Sundberg, 1986; Vodanovich, Verner, & Gilbride, 1991; Watt & Vodanovich, 1992b). Despite the above review, limited research has been devoted to the measurement of boredom. Studies that have been conducted in this area have traditionally measured boredom as a unidimensional construct. For instance, the widely used Boredom Susceptibility subscale of the Sensation Seeking Scale (Zuckerman, 1979), and the more recent Boredom Proneness Scale (Farmer & Sundberg, 1986) both yield a single score that is indicative of the tendency to experience boredom. Singular boredom scores are also provided by instruments that assess specific aspects of the construct such as job boredom (e.g., Grubb, 1975; Lee, 1986) and boredom coping (Hamilton, Haier, & Buchsbaum, 1984). The assessment of boredom as a unitary construct is discrepant with the literature that has described boredom in multidimensional terms (e.g., Drory, 1982; Geiwitz, 1966; Hill & Perkins, 1985). In addition, earlier factor analytic work suggests that boredom, and the BPS in particular, may be multidimensional in nature. For instance, Ahmed (1990) factor analyzed the scores of 154 Canadian undergraduate students on the BPS, and found evidence for the existence of two factors which he labeled Apathy and Inattention. Another factor analysis of the BPS conducted on responses from a sample of American undergraduate students (N = 385) revealed the existence of at least five factors (Vodanovich & Kass, 1990a). …
openalex: W5643769 mag: 5643769
Keywords: openalex:import

Quantifying the role of biosphere-atmosphere feedbacks in climate change: coupled model simulations for 6000 years BP and comparison with palaeodata for northern Eurasia and northern Africa - Texier, D.; Noblet, Nathalie de; Harrison, Sandy P.; Haxeltine, Alex; Jolly, Dominique; Joussaume, Sylvie; Laarif, F.; Prentice, I. Colin; Tarasov, Pavel E. (Climate Dynamics, 1997)
openalex: W1991260169 mag: 1991260169
Keywords: openalex:import

The color of pumice: case study on a trachytic fall deposit, Meidob volcanic field, Sudan - Paulick, Holger; Franz, Gerhard (Bulletin of Volcanology, 1997)
openalex: W2087791102 mag: 2087791102
Keywords: openalex:import

[Child for child: sensitization of eight thousand school children in the Lukula district of the Democratic Republic of the Congo]. (PubMed, 1997)
Many children in Africa drop out of the country¿s formal educational system before finishing elementary school. Young students in Africa are often saddled with household chores, including taking care of the youngest children in the household while their mothers manage other household responsibilities. However, many problems and accidents can occur while the mother leaves her children at home. The best way to help these school-aged children take care of their younger brothers and sisters is to train them for that function. The ¿Child-to-Child¿ approach aims to teach children typical scholastic disciplines, but also to train them in hygiene, health, and disease prevention so they can apply what they learn in the community with their families and friends. 8000 students in 43 Mayumbe primary schools, their 315 teachers and heads, and community members were trained accordingly. The intervention took place in the Lukula area of Congo. The project was made possible through the financial support of 3 nongovernmental organizations. Project implementation, motivating teachers, and project evaluation are discussed. Project evaluation demonstrated students¿ capacity to differentiate between facts and beliefs, and that this educational approach is a valid, long-term investment.
openalex: W4298279424
Keywords: openalex:import

Improving FP education in Tunisia. (PubMed, 1997)
JOICFP contributed expertise to a Japanese Evaluation Team of the Japan International Cooperation Agency (JICA), which was in Tunisia during September 16-30 to evaluate the implementation and achievements of the Project for the Promotion of Family Planning Education. The project, which is geared to promoting family planning (FP) education, was initiated in Tunisia in early 1993 by the National Office for Family and Population of Tunisia with technical cooperation from JICA. The team was headed by Dr. Takefumi Fukuhara, managing director, Medical Cooperation Department, JICA, and included five members from Japan. Ryoichi Suzuki, director, Information Division, JOICFP, contributed expertise on reproductive health as a resource person. During its stay, the team held discussions, exchanged views, and visited the field for firsthand observation. To promote FP education, the project has focused on such areas as improving the quality and quantity of video materials through the Audio Visual Center completed in Tunisia in 1995. The project has also emphasized the training of staff and implemented activities in two pilot areas. In summing up the achievements of the project, the team noted that the CPR in the remote pilot areas of Tataouine and Kasserine had increased from 33.7% and 35.8% in 1994 to reach 38% and 39.1% in 1996. Based on such achievements, the Japanese team and Tunisian side agreed to have further discussions for future collaboration in coordination with international agencies and donors such as UNFPA and the EU.
openalex: W4298035185
Keywords: openalex:import

Knowledge and misconceptions about malaria among secondary school students and teachers in Kassala, Eastern Sudan - Ag, Elzubier; Eh, Ansari; Mh, el Nour; Bella, Hassan (The journal of the Royal Society of Health, 1997)
This study reports the responses of high secondary school students and teachers to a questionnaire on their knowledge and misconceptions about malaria. Knowledge about symptoms and cause of malaria seems to be adequate. However, there were deficiencies regarding knowledge of the seriousness of malaria in primigravidas and children. There was an exaggerated belief that chloroquine may cause abortion. There were also important misconceptions regarding the causation of malaria by the plant Unkoleeb ( sorghum saccharatum), the belief that the local beverage Aradaib ( Tramindus indica) cures malaria, as well as beliefs that chloroquine injections are more effective than tablets, that intravenous fluids are essential for treatment of every attack, and that multi-vitamins may prevent the disease. The study throws light on areas where health education should be focused.
openalex: W2050567895 mag: 2050567895
Keywords: openalex:import

The reliability of self‐reported blood in urine and schistosomiasis as indicators of Schistosoma haematobium infection in school children: a study in Muheza District, Tanzania - Ansell, Juliet; Guyatt, Helen; Hall, Andrew; Kihamia, Charles M.; Kivugo, Joyce; Ntimbwa, Perpetua; Bundy, Donald (TM & IH. Tropical medicine and international health (Print), 1997)
The use of self-reported blood in urine and schistosomiasis by school children was investigated as a tool to estimate the prevalence of infection with Schistosoma haematobium and to identify infected individuals. A general questionnaire about common health problems, including questions about blood in urine and schistosomiasis, was administered by teachers to 25443 children in 137 primary schools in Muheza District, Tanzania. The prevalence of reported schistosomiasis was calculated for each school and used to select 15 schools across a range in prevalence. All children in the 15 schools (n = 2370) were interviewed again by a nurse and gave a urine sample which was subjected to a quantitative microscopical examination for the eggs of S. haematobium by filtration. The prevalence of reported schistosomiasis by the interview in the 15 schools correlated strongly with the prevalence reported during the questionnaire survey. The prevalence of reported schistosomiasis in the interview was strongly correlated with the prevalence of infection determined by microscopy and consistently under-estimated the latter by around 20% across a range in prevalence from 22% to 93%. The sensitivity of diagnosis by an interview increased almost linearly with the prevalence of infection, so that when the prevalence was high, more infected children reported schistosomiasis. The percentage of children who were correct in their self-diagnosis was independent of the prevalence of infection and of the mean concentration of eggs in urine, and averaged 75%. These findings suggest that self-reported schistosomiasis is a useful method to estimate the prevalence of infection in schools and might be used to identify infected individuals.
openalex: W2014668862 mag: 2014668862
Keywords: openalex:import

'There Must Be Something Undiscovered Which Prevents Us From Doing Our Work Well': Botswana Primary Teachers' Views on Educational Language Policy - Arthur, Jo (Language and Education, 1997)
In a small-scale survey of Botswana primary teachers' views on educational language policy there was overwhelming support for English as the medium of instruction. The survey forms part of a wider research project (Arthur, 1995), in which classroom observation revealed classroom communication difficulties created by the use of English, which is effectively a foreign language for the majority of Botswana teachers and pupils. This paper discusses the apparent paradox of teachers' support for English medium, taking account both of the symbolic role of English as the language of educational achievement and its practical role in the national examination system. Parallels are drawn with the reasserted prestige of ex-colonial languages in other African countries over the last decade. Despite the clear overall support for English, the opinions of the teachers surveyed were by no means monolithic. There are variations in the findings which appear related to the language background of respondents. Speakers of minority languages, while acknowledging the prestige of English, apparently experience a conflicting need for access through the education system to Setswana, the politically dominant national language. There is also some evidence that younger teachers may be less in favour of English as the sole medium and more open-minded towards alternatives such as a language-by-subject option.
openalex: W2022064469 mag: 2022064469
Keywords: openalex:import

The Teacher Crisis in South Africa: Quitting, Shirking and ‘Inferior Substitution’ - Black, P.A.; Hosking, Stephen (South African Journal of Economics, 1997)
South African Journal of EconomicsVolume 65, Issue 4 p. 232-236 The Teacher Crisis in South Africa: Quitting, Shirking and ‘Inferior Substitution’ P.A. BLACK, P.A. BLACK School of Economics, University of Cape Town, and Department of Economics University of Port Elizabeth, respectively. Paper read at the biennial conference of the Economic Society of South Africa, Potchefstroom, September 1997. The authors wish to acknowledge the financial assistance given by the South African Network for Economic Research.Search for more papers by this authorS.G. HOSKING, S.G. HOSKING School of Economics, University of Cape Town, and Department of Economics University of Port Elizabeth, respectively. Paper read at the biennial conference of the Economic Society of South Africa, Potchefstroom, September 1997. The authors wish to acknowledge the financial assistance given by the South African Network for Economic Research.Search for more papers by this author P.A. BLACK, P.A. BLACK School of Economics, University of Cape Town, and Department of Economics University of Port Elizabeth, respectively. Paper read at the biennial conference of the Economic Society of South Africa, Potchefstroom, September 1997. The authors wish to acknowledge the financial assistance given by the South African Network for Economic Research.Search for more papers by this authorS.G. HOSKING, S.G. HOSKING School of Economics, University of Cape Town, and Department of Economics University of Port Elizabeth, respectively. Paper read at the biennial conference of the Economic Society of South Africa, Potchefstroom, September 1997. The authors wish to acknowledge the financial assistance given by the South African Network for Economic Research.Search for more papers by this author First published: 22 August 2005 https://doi.org/10.1111/j.1813-6982.1997.tb01377.xCitations: 1AboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinked InRedditWechat Citing Literature Volume65, Issue4December 1997Pages 232-236 RelatedInformation
openalex: W2003707675 mag: 2003707675
Keywords: openalex:import

Student attitudes to dentistry in South African dental schools. - Brand, A A; Chikte, Usuf (PubMed, 1997)
The present study investigated student motives for choosing dentistry in five South African dental schools. An attitude questionnaire was complied and administered to all entering students at these schools. The study population comprised 161 students, 92 males and 69 females. Results indicate that in spite of the changing student populations at all universities, the motives for studying dentistry remain essentially the same. Similarities in attitudes to dentistry tend to outweigh differences. Similarities are shown with respect to service, the need for status, independence and financial security. Differences are reflected in the contradictions between service and status, service and regular working hours, service and financial security. The question these findings raise, is how and to what extent students selected for training, based on their current motivation and attitudes will best adapt to changes in the practice of dentistry, health policies, and increased population demands.
openalex: W2026199365 mag: 2026199365
Keywords: openalex:import

Improvement of Insulin Sensitivity by Short-term Exercise Training in Hypertensive African American Women - Brown, Michael D.; Moore, Geoffrey E.; Korytkowski, Mary T.; McCole, Steve D.; Hagbèrg, James M. (Hypertension, 1997)
Abstract African American women have a high prevalence of insulin resistance, non–insulin-dependent diabetes mellitus, obesity, and hypertension that may be linked to low levels of physical activity. We sought to determine whether 7 days of aerobic exercise improved glucose and insulin metabolism in 12 obese (body fat >35%), hypertensive (systolic blood pressure ≥140 and/or diastolic blood pressure ≥90 mmHg) African American women (mean age 51±8 years). Insulin-assisted frequently-sampled intravenous glucose tolerance tests were performed at baseline and 14 to 18 hours after the 7th exercise session. There was no significant change in maximal oxygen consumption, body composition, or body weight after the 7 days of aerobic exercise. The insulin sensitivity index increased (2.68±0.45 · 10 −5 to 4.23±0.10 · 10 −5 [min −1 /pmol/L], P =.02). Fasting (73±9 to 50±9 pmol/L, P =.02) and glucose-stimulated (332±58 to 261±45 pmol/L, P =.05) plasma insulin levels decreased. Additional measures related to the insulin resistance syndrome also changed with the 7 days of exercise: basal plasma norepinephrine concentrations were reduced (2.46±0.27 to 1.81±0.27 nmol/L, P =.02) and sodium excretion rate increased from 100±13 to 137±7 mmol/d ( P =.03); however, there was no change in potassium excretion or 24-hour ambulatory blood pressure. We conclude that a short-term aerobic exercise program improves insulin sensitivity in African American hypertensive women independent of changes in fitness levels, body composition, or body weight. The present study indicates that short-term exercise can improve insulin resistance in hypertensive, obese, sedentary African American women and confirms previous reports that a portion of the exercise-induced improvements in glucose and insulin metabolism may be the result of recent exercise.
openalex: W2134874488 mag: 2134874488
Keywords: openalex:import

‘Sit down, you haven't reached that stage yet’: African Caribbean children in Leicester schools 1960‐74 - Chessum, Lorna (History of Education, 1997)
(1997). ‘Sit down, you haven't reached that stage yet’: African Caribbean children in Leicester schools 1960‐74. History of Education: Vol. 26, No. 4, pp. 409-429.
openalex: W2082532015 mag: 2082532015
Keywords: openalex:import

The Integrated Rural Nutrition Project, Kawambwa, Zambia: successes of a nutrition education programme. - Friedrich, John A. (PubMed, 1997)
This article presents some findings from an evaluation of the Integrated Rural Nutrition Project (IRNP) in Kawambwa, Zambia. The IRNP was initiated in 1985. The program relied on a multisectoral approach by the Ministries of Health, Education, Agriculture, and Community Development. The program aimed to reduce the rate of malnutrition. Breast feeding was encouraged, and farmers were encouraged to increase production of beans and groundnuts. Extension workers were trained. Findings indicate that nutrition education programs had a significant, positive effect on the nutritional status of children aged under 5 years. The nutrition education component, which aimed at improving knowledge, attitudes, and practices, was more successful than the activities that aimed at increasing food availability. A continuing question was raised by program staff about whether training of extension workers, social marketing, mass education, or direct extension were capable of having an impact on nutrition without addressing food productivity issues. The availability of legumes improved throughout the intervention period. The length of the hunger season was shortened. However, increased food availability did not improve anthropometric measurements, and some children, who were not part of the seed multiplication program, showed improved anthropometric measurements. Children in the intervention area were exposed to better breast-feeding practices: breast feeding for longer periods and fewer introductions to non-milk liquids. After the first month, under 20% of children in the project area and 80-95% in the non-project areas had received breast milk substitutes. Young children in the project area had better weight-for-height, after controlling for wealth, access to services, maternal and paternal education, gender, and age. 3-year-old children in the project area weighed 0.3 of a z-score more than non-project children.
openalex: W2295614720 mag: 2295614720
Keywords: openalex:import

Pattern of surgical admissions in Gondar Teaching Hospital, Ethiopia. - Ghebrat, K (PubMed, 1997)
A retrospective study based on the principal discharge diagnosis of 4121 surgical in-patients, who were admitted to Gondar College of Medical Sciences Hospital over a three year period, is made to document the commonest surgical conditions prevalent in the north west region of Ethiopia. Intestinal obstruction was the commonest cause of surgical admission followed by head injury and soft tissue injury.
openalex: W46093634 mag: 46093634
Keywords: openalex:import

Determining the source of nitrate pollution in the Niger discontinuous aquifers using the natural ratios - Girard, Pierre; Hillaire‐Marcel, Claude (Journal of Hydrology, 1997)
In the semi-arid Niamey area (Niger), more than 10% of the deep wells exploiting the fracture network of the Precambrian aquifer are contaminated by nitrates, with concentrations as high as 10 meq l−1. In order to identify the source(s) of this pollution, nitrate and 15N contents in the polluted wells were monitored over a 20-month period. Potential sources of nitrate contamination were also analyzed for their 15N content. The isotopic compositions of nitrate in polluted waters were > + 12‰ and in rare cases exceeded +17‰. Latrines (∼ + 15‰) may be the major nitrate source for wells showing δ15N values above +15‰. Below this value, waters may be polluted by a combination of nitrates from both latrine and soil sources (∼ + 10‰). In some cases, the soil may account for up to 85% of the groundwater nitrate load. This mode of groundwater pollution is thought to be a consequence of deforestation. Despite their reputation as polluting agents, fertilizers (+0.5 < δ15N < + 3.6‰) which are used in rice paddies close to the contaminated areas, do not appear to be a significant source of nitrate contamination. Denitrification is probably not a significant process in the study area. Results suggest that nitrate contamination of the aquifer is a consequence of unregulated urbanization (home-made latrines) and deforestation. While latrines are limited to the urban zones, intensive cutting of the forest to meet the city dwellers' wood demand occurs in an ever increasing area around the capital, threatening the local water supply.
openalex: W2064307177 mag: 2064307177
Keywords: openalex:import

Development Education Programme African Environmental Law Togo-Benin - Grimeaud, David; Mols, G.P.M.F.; Oğuş, Ayla; Schwarz, Carolyn (1997)
openalex: W2561228848 mag: 2561228848
Keywords: openalex:import

Stereotype Vulnerability in Elementary Aged African American Students - Jandrucko, Sarah K. (1997)
This study explores a link between stereotype vulnerability and the documented under performance of African American students on standardized tests. The subjects were 41 third grade African American students matched according to language arts grades with 41 third grade Anglo students. The students were from predominately middle class suburban schools, with similar educational experiences. The data suggest that third grade African American and Anglo students from predominately middle class schools, with approximately equivalent language arts grades and similar educational experiences, will score comparably to one another regardless of testing conditions. The data also suggest that this sample of third grade students are confident in their academic ability and are not affected by negative stereotyping.
openalex: W628220216 mag: 628220216
Keywords: openalex:import

Reconstruction Years Are the Best Years: establishing good school libraries in South Africa - Kakoma, Albert K. (Information Development, 1997)
The school library scene in Southern Africa is not impressive. Even where the picture is slightly better the school library does not play a meaningful role in the school curriculum. For most of the countries in the region the battle for establishing this educational component which contributes to the image of a good school needs to be restarted from the drawing board. South Africa has to learn from the mistakes of these countries in order to avoid similar pitfalls. The Reconstruction and Development Programme (RDP) which has been put in place by the Government of National Unity (GNU) to redress the various imbalances of the apartheid era should be taken advantage of by all those in positions of influence who take strong exception to lack of good school libraries. Policies should be formulated not only for the provision of purpose-built school library structures but also to ensure that the school library becomes an integral part of the school curriculum. The reasons why it is necessary to do so are given. The long-term advantages of having good school libraries are also stated. Further, the thinking why it is crucial to earmark the development of school libraries during the reconstruction years is explained.
openalex: W2093136612 mag: 2093136612
Keywords: openalex:import

Responses of African livestock and wild herbivores to drought - Kay, R.N.B. (Journal of Arid Environments, 1997)
The ways in which herbivores regulate their energy and water balance under hot, dry conditions are briefly reviewed. Cattle account for about two-thirds of the biomass of domestic stock in Africa, but their Eurasian origin means that their physiology and grazing behaviour are not wholly adapted to the natural pastures and climate of Africa, especially when drought strikes. In general, most herbivores can withstand heat and water shortage quite well, provided conditions do not become extreme. However, malnutrition will inevitably develop as pasture productivity declines under drought and overgrazing. This will affect most seriously animals that cannot range far from water and that depend mainly on drought susceptible grasses rather than on more resistant shrubs and trees.
openalex: W2061086079 mag: 2061086079
Keywords: openalex:import

AIDS education in Tanzania: promoting risk reduction among primary school children. - Klepp, Knut Inge; Ndeki, Sidney; Leshabari, Melkizedeck; Hannan, Peter J.; Lyimo, Babuel A. (American Journal of Public Health, 1997)
The purpose of this study was to test the effects of an education program in Tanzania designed to reduce children's risk of human immunodeficiency virus (HIV) infection and to improve their tolerance of and care for people with acquired immunodeficiency syndrome (AIDS).A randomized controlled community trial including baseline and 12-month follow-up surveys was employed. Public primary schools in the Arusha and Kilimanjaro regions of Tanzania were stratified according to location and randomly assigned to intervention (n = 6) or comparison (n = 12) conditions. Of the 1063 sixth-grade students (average age: 13.6 years) who participated at baseline, 814 participated in the follow-up survey.At follow-up, statistically significant effects favoring the intervention group were observed for exposure to AIDS information and communication, AIDS knowledge, attitudes toward people with AIDS, and subjective norms and behavioral intentions toward having sexual intercourse. A consistent positive but nonsignificant trend was seen for attitudes toward having sexual intercourse and for initiation of sexual intercourse during the previous year (7% vs 17%).It is feasible and effective to train local teachers and health workers to provide HIV/AIDS education to Tanzanian primary school children.
openalex: W2117296887 mag: 2117296887
Keywords: openalex:import

Volcanic vents rooted on extension fractures and their geodynamic implications in the Ethiopian Rift - Korme, Tesfaye; Chorowicz, J.; Collet, Bernard; Bonavia, F. F. (Journal of Volcanology and Geothermal Research, 1997)
Most of the extension fractures located in the Ethiopian rift are related to rift dynamics, and they have consistently similar orientations for hundreds of kilometers. The orientation of extension fracture gives the local extension direction which is perpendicular to its horns (end segments of an extension fracture). We have established clear geometrical relationships between tectonics and volcanism in the Main Ethiopian Rift by interpreting high-resolution images obtained from Landsat-TM and SPOT satellites and by quantitatively analyzing the geometry of extension fractures, elongated vents and linear volcanic clusters. Applying the relationships obtained, we show that extension fractures in the rift served as channels for magma rising to the surface, and that extension fractures underlie most of the elongated volcanic vents and linear volcanic clusters. The geometry of extension fractures beneath volcanic edifices can be deduced from the shape of elongated vents and pattern of linear volcanic clusters rooted on them. Utilizing the orientations of extension fractures directly observed and those inferred from elongated volcanic vents and linear clusters, we found that the extension direction of the Main Ethiopian Rift is northwest–southeast and that the direction has been rotated clockwise for about 20° in the time interval 2.83 to 0.023 Ma. The Recent axis of rift opening is oriented N40° and located closer to the southeastern escarpment giving an asymmetric geometry to the Main Ethiopian Rift (MER).
openalex: W2033710913 mag: 2033710913
Keywords: openalex:import

It Doesn't Add Up: African American Students' Mathematics Achievement - Ladson‐Billings, Gloria (Journal for Research in Mathematics Education, 1997)
Mathematics education has been heralded for its leadership role in the U.S. school reform effort (Stein, Grover,&Henningsen, 1996; Grant, Peterson, & Shojgreen- Downer, 1996). Prominent in the reform of mathematics education is the call for students not merely to memorize formulas and rules and apply procedures but rather to engage in the processes of mathematical thinking, that is, to do what mathematicians and other professional users of mathematics do. The revamped mathematics education program is based on engaging students in problem posing and problem solving rather than on expecting rote memorization and convergent thinking. These changes in mathematics education suggest that mathematics teaching must build on students' learning and on their ability to pose and solve problems previously considered too difficult for their age-grade levels (Carpenter&Fennema, 1988; Fennema, Franke, Carpenter,&Carey, 1993).
openalex: W1529043666 mag: 1529043666
Keywords: openalex:import

It Doesn't Add up: African American Students' Mathematics Achievement - Ladson‐Billings, Gloria (Journal for research in mathematics education, 1997)
openalex: W4254799346
Keywords: openalex:import

Comagmatic A-Type Granophyre and Rhyolite from the Alid Volcanic Center, Eritrea, Northeast Africa - Lowenstern, Jacob B. (Journal of Petrology, 1997)
Granophyric blocks within late-Pleistocene pyroclastic flow ejecta from the Alid volcanic center, northeast Africa, are the rapidly crystallized, intrusive equivalent of pumice from the pyroclastic flow. Phenocryst compositions and geochemical characteristics of the pumice and granophyre are virtually identical. Silicate melt inclusions and other geochemical and geological constraints reveal those processes leading to development of the granophyric texture. Rhyolitic (A-type) magma with ∼2.6 wt % dissolved H2O and a temperature near 870°C was intruded to within 2–4 km of the surface, causing deformation and structural doming of shallow marine and subaerial strata. Eruptions of crystal-poor rhyolite from this shallow magma chamber caused degassing, which forced undercooling and consequent granophyric crystallization of some of the magma remaining in the intrusion. The most recent eruption from Alid excavated the crystallized granitic wall of the magma chamber, bringing the granophyric clasts to the surface.
openalex: W4237869936
Keywords: openalex:import

Comagmatic A-type Granophyre and Rhyolite from the Alid Volcanic Center, Eritrea, Northeast Africa - Lowenstern, Jacob B.; Clynne, Michael A.; Bullen, Thomas D. (Journal of petrology (Print), 1997)
vermicular to cuneiform (Barker, 1970).Typically, the Granophyric blocks within late-Pleistocene pyroclastic flow ejecta from the Alid volcanic center, northeast Africa, are the rapidly groundmass feldspars radiate off pre-existing feldspar crystallized, intrusive equivalent of pumice from the pyroclastic flow.phenocrysts, with which they are in optical continuity Phenocryst compositions and geochemical characteristics of the (Dunham, 1965).Some workers prefer the term pumice and granophyre are virtually identical.Silicate melt inclusions 'micrographic' for highly regular, interlocking arand other geochemical and geological constraints reveal those processes rangements of quartz and feldspar, as in the coarser leading to development of the granophyric texture.Rhyolitic (Agraphic granite (Fenn, 1986;Lentz & Fowler, 1992).type) magma with ~2•6 wt % dissolved H 2 O and a temperature Though Schloemer (1964) has shown that some graphic near 870°C was intruded to within 2-4 km of the surface, causing textures can grow by replacement [see also Augustithis deformation and structural doming of shallow marine and subaerial (1973)], most workers agree that phenocryst-bearing strata.Eruptions of crystal-poor rhyolite from this shallow magma granophyres typically form by rapid and simultaneous chamber caused degassing, which forced undercooling and consequent crystallization of quartz and feldspar from a melt (Smith, granophyric crystallization of some of the magma remaining in the 1974).Such crystallization is generally believed to be due intrusion.The most recent eruption from Alid excavated the cryto pronounced undercooling of the silicate liquid (Vogt, stallized granitic wall of the magma chamber, bringing the grano-1930;Dunham, 1965); not necessarily at eutectic temphyric clasts to the surface.peratures or compositions (Fenn, 1986;London et al., 1989;Lentz & Fowler, 1992).Granophyric textures are common in epizonal granitic bodies, particularly those associated with volcanic rocks (Buddington, 1959;Dunham, 1965).On occasion, they erupt as comagmatic ejecta in pyroclastic deposits (e.g.
openalex: W2162984691 mag: 2162984691
Keywords: openalex:import

Ecological determinants of intestinal parasitic infections among pre-school children in an urban squatter settlement of Egypt - Mahfouz, Ahmed A. (Journal of Tropical Pediatrics, 1997)
Population growth in Egypt has led to the creation of several urban squatter settlements. The aim of the present work was to study the prevalence and some potential risk factors of intestinal parasitic infections among preschool children in a randomly chosen urban squatter settlement in Alexandria, Egypt. A house to house cross-sectional survey was conducted during late 1995. Data were collected through questionnaire interview regarding socio-demographic and environmental conditions from 1324 families residing in the settlement. Stool samples were collected from 658 preschool children below 5 years of age and examined for intestinal parasites. Overall, the prevalence rates of infections with the intestinal Helminths and Protozoa were 47.3 and 31.5 per cent, respectively, which were very high compared to previously reported figures for this age group in Egypt. Multiple logistic regression analysis showed that certain groups of preschool children were much more likely to develop the infection with both groups of intestinal parasites. They included children over 2 years of age (OR = 2.75, 95 per cent CI = 1.23-4.12 and OR = 2.65, 95 per cent CI = 1.70-3.45 for Helminths and Protozoa, respectively), whose families had pools of sewage around houses (OR = 2.13, 95 per cent CI = 1.22-3.19 and OR = 2.83, 95 per cent CI = 1.45-3.95 for helminths and protozoa, respectively) and shared toilets with another family (OR = 1.95, 95 per cent CI = 1.38-2.75 and OR = 1.65, 95 per cent CI = 1.06-2.58 for Helminths and Protozoa, respectively). In addition, certain groups of children were much likely to develop protozoal infections including children whose families lacked tap water inside dwelling (OR = 1.85, 95 per cent CI = 1.26-2.77) and disposed human excreta in septic tank very close to the dwelling (OR = 2.17, 95 per cent CI = 1.43-3.75). Efforts to reduce intestinal parasites should focus on reducing exposures. Improvement in domestic water supplies with the introduction of piped sewerage system is likely to have a marked decreasing effect on the prevalence of infection among this age group.
openalex: W2016433106 mag: 2016433106
Keywords: openalex:import

Multicultural education in secondary schools in South Africa : an analysis of teachers' needs - Merwe, Ann-Marie Van der (1997)
openalex: W778407740 mag: 778407740
Keywords: openalex:import

THE EFFECTS OF ECONOMIC INCENTIVES IN CONTROLLING POLLUTION IN THE SOUTH AFRICAN LEATHER INDUSTRY / DIE UITWERKING VAN EKONOMIESE INSENTIEWE OP DIE BEHEER VAN BESOEDELING IN DIE SUID-AFRIKAANSE LEERBEDRYF - Mowat, Shaun Phillip; Antrobus, G.G.; Fraser, Gavin (Agrekon, 1997)
Pollution of the environment is becoming an increasingly serious problem. A large contributor to this is industry which generates effluent as a by-product of its production process. Two methods of controlling the pollution generated by industry are the so-called “command and control” techniques and economic incentives. In theory, economic incentives promise a more economically efficient and equitable means of pollution control. This paper sets out to ascertain whether this would hold in practice by applying environmental economic theory to the practical problem of controlling the effluent generated by one particular industry, viz the South African leather industry.
openalex: W1995040127 mag: 1995040127
Keywords: openalex:import

The Kenyan Government and the Kikuyu Independent Schools: From Attempted Control to Suppression, 1929–1952 - Natsoulas, Theodore (The Historian, 1997)
openalex: W2123755539 mag: 2123755539
Keywords: openalex:import

Senegal: Defining and implementing priorities in the education sector - Ndoye, Mamadou (PROSPECTS, 1997)
openalex: W2086703527 mag: 2086703527
Keywords: openalex:import

Women and Education in Eritrea: A Historical and Contemporary Analysis - Stefanos, Asgedet (Harvard Educational Review, 1997)
In this article, Asgedet Stefanos examines women and education in the east African nation of Eritrea. She tackles as her central questions whether, and to what extent, Eritrean women have been achieving emancipation; and, if so, what role education has played in that process. Stefanos begins by providing a historical overview that delineates Eritrean women's general social condition and access to education in pre-colonial traditional society and during the eras of Italian and British colonialism. She then evaluates developments during Eritrea's protracted national liberation struggle against Ethiopia and the four years since independence. Stefanos documents significant advances in the emancipation of women and highlights education as a vital arena for change. She observes shortcomings in the Eritrean political leadership's strategy to establish effective educational equity for women, as well as disparities between the goals and assessments of policymakers and the aspirations and experiences of women. Her discussion of contemporary Eritrea is informed by policies and commentary of political leaders and interviews with a diverse sample of Eritrean women. Stefanos concludes by asserting that the current situation confronting an independent Eritrea promotes new obstacles and challenges to a vigorous pursuit of female rights and gender equality, and that the prospects for expanding women's gains in education are very much in the balance.
openalex: W1931043650 mag: 1931043650
Keywords: openalex:import

Conceptions of fair learning practices among low-income African American and Latin American children: Acknowledging diversity. - Thorkildsen, Theresa A.; Schmahl, Cindy M. (Journal of Educational Psychology, 1997)
African American and Latin American elementary students (ages 6-12) from low-income, urban neighborhoods were interviewed about the fairness of 4 teaching practices. Five conceptions of fairness, identified in previous studies with Caucasian students, were evident. This suggests that, to some degree, American children from diverse ethnic groups agree on how the learning process should be organized. Nevertheless, sociocultural variation was also evident. Consistent with previous studies, most children rated peer tutoring as fairest, but some African American and Latin American children equated peer tutoring with cheating. The children of color, when justifying their positions, introduced 4 new educational issues (worry about grades, solitary work, work quality, and resistance to schoolwork): They saw learning situations as taking on some of the properties of tests. Findings support a sociocultural approach to the study of moral reasoning, and measurement that is respectful of individual as well as group variability.
openalex: W2019592811 mag: 2019592811
Keywords: openalex:import

Conceptions of fair learning practices among low-income African American and Latin American children: Acknowledging diversity. - Thorkildsen, Theresa A.; Schmahl, Cindy M. (Journal of Educational Psychology, 1997)
African American and Latin American elementary students (ages 6-12) from low-income, urban neighborhoods were interviewed about the fairness of 4 teaching practices. Five conceptions of fairness, identified in previous studies with Caucasian students, were evident. This suggests that, to some degree, American children from diverse ethnic groups agree on how the learning process should be organized. Nevertheless, sociocultural variation was also evident. Consistent with previous studies, most children rated peer tutoring as fairest, but some African American and Latin American children equated peer tutoring with cheating. The children of color, when justifying their positions, introduced 4 new educational issues (worry about grades, solitary work, work quality, and resistance to schoolwork): They saw learning situations as taking on some of the properties of tests. Findings support a sociocultural approach to the study of moral reasoning, and measurement that is respectful of individual as well as group variability.
openalex: W2019592811 mag: 2019592811
Keywords: openalex:import

Conceptions of fair learning practices among low-income African American and Latin American children: Acknowledging diversity. - Thorkildsen, Theresa A.; Schmahl, Cindy M. (Journal of Educational Psychology, 1997)
African American and Latin American elementary students (ages 6-12) from low-income, urban neighborhoods were interviewed about the fairness of 4 teaching practices. Five conceptions of fairness, identified in previous studies with Caucasian students, were evident. This suggests that, to some degree, American children from diverse ethnic groups agree on how the learning process should be organized. Nevertheless, sociocultural variation was also evident. Consistent with previous studies, most children rated peer tutoring as fairest, but some African American and Latin American children equated peer tutoring with cheating. The children of color, when justifying their positions, introduced 4 new educational issues (worry about grades, solitary work, work quality, and resistance to schoolwork): They saw learning situations as taking on some of the properties of tests. Findings support a sociocultural approach to the study of moral reasoning, and measurement that is respectful of individual as well as group variability.
openalex: W2019592811 mag: 2019592811
Keywords: openalex:import

Field Trial of Cowpeas (Vigna unguiculata (L.) WALP.), Differing in Drought Tolerance, in the Dry Season of Sudan Savanna and Dry Matter Production of Potted Plants under Water-stress - Watanabe, Iwao; Terao, Tomio (Japanese journal of tropical agriculture, 1997)
openalex: W2519191467 mag: 2519191467
Keywords: openalex:import

Circulation changes and teleconnections between glacial advances on the west coast of New Zealand and extended spells of drought years in South Africa - Tyson, Peter; Sturman, Andrew; Fitzharris, B. B.; Mason, Simon J.; Owens, I. F. (International Journal of Climatology, 1997)
Twentieth century changes in the terminal position of the Franz Josef Glacier on the west coast of New Zealand are compared with an area-averaged mean annual rainfall series for the summer rainfall region of South Africa. Distinctive teleconnections are evident in an out-of-phase relationship between the two series, each of which exhibits an oscillation of 18–20 years. Periods of glacial advance are shown to coincide with extended dry spells in South Africa, when drought years are prevalent. Reconstructed pressure anomaly fields are presented for periods of advance and recession of the glacier and for the inter-decadal wet and dry spells in South Africa. In both cases major regional atmospheric circulation adjustments take place in a quasi-regular fashion over time to produce an enhancement in westerly airflow during the periods of drought in Africa and glacial advance on the west coast of New Zealand. Extended wet periods and glacial recession are likewise shown to be associated with an enhancement of easterly components of the circulation. Changes in precipitation, temperature and moisture transport are examined and associations with the Southern Oscillation Index are investigated. Franz Josef glacial advances are shown to occur 4–5 years after the onset of enhanced south-westerly airflow on to the west coast of New Zealand. Advances occur on average 4 years after the onset of extended dry spells in South Africa. Similar atmospheric circulation anomalies in the respective sectors of the Southern Hemisphere and adjustments in the locations of the positions of the ridges in standing wave three are responsible for this correspondence. © 1997 Royal Meteorological Society.
openalex: W1965666162 mag: 1965666162
Keywords: openalex:import

Special Employment and Skill Development Programmes for the Disabled : Can Cameroon Learn from the Experience of the Netherlands? - Takor, Tabe Peter (1997)
openalex: W26986336 mag: 26986336
Keywords: openalex:import

Microwave Propagation in Dust Storms at 10.5 GHz - A Case Study in Khartoum, Sudan - Ghobrial, S.I.; Jervase, J.A. (IEICE Transactions on Communications, 1997)
openalex: W1604699469 mag: 1604699469
Keywords: openalex:import

Science Education in Egypt and Other Arab Countries in Africa and West Asia - Hassan, F. (Frontiers: The interdisciplinary journal of study abroad, 1997)
The Egyptian education system is large, and current practices are very rigid. It is accustomed to mass education as was developed in Europe over the past two hundred years, following closely the British tradition. Full-scale renovation of the existing system will take time; a ten-year period is estimated.
Significant changes are taking place in science programs offered to future citizens. Traditional patterns of science education, which build a strong theoretical tradition with less emphasis on laboratory and practical experiences, are changing rapidly. New programs and systems with more emphasis on research are being introduced. The content and teaching methods incorporated in these programs are based on the most up-to-date theories about what science is most worth knowing. The primary goal of the new generation science programs is to reflect the national interest of having a scientifically literate population.
openalex: W114635759 mag: 114635759
Keywords: openalex:import

Science Education in Kenya - Okelo, Ochong (Frontiers: The interdisciplinary journal of study abroad, 1997)
This paper briefly presents the structure and organization of science education from preschool (preprimary) to university level. It also addresses such sociocultural issues as religion and acceptance or resistance to science by the Kenyan society.
openalex: W319697090 mag: 319697090
Keywords: openalex:import

A Comparative Study of the Factors Which Predict Persistence for African American Students at Historically Black Institutions and Predominantly White Institutions. ASHE Annual Meeting Paper. - Himelhoch, Carol R.; Nichols, Adriana; Ball, Stephen R.; Black, Lana Collister (1997)
openalex: W2724422934 mag: 2724422934
Keywords: openalex:import

Experiences of African-American Baccalaureate Nursing Students Examined through the Lenses of Tinto's Student Retention Theory and Astin's Student Involvement Theory. ASHE Annual Meeting Paper. - Janes, Sharyn (1997)
openalex: W44288349 mag: 44288349
Keywords: openalex:import

Science Teachers Attitudes at Gaza Basic Schools toward Scientific Creativity, Scientific Qualifications and Years of Experience - Al-Austath, Mahmud; Amleh, Mohammad Salim (An-Najah University Journal for Research - B (Humanities), 1997)
This study aimed at investigating the effect of sex, academic qualifications and years of teaching experience on the attitudes of science teachers at middle stage in Gaza Strip schools toward creativity in science classes. The sample of the study consisted of 77 science teachers (46 males and 3 1 females). Attitude Scale toward creativity developed by the researchers was used. The results indicated that there was a significant difference in teachers attitudes toward creativity related to years of experience and academic qualifications while there was no effect on their attitudes toward creativity related to sex. A week correlation appeared between student attitudes toward creativity and their achievement. According to these results the study recommended to develop positive attitudes toward creativity, to carry out more similar studies in different levels and to design other scales in order to locate the creativity and the attitudes toward creativity for both teachers and their students. هدفت هذه الدراسة إلى بحث اثر كل من الجنس والمؤهل العلمي والخبرة التدريسية على اتجاه معلمي العلوم في المرحلة الأساسية العليا في قطاع غزة نحو الإبداع العلمي وعلاقته بالتحصيل الدراسي. تكونت عينة الدراسة من 77معلما معلمة (46معلما، 31معلمة). وتجمع المعلومات ثم استخدام مقياس الاتجاه نحو الإبداع في العلوم الذي أعده الباحثان بالاعتماد على مراجعة الدراسات السابقة ذات الصلة بموضوع الدراسة. وتم استخدام اختبار تحصيلي في مادة العلوم من إعداد الباحثين أيضا. وقد استخدم الباحثان كلا من اختبار "ت"ومعامل ارتباط بيرسون لاختبار فرضيات الدراسة التي دلت على وجود فروق ذات دلالة إحصائية تعزي لكل من المؤهل العلمي والخبرة التدريسية نحو الإبداع بينما لم يكن هناك فرق ذو دلالة إحصائية نحو الإبداع يعزي إلى الجنس. كما لم يكن هناك علاقة ارتباط قوية بين اتجاهات المعلمين نحو الإبداع ومتوسطات درجات التحصيل الدراسي لطلبتهم في العلوم. وقد أوصت هذه الدراسة على ضوء النتائج بتنمية اتجاهات ايجابية نحو الإبداع لكل من المعلم والطالب سواء وكذلك وجوب التميز بين الجوانب التحصيلية والجوانب الإبداعية التي تثار السلوك الصفي. كما أوصت بتصميم مقاييس جديدة ومقننة على البيئة المحلية لقياس الإبداع والاتجاه نحوه لكل من المعلمين وطلبتهم سواء بسواء.
openalex: W55659327 mag: 55659327
Keywords: openalex:import

The Crisis of Higher Education in Sub‐Saharan Africa: the continuing search for relevance - Banya, Kingsley; Elu, Juliet U. (Journal of Higher Education Policy and Management, 1997)
Abstract Abstract Based upon an empirical research conducted in 1994, the purpose of this article is to examine the contribution that higher education institutions have played in Sub‐Saharan development. After thirty years of formal independence, it is time to take a critical look at the role of higher education in nation building in Sub‐Saharan Africa. The conclusion from the research is that though higher education has contributed significantly to meeting the human resource needs of each country, the overall performance has been less than satisfactory. Everywhere in Sub‐Saharan Africa the progress anticipated at the time of independence has not materialised. In some cases the socioeconomic situation has deteriorated, as in the case of Sierra Leone and Guinea. Higher education needs to examine its priorities in light of the current situation.
openalex: W2026445630 mag: 2026445630
Keywords: openalex:import

Women, occupation and health in rural Africa: Adaptation to a changing socioeconomic climate - Barrett, Hazel (Journal of Occupational Science, 1997)
Abstract Over the last ten to fifteen years socioeconomic conditions in sub‐Saharan Africa have declined. Economic crisis has resulted in the adoption of International Monetary Fund and World Bank sponsored economic structural adjustment policies by most African governments. These highly criticised policies have had limited economic success and are often blamed for stagnant and even deteriorating human development indicators and declining living standards. At the same time families and communities are coping with the increasing morbidity and mortality and social issues associated with HIV/AIDS. These changing socioeconomic conditions have particular implications for vulnerable groups, such as poor rural women and their families. Using empirical material collected by the author in Southern and Western Africa, the paper examines the triple workload borne by rural African women. Their roles as biological and social reproducers as well as economic providers are described and the links between these occupations and personal and family health are explored. The extra burden imposed by recent socioeconomic changes, in particular poverty and HIV/AIDS is examined. The desire and need for children is explained and the demands of poverty on rural women is explored. The evidence indicates that deteriorating socioeconomic conditions in sub‐Saharan families are adversely affecting the lives and health of rural African women and their families. Poverty and the shadow of HIV/AIDS have serious implications for rural African women, for whom access to labour and income is now critical to family well‐being and survival in many parts of rural Africa. The international community must recognise the changing and varied occupational roles that rural women now perform and should be prepared to respond to the needs and challenges that African women will face as the new millennium approaches.
openalex: W2035857456 mag: 2035857456
Keywords: openalex:import

Ottawa students mark "5 wonderful years" in Malawi - Chan, King-chung (Canadian Medical Association Journal, 1997)
openalex: W77911224 mag: 77911224
Keywords: openalex:import

Mukumu Girls' schools et l'éducation des filles au Kenya - Charton, Hélène (Clio, 1997)
D'apres le recensement de 1989, 76% des jeunes kenyanes âgees de 6 a 24 ans frequentent un etablissement scolaire. Ce chiffre, eleve pour un pays africain, temoigne d'une evolution rapide et continue puisque 58% des femmes de 30 a 40 ans ont beneficie d'une education scolaire contre 18% pour les plus de 45 ans. Une progression aussi spectaculaire invite a une reflexion sur la nature et le degre des transformations sociales qui en resultent. L'observation d'une institution scolaire part...
openalex: W2002364117 mag: 2002364117
Keywords: openalex:import

South Africa increases central control of higher education - Cherry, Michael (Nature, 1997)
cape town South Africa's parliament has approved a major reform of the country's higher education system, despite concern about language policy and central control.
openalex: W1645745948 mag: 1645745948
Keywords: openalex:import

A genealogical study of South African literature teaching at South African universities : towards a reconstruction of the curriculum - Chetty, Rajendra (1997)
openalex: W655163533 mag: 655163533
Keywords: openalex:import

Reading, Rioting, and Arithmetic: The Impact of Mission Education on Black Consciousness in South Africa - Comaroff, Jean (中央研究院民族學研究所集刊, 1997)
openalex: W2293348500 mag: 2293348500
Keywords: openalex:import

Historiographical and methodological trends in the teaching and curriculum development process of history in a changing South Africa - Eeden, Van; Elize, S (Historia, 1997)
Historiografiese en metodologiese strominge in die onderrig en kurrikulumontwikkelingsproses van in 'n veranderende Suid-Afrika Suid-Afrika is tans op die vooraand van insiggewende veranderinge op onderwysvlak. as vak staan baie duidelik sentraal in hierdie veranderinge. Hiervan spreek die kontroversie om die vak boekdele. Die dryfvere vir hervertolking, innovasie en vernuwing van geskiedenissillabusse oor die afgelope aantal jare het aan etlike nuwe strukture of prosesse beslag gegee. Sommige strukture is as kontroversieel gesien, en ander is te emosioneel verbonde aan die apartheidsverlede. Die koorsagtige haas vir regstellende veranderinge van geskiedenisinhoud, sowel as die verwydering van die benaming Geskiedenis op skoolvlak kan in so 'n mate eerste prioriteit word dat universele tendense in geskiedenisonderrig (metodologies en historiografies) geignoreer kan word, of selfs in die volgende paar jaar in Suid-Afrika kan stagneer. In a dynamically changing South Africa, History as subject holds a key position in the striving for change. The former provincial education departments are regarded to have been autocrative white eurocentric systems. To date history syllabi used in South Africa were developed by associated members and specialists of these departments. The drive for reinterpretation, innovation and revitalisation of history syllabi over the past years gave rise to numerous discussions and new structures - some of which are regarded as quite controversial, emotional and belonging to the so-called apartheid past. So feverish may the quest for affirmative change in the contents, and even the name of History on school level, become that for example universal trends in History teaching (methodologically and historiographically) might sadly stagnate or be totally neglected in South Africa in the years to come.
openalex: W2282304155 mag: 2282304155
Keywords: openalex:import

Health outcomes among african american and caucasian adults following a randomized trial of an asthma education program∗ - Ford, Marvella E.; Havstad, Suzanne; Tilley, Barbara C.; Bolton, Mary Beth (Ethnicity and Health, 1997)
Re-analysis of a randomized trial of an asthma education program designed to assess the effects of the intervention on emergency department visits, limited days of activity and asthma knowledge and beliefs separately for African American and Caucasian adults with asthma.Two hundred and forty-one respondents between the ages of 18 and 70 were evaluated in two emergency departments (one inner city and one suburban location) of a large, midwestern health care system and were randomized to an intervention or control group.Regardless of race, members of the intervention group showed a decrease in the number of post-intervention emergency department visits (ANOVA interaction between race and group effect p value = 0.93). The greatest decrease occurred during the first four post-intervention months. No differential effect of the asthma education intervention by race was found on the change in asthma knowledge and beliefs over the study period (ANCOVA interaction between race and group effect p value = 0.60).This study demonstrates that post-intervention, both African American and Caucasian study participants showed a decrease in emergency department visits and an increase in asthma self-management. This finding is especially important for African Americans, who face increasing asthma mortality and morbidity.
openalex: W1976526094 mag: 1976526094
Keywords: openalex:import

Research, Extension and Training Needs for Agroforestry Development in Southern Africa - Govere, Ephraim M. (Southern African forestry journal, 1997)
SYNOPSIS The socio-economic lifeline of Southern African Development Community (SADC) countries (Angola, Botswana, Lesotho, Malawi, Mauritius, Mozambique, Namibia, South Africa, Swaziland, Tanzania, Zambia and Zimbabwe) is anchored on agriculture and agricultural related enterprises. There is a growing realisation that the lifeline can collapse unless sustainable land-use systems that harmonise land-derived benefits with environmental components (soil, fauna, flora, water and air) are adopted. Among the land-use systems practiced in SADC, agroforestry has the potential to become one of the key strategies in SADC's endeavour to provide multiple benefits with minimum degradation to the environmental components. However, the introduction and implementation of agroforestry activities and the degree of success depend on a clear awareness of the agroforestry development needs. This paper presents agroforestry research, extension and training needs as identified at an international workshop held at the University of Alberta, Canada, and at a seminar held at the University of Zimbabwe, Zimbabwe. It is hoped that the information presented will facilitate coordinated agroforestry activities in the SADC region and increase the efficiency and effectiveness in implementing the activities.
openalex: W1998756159 mag: 1998756159
Keywords: openalex:import

Community education to encourage use of emergency obstetric services, Kebbi State, Nigeria - Gummi, F Bello; Hassan, M; Shehu, D; Audu, L R (International Journal of Gynecology & Obstetrics, 1997)
Focus group discussions and a mini-survey in Kebbi State, Nigeria, revealed poor knowledge of obstetric complications, lack of confidence in health services, and cultural barriers to seeking care.After upgrading services in emergency obstetric facilities, the team began community education to encourage utilization. Messages focused on recognition and need for prompt treatment of complications, and addressed men's role as decision-makers. Beginning in 1992, messages were disseminated through weekly meetings with community opinion leaders, video shows, posters and handbills.A post-intervention mini-survey showed knowledge gains of over 30% among women and men. The increase was greatest (59% increase among women and 55% among men) on the need for prompt care for women with obstetric complications. However, utilization of emergency obstetric services did not increase. At Maiyama Maternity Center, referrals declined from 18 in 1992 to four in 1995. At Jega Health Center, referrals remained relatively stable at 20-30/year, but the number of women with major obstetric complications treated declined from 234 in 1992 to 136 in 1995. At Birnin Kebbi Specialist Hospital, the referral center, the number of women with complications treated declined from 200 in 1990 to 152 in 1995.The cost of community education was approximately US $9500, of which 15% was contributed by the community.Increased awareness of the signs of obstetric complications and the need for prompt treatment among community women and men did not result in greater utilization of emergency obstetric services at the facilities studied.
openalex: W2059002051 mag: 2059002051
Keywords: openalex:import

Improving the quality of obstetric care at the teaching hospital, Zaria, Nigeria - Ifenne, D. I.; Essien, E.S.; Golji, N; Sabitu, Kabir; Alti-Mu'azu, M; Musa, Abdullahi; Adidu, V; Mukaddas, M (International Journal of Gynecology & Obstetrics, 1997)
Abstract Preliminary studies: Research at Ahmadu Bello University Teaching Hospital (ABUTH), Zaria, Nigeria, showed delay in treating women with obstetric complications and highlighted multiple contributing factors. Interventions: In response, a surgical theater was restored to working order, the maternity ward renovated, resident physicians trained in obstetrics and an emergency drug pack system instituted. A system of blood donation from families of women attending antenatal clinics was introduced. Later, community interventions focused on improving access and reducing delay in seeking care. Results: Mean admission‐to‐treatment interval was reduced by 57%, from 3.7 h in 1990 to 1.6 h in 1995. The proportion of women treated in less than 30 min increased from 39% in mid‐1993 to 87% in late 1995. Case fatality rate (CFR) among women with major obstetric complications fell from 14% in 1990 to 11% in 1995. The annual number of women with complications seen, however, declined from 326 in 1990 to 65 in 1995. Costs: Cost of material improvements was approximately US $135 000, of which 65% was provided by government. An additional $8000 per year in new staff salaries was paid by the government. Conclusions: Hospital obstetric services can be improved and government can be mobilized to contribute. Treatment delay and obstetric CFR can be reduced. Deteriorating economic conditions, however, may diminish utilization of services despite improvements. © 1997 International Federation of Gynecology and Obstetrics
openalex: W2027562163 mag: 2027562163
Keywords: openalex:import

Students' Perceptions of Science and Technology in Botswana and Lesotho - Kent, David; Towse, Peter (Research in Science & Technological Education, 1997)
Abstract Master's students were involved in the design, and later the administration, of a questionnaire for 500 junior secondary students in Botswana and Lesotho, to buildup a picture of student perceptions of science and technology. Responses to mainly open‐ended questions were categorised according to key phrases mentioned by the students. There was some confusion over the differences between science and technology, but they were overwhelmingly perceived as subjects appropriate to both sexes. Science and technology were seen in broad socio‐economic terms, enabling people to cope in the modern world, gain employment in both the formal and informal sectors, and contribute towards national development. Although science and technology were judged to have enhanced the quality of life, they had introduced conflicts into traditional beliefs and cultures, in part as a result of increasing female emancipation. The attitudes of the students towards the two subjects, and to the impact they have had on everyday life, were congruent with the philosophical aims of the science and technology syllabuses of both countries and with global initiatives such as Project 2000 +.
openalex: W2026404030 mag: 2026404030
Keywords: openalex:import

Reaching Unreached Learners in Mozambique: A Report to the Minister of Education on Learning Needs and Alternative Pathways to Learning in the Perspective of an Integrated Response to the Needs of a Rapidly Developing Society in a Complex World. - Klees, Steve; Matangala, Anisio; Spronk, Barbara; Visser, Jan (1997)
openalex: W227101044 mag: 227101044
Keywords: openalex:import

The South African Schools Act of 1996: A Break with the Past. - Maithufi, I. P. (1997)
openalex: W43730451 mag: 43730451
Keywords: openalex:import

Contamination of traditional drinking water sources during a period of extreme drought in the Zvimba communal lands, Zimbabwe. - Moran, Patrick; Nhandara, C; Hove, Innocent; Charimari, Lincoln; Katito, Campbell; Bradley, Melissa A.; Williams, M A (PubMed, 1997)
Diarrhoeal disease is a significant public health concern in Zimbabwe, particularly for the population living in rural settings. The present study was undertaken to investigate the quality of water in a rural area of Zimbabwe during a period of extreme drought.A cross sectional survey study design was used. During the month of July 1995, water samples were collected from various actively used sources in the Zvimba communal lands, Zimbabwe.The level of contamination was estimated by use of the membrane filtration technique to detect the presence of Escherichia coli.Mean concentrations of E. coli found in boreholes and piped water were 9.3 and zero colonies per 100 ml, respectively. Using standardized criteria to define suitable drinking water quality, borehole and piped sources were determined to be more likely to provide satisfactory drinking water.Water samples collected from semi-protected and unprotected wells, which serve the majority of the population in the study area, were found to be unsatisfactory for drinking (range from two to 1,960 colonies of E. coli per 100 ml). Included are suggestions on how to efficiently utilize available water.
openalex: W1517658129 mag: 1517658129
Keywords: openalex:import

Self-Concept and Social Acceptance in Multiracial African Schools: A Test of the Insulation, Subjective Culture, and Bicultural Competence Hypotheses - Mpofu, Elias; Watkins, David (Cross-Cultural Research, 1997)
Self-concept and social acceptance were examined for a sample of 154 Black and 203 White Zimbabwean schoolchildren attending racially integrated schools. Marsh's Self-Description Question naire-1 and multiple measures of social acceptance were used. Although Black children had levels of global self-esteem compara ble with, or higher than, that of their White classmates, Black pupils taught by White teachers had significantly lower reading and academic self-esteem. Pupils in classes taught by Black teachers tended to choose for best friends peers in other classes significantly more than did pupils in classes taught by White teachers. Analysis by gender indicated that male pupils tended to have significantly higher physical ability, physical appearance, and math self-esteem and relatively higher levels of social participation than female students. Results partially supported the bicultural competence, subjective culture, and the insulation hypotheses on children's social status in multiracial school contexts.
openalex: W2049092879 mag: 2049092879
Keywords: openalex:import

The development of a teaching practice curriculum for teacher education in Zimbabwe - Ndlovu, Themba Petros (1997)
openalex: W1575214140 mag: 1575214140
Keywords: openalex:import

Physical impacts of regional climate change in the West African Sahel and the question of desertification - Nicholson, S.E.; Ba, Mamoudou B. (1997)
The question of desertification is examined in the West African Sahel region by considering various physical indicators assumed to accompany this process. The study considers only the past 14 years, since the availability of comprehensive satellite data sets. The physical indicators examined include vegetation cover, surface albedo, soil moisture, wind-borne dust, river flow, lakes, and the ratio of available moisture to vegetation growth. Vegetation cover and albedo are assessed from satellite data. Soil moisture is assessed using a surface hydrologic model. Dust is estimated from visibility measurements. The most important results are that: (1) there is no progressive change in the vegetation cover, (2) an increase of albedo as the region dries up cannot be documented, and (3) there has been a tremendous increase in wind-borne dust over the Sahel. The vegetation cover responds almost directly to rainfall and the movement of the desert boundary corresponds roughly to rainfall fluctuations. The most important meteorological effect of the drought and/or desertification in the Sahel may be the enhanced dust generation, with the region becoming a major global source of atmospheric mineral dust. 5 refs., 7 figs., 1 tab.
openalex: W2292695115 mag: 2292695115
Keywords: openalex:import

Community education to improve utilization of emergency obstetric services in Ghana - Opoku, Stephen; Kyei-Faried, S.; Twum, Stephen Boakye; Djan, J.O.; Browne, Edmund; Bonney, Joseph (International Journal of Gynecology & Obstetrics, 1997)
Abstract Preliminary studies: Focus group studies in the Ashanti region showed that people avoided utilizing health facilities because of lack of confidence in the services and concern about the availability of drugs and supplies, among other reasons. Interventions: After services at the health center were upgraded, community education activities began in early 1994. These activities were carried out through existing mechanisms — e.g. Ministry of Health (MOH) outreach workers and village health workers, public health nurses and midwives, and village health committees. They addressed a variety of audiences, including women's and church groups, emphasizing early recognition and treatment of obstetric complications, and the improved availability of services. Results: The number of women with obstetric complications admitted to the health center rose from 26 in 1993 to 73 in 1995. It was the impression of the health center staff that women were also coming for treatment more promptly. Costs: The cost of this intervention was US$1950. This was mostly project funds, with the government and community together contributing approximately one‐fifth. Conclusions: Once services are available, community education and information activities can enhance utilization. The cost of such activities can be reduced, and sustainability promoted, by involving MOH personnel and community groups. © 1997 International Federation of Gynecology and Obstetrics
openalex: W2120186604 mag: 2120186604
Keywords: openalex:import

Italian schools in Egypt - Petricioli, Marta (British Journal of Middle Eastern Studies, 1997)
Abstract This paper analyses the relevance of the Italian schools in Egypt from 1922 to 1940. The Italian fascist regime made a concerted effort to improve the quality of its schools abroad in order to enrol the greatest number of children from the families of the large Italian colony. Their aim was to improve their chances of finding a job in Egypt after leaving school and to indoctrinate them with the fascist ideology. This effort failed because of the changes brought about by the abolition of Capitulations in Egypt (1937), and because the Italian anti‐Semitic laws (1938) led the Italian Jews of Egypt to send their children to French and British schools. In 1940, with Italy's entry into World War II, all the Italian schools in Egypt were closed by the Egyptian authorities.
openalex: W2094730726 mag: 2094730726
Keywords: openalex:import

Teaching about Democratization in the High-School Classroom: The Case of South Africa - Rossi, John Allen; Tlou, Josiah (The Social Studies, 1997)
openalex: W2075767618 mag: 2075767618
Keywords: openalex:import

Potential Demand for Drought Insurance in Burkina Faso and Its Determinants - Sakurai, Takeshi; Reardon, Thomas (American Journal of Agricultural Economics, 1997)
Abstract The objectives of this paper are twofold: ( a ) to estimate demand for formal drought insurance using farm household data in Burkina Faso and ( b ) to find what determines insurance demand. The following findings are salient. First, effective demand is found in all zones, which implies inadequacies in households' current self‐insurance strategies. Second, there is much heterogeneity in the strategies to self‐insure even within zones. Third, the expectation of public food aid decreases demand for drought insurance, which suggests that food aid is causing moral hazard. Fourth, households with large livestock holdings can reduce the size of herd by substituting drought insurance for livestock holdings.
openalex: W2118793744 mag: 2118793744
Keywords: openalex:import

Teaching tropical medicine in Kenya and Uganda: Review after seven expeditions - Schaefer, K. U. (Wilderness & Environmental Medicine, 1997)
Traveling to the tropics is becoming more popular in the Western world [1].As a result an increasing number of tourists, businessmen, and politicians return to their home countries with tropical infectious diseases.The severe but subsequently cured malaria infection of the German Minister of Economics, who was on an official visit to Sub-Saharan Africa in the summer 1996, has been one of many examples.The continuous stream of refugees and asylumseekers to Europe and North America [2] presents health care professionals with tropical infectious diseases that they have not seen before.As global warming becomes a likely event, tropical infectious diseases will assume an even greater profile in the coming years in temperate climates [3].Recent figures in European hospitals have shown that an increasing number of malaria patients were not recognized on first observation [4J.This indicates that health care professionals in the Western world require further practical experience in clinical tropical medicine, and this has been the objective of these expeditions to Kenya and Uganda.
openalex: W1979244419 mag: 1979244419
Keywords: openalex:import

Evolution Education in Papua New Guinea: trainee teachers’ views - Vlaardingerbroek, Barend; Roederer, Christopher J. (Educational studies, 1997)
Summary Educated Papua New Guineans’ conceptual ecologies need to accommodate competing and conflicting traditional ethnoscientific, Western religious and modern scientific paradigms. Papua New Guinea is a constitutionally self-declared ‘Christian country’ and evolution is a controversial issue. The upper secondary school biology syllabus contains a terminating unit on evolution but the curriculum is of expatriate design and the rapid localisation of senior educational positions makes the views of indigenous teaching personnel a high research priority, particularly in the light of the current upgrading of secondary teacher training to degree level. This paper presents data arising from a study of trainee primary and secondary science teachers’ views towards evolution education. Primary science trainees were found to exhibit a poor awareness of the centrality of evolution to modern biology. For secondary science trainees, it was found that exposure to upper secondary school biology, in spite of adding little to students’ knowledge about evolution, was associated with their increasingly positive attitudes towards evolution education, as was the dual acceptance of evolution and religious belief.
openalex: W1999708884 mag: 1999708884
Keywords: openalex:import

Assessing the Learning Processes of Black South African Students - Watkins, David; Mboya, Mzobanzi M. (The Journal of Psychology, 1997)
Abstract Data based on responses of 126 male and 201 female 14- and 15-year-old Black South African secondary school students showed the Learning Process Questionnaire (LPQ; Biggs, 1987) to be fairly reliable and factorially valid. Comparison with the LPQ means for like-aged students from Australia and Hong Kong called into question the common assertion that Black South African students are more prone to use superficial learning processes than are Western students. In particular, the South African responses to the LPQ indicated that they were less shallow and more oriented toward achievement in their approach to learning than the Australian students were.
openalex: W2107852520 mag: 2107852520
Keywords: openalex:import

A role for pneumolysin but not neuraminidase in the hearing loss and cochlear damage induced by experimental pneumococcal meningitis in guinea pigs - Winter, Andrew; Comis, S. D.; Osborne, Michael P.; Tarlow, M J; Stephen, J.; Andrew, PW; Hill, Jonathan; Mitchell, Tim (Infection and Immunity, 1997)
We investigated the roles of pneumolysin and neuraminidase in the pathogenesis of deafness and cochlear damage during experimental pneumococcal meningitis. Anesthetized guinea pigs were inoculated intracranially with 7.5 log10 CFU of either (i) wild-type Streptococcus pneumoniae D39 (n = 8), (ii) PLN-A, a defined isogenic derivative of D39 deficient in pneumolysin (n = 5), or (iii) deltaNA1, a new derivative of D39 deficient in neuraminidase constructed by insertion-duplication mutagenesis of the nanA gene (n = 5). To quantify hearing loss, the auditory nerve compound action potential evoked by a tone pulse was recorded from the round window membrane of the cochlea every 3 h for 12 h. The organ of Corti was intravitally fixed for subsequent examination by high-resolution scanning and transmission electron microscopy. All animals sustained similar meningeal inflammatory responses. PLN-A induced significantly less hearing loss than D39 over the frequency range of 3 to 10 kHz. Levels of mean hearing loss at 10 kHz 12 h postinoculation were as follows: D39, 50 dB; deltaNA1, 52 dB (P = 0.76 versus D39), and PLN-A, 12 dB (P < 0.0001 versus D39). The mean rates of hearing loss at 10 kHz were 4.4 dB/h for D39, 4.3 dB/h for deltaNA1, and just 1.0 dB/h for PLN-A (P < 0.0001 versus D39). Suppurative labyrinthitis was universal. PLN-A induced the accumulation of less protein in the cerebrospinal fluid (P = 0.04 versus D39). Infection with D39 and deltaNA1 induced significant damage to the reticular lamina, the sensory hair cells, and supporting cells of the organ of Corti. By contrast, after infection with PLN-A, the organ of Corti appeared virtually intact. Pneumolysin seems to be the principal cause of cochlear damage in this model of meningogenic deafness. No clear pathogenic role was demonstrated for neuraminidase.
openalex: W1914479285 mag: 1914479285
Keywords: openalex:import

Racial Identity Attitudes, School Achievement, and Academic Self-Efficacy Among African American High School Students - Witherspoon, Karen McCurtis; Speight, Suzette L.; Thomas, Anita (Journal of Black Psychology, 1997)
Literature has postulated that African American students often choose not to succeed in school because achievement is seen as acting White. This study examined the extent to which racial identity, self-esteem, and academic self-concept were related to academic achievementfor 86African American high school students. The majority of students indicated supportfrom both peers and parents for their academic work. Multiple regression analysis indicated that grade point average is best predicted by immersion racial identity attitudes and academic self-concept. Limitations of the present study, implications, and suggestionsforffuture research are presented.
openalex: W2149320624 mag: 2149320624
Keywords: openalex:import

When the world is menstruating. thoughts on drought and desert aming the Ovahimba of North-West Namibia - Wolputte, Steven Van (1997)
openalex: W2519910475 mag: 2519910475
Keywords: openalex:import

Child labour or school attendance? Evidence from Zambia - Jensen, Peter; Nielsen, Helena Skyt (Journal of Population Economics, 1997)
openalex: W2094483295 mag: 2094483295
Keywords: openalex:import

Speech, Language, Learning, and the African American Child - Keulen, Jean E. van; Weddington, Gloria; DeBose, Charles (1997)
All chapters include Chapter Overview, Summary, and References and most chapters include Practical Application. Preface. By Way of Introduction: Race, Culture, Ethnicity and African American English. 1.Higher Ground: The Knowledge Base of African American Language and Cultural Studies. Linguistics. Linguistics System. African Continuities. All Languages Are Equal. Speech-Language Pathology. Biased Based Criteria. Education. African American Experience: Past and Present. Deficit Models. Multicultural Education. Pedagogical Implications. 2.Descriptive versus Prescriptive Grammar. Contrasting Properties of Descriptive and Prescriptive Rules. Native Speaker Intuitions and Grammaticality. Grammar as a Description of Language. Dialectical Differences. Prescriptive Rules Frequently Violated by Speakers of High-Prestige Dialects. 3.African American Bilingualism. The Situational Nature of Language Use. Sociolinguistics. The Cultural Context of Social Situations. African American Oral Literature. The Language Situation in Black America: Class Stratification or Code Switching. 4.African American Bilingualism. What Should the Language of African Americans Be Called? Is African American Language a Different System from Standard English? The Uniqueness of the African American English Lexicon. What Type of Linguistic System Is African American Language? The Origin of African American English. 5.African American Communication Styles. The General Communication Process. Psychological Themes. Emotional Vitality. Meanings and Values of Black and White Communication Styles and Cultures. Language Style. Core Symbols of Communication Styles. 6.Speech and Language Disorders versus Differences. Normal Language Acquisition. Communication Disorders. 7.Diagnosis of Communication Disorders of African American Children. The Assessment Process. Assessment Procedures. Communicating Assessment Information to Parents. Communicating with Teachers. The Written Report. 8.Educational Assessment Practices and African American Students. Cultural Influences on the Assessment of Black Children. Legislated Nondiscriminatory Evaluation. Observation of Student Behaviors. 9.Treatment of Speech-Language Disorders. Service Delivery for African Americans. Qualities Required to Serve African American Clients. Determining Therapy Goals from Assessment Results. Instructional Methods. 10.Facilitating Standard English Acquisition for African American Children. Standard English. Correcting. Language Acquisition. Modeling. Role Playing. Immersion, and Grouping Strategies which Facilitate Language Acquisition. The Reading Hypothesis. The Writing Process. Dialect Readers and Multicultural Literature. 11.School Biases and African American Children. Overrepresentation in Special Education Classes. Cultural Discontinuity. Traditional American Schools. 12.Importance of Spoken Language to Reading Skills. Language and Literacy: The Black Child. Teacher Attitudes and Black Student's Language. Selecting Reading Materials and Activities. 13.Empowering African American Children. Teachers' Influence on Empowerment. Building Self-Respect. Developing Positive Self-Images and Self-Esteem. Parents' Influence on Self-Esteem, Self- Discipline, and Empowerment. Parental Influence on Black Child Development.
openalex: W617216062 mag: 617216062
Keywords: openalex:import

Pollution of groundwater in the coastal Kwale District, Kenya - Tole, Mwakio (IAHS-AISH publication, 1997)
Groundwater is a last-resort source of domestic water supply at the Kenyan coast because of the scarcity of surface water sources. NGOs, the Kenya Government, and international aid organizations have promoted the drilling of shallow boreholes from which water can be pumped using hand- operated pumps that are easy to maintain and repair. The shallow nature and the location of the boreholes in the midst of dense population settlements have made these boreholes susceptible to contamination from septic tanks and pit latrines. Thirteen percent of boreholes studied were contaminated with E. coli, compared to 30% of natural springs and 69% of open wells. Areas underlain by coral limestones show contamination from greater distances (up to 150 m away) compared to areas underlain by sandstones (up to 120 m). Overpumping of the groundwater has also resulted in encroachment of sea water into the coastal aquifers. The 200 ppm CI iso-line appears to be moving increasingly landwards. Sea level rise is expected to compound this problem. There is therefore an urgent need to formulate strategies to protect coastal aquifers from human and sea water contamination.
openalex: W350361993 mag: 350361993
Keywords: openalex:import

The South African One Thousand Schools Project and Stephens' Quality Wheel - Brown, Mandy; Ashley, Michael (Systems practice, 1997)
openalex: W2071134220 mag: 2071134220
Keywords: openalex:import

The hearthhold in pastoral Fulbe society, central Mali: social relations, milk and drought - Bruijn, Mirjam de (Africa, 1997)
Abstract In pastoral Fulbe society in central Mali women had and in some degree still have an important social and economic role, concentrated on a milk economy organised through a special female-headed, women-centred unit called by the Fulbe fayannde , or ‘hearthhold’. In a society of semi-nomadic pastoralists who live most of the year in small social units, social relations and networks are very important, perhaps even crucial to the success of their main survival strategy, which is transhumant cattle-keeping. In the literature on the Fulbe this social unit has received relatively little attention. An analysis from the perspective of the ‘hearthhold’ sheds new light on property and gender relations in Fulbe society in general. Drought has had an enormous impact on the situation of the Jallube studied in this article. Economic change—a switch to agriculture and production for the market—has brought about a shift of focus for the men. Economically, milk is no longer essential for them, and hence the fayannde loses its importance; socially, too, the role of the fayannde , as symbolised by milk, is changing. For women the erosion of the fayannde is serious: an analysis of marriage gifts shows how important the fayannde is not only to the social organisation of the Jallube but also to their economic viability. In times of stress this importance may be greater for women than for men. The decline of the fayannde may lead to a transformation of gender relations, the marriage ceremony and women's social security—changes that the return of the rains or the re-establishment of herds may not reverse.
openalex: W2011891360 mag: 2011891360
Keywords: openalex:import

Education and the Marginalisation of Girls in Post‐GATT Mauritius - Bunwaree, Sheila (Compare: A Journal of Comparative and International Education, 1997)
This paper describes the history and geography of Mauritius and its elitist colonial educational system; presents a literature review of female education, development, and position in the labor market; discusses the economy in the post-GATT era and wasted potential; and calls for a new educational order. Mauritius has a multiplicity of cultures and a complex cultural, socioeconomic, and political context. French colonialism is characterized as limiting expansion of education on the island. Education was expanded under British colonial rule; mass education was promoted, but not much changed in the nature and role of schooling. The elites of today are those descendants of diverse ethnic people who managed to become educated. Mauritians are marginalized today due to the lack of implementation of its official policy of equal opportunity. About 6% of primary school children leave the system illiterate. About 20% are functionally illiterate. Many leave primary schools without passing the Certificate of Primary Education tests. A 1994 survey indicated that female labor force participation rates were higher among persons with lower levels of education. Women have a subordinate role in the labor market due to a long history of a subordinate role, gender inequity, a large concentration of women in the clothing sector of the Export Processing Zone, and gender segregation in managerial and professional occupations and advancement. Some associate development with marginalization of women. Teachers and textbooks reinforce gender roles. Mauritius needs to retain students, gender sensitize the educational system, and eliminate job discrimination.
openalex: W2070749847 mag: 2070749847
Keywords: openalex:import

British ‘practice’ towards Islam in the East Africa protectorate: Muslim officials,Waqfadministration, and secular education in Mombasa and environs, 1895–1920 - Carmichael, Tim (Journal of Muslim Minority Affairs, 1997)
openalex: W2043950733 mag: 2043950733
Keywords: openalex:import

Cultural orientation and use of cannabis and inhalants among secondary school children in Zimbabwe - Eide, Arne Henning; Acuda, S. W. (Social science & medicine (1982. Print), 1997)
A survey among 3061 secondary school children in four provinces in Zimbabwe was conducted in 1994. In the present paper, the relationships between cultural and social factors and use of inhalants and cannabis are explored. Respondents were selected by means of a two-stage sample design, first based on a complete list of schools in the four provinces and subsequently on lists of students at the randomly selected schools. Stratification was based on the identification of four different sociocultural groups. Data collection followed standardised procedures and was conducted by a research team from University of Zimbabwe. Cultural orientation was operationalised by means of a Likert-type 14-item scale on choice of media, language and music. Exploratory principal component analysis revealed a two-factor solution, representing a global or Western cultural orientation and a local or Zimbabwean cultural orientation. Drug use by older siblings and best friends represented social factors. A combined model of cultural and social variables was subject to a multiple logistic regression analysis. Results revealed that the social variables and global cultural orientation were significantly associated with increased use of both drugs, whereas a local cultural orientation was found not to be associated with use of these substances. Findings are discussed in the light of historical and cultural factors.
openalex: W2075356768 mag: 2075356768
Keywords: openalex:import

Dialogic Education and the Schemas to Guide Dialogue: An Example from Malaria Research in Guinea - Gordon, Andrew; Baldé, Karim Abdul (The International Quarterly of Community Health Education, 1997)
This article first reviews the importance of dialogical education in general and in malaria control specifically. Dialogical education requires knowledge of how people think as well as what people think. Through a mutual appreciation of the educators' and learners' respective frame of reference, the intended learners may come to appreciate differences between the educators' and learners' viewpoints and the ways these differences may constrain understanding and acceptance of new knowledge and practices. Dialogical education is presented as a means by which all involved in health education (professionals and non-professionals, those educating on-the-job, and those doing it informally) may be involved in health education. The appropriate presentation of research findings is central to the task of preparing for dialogical education. This article then discusses the discovery and the presentation of a culture's schemas. Schemas are concisely stated formulations of cultural orientation. They are core principles and rules. The schemas of the intended learner are critical for the educator to know so as to educate in a dialogic mode, to motivate acceptance and understanding. The schemas for malaria held by the Fulani of Guinea, West Africa, are presented as a case in point for a presentation of research findings in a form that is concise, comprehensible, accessible, and useful for nourishing dialogical education.
openalex: W2138175321 mag: 2138175321
Keywords: openalex:import

Anthropometric study of Ethiopian pre-school children. - Hailu, Asrat; Tessema, Tsegaw Muche (PubMed, 1997)
A community based cross sectional anthropometric study was conducted to assess the nutritional status of children under 5 years of age in north western Ethiopia. One thousand four hundred and twenty two children were enrolled in the study. Stunting which is expressed by height for age below -2 standard deviation (SD) was seen in 43% of the children. The prevalence of wasting which is expressed by weight for height below -2 SD was 9%. The highest percentages of stunting and wasting were found in the age group 12-23 months. Compared with the national Center for Health Statistics (USA)/World health organization (NCHS/WHO) reference data all the indicators were shifted to the left. Urgent nutritional rehabilitation for those that are wasted, proper nutritional education for reducing the high prevalence of malnutrition and identifying risk factors for the poor nutritional status is suggested.
openalex: W2405084500 mag: 2405084500
Keywords: openalex:import

The quality of education in the Middle East and North Africa (MENA) - Heyneman, Stephen P. (International Journal of Educational Development, 1997)
The quality of education is an issue in every region undergoing economic change, hence it is a universal issue. Where the quality of education is already low, the need to raise it is more urgent. In the Middle East and North Africa, data on educational quality are scarce. Nevertheless, available data would suggest that the quality of education is low. The cause of the problem, however, is not a scarcity of monetary resources but the inefficiency of managing the resources already allocated. Many of the regulations and traditions for managing educational systems in the Middle East and North Africa have their origin in the era of central economic planning. Changes are suggested in six areas. These include: an end to early vocational tracking; coherence in content between curriculum, examinations, textbooks and classroom teaching; a shift in textbook production away from state monopolies; a professionalized teaching force with higher salaries differentiated by mandatory re-licensing; creative financing and provision of higher education; and a significant improvement in education statistics and indicators of progress.
openalex: W2149054514 mag: 2149054514
Keywords: openalex:import

The Emergence of an Industrial Workforce: Recruitment and Training in the Papua New Guinea Mining Industry - Imbun, Benedict Y (International journal of employment studies, 1997)
The emergence of an industrial workforce in the Papua New Guinea mining sector and its human resource implications are tentatively explored in the following article. The central theme is the role of recruitment and training on greenfield sites in the remote locations where the mines are situated. The research is based on available documentary evidence and fieldwork interviews with mining company management, employees and community representatives. The findings are discussed within the context of Kerr et al.'s general model of the industrialising process.
openalex: W2247277595 mag: 2247277595
Keywords: openalex:import

[Sexuality of adolescent students in Yaounde (Cameroon)]. - Kamtchouing, P.; Takougang, Innocent; Ngoh, Nkele Ndeki; Yakam, I (PubMed, 1997)
Undesired pregnancies are a major cause of school drop out among female adolescents in Cameroun. Studies were undertaken to assess the knowledge and practices of contraceptive methods and the prevention of undesired pregnancies and sexually transmitted diseases (STD). Of the 670 questionnaires that were distributed in 10 class rooms of 5 randomly selected secondary schools of the city of Yaoundé. 574 students responded among whom 233 males and 341 females, aged 12 to 19 years. The responses to the questionnaire revealed that 52% of the students were sexually active, and 56% of these had their first sexual intercourse between 15 and 17 years. The use of contraceptives was reported by 41% of the sexually active students. The main contraceptive methods used were condoms (54%) and periodic abstinence (31%). Periodic abstinence, coitus interruptus report by adolescents is of questionable efficacy in the prevention of STDs, and unwanted pregnancies. The average number of sexual intercourses was 5 times during the month before the survey. The rate of undesired pregnancies was 24%. Knowledge on contraception was more from the mass media (53%), school (21%), peers (16%), than parents (9%). Education for the deculpabilisation of contraception and a better management of sexuality should be undertaken in youth associations and schools. Parents should be taught to dialogue with their children on matters related to sexuality, in order to prevent STDs, unwanted pregnancies, clandestine abortions and their psychological and medical consequences.
openalex: W2417050762 mag: 2417050762
Keywords: openalex:import

Moi scuppers sex-education plans in Kenya - Kigotho, Anderson Wachira (Lancet (British edition), 1997)
President Daniel arap Moi and the ruling party of Kenya, KANU (Kenyan African National Union), have bowed to election year pressure from anti-abortion groups and Catholic bishops, including Bishop Alfred Rotich who led a anti-sex education demonstration in Nairobi, and shelved a sessional paper on family life education that was to be discussed by parliament this month. If the paper had been adopted, sex education could have been introduced in the schools and integrated with primary health care. The document would have been the basis for making students aware of the dangers of adolescent pregnancy, abortion, drug abuse, HIV/AIDS, and sexually transmitted diseases (STDs). 12% of the girls who leave school are pregnant or have married early; 10,000 girls become pregnant per year according to Ministry of Education estimates. The local AIDS council believes that the pandemic is on the rise among Kenyan youth; it is estimated that 1-3 million persons will become infected by the year 2000 and that Kenya will have more than a million AIDS orphans. Real intervention would be to create awareness and provide family planning services, according to the council. Bishop John Njue, Chairman of the Kenya Episcopal Conference, states that the Catholic Church will fight any introduction of sex education in the schools.
openalex: W2079580579 mag: 2079580579
Keywords: openalex:import

Strategies for Survival in Kenya: Women, Education, and Self-Help Groups - Mbugua-Murithi, Tata (International journal of educational reform, 1997)
openalex: W33280948 mag: 33280948
Keywords: openalex:import

Distance teacher education in South Africa: A critical analysis of pedagogical assumptions - Modiba, Maropeng (Teaching and Teacher Education, 1997)
Distance education has, historically, been advanced as a major means of upgrading the quality of African teachers in South Africa. There is, however, little knowledge of the quality of existing materials currently in use. Nor is there much work yet focusing on the pedagogical assumptions contained in these distance upgrade programmes. This paper evaluates a few sections in the materials dealing with education theory, and concludes that both content and pedagogical forms do not explore the experiences and views of practising teachers working through these materials. In the light of this observation it is argued that distance education can only be a successful mode of upgrading teachers if both content and pedagogy of materials are improved.
openalex: W2003015507 mag: 2003015507
Keywords: openalex:import

Attendance, schooling quality, and the demand for education of Mexican Americans, African Americans, and non-Hispanic whites - Mora, Marie T. (Economics of Education Review, 1997)
This study examines the influence of the opportunity costs of school attendance, educational quality attributes, and household socioeconomic status on the educational demand of Mexican Americans, African Americans, and non-Hispanic whites using the 1988–1990 surveys of the National Education Longitudinal Study. Implementing a utility-maximizing framework, educational demand assumes the form of schools' average daily attendance rates and student dropout decisions between the 8th and 10th grades. The basic results suggest that a school's attendance rate is sensitive to educational quality and student characteristics. Moreover, the demand for education measured by student attrition inversely relates to unexplained school attendance, and is positively affected by household socioeconomic status. Some policy recommendations based on the results are discussed.
openalex: W2005795508 mag: 2005795508
Keywords: openalex:import

SCHOOL PSYCHOLOGY PRACTICES IN EAST AND SOUTHERN AFRICA: SPECIAL EDUCATORS' PERSPECTIVES - Mpofu, Elias; Zindi, Fred; Oakland, Thomas; Peresuh, M. (Journal of Special Education, 1997)
A semistructured questionnaire was used to collect data on the practice of school psychology in 12 East and Southern African countries: Botswana, Eriteria, Ethiopia, Kenya, Lesotho, Malawi, Namibia, Swaziland, Tanzania, Uganda, Zambia, and Zimbabwe. The survey sought to capture consumer perspectives as to the status of school psychology in reference to the following: regulations for school psychology practice, qualification of school psychologists, work settings, public awareness, utilization and need, and research on psychological test use and development. Respondents were 42 special education leaders working in universities ( n = 13), special education institutions ( n = 18), and schools with special education facilities ( n = 11). The need for school psychology services was endorsed in ali 12 countries. Although differences among countries were apparent, the special education experts reported that the availability, regulation, and utilization of school psychology services in the 12 countries to be generally low. Respondents in countries with some formal recognition and regulation of professional school psychology (Namibia, Zambia, Zimbabwe) tended to report greater public awareness and utilization of school psychologists and higher involvement in test development. Findings are discussed within the context of the potential for the development of school psychology services in sub-Saharan African countries.
openalex: W2009544561 mag: 2009544561
Keywords: openalex:import

Teachers' biographies and educational development: a Kenyan case study - Osler, Audrey (International Journal of Educational Development, 1997)
Over the last decade there has been a growing interest among academics in the lives and work of teachers in industrialised countries. Many of these studies have sought to understand how teachers perceive their work and how they develop their particular professional identities. There is a growing recognition of the impact of teachers' own biographies on their training and on curriculum development and implementation. This paper examines the perspectives of a group of Kenyan educators, advisors and inspectors, from different regions, who have taken part in a national project designed to strengthen primary education through the in-service training of teachers. The aim is to examine the potential of biographical research to provide new insights into the processes of educational development. The participants in the research reflect on their own career development and life histories; on their identities, both professional and personal; and on the impact of these on their work. Drawing on an issue which divided the group, that of gender equality, the paper considers some of the biographical and cultural factors which permit and restrict development.
openalex: W2006755898 mag: 2006755898
Keywords: openalex:import

Technological learning in African industry: A study of engineering firms in Nigeria - Oyelaran-Oyeyinka, Banji (Science and Public Policy, 1997)
The engineering sector produces a wide array of products and provides significant technological learning avenues. This study examines the process of technological learning in small and medium-sized engineering firms in four Nigerian cities. It identifies the learning mechanisms adopted by firms and the determinants and motivation for investment. The firms studied were mostly set up by semi-literate traders showing that the learning process can take place without formal education or state intervention. Policy may consider assisting entrepreneurs to obtain more formal education to help them to acquire greater technological mastery. Improvements to the poor infrastructure would bring great benefits to small firms.
openalex: W2118668661 mag: 2118668661
Keywords: openalex:import

Regional discrimination of chemical explosions and earthquakes: A case study in Morocco - Plafcan, Dan; Sandvol, Eric; Şeber, Dog̃an; Barazangi, Muawia; Ibenbrahim, Aomar; Cherkaoui, Taj-Eddine (Bulletin of the Seismological Society of America, 1997)
Abstract To examine the limitations in the techniques for discriminating between chemical explosions and earthquakes at local and regional distances, we have applied several standard heuristics to seismic events in northwest Morocco where little a priori information was available. Although the eight Oud Zem phosphate mine explosions have similar geographic locations, total charge size, and presumably ripple-fired mechanisms, the seismic recordings are characterized by a surprising amount of diversity. Time and path independent modulations, due to the periodic source mechanism of the ripple-fired explosions, rarely unequivocally distinguish the explosions from the earthquakes. Our findings imply that more often than the current literature suggests, source inconsistencies such as differing blasting arrangements have a role in the failure of common discriminants. Furthermore, crustal seismic velocity and the attenuation structure seemed to shape the seismic signals more than the nature of the source mechanism, although site effects could not be ruled out. The 10-to 15-Hz Pg/Sg ratio test proved to be the most precise and accurate discriminant. Popular intraphase spectral and cross-spectral ratios performed considerably worse. Finally, we argue that a regional case-based approach requires extensive regional information to meet the demanding verification goals of the Comprehensive Test Ban Treaty.
openalex: W2132068646 mag: 2132068646
Keywords: openalex:import

The challenges facing energy and climate change policy in South Africa - Praetorius, Barbara (Economic bulletin, 1997)
openalex: W165036555 mag: 165036555
Keywords: openalex:import

African American and White Mothers of Adults with Chronic Disabilities: Caregiving Burden and Satisfaction - Pruchno, Rachel; Patrick, Julie Hicks; Burant, Christopher J. (Family Relations, 1997)
African American and White Mothers of Adults With Chronic Disabilities: Caregiving Burden and Satisfaction* Rachel Pruchno, Ph.D.,** Julie Hicks Patrick, and Christopher J. Burant A model is developed and tested that explains the effects of race on the caregiving experience by patterning relationships between race and several causal agents. Data from 741 White and 100 African American women with adult children having chronic disabilities revealed that while the African American and White subsamples differed from one another in terms of age, education, income, living arrangements, physical health, caregiving burden, and caregiving satisfaction, race had no direct or indirect influence on either caregiving burden or caregiving satisfaction. Rather, variables representing the sociocultural, interpersonal, situational, temporal, and personal contexts which relate to race explained the observed variance in both caregiving burden and caregiving satisfaction. Key Words: caregiving, chronic disability, race. Although African American caregivers typically have lower incomes (Hinrichsen & Ramirez, 1992), are less well-educated (Staples, 1981; Young & Kahana, 1995), are in poorer health (Gibson & Jackson, 1987; Markides, 1989; Mui, 1992; Young & Kahana, 1995), are more likely to be widowed at earlier ages (Hinrichsen & Ramirez, 1992; Mui, 1992), and care for more impaired relatives (Mui, 1992; Young & Kahana, 1995) than their White counterparts, studies indicate that they report lower levels of caregiving burden (Hinrichsen & Ramirez, 1992; Lawton, Rajagopal, Brody, & Kleban, 1992; Macera, 1992; Mintzer & Macera, 1992; Mui, 1992; Young & Kahana, 1995), lower levels of grief (Struening et al., 1995), lower levels of depression, anger, and hostility (Haley et al., 1995; Miller, Campbell, Farran, Kaufman, & Davis, 1995) and higher levels of caregiver satisfaction (Lawton et al., 1992). These unexpected, yet consistent trends beg for explanation. The analyses that follow will develop and test a model that explains the effects of race on the caregiving experience by patterning relationships between race and the ecological niche in which caregiving occurs. The contexts that will be explored, based on a model described by Dilworth-Anderson and Anderson (1994) include the sociocultural, interpersonal, situational, temporal, and personal. These relationships will be examined using data from a sample of mothers who have adult children with chronic disabilities. Examination will focus on the mechanisms that link these contextual variables to the caregiving experience. Attempts to explain why African American caregivers generally fare better than their White counterparts, despite experiencing more stressors and having fewer resources, have taken several different approaches. On the one hand, there have been suggestions that studies may be contrasting the most fit African Americans, those people who have survived to old age, with a more heterogeneous group of Whites (Gibson, 1982; Jackson, Chatters, & Neighbors, 1982; Manton, Poss, & Wing, 1979; Markides & Black, 1996; Taylor, 1985). A second, related explanation suggests that African Americans may be more resilient to the psychological effects of caregiving than Whites because they are more likely to have experienced a lifetime of adversity (Neighbors, Jackson, Bowman, & Gurin, 1983; Rodgers-Rose, 1980; Spurlock, 1984; Taylor & Chatters, 1986). In fact, some researchers have suggested that Black caregivers may even derive unique benefits and satisfactions from the caregiving role (Dilworth-Anderson & Anderson, 1994; Lawton et al., 1992). A third approach has begun to examine various cultural traditions that result in the empowerment of African American, but not White caregivers. Among the cultural traditions that have been examined are family role involvement, social support, and participation in church activities (Anderson, 1991; Angel & Tienda, 1982; Chatters, Taylor & Jackson, 1985; Coke, 1992; Dungee-Anderson & Beckett, 1992; McAdoo, 1978; Mitchell & Register, 1984; Mutran, 1985; Segall & Wykle, 1988; Taylor, 1986). …
openalex: W2023572439 mag: 2023572439
Keywords: openalex:import

The contradictions of scientific management as a mode of controlling teachers' work in black secondary schools: South Africa - Sebakwane, Shirley M. (International Journal of Educational Development, 1997)
Abstract Using teaching as a labour process, this paper shows how teachers' work is controlled by the state. By using data collected from the Lebowa bantustan in South Africa, the analysis focuses on structural/material constraints on teachers' work; how scientific management has been transferred from industrial corporations to South African black schools as a post-1976 reform strategy, to bring control over teachers and students at a time when the system of education of blacks was characterised by massive student and teacher protests. However, contradictory developments emerged whereby teachers responded and resisted these controls in a variety of ways in different work contexts. Since the research was conducted in the late 1980's, the paper seeks to discuss how widespread scientific management ideas are in the post-apartheid era.
openalex: W2060648814 mag: 2060648814
Keywords: openalex:import

Systematic variations in the 3He/4He ratio and carbon of fumarolic fluids from active volcanic areas in Italy: Evidence for radiogenic 4He and crustal carbon addition by the subducting African plate? - Tedesco, Dario (Earth and Planetary Science Letters, 1997)
The isotopic composition of helium from active volcanic areas in Italy differs from those of other arc volcanic areas (circum-Pacific region), even though the tectonic settings are similar [1–4]. Helium isotopic values of fumarolic gases were obtained for the southern Italian volcanoes, Mount Etna and the Eolian Islands ([5,6]; this work), and from central Italian volcanoes in Neapolitan, Roman and south Tuscany volcanic provinces ([7,8]; this work). The 3He/4He ratios decrease from south to north, from values slightly lower than those of MORB to near crustal values, including ratios lower than atmospheric (Ra = 1). Contamination by crustal radiogenic helium, derived from the natural decay of uranium and thorium, is the most likely candidate for lowering 3He/4He ratios. Increases from south to north in the U and Th contents of volcanic rocks are in agreement with this hypothesis. Local crustal and surficial contaminations may also explain the systematic changes in ratios. Subduction of the African plate beneath the Tyrrhenian Sea seems to be the most logical process to explain the 3He/4He ratio decrease. Similarly, carbon isotopic data show higher values from south to north, which suggests increasing contamination of subducted sedimentary carbon into magmatic gases. Correlations with strontium and neodymium isotope data support the above mentioned hypothesis and demonstrate the remarkable link between helium and carbon isotope variations and tectonic processes. Comparison with low helium data from the Banda arc (Indonesia), although with a different mechanism, agrees with the presence of a continental end-member below the Tyrrhenian Sea volcanoes.
openalex: W2078266134 mag: 2078266134
Keywords: openalex:import

Education in a New South Africa: The Crisis of Conflict, the Challenges of Change - Williams, H. Drake; Davis, James Earl; Soudien, Crain (1997)
The birth of the new South Africa marks one of the most profound events of the close of the 20th century. Indeed, the historical events culminating in the first truly democratic elections in South Africa in 1994 have ramifications for people around the globe. Millions worldwide have experienced renewed faith and a revitalized sense of hope with the demise of the infamous apartheid system and with the many transformations, large and small, that are taking shape in this youngest democratic republic. This latest jewel in the crown of Africa is determined to be both a positive force for change and a wellspring of serious developmental action. The world community is dizzy with plans and ideas to salute the new nation's future. Indeed, there are numerous reasons to join the celebratory chorus. Internally, every aspect of life for South Africa's diverse citizenry is undergoing massive change: education, politics, spiritual life, health, law enforcement, transportation, housing and land issues, and countless other areas. Not surprisingly, however, the dawning of the new millennium finds the budding democracy struggling with inevitable growing pains. Acknowledging the atrocities and shedding the memories of a violent past has been a difficult, traumatic process. The upcoming round of general elections in 1999 poses yet another challenge to the reconfigured state as President Nelson R. Mandela, an icon of political and cultural transformation, has promised to step aside and let a new national leadership take the helm. Once again then the process of reform in all sectors of education-primary, secondary, and tertiary-stands to be mightily tried and tested by political and social change (Constas, 1997; Moja, Muller, & Cloete, 1996). Such massive challenges are not new to the South African scenario, however. in South Africa has a long tradition of being used as a political tool, whether as the social controlling force of Bantu education or the progressive use of schools as critical sites of resistance in the anti-apartheid struggle. The politicization of education in the new South Africa will no doubt continue, albeit it will be manifested in different forms and with different social and economic consequences at stake (Nieuwenhuis, 1996). Two years ago, some of us heard and answered the call to join in action, scholarship, and struggle with the citizens of South Africans to keep their dream growing. Two years in the making, this Yearbook issue of the Journal of Negro echoes the extraordinary theme of hope for the new South Africa. As such, it presents a well-conceived and thoughtful analysis of several of the key educational issues that presently confront the nation. While illuminating the shifting political setting and highlighting strategies that mark the possibilities of effective institutional change, this Yearbook presents concrete ideas for innovative educational approaches and programs. Education in a New South Africa: The Crises of Conflict, the Challenges of Change, is divided into three sections. Section one provides insights on the historical and contemporary status of educational efforts in South Africa. It additionally tackles the tough issue of educational decentralization as well as examines issues related to the incorporation or exclusion of multiple languages and cultures into the nation's curricula and pedagogy. This section also considers factors surrounding the education of South Africa's women and girls, and discusses opportunity-to-learn issues common to learning environments in the United States and South Africa. Section two scans the various levels of education, beginning with a much-needed focus on preschool education for Black South African children and a look at factors related to teacher collaboration within South African schools. From these key points, the attention turns to the critical issue of admissions and retention policies at the university level, especially at the rapidly integrating previously historically White universities, and to education in the vital, skilled areas of engineering and technology. …
openalex: W322339837 mag: 322339837
Keywords: openalex:import

Linking priorities for training, research and policy on ageing in sub-Saharan Africa - Wilson, Adrian O.; Adamchak, Donald J. (Southern African journal of gerontology, 1997)
This forum raises for debate the issues of training, research and policy on ageing in sub-Saharan Africa. The obstacles to a seamless linkage between these areas are discussed. The forum concludes with recommendations to overcome the obstacles, for consideration by all individuals involved in ageing and health on the sub-continent.
openalex: W2354158165 mag: 2354158165
Keywords: openalex:import

A Qualitative Investigation of Alcohol Drinking among Male High School Students from Three Communities in the Cape Peninsula, South Africa - Ziervogel, C. F.; Morojele, Neo K.; Riet, Job van; Parry, Charles; Robertson, Brian (The International Quarterly of Community Health Education, 1997)
This article reports on a qualitative study using focus group discussions about alcohol binge drinking with tenth grade male high-school students. Groups were run separately with binge drinking and non-binge drinking adolescents in three different communities. The Theory of Planned Behaviour with two additional constructs was used to provide a theoretical framework for the semi-structured discussions and for the analysis of the data. Although the findings are complex some clear differences did emerge between binge drinkers and non-binge drinkers and between participants from the three different communities. The binge drinkers perceived positive outcomes from binge drinking, were embedded within a peer group culture of binge drinking, and found few obstacles of obtaining alcohol. The non-binge drinkers were more concerned with longer term life goals and were motivated to comply with family pressures not to drink excessively. The implications of these findings for preventive programs and for future research are discussed.
openalex: W2135913634 mag: 2135913634
Keywords: openalex:import

The future of medical education in South Africa - Hoffenberg, R. (The BMJ, 1997)
When I left South Africa in 1968 academic medicine was flourishing. The best graduates wanted to pursue academic careers and there was fierce competition for posts in teaching hospitals. Although not in itself a manifestation of profound research the world's first heart transplant had revealed just how sophisticated medicine was in the country. The general medical scene was less satisfactory. Few black doctors were being trained—seven in 1966; 11 in 1967; 10 in 1968—and the distribution of doctors was grossly distorted in favour of white suburbs. This inequality of service was reflected in patterns of health and disease. At the end of 1995 I returned to join an advisory group set up by the minister of health, Dr N C Zuma, to try to restore a badly depleted and demoralised academic sector. What I found was extremely depressing. The status of academic medicine had declined seriously, the teaching hospitals had been deprived of funds, salaries for academics and those working in the public sector were quite inadequate with a resultant haemorrhage into private practice. Vast numbers of doctors had emigrated. The mix of private and public medicine had changed completely. Only 39% of health expenditure went to the public sector, 61% to the private; one third of all hospital beds were in the private sector. The new minister was determined to do something about the unequal …
openalex: W1984942417 mag: 1984942417
Keywords: openalex:import

[Uganda–a visit to the hospital and nursing school in Masaka]. - Hansen, Gunnar Vold (PubMed, 1997)
openalex: W2409029952 mag: 2409029952
Keywords: openalex:import

Training TBAs in Ghana. (PubMed, 1997)
The Planned Parenthood Association of Ghana (PPAG), in cooperation with Ghana's Ministry of Health, trained 43 trusted members of communities in which home delivery remains the norm for most women in hygienic methods of child delivery, how to identify risk factors during pregnancy, when and where to refer clients for medical assistance, and how to prepare nutritional foods for pregnant women and mothers from locally available foods for 15 days over a 5-week period. The traditional birth attendants (TBAs), aged 30-90 years, were drawn from areas in Ghana where JOICFP's Integrated Project (IP) is implemented. Songs and role plays were used extensively in the training, with the TBAs also provided information in pictorial form. The trainees had many misconceptions. Another training goal was to foster closer working relationships between the TBAs and local health personnel and to gain TBA support for the promotion of reproductive health/family planning (RH/FP) services, particularly by reinforcing the linkages between TBAs and clinics for referrals and the work of community-based distribution agents.
openalex: W4300711290
Keywords: openalex:import

Learning in the Africanized Honey Bee: Apis mellifera L. - Abramson, Charles I.; Aquino, Italo S.; Silva, Maurizete C; Price, James (Physiology & Behavior, 1997)
Several series of experiments are reported that investigate learning in the Africanized honey bee. In the first series, classical conditioning of proboscis extension was studied by confining bees to small metal tubes where they received pairings of an odor with a 3-s feeding of sucrose. After a number of odor-sucrose pairings, the bees began to extend their proboscis to the odor. Controls include Unpaired, Discrimination, and Pseudoconditioning Groups. This technique was used to look at conditioning to a light CS, and to the odors of beeswax, geraniol, citral, and hexanal. The results indicate that acquisition was best when sucrose was paired with the odor of beeswax. Conditioning to the remaining odors was roughly similar, but acquisition did not occur using a light. In a second series of experiments, odors were no longer followed by sucrose feedings and the conditioned response slowly disappeared. With the exception of geraniol as a CS, this extinction effect did not occur if the animals continued to be fed on an unpaired schedule. In a third series of experiments, conditioned inhibition was demonstrated when geraniol was used as conditioned stimuli, but no effect was found when the odors of hexanal, citral and wax were used. In a fourth series of experiments, unrestrained bees flew back and forth from the laboratory to the hive, where they were taught to distinguish targets based on color and odor. With this technique, color and odor discrimination in the Africanized bees was demonstrated. In addition, it was found that more intruder bees visited the experimental station when the stimuli used were olfactory rather than visual.
openalex: W2040511313 mag: 2040511313
Keywords: openalex:import

Determinants of Personal Space Among South African Students - Akande, Adebowale (The Journal of Psychology, 1997)
(1997). Determinants of Personal Space Among South African Students. The Journal of Psychology: Vol. 131, No. 5, pp. 569-571.
openalex: W2148548294 mag: 2148548294
Keywords: openalex:import

Towards a participatory and demand-driven training and visit (T & V) agricultural extension system: A case of Tanzania - Ban, A.W. van den; Mkwawa, Dawara (European journal of agricultural education and extension, 1997)
Abstract Tanzania uses the T & V system of agricultural extension. At this moment this is a rather top-down system for the transfer of technologies, but the Ministry is convinced that the extension system would become more effective if it was more participatory and demand-driven. The Village Extension Officers are taught impact points, which they are expected to passon to the farmers. However, most farmers do not follow these recommendations, often because in formulating these recommendations one has not given enough attention to the limited possibilities many farmers have to make investments. With the large diversity among the farmers in income, access to markets and agro-ecological situation blanket recommendations cannot work. Farmers need information that helps them to make better decisions themselves adjusted to their goals and their situation. This can only be realised with a decentralised system of decision- making in the extension service and a participatory system of supervision and inservice training. Discussed are difficulties involved in realising such a major change in the extension approach. It takes time, training and a systematic strategy of organisational change to overcome these difficulties.
openalex: W2010455019 mag: 2010455019
Keywords: openalex:import

Rainbows and Spider Webs: new challenges for theatre in a transformed system of education in South Africa - Carklin, Michael (Research in Drama Education: The Journal of Applied Theatre and Performance, 1997)
Abstract South African society has undergone immense change in recent years and arguably one of the most fundamental challenges has been transforming the education system from one that was strongly authoritarian, subject‐centred and based on political indoctrination, to one which embraces notions of child‐centredness, diversity, multicul‐turalism and multilingualism. The key idea of this article is ‘intervention’, exploring the ways in which theatre ‘intervenes’ in the South African education system. Three areas of intervention are highlighted: firstly, through introducing drama as a formal subject of school study; secondly, as a methodology for teachers across the curriculum, and thirdly, as an intervention from the outside, through, for example, visiting theatre companies, and in this case, the DramAidE company which focuses on HIV/AIDS and lifeskills education. Whilst these areas of dramatic engagement are not new, it is unlikely that drama will automatically become part of the transformed system without clear intervention from arts educators. This article traces developments that have taken place in South African drama and education policy formulation, highlighting the need for practical intervention at the levels of both content and methodology from within, and outside of, the school system.
openalex: W2044763660 mag: 2044763660
Keywords: openalex:import

The Influence of Self-Esteem on Smoking among African-American School Children - Crump, Regan L.; Lillie-Blanton, Marsha; Anthony, James C. (Journal of Drug Education, 1997)
This study provides some evidence, although not very strong, that self-esteem is associated with the likelihood of smoking among African-American children. In a sample of 1,256 children, those with lowest levels of self-esteem were twice as likely to have ever smoked as those with highest level of self-esteem (95% C.I. = 1.10–7.78). Girls, more so than boys, have an increased risk of smoking at the lowest level of self-esteem. Girls with the lowest level of self-esteem were 2.8 times (95% C.I. = 3.85–16.59) as likely to have smoked when compared to girls with higher self-esteem. The findings suggest preventive interventions that seek to build self-esteem may reduce the likelihood of smoking among girls, although perhaps only modestly. Further study is needed to identify potentially effective methods for reducing the likelihood of smoking among African-American boys.
openalex: W1995168033 mag: 1995168033
Keywords: openalex:import

Attitudes of secondary school students toward agriculture in Swaziland - Dlamini, B.M. (European journal of agricultural education and extension, 1997)
Abstract The primary purpose of the research is to describe and explain the attitude of secondary agriculture school students toward agriculture, and to determine students' perceived usefulness of agriculture as compared with other subjects. A descriptive correlational research was employed. Results revealed that secondary agriculture students hold a slightly positive attitude toward agriculture, and that eleventh and twelfth grade students held a statistically significant higher positive attitude than tenth grade students, when compared, using the Tukey method Agriculture as a subject is more useful in the home situation (mainly rural) than for further education. Results of stepwise regression analysis revealed that out of seven independent variables, only three are significant predictors of attitude at alpha .05. The best predictor variables are school location (urban vs rural), performance level, and growing of crops by family.
openalex: W2043360992 mag: 2043360992
Keywords: openalex:import

Impaired antioxidant defence in guinea pig heart tissues treated with halothane - Durak, İlker and Kurtipek, Ömer and Öztürk, Hakan and Bırey, Mehmet and Turan, Güven and Kavutçu, Mustafa and Kaçmaz, Murat and Dikmen, Bayazıt and Yel, Mustafa and Canbolat, Orhan (Canadian Journal of Anesthesia/Journal canadien d'anesthésie, 1997)
To investigate the effects of halothane and halothane plus vitamin E treatment on myocardial free radical metabolism in guinea pigs.Four groups of seven animals were studied: control, halothane, halothane plus vitamin E and vitamin E groups. In the halothane group, halothane 1.5% in oxygen was given for 90 min over three days. In the halothane plus vitamin E group, 300 mg.kg-1.day-1 vitamin E im was started three days before the first halothane treatment and continued for three days. Following sacrifice, the hearts were assayed for superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) and malondialdehyde (MDA) level was determined. Electron spin resonance (ESR) analysis and electron microscopy (EM) were also performed.In the halothane group, SOD activities and MDA concentrations were increased compared with control and GSH-Px and CAT activities were decreased. In the halothane plus vitamin E group, there were no differences in enzyme activity compared with halothane alone but the MDA level was decreased. In the vitamin E group, enzyme activities were increased compared with control. Mainly the CF3CHCl radical was identified by ESR analysis in heart tissues exposed to halothane and the concentration of this radical was reduced by vitamin E. Electron microscopy showed cytoplasmic vacuolisation and dilation in sarcoplasmic reticulum in the heart tissues exposed to halothane: both were prevented by vitamin E.Although halothane causes impairment in enzymatic antioxidant defence potential, due to lowered GSH-Px and CAT activity, and accelerates peroxidative reactions in the tissues affected, no subcellular damage occurred. Vitamin E may protect tissues against free radical attack by scavenging toxic free radicals formed in heart tissue during halothane anaesthesia.
openalex: W2005361275 mag: 2005361275
Keywords: openalex:import

Library Education in Libya - Dyab, Muftha Mohammed (Information development, 1997)
Briefly reviews the development of formal library and information science education at the Department of Library and Information Science, University of El-Fateh, Tripoli, Libya, the first library and information science school established in the country. Provides information on the educational programmes, faculty members, curriculum development, information technology, and material facilities of the Department.
openalex: W2093617715 mag: 2093617715
Keywords: openalex:import

Prevalence of skin diseases in school children in rural and urban communities in the Illubabor province, south-western Ethiopia: a preliminary survey - Figueroa, Jose I.; Hawranek, Thomas; Abraha, Aynalem; Hay, Roderick J. (Journal of the European Academy of Dermatology and Venereology, 1997)
Background Skin disease is usually the second most common reason for consultation by children in rural clinics in developing countries. The majority of epidemiological studies published so far are based on the analysis of medical records from specialised centres. These, however, account for expressed needs only and do not portray the real prevalence of paediatric skin disease at the community level. Aim To determine the prevalence of skin disease in unselected paediatric populations from rural and urban communities in the Illubabor province, south-west Ethiopia. Patients and methods A cross-sectional prevalence survey of 219 junior school children in three schools was performed. Ninety-one children (42%) from two rural communities and 128 (58%) from an urban settlement were examined clinically and asked to complete a simple questionnaire. Results Three hundred and eighty-two cutaneous findings were present in 212 (96.8%) children. Parasitic infestations, particularly pediculosis capitis, and infections, of which fungal infections affected at least one in four children, were the most prevalent skin conditions in both environments. Conclusions Community based epidemiological data are needed for monitoring early changes in disease patterns in children so that health care programmes can be expeditiously modified accordingly.
openalex: W1982253334 mag: 1982253334
Keywords: openalex:import

Prevalence of skin diseases in school children in rural and urban communities in the Illubabor province, south‐western Ethiopia: a preliminary survey - Figueroa, Jose I.; Hawranek, Thomas; Abraha, Aynalem; Hay, Roderick J. (Journal of the European Academy of Dermatology and Venereology, 1997)
Abstract Background Skin disease is usually the second most common reason for consultation by children in rural clinics in developing countries. The majority of epidemiological studies published so far are based on the analysis of medical records from specialised centres. These, however, account for expressed needs only and do not portray the real prevalence of paediatric skin disease at the community level. Aim To determine the prevalence of skin disease in unselected paediatric populations from rural and urban communities in the Illubabor province, south‐west Ethiopia. Patients and methods A cross‐sectional prevalence survey of 219 junior school children in three schools was performed. Ninety‐one children (42%) from two rural communities and 128 (58%) from an urban settlement were examined clinically and asked to complete a simple questionnaire. Results Three hundred and eighty‐two cutaneous findings were present in 212 (96.8%) children. Parasitic infestations, particularly pediculosis capitis, and infections, of which fungal infections affected at least one in four children, were the most prevalent skin conditions in both environments. Conclusions Community based epidemiological data are needed for monitoring early changes in disease patterns in children so that health care programmes can be expeditiously modified accordingly.
openalex: W4251358622
Keywords: openalex:import

Education systems in East Africa. Trends and Issues - Florida, A Karani (1997)
openalex: W2324584736 mag: 2324584736
Keywords: openalex:import

An Evaluation of a Program to Influence Academic Self‐Concept Among African American Male College Students - Fortson, Stephen B. (Journal of Employment Counseling, 1997)
African American men suffer one of the highest attrition rates of any racial or gender group in college. This study evaluated a retention program designed to increase academic self‐concept by engaging participants in a 10‐week course that taught career planning, cultural awareness, job interviewing and resume writing skills, and academic responsibility. The results of the analysis suggest that the course had no effect on academic self‐concept.
openalex: W2168284903 mag: 2168284903
Keywords: openalex:import

Increasing African Americans' Participation in Higher Education - Freeman, Kassie (The Journal of Higher Education, 1997)
(1997). Increasing African Americans' Participation in Higher Education. The Journal of Higher Education: Vol. 68, No. 5, pp. 523-550.
openalex: W1987512317 mag: 1987512317
Keywords: openalex:import

Increasing African Americans' Participation in Higher Education: African American High-School Students' Perspectives - Freeman, Kassie (The Journal of Higher Education, 1997)
openalex: W4249159902
Keywords: openalex:import

Serum retinol concentrations and Schistosoma mansoni, intestinal helminths, and malarial parasitemia: a cross-sectional study in Kenyan preschool and primary school children - Friis, Henrik; Mwaniki, Dennis; Omondi, B; Muniu, Erastus; Magnussen, Pascal; Geissler, Wenzel; Thiong'o, F; Michaelsen, Kim Fleischer (The American Journal of Clinical Nutrition, 1997)
Parasitic determinants of serum retinol concentrations were studied in 159 preschool (0.25-5.1 y) and 695 primary school (9.2-17 y) children in western Kenya. Mean serum retinol was 0.63 micromol/L in preschool and 0.94 micromol/L in primary school children; 62% and 24%, respectively, had serum retinol < 0.70 micromol/L. Serum retinol was lower in boys than in girls among both preschool (P = 0.04) and primary school children (P = 0.0001). Schistosoma mansoni, Ascaris lumbricoides, hookworm, and Trichuris trichiura egg output and malarial parasitemia were determined and their relation with serum retinol assessed. Among preschool children, sex, elevated serum concentrations of C-reactive protein, and malarial parasitemia were significant predictors of serum retinol. Among the 63 children from whom stool samples were available, none of the helminth infections were significant predictors of serum retinol. For primary school children, age, sex, and S. mansoni egg output were predictors of serum retinol. Malarial parasitemia among nonimmune preschool children may contribute to low serum retinol, whereas malarial parasitemia did not have any effects in semiimmune primary school children. In contrast, the inverse relation between S. mansoni and serum retinol found in primary school children could be due to an effect of infection on serum retinol or an increased susceptibility to infection among children with low serum retinol. Although parasitic infections may contribute to poor vitamin A status in children, they do not explain the age and sex differences.
openalex: W1934745097 mag: 1934745097
Keywords: openalex:import

Innovation management issues raised by a distance-learning project in Eritrea: Can such projects be successfully transplanted from one developing country to another? - Guariento, Bill (System, 1997)
This paper, using field work carried out in Eritrea, will examine ways of promoting “ownership” resulting from the adaptation of a project originally developed outside the host country. The author will argue that while project organisers will probably encounter basic problems concerning local competence, the stress must, above all, fall on an awareness of what Holliday has termed “intercompetence”, “an intermediate stage in behavioural competence which occurs during confrontation with a new culture” (Holliday, 1994: p. 223). The author believes that more effort should be dedicated to ways of adapting ELT material produced in one developing country in order to enable use in another. Just as there are situations in which context-specificity and differing needs clearly preclude adaptation and transplantation within the developing world, so are there cases in which context and needs resemble one another to an extent suggesting that adaptation may be worthwhile. In countries which lack the resources to fund improvements in teacher training and/or the trainer expertise required to provide such development, the use of materials already existing elsewhere provides a low-cost alternative, and one able to offset local skills-shortfalls.
openalex: W1995662118 mag: 1995662118
Keywords: openalex:import

Family influences on school achievement in low-income, African American children. - Halle, Tamara; Kurtz‐Costes, Beth; Mahoney, Joseph L. (Journal of educational psychology, 1997)
The authors examined the achievement-related beliefs and behaviors of parents of economically disadvantaged African American youth, and the relations among parental factors and children's academic self-concept and achievement. Forty-one children and their primary caregivers were interviewed. Parents reported on their academic-related beliefs and behaviors. Children completed measures of academic self-concept and 2 standardized achievement tests: 1 during the summer and 1 at the end of the following school year. Significant and positive relations were found between parental belief and behavior measures within the domains of reading and math; however, parental beliefs were more strongly linked with child outcomes than were parents' achievement-oriented behaviors. The relation between parental beliefs and child outcomes was not mediated by children's academic self-concept. Results are discussed in light of models of family influences on achievement.
openalex: W2018128668 mag: 2018128668
Keywords: openalex:import

Southern African climate change simulated by the GENESIS GCM - Hudson, Debra (South African Journal of Science, 1997)
This paper examines the summer (DJF) and winter (JJA) equilibrium response of the climate system to an instantaneous doubling of CO2 using the T31 GENESIS general circulation model (GCM) (version 2.0.a). The results are analysed over southern Africa and the adjacent oceans (90i?½S to 0i?½; 70i?½W to 110i?½E) in order to evaluate the control simulation and determine the large-scale response to the CO2 forcing. The GCM has been shown to perform well under present-day conditions, perhaps with the exception of precipitation, which is overestimated in the model. In response to the doubling of CO2, there is a general increase in surface temperatures over the analysis window, with an increase of between 2i?½ and 3i?½C over South Africa and the temperature differential between high and low latitudes is reduced during both seasons. There are increases in sea-level pressures and 500 hPa heights south of Africa in the mid-latitudes during summer and winter in the 2 x CO2 simulation, which is indicative of a weakening of the westerly circulation in this region. For winter, there is a reduction in the speed of the 500 hPa winds south of South whereas in summer there is a weakening of the subtropical jet stream and an increase in strength the subpolar jet stream. Specific humidities increase in response to the increase in CO2 during both seasons, as do the 700 hPa moisture fluxes. For winter; there is greater transport of moisture from over the Atlantic Ocean towards southern Africa in the 2 x CO2 simulation compared with the control. Mid-latitude cyclone densities are generally found to decrease in the mid-latitudes and increase in a narrow band surrounding the Antarctic continent for both seasons in the 2 x CO2 simulation. This has been related to changes in surface temperatures and positioning of the sea-ice margin.
openalex: W2511041211 mag: 2511041211
Keywords: openalex:import

Effects of Achievement Motivation and Study Habits on Nigerian Secondary School Students' Academic Performance - Jegede, Joseph O.; Jegede, Ruth T.; Ugodulunwa, Christianah A. (The Journal of Psychology, 1997)
Abstract An experimental analysis of the effects of achievement motivation and study habits on Nigerian secondary school students' English language performance was carried out in 1990. The two hypotheses tested were that each of the treatment groups would perform significantly better in English than the control group and that the students treated for the combination of improved study habits and higher achievement motivation would perform better in English than any of the other groups (study habit, achievement motivation, and control). The sample consisted of 160 students in 10th grade, selected from 4 schools in Nigeria. Students' entry and exit achievement motivation, study habits, and English language performance were examined. Analyses of covariance were used to test for the significance of the results, and both hypotheses were supported.
openalex: W2013937814 mag: 2013937814
Keywords: openalex:import

Traditional Education and Creativity in an Afro‐Arab. Islamic Culture: The Case of Sudan - Khaleefa, Omar; Erdos, George; Ashria, Ikhlas H. (The Journal of Creative Behavior, 1997)
ABSTRACT This study investigated the differing effect upon creativity of traditional and modern education in the Sudan. The salient characteristics of the two types are presented, with a brief discussion of their likely effects. Four creativity tests, suitably modified for local conditions, were administered to 264 male and female students, with an age range of 15–20 years. The results indicated that the group receiving modern education performed significantly better than the traditionally educated group on two of the four creativity tests, but with equal performance on one test. The traditionally educated group performed significantly better on the fourth test. The discussion suggests there are a number of factors, both sociocultural and methodological, which may account for these findings.
openalex: W2060909538 mag: 2060909538
Keywords: openalex:import

Segregation, science and commissions of enquiry: the contestation over native education policy in South Africa, 1930–36 - Krige, Sue (Journal of Southern African Studies, 1997)
Abstract This is a study of relations between English Protestant missions and secular forces in and outside the state in the arena of African education between 1930 and 1936. During these years both the state and secular organisations devoted a great deal of time and money, in the form of commissions and conferences, to debating and investigating solutions to the ‘Native Problem’. Education was seen as key in this debate. The article argues that, through these public debates, newly emerging secular experts attempted to silence the missions and educated African elite as illegitimate amateurs, no longer able to speak with authority on African education. It shows the way in which new sciences like anthropology and psychology were used to bolster and hone earlier notions of ‘adapted education’. It challenges the idea that the missions accepted these ideas, showing that a robust critique was emerging which drew both on missionary opposition to ‘adapted education’ in British colonies and critiques of segregationist policy in South Africa.
openalex: W1991008876 mag: 1991008876
Keywords: openalex:import

Day-to-Day Variation of Egg Output and Schistosome Circulating Antigens in Urine of Schistosoma Haematobium-Infected School Children from Gabon and Follow-up after Chemotherapy - L, Van Etten; Pg, Kremsner; Fw, Krijger; Am, Deelder (American Journal of Tropical Medicine and Hygiene, 1997)
"Day-to-Day Variation of Egg Output and Schistosome Circulating Antigens in Urine of Schistosoma Haematobium-Infected School Children from Gabon and Follow-up after Chemotherapy" published on Sep 1997 by The American Society of Tropical Medicine and Hygiene.
openalex: W2294013813 mag: 2294013813
Keywords: openalex:import

Geriatric medicine in South Africa–the onus is on medical schools. - Louw, Steven (PubMed, 1997)
openalex: W2474131869 mag: 2474131869
Keywords: openalex:import

A school‐based approach to the control of urinary schistosomiasis and intestinal helminth infections in children in Matuga, Kenya: impact of a two‐year chemotherapy programme on prevalence and intensity of infections - Magnussen, Pascal; Muchiri, Eric M.; Mungai, Peter; Ndzovu, Malick; Ouma, John H.; Tosha, Saidi (Tropical Medicine & International Health, 1997)
A school- and chemotherapy-based urinary schistosomiasis and intestinal helminth infection control programme was conducted in Matuga Division, Kwale District, Coast Province with teachers taking care of diagnosis, treatment and health education. More than 12,000 children in 36 primary schools were included in the 2-year programme. Results for 20 evaluation schools are presented. Children with haematuria were treated with praziquantel (40 mg/kg) once a year. Within 2 years, the prevalence of haematuria in the schools was reduced from 28% (range 8-68%) to 11.4% (range 3-23%). More than 80% of the schoolchildren were infected with one or more intestinal helminths at baseline. After one year with levamisole mass chemotherapy, single dose (2.5 mg/kg) three times a year (once per school term), the prevalence of Ascaris infection was reduced by 83% from 18% to 3%, but there was no change in pretreatment prevalences of hookworm (57%) and Trichuris (56%) infections. In the second year of the programme, albendazole 600 mg once every six months was administered to the children in 10 randomly selected schools. This resulted in 52% and 23% reductions in prevalences of hookworm and Trichuris infections, respectively, in these schools and a reduction in mean intensity of infection of 52.8% and 50.3%, respectively.
openalex: W1964722651 mag: 1964722651
Keywords: openalex:import

Review: Freedom Road: Adult Education of African Americans - Martin, Larry G. (Adult learning (Washington, D.C.), 1997)
openalex: W2730599032 mag: 2730599032
Keywords: openalex:import

The development of students' writing ability in English at university level in Syria - Meygle, Abdul Hamid (1997)
This research concerns the development of Syrian undergraduates' writing ability in English. The aim of the research was to establish whether students' writing improved during their period of study, and to identify the nature of any changes that occurred. Secondary objectives concerned how previous research and current theories can help us understand and offer explanations for progress or lack of progress. In addition, students were consulted about their attitudes to writing through a questionnaire and interviews. Written data was obtained by sampling first and final year examination scripts, which were (1) objectively analysed for linguistic features to establish measurable characteristics and (2) subjectively evaluated by native speaker teachers of English to take account of factors such as discourse structure and organisation. The thesis consists of nine chapters. Chapter 1 describes the setting of the current research. Chapter 2 describes the data collection and introduces research methods, and this followed in Chapter 3 by a survey of relevant literature on non-native speaker writing.. The main body of the linguistic research is reported in Chapter 4 (sentence length and syntactic structure), Chapter 5 (grammatical features and spelling) and Chapter 6 (lexis). The subjective assessment of samples of student writing by native teachers of English is reported in Chapter 7, and the results of the survey into students' attitudes to writing are also reported in Chapter 8. Chapter Nine concludes the thesis with a summary of the findings, implications for teaching and suggestions for further research. The analyses revealed improvements in almost all aspects of students' writing on both objective and subjective measures but particularly in syntactic complexity and vocabulary.
openalex: W17219538 mag: 17219538
Keywords: openalex:import

In vivo sensitivity of Plasmodium falciparum to chloroquine and sulfadoxine–pyrimethamine in school children in Hoima district, Western Uganda - Ndyomugyenyi, Richard; Magnussen, Pascal (Acta tropica (Print), 1997)
In vivo testing of Plasmodium falciparum sensitivity to chloroquine and sulfadoxine–pyrimethamine was carried out among asymptomatic school children from seven schools in four sub-counties in Hoima District in western Uganda. Seven hundred and twenty five children were screened, 487 (67%) had parasitaemia and 307 met the inclusion criteria. Full sensitivity to chloroquine in urban areas was found in 42%. Chloroquine resistance at RII level was observed in 46% (33–58%) and RIII level in 13% (0–24%) In rural areas, however, full sensitivity to chloroquine was found in 76% (70–84%). Resistance at RII and RIII level was found in 18 and 6% respectively. Full sensitivity to sulfadoxine–pyrimethamine was found in 98% and only 2% resistant at RII level. The relatively high proportion of chloroquine resistance at RII and RIII levels in urban areas could be attributed to easy access to chloroquine as well as frequent and probably inadequate use of chloroquine. Chloroquine can still be used as first line antimalarial drug in the area. Sulfadoxine–pyrimethamine should be the second line drug for cases not responding to chloroquine.
openalex: W2039211221 mag: 2039211221
Keywords: openalex:import

An integrated model for the deep structure of the Chyulu Hills volcanic field, Kenya - Novak, O.; Ritter, Joachim; Altherr, Rainer; Garasic, V.; Volker, F.; Kluge, Christina; Kaspar, Tilo; Byrne, G.F.; Sobolev, S. V.; Fuchs, Karl (Tectonophysics, 1997)
The Chyulu Hills, a 1.4 Ma B.P. to Holocene volcanic field located about 150 km to the east of the Kenya rift, is one of the few locations on Earth for which detailed geochemical (volcanic rocks), thermobarometric (xenoliths), seismological and gravity data are available. This paper combines these data to achieve an integrated seismic-petrological model for the deep structure of this volcanic field. Results of a wide-angle reflection and refraction experiment reveal an average crustal thickness of 40 km and a thickness of 20 km for the lower crust. Beneath the volcanic field, the crust thickens to about 44 km. In this region a low-velocity body (LVZ) is modelled which extends from about 30 ± 5 km depth to the Moho. The LVZ is characterised by an increased vP/vS-ratio ranging from 1.81 to 1.93 depending on the possible extents of this body. This is in contrast to the surrounding crust where a ratio of only about 1.76 is observed. In the same area, the results of a teleseismic tomography study show a P-wave low-velocity anomaly of −3%. The seismic data can be explained by either an anorthositic body directly above the Moho in the region of the Chyulu Hills or by the presence of partial melt. Directly beneath the Chyulu Hills, a P-wave velocity of 7.9 km/s is determined for the uppermost mantle; this velocity is 0.2–0.3 km/s lower than that of the surrounding mantle region. The teleseismic tomography model suggests a P-wave low-velocity anomaly of −2.5 to −3.5% in the uppermost mantle (<70 km depth). Widespread garnet-bearing pyroxenitic and lherzolitic mantle xenoliths are mostly well equilibrated and suggest an apparent lithospheric thickness of about 105 km. Most garnet-free spinel harzburgitic xenoliths and some garnet pyroxenitic xenoliths were significantly heated before they were sampled and erupted by the host magmas. Heating events lasted for less than 210 ka as indicated by chemical diffusion profiles observed in orthopyroxene grains. It is suggested that heating was caused by stagnating magmas in the uppermost lithospheric mantle. At the same depth P-wave velocity perturbations of the tomographic model show a low-velocity zone directly underneath the youngest part (SE) of the volcanic field. At depths greater than about 70 km, this low-velocity zone is shifted towards the east, away from the volcanic field.
openalex: W1983440775 mag: 1983440775
Keywords: openalex:import

Donor-driven Initiatives and Media Training in Africa - Ogundimu, Folu F. (Journalism & mass communication educator, 1997)
In 1992, the U.S. Agency for International Development, (AID), launched a $15-million program to consolidate democracy in Zambia. The aid program followed multiparty elections which ended the 28-year reign of Kenneth Kaunda and the United National Independence Party, (UNIP). For 17 of those 28 years, Zambia had operated a single-party state, with UNIP serving as the sole, legitimate party (Bratton, 1992). The defeat of Kaunda and UNIP at the 1991 general elections, and the victory of former trade union leader, Frederick Chiluba, and his Movement for Multiparty Democracy, (MMD), was seen by many as an opportunity to consolidate democratic pluralism in Zambia (Bratton, op.cit.). It was this vision of democratic pluralism that led the U.S. government, acting through its Agency for International Development, (AID), to embark on a bold initiative it termed the Democratic Governance Project (DGP). The central objective of this initiative was to render public decision making more accessible and effective.(USAID Project Paper, 1992).1 Five years after the launching of the project, AID is scaling it down, uncertain about the future of democracy in Zambia. Part of the pessimism stems from the performance of the Chiluba government and the Movement for Multiparty Democracy, (MMD), in the post single-party government era. Dogged by charges of corruption, economic mismanagement, and political intolerance throughout much of its first term, critics of the MMD government say that its record so far has been just as bad as that of the Kaunda regime it succeeded (Bratton and Liatto-Katundu, 1994). Others point to more systemic problems. According to Ihonvbere (1995), Zambia is caught in the contradiction of nurturing and consolidating plural democracy under very difficult socioeconomic conditions (Ihonvbere, 1995:23). The controversies over freedom of the press, and the failure to conduct free and fair elections at the end of Chiluba's first term in office, are perhaps the most significant emblems of this failure at consolidating democratic pluralism in Zambia. For example, Chiluba's entire first term was marked by several tussles with the press, particularly the private-enterprise press. Notwithstanding the shortcomings of the private-enterprise independent press, those supporting transition to democratic pluralism argue that the frequent tussle with the press over critical and sensational stories against members of the Chiluba government did not help with the image of progress toward democracy.2 As for constitutional reforms, the government's failure at compromise with the opposition over several issues, including proposals for an independent judiciary, the need for an independent electoral commission, the procedure for adopting the constitution, and plans to include a Bill of Rights in the main constitution, seriously undermined the legitimacy of the constitution.5 Worse still, the refusal to rescind a clause in the new constitution which forbade former president, Kenneth Kaunda, from contesting the elections as a presidential candidate because his parents were not of Zambian origin, seriously compromised the integrity of the democratic process . The subsequent boycott of the elections by Kaunda's UNIP, and the denunciation of the 1996 elections by several groups as unfair, and undemocratic, was one by-product of the failure at constitutional reforms. Significantly, two of the key components of the U.S. Agency for International Development's democratic assistance plan for Zambia dealt with freedom of the press and constitutional reforms. Is-ow that Zambia is under attack on both of these scores, it is not surprising that AID is scaling back its commitments to assist Zambia in achieving democratic consolidation. This paper examines AID's media assistance plan under the Democratic Governance Project initiative, with particular emphasis on three aspects: (a.) the attempt at policy reforms that were intended to protect freedom of the press and ensure the privatization of mass media institutions in Zambia; (b. …
openalex: W2003528059 mag: 2003528059
Keywords: openalex:import

Curricula for Media Education in Anglophone Africa - Okigbo, Charles; Pratt, Cornelius B. (Journalism & Mass Communication Educator, 1997)
First, a caveat. This article uses and interchangeably primarily because, in the African context, no rigid pedagogical and practical distinctions are made between them. Even though Africa's mass-communication programs emphasize education, they do not entirely preclude human-, interpersonal-, or speech-communication courses. Additionally, in the realm of reception analysis within the African context, the boundaries between mass-media fare and interpersonally generated are in a flux, with one medium complementing-sometimes competing with-the other. The purposes of this article are threefold. First, it provides the basis for reconstructing curricula by integrating normative theory with Africa's media-education and media-training programs. Second, it profiles programs in Kenya, as a case study of similar programs in Anglophone Africa. Third, consistent with the program objectives of the Communication Division of the United Nations Educational, Scientific and Cultural Organization (UNESCO), it proposes a model curriculum for Kenya, in particular, and for Anglophone Africa, in general. To respond to UNESCO's recent charge to develop model curricula that are amendable, flexible, and adaptable to a variety of training contexts, the African Council for Communication Education (ACCE), a 23-year-old nonprofit organization that develops and implements communication programs in Africa, created in 1996 a project titled Planning/ Modifying Curricula for Communication Training in Africa: Modalities and Strategies. Integrating normative theory The normative theory of performance is grounded in the prescriptive ideals of routines and professional values. It examines how sources are interviewed and news stories or information is reported, narrated, or framed; how programs are justified, designed, implemented, and evaluated; how objectivity and truth are ensured; how organizational and audience interests are balanced; how the information specialist's personal attitudes, beliefs, and values are shielded from content; and how the can assert their independence in the face of competitive pressures from, say, the targets of investigations, an overbearing government or a owner. Whereas positive (that is, descriptive, or as-is) theories enable us to understand problems, normative theories are used to solve problems (Massy & Weitz, 1977), for example, those associated with curricular development. The theory can explain attempts by organizations to identify, develop, and justify basic moral principles, values, and virtues by which their operations should be-or ought to be-conducted. The theory prescribes and proscribes. McQuail (1994) writes, A common element of all the normative press theories . . . is that the should meet the needs and interests of their audience in the first instance and the interests of clients and the state only secondarily (p. 193). According to Baran and Davis (1995), Normative theories describe roles for media, recommend and envision consequences (p. 76). To integrate Baran and Davis's ideal roles for media with those for the African requires, as Moemeka (1997) notes, requires that communication in the communalistic societies of Africa be used to confirm, to solidify, and to promote communal social order and to maintain and improve interpersonal relationships. Bourgault (1995) describes such communication as communitarian (p. 247), which she defines as non-hierarchical, dialogical communication and grassroots participation in development (p. 248). Regarding Baran and Davis's recommended practices, they reflect what Ugboajah (1985) referred to as interpersonal communication in Africa's multi-ethnic societies, where messages should be consistently couched in the context of linguistic, cultural, normative, and semantic milieux. …
openalex: W2066878831 mag: 2066878831
Keywords: openalex:import

Political Overview in Namibia: the effects on arts/drama education - Olivier-Sampson, L (Research in Drama Education: The Journal of Applied Theatre and Performance, 1997)
openalex: W2087109357 mag: 2087109357
Keywords: openalex:import

Creating inclusive environments for African American children and youth with gifts and talents - Patton, James M.; Townsend, Brenda L. (Roeper Review, 1997)
While African American children in general have been widely discussed in the literature, those with academic gifts and talents have not (Frasier, 1989; Patton & Baytops, 1995). In comparison with their cognitive development, even less attention is placed on these children's socio‐cultural and psychosocial development (Ford, 1992; Shade, 1990; Patton & Baytops, 1995). Increasingly, African American learners with gifts and talents are being educated in general class settings. For these settings to be genuinely inclusive, the sociocultural and psychosocial needs of African American children and youth should be addressed. Hence, this discussion identifies several sociocultural and psychosocial needs unique to gifted African American learners. Classrooms aiming to be inclusive should respond to those needs. Thus, strategies are suggested to create inclusive environments for African American learners. The authors believe that inclusive environments for gifted African American learners result when educators become knowledgeable of African American cultural traditions and history and translate that knowledge into effective pedagogy. In addition, inclusive educators can be equipped to forge collaborations with other professionals, the learners' families, and their communities. These deliberate actions are hallmarks of inclusive environments for gifted African American children and youth.
openalex: W1989357152 mag: 1989357152
Keywords: openalex:import

The Economic Impact of Marine Pollution on the South African Fishing Industry: An Investigative Framework. - Saville, Adrian; Lumby, Anthony (South African Journal of Economics, 1997)
South African Journal of EconomicsVolume 65, Issue 3 p. 163-172 The Economic Impact of Marine Pollution on the South African Fishing Industry: An Investigative Framework. A.D. SAVILLE, A.D. SAVILLE Department of Economics, University of Natal, Durban.Search for more papers by this authorA.B. LUMBY, A.B. LUMBY Department of Economics, University of Natal, Durban.Search for more papers by this author A.D. SAVILLE, A.D. SAVILLE Department of Economics, University of Natal, Durban.Search for more papers by this authorA.B. LUMBY, A.B. LUMBY Department of Economics, University of Natal, Durban.Search for more papers by this author First published: 22 August 2005 https://doi.org/10.1111/j.1813-6982.1997.tb01369.xAboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinkedInRedditWechat Volume65, Issue3September 1997Pages 163-172 RelatedInformation
openalex: W2115261891 mag: 2115261891
Keywords: openalex:import

Demanding Schools: The Umchingwe Project and African Men's Struggles for Education in Southern Rhodesia, 1928-1934 - Summers, Carol (African Studies Review, 1997)
From at least 1900 on, Africans in Southern Rhodesia, its successor Rhodesia and today's Zimbabwe, have demanded schools and education, leaving behind evidence of their demands in a wide variety of sources: mission records, government reports and the recollections of former students. Even more than demands for land, higher producer prices or higher wages, demands for education were explicit attempts to negotiate not just economic issues, but also a place within Southern Rhodesia's increasingly segregated culture and society. But what, exactly, did students, parents and would-be students want, and were these demands being met? Fathers petitioned for schools for their sons, sons and daughters actively sought or avoided schooling and missions and the administration offered schools as answers to diverse political, social and economic difficulties. This paper will use a close examination of the life of a single ephemeral school at Umchingwe, in the Insiza district of Southern Rhodesia, to explore how senior men sought a school in an effort to rebuild strained ties with young men and restructure their community in Depression-era Southern Rhodesia, and why they failed. Studies of education in Southern Africa have generally acknowledged that missions, with the help of state grants-in-aid, built and operated schools not merely from humanitarian impulses but because schools were one of the most powerful ways to attract Africans to a mission station and convince them to become Christians. The government helped fund mission schools and built two flagship institutions of its own as part of an effort to use schools to cultivate a useful, disciplined and controllable class of African workers and leaders. Schools were not merely imposed on a resisting African population, though. From the early years of the twentieth century, with increasing volume, Africans requested schools from missions, and from the government. Yet much of what we know about the development and expansion of the schooling in the region has focused less on what that education meant to students and their parents than on how the state, the white population and the Native Administration, worked to channel and modify Africans' educational demands through schools which were designed to produce useful subjects and workers for a settler state (Summers 1994a; Challiss 1982; Vambe 1972).
openalex: W2011243606 mag: 2011243606
Keywords: openalex:import

Challenges to Implementing Health Promoting Schools: The Papua New Guinea Experience - Tetaga, Jerry E. (Promotion & Education, 1997)
openalex: W2075828261 mag: 2075828261
Keywords: openalex:import

Education, occupation and health status of people of age five years or more living in a high density urban area in Zimbabwe. - Watts, Tim; Siziya, Seter (PubMed, 1997)
To find out the education, occupation and health status of people aged five years or more living in a high density urban area in Zimbabwe.Cross sectional.Households in Chitungwiza.Persons of age five years or more available in a household at the time of the survey. In 1990 and 1993, 822 and 1,023 people were surveyed, respectively.Educational level, employment, rate of smoking, nutritional status, blood pressure level, and rate of disability.After the age of 24 years, more males than females were observed in both periods. A much higher proportion (x2 = 20.34, df = 1, p < 0.001) of women were in informal employment in 1993 (28.6%) than in 1990 (12.9%). Meanwhile, about an equal proportion of men were in the informal sector in both periods (12.0% and 10.4% in 1990 and 1993, respectively). For females of age 15 years or more, fewer (40.8%) had attained secondary education than males (76.4%) in 1990 (x2 = 50.2, df = 1, p < 0.001). Overall, 208 (36.1%) men and eight (1.3%) women of age 15 years or more smoked. Raised blood pressure for both sexes increased significantly with age (x2 for linear trend = 20.21 for men and 65.81 for women, df = 1, p < 0.001 for both sexes). More women of age 45 years or more had raised blood pressure than men (x2 = 4.67, df = 1, p = 0.031). Many more women (8.0%) than men (0.7%) had a Ponderal Index of greater than 27 (x2 = 19.33, df = 1, p < 0.001). A total of 12 (1.5%) persons were disabled.Raised blood pressure and obesity mainly affected women and interventions to improve their health is recommended.
openalex: W2239053611 mag: 2239053611
Keywords: openalex:import

Statistics training in eastern and southern Africa: a study of supply and demand - Woodward, Mark; Dourmashkin, Neil; Twagirumukiza, Etienne; Mbago, Maurice C.Y.; Cunha, Adrião S. Ferreira Da (The Statistician, 1997)
In recent years considerable concern has been expressed, from within and outside the continent, about the standard of official statistics in Africa. This has prompted the question of how ef fective the training of African statisticians has been. This paper describes findings from studies of current supply and future demand for statistics training in Angola, Botswana, Ethiopia, Kenya, Lesotho, Malawi, Mozambique, Namibia, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe, carried out in 1993 and 1994. Recommendations for future develop ment of training systems are given. These include strengthening in-service training in national statistics organizations and developing regional courses for professional statisticians
openalex: W2013812869 mag: 2013812869
Keywords: openalex:import

Cultural Descriptors of Hispanics by African American University Students of Spanish. - Garrott, Carl L. (1997)
A study conducted in a predominantly black university investigated the ways in which African American students of Spanish described Hispanics, and changes in these perceptions across Spanish language instructional levels. Subjects were 26 students in Spanish 101, 25 in Spanish 102, and 26 in Spanish 201. Measures used were a semantic differential technique (Osgood, Suci, Tannenbaum, 1957) for ethnic descriptions and a Bogardus Social Distance Scale (Bogardus, 1925). Results indicate that Spanish 101 students characterized Hispanics as poor, impulsive, excitable, good, sociable, dishonest, proud, aggressive, and clean. Spanish 102 students saw them as good, excitable, graceful, happy, kind, proud, generous, sociable, strong, and humorous. Spanish 201 students perceived Hispanics as good, strong, sociable, poor, excitable, clean, proud, and graceful. Early learners appear to deduce the concept Hispanic from stereotypes; later learners armed with knowledge and experience attribute fewer stereotypical characteristics. Semantic differential results suggest that increased language study and/or cultural exposure does not increase positive concepts of Hispanics. Possible explanations for these apparently contradictory results are offered, and areas for further research are outlined. Data tabulations are appended. Contains 31 references. (MSE) ******************************************************************************** Reproductions supplied by EDRS are the best that can be made from the original document. ******************************************************************************** CULTURAL DESCRIPTORS OF HISPANICS BY AFRICAN AMERICAN UNIVERSITY STUDENTS OF SPANISH
openalex: W30109031 mag: 30109031
Keywords: openalex:import

Breastfeeding training improves health worker performance in rural Nigeria. - Aa, Davies-Adetugbo; Ak, Fabiyi; Eo, Ojoofeitimi; Adetugbo, K (PubMed, 1997)
The training of health workers in breastfeeding and lactation management is to enable them make correct breastfeeding recommendations to mothers. This study aims to provide answers to two research questions: what components of breastfeeding training are easily achieved with extension health workers, and what health worker variables affect these outcomes. Multivariable analysis of the outcomes of a controlled breastfeeding training programme for community health workers (CHW) in rural communities of Osun State, Nigeria, was performed by logistic regression. The results show that the training was the most powerful predictor of correct CHW recommendations on breastfeeding (OR = 60.25, p-0.0000), and of 'perfect' breastfeeding knowledge (OR = 192.49, p = 0.0000). Younger CHWs (in the age bracket 20 to 29 years) were significantly more likely to make correct recommendations on exclusive breastfeeding (OR = 3.02, p = 0.0304). Other CHW variables such as sex, experience, job status, and marital status did not make consistently significant independent contributions to the outcomes. The results suggest that breastfeeding education can enhance CHW professional recommendations on breastfeeding and should be extended to all categories of health workers.Health worker training is a key component of Nigeria's National Breast Feeding Program. Problematic, however, have been situations where the current recommendation of exclusive breast feeding conflicts with local knowledge and practices. This conflict can be resolved only by convincing rural community health workers (CHWs) of the legitimacy and benefits of exclusive breast feeding. A study conducted in the Ife South Local Government area of Nigeria's Osun State evaluated the impact of intensive breast feeding training on CHWs. The intervention was guided by focus group discussions among health workers, lactating mothers, and grandmothers. A total of 66 CHWs received the Ife South Breast Feeding Project (ISBFP); another 67 CHWs were not exposed to the training. Logistic regression analyses indicated that ISBFP training was the strongest predictor of CHW recommendations of exclusive breast feeding and against early supplementation (odds ratio, 60.25). Younger CHWs (20-29 years) were 3.02 times more likely than their older counterparts to promote exclusive breast feeding, but no other sociodemographic characteristics of health workers were significant. Recommended, in light of these findings, is expansion of health worker training to include breast feeding and lactation management and on-the-job retraining of current CHW cadres. If outreach to pregnant women is handled in a culturally sensitive way, clients of trained CSWs should be able to overcome the constraints of local tradition.
openalex: W1564779965 mag: 1564779965
Keywords: openalex:import

Ethnicity, test anxiety and science achievement in Nigerian students - Adigwe, J. C. (International Journal of Science Education, 1997)
Abstract This study investigated ethnic and gender differences in test anxiety and achievement test performances of Nigerian junior secondary school students. The sample consisted of 100 Ibibio, 100 Yoruba and 100 Tiv students randomly drawn from four rural schools in each ethnic zone. Each sample consisted of 50 male and 50 female students, between the ages of 11 and 16. Two research instruments, a test anxiety scale and an integrated science multiple‐choice test, were used, Multivariate analysis of variance indicated that: (i) there were significant ethnic and gender effects on the test anxiety and achievement test performance of the students; (ii) there was significant negative correlation between test anxiety and achievement test performances for the ethnic and gender groups of the students, except for the Yoruba female students who had insignificant negative correlation for the two variables. The significant negative correlation remained when the effects of gender and ethnicity were statistically controlled; (iii) test anxiety was affected by the inter‐active effects of gender and ethnicity; (iv) achievement test performance was affected by gender, ethnicity and test anxiety, and their interactive effects.
openalex: W1983900943 mag: 1983900943
Keywords: openalex:import

The impact of law on female education in Nigeria - Bamgbose, O. (1997)
openalex: W2911234193 mag: 2911234193
Keywords: openalex:import

Science, technology and the education of the South African child - Cortie, L.D.; Cortie, Michael (South African Journal of Science, 1997)
The Department of Education's Curriculum 2005 discussion document descriptionbes the 'outcomes' that are desired from the education to be offered to children at school in the years to come. It is debatable whether they will be achieved to the extent required in the natural sciences and technology.
openalex: W2461327564 mag: 2461327564
Keywords: openalex:import

Training surgically competent doctors for South African rural settings. - El, Mazwai (PubMed, 1997)
The training of surgically competent doctors for South African rural settings is governed by several factors and determinants which include population demographics, distribution of doctors, infrastructural development and socio-economic conditions of the communities. Demands will be influenced by the disease profile, available facilities and academic support. Training options will include community-oriented/based (undergraduate) curriculum and restructured internship training period and acquisition of skills. Postgraduate diplomas and fellowships and continuing medical education and academic support will form an integral part of the training.
openalex: W2405333720 mag: 2405333720
Keywords: openalex:import

The alkaline Meidob volcanic field (Late Cenozoic, northwest Sudan) - Franz, Gerhard; Breitkreuz, Christoph; Coyle, D. A.; Hur, Bushra El; Heinrich, Wilhelm; Paulick, Holger; Pudlo, Dieter; Smith, Robyn; Steiner, Gesine (Journal of African Earth Sciences, 1997)
The Meidob volcanic field (MVF) forms part of the Darfur Volcanic Province and developed from 7 Ma to 5 ka as indicated by K/Ar, thermoluminescence and 14C ages. It is situated in an uplifted high of the Pan-African basement, which consists of greenstones, high-grade gneisses and granites, and which is covered by Cretaceous sandstone. The MVF basaltic lavas, which originated from more than 300 scoria cones, formed a lava plateau of 50×100 km and up to 400 m thickness in the time between 7 and < 0.3 Ma. Young phonolitic mesa flows, together with rare trachyticbenmoreitic lava flows, trachytic pumice fallout deposits, ignimbrites and maars, form the central part of the field. The total amount of volcanic rocks is between 1400 and 1800 km3, with 98 vol.% being basaltic rocks, which results in an integrated magma output rate of ∼ 0.0002 km3 a−1. A combination of age data of the lavas with erosional features yields uplift rates for the Darfur Dome of ∼30 m Ma-1 in the MVF area. Magma was generated by 3–5% melting of predominantly asthenospheric mantle with a HIMU contribution. Fractionation of olivine, pyroxene, An-poor plagioclaseanorthoclase, magnetite and apatite leads to a differentiation from basanite to phonolite. Assimilation of crustal rocks near the top of the phonolitic upper crustal magma chambers - facilitated by volatile enrichment - produced magmas which gave way to benmoreitic and trachytic lavas, as well as to trachytic ignimbrites and pumice fallout deposits. Ultramafic cumulate xenoliths indicate the existence of major magma reservoirs at the crust-mantle boundary during MVF activity. Magma ascent occurred in a tensional regime, which changed its orientation at around 1 Ma. Early during MVF development, west-east and subordinately northeastsouthwest trending lineaments were active whereas volcanic activity younger than 1 Ma took place along northwest-southeast and northeast-southwest trending systems. The Central African Fault Zone, a transcontinental, lithospheric shear zone, played an important role for the rise of magmas in the Darfur Dome. Le district volcanique de Meidob fait partie de la province volcanique de Darfour et s'est développé entre 7 Ma et 5 ka d'après des âges K/Ar, thermoluminescence et 14C. II est situé dans une zone surélevée du socle panafricain, qui consiste en roches vertes, en gneiss et en granites, et qui est recouverte par des grès crétacés. Les laves basaltiques du district de Meidob, qui émanent de plus de 300 cones de scorie, forment un plateau de laves mesurant 50×100 km, d'une paissure de 400 m. De jeunes coulées phonolitiques avec de rares coulées de trachyte benmoréïte, de depots de pumice trachytique, d'ignimbrites et de maars constituent la partie centrale du district. Le volume total des roches volcaniques est entre 1400 et 1800 km3, avec 98% vol de roches basaltiques, qui donne un taux de production de magma de 0,0002 km3 a−1. La combinaison des donndes sur ages des laves et sur l'erosion indique des taux de surrection pour le Dôme de Darfour de 30 m Ma−1 dans le district de Meidob. Le magma a W généré par une fusion de 3 à 5% du manteau asthénosphérique avec une contribution HIMIJ. Le fractionnement de ('olivine, du pyroxéne, d'un plagioclase-anorthose à faible teneur en An, de magnetite, et d'apatite produit une lignée de différenciation dela basanite à la phonolite. L'assimilation de roches crustales près du sommet des chambres magmatique des phonolites - facilitée par un enrichissement en volatiles - ont procluit des magmas donnant lieux à des laves benmoréïtiques et trachytiques, ainsi qu'è des ignimbrites trachytiques et à des dépots de pumice. Des xénolithes ultramafiques cumulatives indiquentl' éxistence de reservoirs majeurs à la limite croûte-manteau. La montée du magma a eu lieux dans un regime de tension, qui a change d'orientation autour de 1 Ma. Tôt clans le développement du district, des lineaments W-E et NE-SW subordonnés étaient actives tandis que I'activité volcanique plus jeune que 1 Ma est localisée le long des directions NW-SE et NE-SW. La Zone de Failles Centre Africaine, une zone de cisaillement lithosphérique transcontinentale, a joué un rôle important dans la montée des magmas dans le Dôme de Darfour.
openalex: W2060908872 mag: 2060908872
Keywords: openalex:import

Participation in Health Education, Health Promotion, and Health Research by African Americans: Effects of the Tuskegee Syphilis Experiment - Green, Bernard Lee; Maisiak, Richard; Wang, Min Qi; Britt, Marcia F.; Ebeling, Nonie (Journal of Health Education, 1997)
Abstract This study investigates the effect of the Tuskegee Syphilis Experiment (TSE) on participation in health promotion activities and research studies by African Americans. Random-digit dialing was used to interview 421 adults with telephones living in households in Jefferson County, Alabama in the summer of 1994. Respondents were asked if they had ever heard of the TSE and, if yes, because they knew about the experiment, were they less interested in participating in health promotion or research activities. The primary results were that African Americans, in general, reported less interest in participating in health promotion and research because of their knowledge of the TSE. African American males in particular reported a high degree of resistance because of knowledge of the TSE. These results may have implications for practitioners and researchers recruiting African American subjects for research studies and participation in health promotion and health education programs. It may be necessary to discuss the Tuskegee Experiment openly and to address concerns of the African American community regarding this issue. This open discussion about The TSE may help rebuild trust and allow for development of programs and services that meet the needs of the African American community.
openalex: W2069218963 mag: 2069218963
Keywords: openalex:import

Effect evaluation of an oral health education programme in primary schools in Tanzania - Helderman, W.H. van Palenstein; Munck, Lars Kristian; Mushendwa, S.; Hof, M.A. van ‘t; Mrema, F. G. (Community Dentistry and Oral Epidemiology, 1997)
Abstract This study aimed to assess the clinical oral health outcome effects among schoolchildren participating in a school-based oral health education (OHE) programme. Local social, cultural and environmental conditions were determinants of the school-based OHE programme, which was compiled on the basis of prevailing beliefs and on what teachers and educational authorities considered to be important for the oral health of schoolchildren. Consequently, the practical aspects of oral hygiene and information on the cause and prevention of caries and gingivitis were the components of oral health education. The teachers were prepared to carry out weekly supervised toothbrushing sessions and monthly lessons on aspects of oral health for the school year in grade 4. Eight participating schools were selected for the clinical effect evaluation and four non-participating schools served as the control. In total, 309 children from the participating schools and 122 children from the non-participating schools were available for the evaluation. Their ages varied between 9 and 14 years. The mean plaque score, calculus score and gingival bleeding score at baseline and at follow-up examinations 3, 8, 15 and 36 months later were not significantly different for participating schools and controls. The mean DMFT value at baseline was 0.4 and 3 years later 0.9 in both the participating and control schools. In conclusion, the present study shows that the implemented school-based OHE programme did not result in significant reductions of the clinical parameters measured.
openalex: W2117654707 mag: 2117654707
Keywords: openalex:import

Recruitment and Training Issues from Selected Lay Health Advisor Programs among African Americans: A 20-Year Perspective - Jackson, Ethel; Parks, Carolyn P. (Health Education & Behavior, 1997)
The use of lay health advisors (LHAs) to address the health disparity among African Americans is well documented and considered a culturally appropriate model of community health promotion. The recruitment and training of LHAs are important components of the model but have not been fully explored in the LHA literature. Recruitment and training of LHAs should reflect both the existing roles they have in their respective communities and those proposed by the programs to which they are recruited. This article reviews and describes the components of recruitment and training as implemented in selected LHA programs among African Americans. The article will address the role and purpose of LHAs in health promotion among African Americans, a historical perspective of recruitment and training, recruitment and training methods in selected LHAs programs for African Americans, and recommendations for the recruitment and training of LHAs for health promotion among African Americans.
openalex: W2138334718 mag: 2138334718
Keywords: openalex:import

Bilharzia interrupts children's education in Kenya - Kigotho, Anderson Wachira (The Lancet, 1997)
Bilharzia infection among schoolchildren in Kenya's coastal districts has reached alarming levels, according to a study done by the Kenya Medical Research Institute (KEMRI) and the London School of Hygiene and Tropical Medicine, UK. The study also attributes poor academic performances in schools to bilharzia. Ng'ethe Muhoho, a senior KEMRI researcher, says that on average 78% of schoolchildren in Mombasa, Kwale, Kilifi, Malindi, and Lamu districts are infected with bilharzia and other intestinal parasites. Hard hit is Kwale district, where infection in some areas is 90% of all schoolchildren. The district has 265 primary schools with 80000 pupils.
openalex: W2070214292 mag: 2070214292
Keywords: openalex:import

Declining Expectancies in African American College Students: The Influences of Attributions and Self-Esteem across the College Years. - Laar, Colette van (1997)
openalex: W256779812 mag: 256779812
Keywords: openalex:import

Hexamethylene Diisocyanate (HDI)‐Induced Lung Impairment: Studies in Isolated Perfused and Ventilated Guinea Pig Lungs - Låstbom, Lena; Skarping, Gunnar; Moldéus, Peter; Ryrfeldt, Åke (Pharmacology & Toxicology, 1997)
Abstract: Isolated, perfused and ventilated guinea pig lungs were exposed to hexamethylene diisocyanate via the air passages. Two air concentrations of hexamethylene diisocyanate were studied (3.5 and 11 mg/m 3 ). There was a statistically significant (P<0.05 − 0.001) dose‐related reduction in both conductance and compliance but no effects were noted on the pulmonary circulation. With 3.5 mg/m 3 hexamethylene diisocyanate the conductance capacity was reduced with 38% and compliance with 30% after 60 min. exposure. Eleven mg/m 3 hexamethylene diisocyanate reduced the conductance and compliance capacity with 86 and 69 %, respectively, on an average. The reduction in lung function (with 11 mg/m 3 ) was abolished when 100 μM diclofenac, a cyclooxygenase inhibitor, was added to the perfusate (P<0.01). The thromboxane A 2 antagonist L‐670,596 (20 μM) exerted a partial protective effect. The capacity of conductance and compliance decreased with 46 and 32% respectively, on an average, after preperfusion with L‐670,596 and a following exposure of 11 mg/m 3 hexamethylene diisocyanate for 60 min. Statistically significant protection (P<0.05) was obtained on compliance and the P‐value was<0.1 for conductance. Thus, these data indicate that hexamethylene diisocyanate‐induced bronchoconstriction is mediated via arachidonic acid release and thromboxane formation, in isolated, perfused and ventilated guinea pig lungs.
openalex: W2061686512 mag: 2061686512
Keywords: openalex:import

Getting through Grade 2: Predicting Children’s Early School Achievement in Rural South African Schools - Liddell, Christine; Lycett, John; Rae, Gordon (International Journal of Behavioral Development, 1997)
Children in the second-grade classrooms of three rural schools ( n 150) completed a variety of psychometric and curriculum-based tests, and were rated by their teachers and parents on dimensions of their everyday behaviour; demographic data (e.g. socioeconomic status, presence of mother in the home) and biographical information (e.g. gender, age, birth order) were also collected for each child. Some of these data (e.g. child’s age and gender) were more cost-efficient to collect than others (e.g. parent ratings). Measures were evaluated in terms of their salience for constructing a multivariate model that would predict subsequent grade 2 outcome, with the most cost-effective variables being inserted first. In this way, both the cost-efficiency and predictive power of independent variables (IVs) were taken into consideration when attempting to build a predictive model. A model containing three IVs (scores on curriculum-based tests, teacher ratings of children’s attention span, and teacher ratings of helpfulness) ultimately predicted 51% of the variance in grade 2 outcome. These results demonstrate, first, that it is possible to build a relatively strong predictive model of grade 2 outcome, although not based on variables that are cheap and quick to measure. Second, that doing well in grade 2 is not so much a matter of having well-developed, broad-ranging psychometric abilities, but more a matter of mastering elements of the curriculum and behaving in ways that permit adaptation to the requirements of crowded and under-resourced African classrooms.
openalex: W2156252034 mag: 2156252034
Keywords: openalex:import

Developing a competence‐based teacher education programme in Swaziland - Mndebele, C.B.S. (Journal of Education and Training, 1997)
The workplace of the twenty‐first century will be, in many respects, significantly different from that of today; therefore, vocational educational graduates need to be prepared for the changes expected in the workplace. Calls for vocational teacher education programmes that incorporate critical skills for high school vocational teachers. Reports the findings of a study conducted to identify professional vocational education competences needed by Swaziland teachers of practical studies (agricultural, commercial, home economics, and technical). Employs a procedure to develop professional competences. Identifies eleven competence areas developed by a professional panel of experts at a two‐day focus group interview workshop.
openalex: W2081533206 mag: 2081533206
Keywords: openalex:import

Proteinuria, other selected urinary abnormalities and hypertension among teenage secondary school students in Nairobi, Kenya. - Muraguri, P W; McLigeyo, Seth O.; Kayima, J K (PubMed, 1997)
Four hundred and three teenage secondary school students (50.6% males) from two girls' and two boys' Nairobi City Schools, selected by stratified sampling, were screened to determine the prevalence of proteinuria, haematuria, nitrituria and hypertension. Nine students (2.2%) had significant proteinuria while 14 (3.5%) had microscopic haematuria. Two students had combined proteinuria and haematuria. There was no statistically significant difference in the prevalence of proteinuria and/or haematuria between the sexes. Other urinary abnormalities detected were leucocyturia in 14(3.5%) and nitrites in four (1%). Leucocyturia was commonner in females (p = 0.001). Cloudy urinary appearance was significantly associated with the presence of leucocyturia (p = 0.0028) and proteinuria (p = 0.0276). Neither personal history of recurrent sore throat and skin infections nor family history of hypertension, diabetes mellitus or kidney disease was significantly associated with proteinuria or haematuria. Blood pressure tended to increase with age. Mean systolic and diastolic blood pressures were significantly higher in boys than girls in the age group 15-18 years (P < 0.001). Of the 397 students whose blood pressures were measured, four (1%) were found to be hypertensive. Weight and body mass index were strong positive correlates of blood pressure. The prevalence of proteinuria, haematuria, other urinary abnormalities and hypertension ranges between 1% and 3.5% among teenage secondary school children. The majority are asymptomatic and have no significant associations. It is recommended that routine urinalysis and blood pressure measurements should be part of the school health service so as to identify asymptomatic students who require close monitoring and/or intervention.
openalex: W1938500684 mag: 1938500684
Keywords: openalex:import

The Impact of Sexual Activity and Fertility Timing on African American High School Graduates' Later Life Experiences - Murry, Velma McBride (Families in Society, 1997)
There has been national concern since the early 1980s over the need to prevent teen pregnancy. Much of that concern has stemmed from concerns over the notion that families formed as a result of adolescent parenthood are often poor and welfare dependent. Much of the research on adolescent childbearing implies that having a child disadvantages adolescents in terms of future life options. The author examined the life experiences of 1666 Black female high school graduates of average age 25.4 years 5 years out of high school using data from the National Survey of Family Growth Cycle IV. 474 virgins, 570 never-pregnant women, 65 ever-pregnant women, and 557 adolescent mothers were examined. Most of the women had never married, with virgins and adolescent mothers the least likely to be in marital relationships. Relative to the other subgroups, virgins reported higher educational, financial, and occupational achievement. However, a significant proportion of adolescent mothers were more successful than conventional stereotypes suggest. Several had secured professional jobs, had middle-income status, and were pursuing additional educational training. The implications for future research, education, and policy are discussed.
openalex: W2044672798 mag: 2044672798
Keywords: openalex:import

Psychological Storms: The African American Struggle for Identity - Parham, Thomas A. (1997)
openalex: W10566816 mag: 10566816
Keywords: openalex:import

Training of medical assistants in Mozambique for surgery in a rural setting. - Pi, Garrido (PubMed, 1997)
openalex: W2430856282 mag: 2430856282
Keywords: openalex:import

Impact of literacy training on spatial representation in Southwest Ethiopia - Pontius, Anneliese A. (International Journal of Intercultural Relations, 1997)
In order to study the impact of literacy training on visual-spatial cognitive performance, the Kohs Block Design and the “Draw-a-person-with-face-in-front (DAPF)” test were administered to two distinct populations of agricultural pastoralists in Southwest Ethiopia. The Karo have no literacy training while the Hamar subjects had had several years of schooling. As expected, Hamar subjects (who were literate) produced a larger percentage (43.1%) of correct block constructions as compared to the Karo who produced only 16.7% correct block constructions. Error analysis, however, revealed that the Karo produced a larger proportion (27.08%) of “nonrandom” error types (errors which nevertheless preserved essential spatial attributes, the shapes of the target design, while neglecting its spatial relations) than did the literate Hamar subjects (9.03%). Similarly 57.6% of face drawings by nonliterate Karo subjects and only 8.3% of Hamar drawings were classified as resembling the “neolithic” prototype (also neglecting spatial relations). Results support the hypothesis that literacy influences spatial-relational cognitive skills.
openalex: W2006144063 mag: 2006144063
Keywords: openalex:import

Fungal microflora biodiversity as a function of pollution in Oued Sebou (Morocco) - Sage, Lucile; Bennasser, Laïla; Steiman, R.; Seigle‐Murandi, F. (Chemosphere, 1997)
An inventory of the fungal microflora present in sediments collected at 11 sites along Oued Sebou has been established. The influence of some climatic parameters (temperature, rainfall) and of pollution on the composition of the fungal communities has been questioned. Emericella nidulans, Eurotium amstelodami, Neosartotya fesheri var. glabrum (Ascomycetes), Dreschslera biseptata (Dematiac˦;), Penicillium citrinum (Mucedinace˦) and Phoma sp. (Sph˦ropsidale) can be considered as strains sensitive to pollution. Penicillium janthelinum, Trichoderma koningii (Mucedinace˦) and Candida albicans (Yeast) were found only at the most polluted sites ; Talaromyces flavus (Ascomycete) Rhodotorula rubra, Saccharomyces cerevisi˦ (Yeasts) and Fusarium oxysporum (Tuberculariales) were more often found at heavily polluted sites than at lightly polluted ones.
openalex: W2083042583 mag: 2083042583
Keywords: openalex:import

Church‐based education: An outreach program for African Americans with hypertension - Smith, Eva D.; Merritt, Sharon L.; Patel, Minu (Ethnicity and Health, 1997)
Abstract The goals of this education outreach demonstration study were to prepare a cadre of registered nurses (RN) as Church Health Educators (CHE), and to test the efficacy of a hypertension (HBP) education and support program in African American (AA) churches for persons with HBP in managing blood pressure (BP). In this two‐phase study, RNs were prepared as CHEs in phase 1 and a convenience sample of 97 subjects with HBP was taught by the CHEs in phase 2. The intervention's content included the bases of HBP and HBP management strategies, and was taught in eight 1‐hour sessions. Using a pre‐test‐post‐test design, data on knowledge, social support and BP were collected at baseline (pre), post‐intervention (post1) and 3 months post‐intervention (post2). Major findings include: (1) there was a significant increase in knowledge scores from pre to post1 and post2 (P ≤ 0.0001; F = 95.08; df = 1,79); (2) education, age and number of years with HBP explained 49% of the variance associated with HBP knowledge; (3) systolic BP (SBP) and mean arterial BP (MAP) significantly decreased from pre to post1 and post2 (SBP—p ≤ 0.0001, F = 18.35, df = 1,91; MAP—p ≤ 0.0001, F = 17.80, df = 1,86); (4) DBP significantly decreased from pre to post1 only (p ≤ 0.008, F= 17.48, df = 1,91); and (5) relationships were found between social support and DBP, and social support and MAP. Issues that emerged from this study with implications for outreach programming include recruitment and retention, randomization, selective sampling, intervention design and use of volunteers.
openalex: W2047294403 mag: 2047294403
Keywords: openalex:import

The relationship between parental incarceration and African-American high school students' attitudes towards school and family. - Stroble, Willie Lee (1997)
openalex: W2802890163 mag: 2802890163
Keywords: openalex:import

Training of medical practitioners in Nigeria (west Africa) for surgery in the rural areas. - Tf, Solanke (PubMed, 1997)
Awojobi Clinic in Eruwa, Nigeria, a hospital in a rural setting, is used as a case study. Medical practitioners hoping to practise surgery in a rural setting should be able to carry out certain essential life-saving procedures. The curricula of surgical training in medical institutions are examined to determine their relevance to performing surgery in a rural setting, and some suggestions are proffered.
openalex: W2413789644 mag: 2413789644
Keywords: openalex:import

Training agricultural economists for Southern Africa and the 21st century - Kirsten, Johann F. (1997)
openalex: W91247734 mag: 91247734
Keywords: openalex:import

Experience with cleft lip and palate patients seen in a Nigerian Teaching Hospital - Ugboko, V.I.; Owotade, FJ; Otuyemi, Olayinka Donald; Adejuyigbe, O (Pediatric dental journal : international journal of Japanese Society of Pediatric Dentistry, 1997)
openalex: W399431225 mag: 399431225
Keywords: openalex:import

The Effect of the Family on the Emotional Life of Ethiopian Immigrant Adolescents in Boarding Schools in Israel - Ben‐David, Amith; Msw, Tamar Erez-Darvish (Residential Treatment for Children & Youth, 1997)
ABSTRACT This study examines the relationship between the family functioning of adolescent Ethiopian immigrants, as assessed by father, mother, and adolescent, and their school performance as evaluated by their teachers. Forty adolescents were randomly selected from all the 15–18-year-old students, with intact families, studying in boarding schools in the northern part of Israel. The students and their parents were given the FACES III (Family Adaptability and Cohesion Evaluation Scales) to determine family cohesion and adaptability. Teachers were approached to determine the adolescents' success in school achievement, personal relations with peers and school teachers, and predisposition to somatization and mood fluctuations. Results show that there was no relationship between family functioning and school achievement or personal relations with peers and school teachers. However, a strong relationship between fathers' and mothers' perceptions of family adaptability and cohesion was found, with most families clustered in the middle levels of family adaptability, while cohesion tended to be somewhat more extreme. Family cohesion and sense of coherence were associated with absence of moodiness and somatization in the adolescents, indicating that family functioning may predict their emotional stability in boarding school.
openalex: W1972495261 mag: 1972495261
Keywords: openalex:import

Ariaal Pastoralists of Kenya : Surviving Drought and Development in Africa's Arid Lands - Fratkin, Elliot (1997)
openalex: W2089888922 mag: 2089888922
Keywords: openalex:import

Shallow dips of normal faults during rapid extension: Earthquakes in the Woodlark‐D'Entrecasteaux rift system, Papua New Guinea - Abers, G. A.; Mutter, Carolyn Z.; Fang, J. (Journal of Geophysical Research, 1997)
Earthquakes in the Woodlark‐D'Entrecasteaux rift system reveal changes in fault geometry along strike, as extension progresses from continental to oceanic modes. In one segment, evidence is found for earthquakes on shallow‐dipping normal faults. To examine these trends, locations of 147 earthquakes are redetermined, and focal mechanisms for 21 events are derived from waveform inversion. Where seafloor spreading occurs, east of 152°E, most earthquakes illuminate a NE‐SW strike‐slip fault north of the oceanic rift system along the Woodlark Rise. Elsewhere, earthquakes occur along a well‐defined rift zone, and focal mechanisms reveal normal faulting with north‐south T axes and depths less than 10 km. Most normal‐faulting earthquakes show high‐angle fault planes (dips 40°–50°), but several are consistent with slip on moderately low‐angle planes dipping 15°–35°. These low‐angle nodal planes are only found in a region between 150.5°E and 152.5°E, where the transition occurs from seafloor spreading to continental rifting. A seismic reflection profile near 151°E reveals a major normal fault that dips to the north at 25°–35° just landward of the oceanic rift tip. That fault and parallel structures are excellent candidates for the fault that slipped in at least two of the earthquakes studied. Hence normal faults dipping ∼30° are likely to be seismically active in at least one part of this rift system. In this region just landward from the rift tip the highest extension rates are expected (∼40 mm/yr) and strain appears localized on a single system of normal faults. Because shallow dips for normal faults are seen near the rift tip, but not elsewhere along strike, high strain rates may be an important factor in allowing normal faults to slip at unusually shallow dips. Perhaps high shear traction at the base of the upper crust, localized by nearby spreading, sufficiently alters the local stress regime.
openalex: W2082990071 mag: 2082990071
Keywords: openalex:import

Ecclesiology and theological education: A South African reformed perspective - Wethmar, C. J. (Verbum Et Ecclesia, 1997)
Ecclesiology and theological education: A South African reformed perspective. The church is one of the primary contexts in which theology is done. In the South African theology education debate the implications which this context has for the nature of theological education has not yet been adequately described. This article therefore intends dealing with this issue. The well known four attributes of the church are used as indicators of the nature of theological education which results in confessionality, spirituality, ecumenicity and hermeneutics being identified as its main dimensions.
openalex: W2161147115 mag: 2161147115
Keywords: openalex:import

The 25th International Forestry Students Symposium (IFFS) 1997 in South Africa (Southern African forestry journal, 1997)
openalex: W4241638294
Keywords: openalex:import

Workers’ education and human crisis in Zambia: democracy and the ‘new’ world order - Alexander, David (International Journal of Lifelong Education, 1997)
Abstract The most important challenge in our era is finding ways and means to enable workers to survive the realities of the Structural Adjustment Programme which has brought untold misery and poverty on peasants and workers in Zambia. Changes taking place in the political, social and economic life of the country need to be carefully studied and thoroughly understood by workers and union leaders so that we manoeuvre through the situation in a much more rational and positive way if our newly founded democracy is to be safeguarded. To this effect workers’ education is going to play an important role in consolidating democracy. (Willie Kasase, Director of Workers’ Education & Training, Zambia Congress of Trade Unions [ZCTU] 1993: 10) Workers’ education must go towards the goal of understanding the ‘New’ World Order, in order to deal with it and challenge it locally. (Senior Zambian Trade Unionist, August 1992)
openalex: W2013741980 mag: 2013741980
Keywords: openalex:import

Book review of Encyclopedia of African-American Education - Banks, James A. (Journal of Education for Students Placed at Risk (JESPAR), 1997)
openalex: W1966970022 mag: 1966970022
Keywords: openalex:import

“Sewing” Civilization: Cuban Female Education in the Context of Africanization, 1800-1860 - Childs, Matt D. (The Americas, 1997)
At the turn of the nineteenth century, the Spanish Crown issued a Real Cédula (Royal Decree) authorizing the administration of public education in Cuba to an elite Creole group of twenty-seven large landholders known as the Sociedad Económica de Amigos del País . The Real Cédula provided for the expansion and secularization of primary education in Cuba. The Sociedad embodied the elite planter Creole class whose influence had increased in Cuba steadily during the second half of the eighteenth century with the initial development of a slave-labor plantation economy. During the nineteenth century, their power and strength grew rapidly with the proliferation of sugar cultivation, culminating in the 1840s when Cuba became the world's primary producer. The Real Cédula entrusting the Sociedad with education recognized the emergence of the Creole planter class as a major influence in Cuban society. Just as the Creoles increasingly wielded more influence economically and politically in determining the future of the island, their control over the administration of public education allowed them to articulate their vision for the cultural and intellectual development of Cuba. The promotion of public education provided an essential medium to express the Sociedad's vision of Cubanidad (Cubanness), precisely at the time when the racial composition of the population was changing dramatically through the massive importation of African slave labor.
openalex: W1985283314 mag: 1985283314
Keywords: openalex:import

Early Childhood Education in Zimbabwe: Recent Trends and Prospects - Cleghorn, Ailie; Prochner, Larry (Early Education and Development, 1997)
Recent trends in early childhood teacher education in Zimbabwe are reviewed in the context of overall teacher reform. Social tensions which stem from the current system of early education and care are described, together with a survey of beliefs regarding early education held by parents, teachers, and primary school headmasters. The results point to the diversity of meanings attached to early education in Zimbabwe, and the challenge this poses for parents, teachers, and policy makers in Zimbabwe.
openalex: W2154789261 mag: 2154789261
Keywords: openalex:import

AIDS Education: A Conversation with an African American Adolescent. - Davis, Marjorie T. (Journal for a Just and Caring Education, 1997)
openalex: W280143428 mag: 280143428
Keywords: openalex:import

Peer education without pressure: spreading hygiene messages in Burkina Faso - Dieleman, Marjolein; Traoré, San (Waterlines, 1997)
However keen the take up of the new technology, a programme stands or falls on whether people change their normal behaviour for the better. But who wants to tell their neighbours what to do?
openalex: W1985103012 mag: 1985103012
Keywords: openalex:import

Impairment of endothelium‐dependent but not of endothelium‐independent dilatation in guinea‐pig aorta rings incubated in the presence of elevated glucose - Dorigo, P.; Fraccarollo, Daniela; Santostasi, Giovanni; Maragno, I (British journal of pharmacology, 1997)
Purine compounds such as ATP and adenosine, respectively endothelium‐dependent and‐independent vasodilators, are largely involved in the control of vascular tone and vascular reactivity to contracting stimuli. We investigated the relaxing activity of ATP and adenosine in guinea‐pig aorta rings exposed for 6 h to elevated glucose concentration (50 m M ), in order to mimic hyperglycaemic conditions. Guinea‐pigs were reserpine‐treated (2 mg kg −1 , i.p., 48 and 24 h before death). Rings of aortae incubated in 50 m M glucose, contracted submaximally by 1 μ M noradrenaline, lost endothelium‐dependent relaxation in response to acetylcholine (10 n M to 10 μ M ). Aortae incubated with 50 m M mannose, as a hyperosmotic control, relaxed to acetylcholine normally. Rings of aortae incubated in 50 m M glucose, contracted submaximally by 3 m M 4‐aminopyridine, lost endothelium‐dependent relaxation in response to ATP (30 μ M ) whereas endothelium‐independent relaxation in response to adenosine (0.3 m M ) was well preserved. The relaxation induced by A23187 or sodium nitroprusside (10 n M to 0.1 μ M ) did not differ between rings exposed to control (5.5 m M ) or elevated glucose (50 m M ) and contracted submaximally by 3 m M 4‐aminopyridine. When incubated with aortic tissue in the presence of elevated glucose, the cyclo‐oxygenase inhibitors, indomethacin (10 μ M ) and mefenamic acid (30 μ M ), or the scavenger of superoxide anions, superoxide dismutase (150 u ml −1 ), prevented the impairment of ATP‐mediated relaxation. The present results indicate that endothelium‐dependent, receptor‐induced relaxation in response to acetylcholine and ATP is impaired in guinea‐pig aorta rings exposed to elevated glucose. The endothelial dysfunction caused by glucose might be located at a step between receptor activation and intracellular calcium increase, and might be related to an increased metabolism of arachidonic acid coupled to an increased production, or to a reduced inactivation of superoxide anions.
openalex: W2056210239 mag: 2056210239
Keywords: openalex:import

The relationship of school strain to school functioning and self-worth among urban African American early adolescents - Fenzel, L. Mickey; Magaletta, Philip R.; Peyrot, Mark (Psychology in the Schools, 1997)
Fitting the environment of a school to the developmental needs of early adolescents is particularly important for inner-city African American students who tend to drop out of school in large numbers. The present study examined the person-environment fit in terms of the relation of school strain to self-worth and three indicators of school functioning—scholastic competence, intrinsic motivation, and grade point average—among 102 subjects enrolled in an academic intervention program. Results showed a consistent relation of peer strain to self-worth during the Fall and Spring and strong relations in the Spring of strain associated with teacher relations and school demands to scholastic competence and intrinsic motivation. Furthermore, strain increased during the year, and males experienced greater peer strain than did females. Results are discussed in light of previous research on effective middle schools and the developmental needs of urban African American early adolescents. © 1997 John Wiley & Sons, Inc.
openalex: W2010923457 mag: 2010923457
Keywords: openalex:import

The relationship of school strain to school functioning and self‐worth among urban African American early adolescents - Fenzel, L. Mickey; Magaletta, Philip R.; Peyrot, Mark (Psychology in the Schools, 1997)
Fitting the environment of a school to the developmental needs of early adolescents is particularly important for inner-city African American students who tend to drop out of school in large numbers. The present study examined the person-environment fit in terms of the relation of school strain to self-worth and three indicators of school functioning—scholastic competence, intrinsic motivation, and grade point average—among 102 subjects enrolled in an academic intervention program. Results showed a consistent relation of peer strain to self-worth during the Fall and Spring and strong relations in the Spring of strain associated with teacher relations and school demands to scholastic competence and intrinsic motivation. Furthermore, strain increased during the year, and males experienced greater peer strain than did females. Results are discussed in light of previous research on effective middle schools and the developmental needs of urban African American early adolescents. © 1997 John Wiley & Sons, Inc.
openalex: W4230099132
Keywords: openalex:import

Geophagy among school children in Western Kenya - Geissler, Paul Wenzel; Mwaniki, Dennis; Thiong'o, F; Friis, Henrik (Tropical Medicine & International Health, 1997)
A cross‐sectional study was conducted among 285 school children aged 5–18 years in Nyanza Province, Western Kenya, to determine the prevalence of geophagy and the types and amounts of soil eaten. Stool samples were taken from a subsample of 53 (19%) and their silica content determined to compare the results with the reported geophagy. Geophagy was practised by 73% of the children. The prevalence decreased with age for both sexes up to age 15, then remained stable for girls between 15 and 18 years but continued to decrease for boys in that age range. Most children ate soil from the surface of termitaria; others preferred the edges of paths and gullies, material from the wall of huts, and a chalk‐like, soft stone commonly found in the area. The soil was eaten dry and was occasionally ground, but not processed in other ways. All but 4 of the children practising geophagy reported to eat soil at least once daily. The median amount reported eaten was 28 g daily, ranging from 8 to 108 g. The reported amount of soil eaten daily was significantly correlated to the results of the stool silica determinations. Using the median of 1% silica of faecal wet weight as a cut‐off point to distinguish geophageous children from non‐geophageous, the examination of a single stool sample had a sensitivity of 76% and a specificity of 80% to detect a geophageous child compared to the interview method. The cultural context of geophagy and its potential health impact in terms of infection and nutrition need to be further investigated, and it is suggested that more school and community‐based studies on geophagy in different societies should be undertaken.
openalex: W2002520488 mag: 2002520488
Keywords: openalex:import

Science and technology education and the new South African school curriculum - Gibson, Georgia; Smith, Stacy; Chamberlain; Falcón; Gerrans, R.M.S. (Journal of The South African Institute of Mining and Metallurgy, 1997)
Manpower competencies in the mining, minerals processing and energy industries in South Africa into the next century will, to a large extent, derive from the nature and quality of the teaching which pupils receive at school. This paper provides an overview of the current developments towards a new National Curriculum in South African Schools and highlights areas in which the Minerals Industry might provide input into this process.
openalex: W2604405271 mag: 2604405271
Keywords: openalex:import

Gender and Education Impacts on Employment and Earnings in West Africa: Evidence from Guinea - Glick, Peter; Sahn, David E. (Economic Development and Cultural Change, 1997)
Previous articleNext article No AccessGender and Education Impacts on Employment and Earnings in West Africa: Evidence from GuineaPeter Glick David E. Sahn Peter GlickCornell University Search for more articles by this author David E. SahnCornell University Search for more articles by this author Cornell UniversityPDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Economic Development and Cultural Change Volume 45, Number 4July 1997 Article DOIhttps://doi.org/10.1086/452308 Views: 256Total views on this site Citations: 62Citations are reported from Crossref © 1997 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Andrew M. Simons What is the optimal locus of control for social assistance programs? Evidence from the Productive Safety Net Program in Ethiopia, Journal of Development Economics 158 (Sep 2022): 102897.https://doi.org/10.1016/j.jdeveco.2022.102897Francisco M. P. Mugizi Stronger together? Shocks, educational investment, and self-help groups in Tanzania, Journal of Social and Economic Development 67 (May 2022).https://doi.org/10.1007/s40847-022-00183-3Melaku Abegaz, Gibson Nene Gender Wage and Employment Gaps in the Sub-Saharan Africa Economic Sectors, (May 2022): 919–941.https://doi.org/10.1007/978-3-030-75556-0_36Melek AKDOĞAN-GEDİK, Tuğay GÜNEL FACTORS AFFECTING GENDER WAGE GAP: EVIDENCE FROM SELECTED OECD COUNTRIES, Ömer Halisdemir Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi (Jan 2021).https://doi.org/10.25287/ohuiibf.823479Jince Shajan, Bevinje Subbyamoola Sumalatha Maternal employment and children's health in India: An exploratory analysis, Journal of Public Affairs 13 (Dec 2020).https://doi.org/10.1002/pa.2580Koami M. Midagbodji, Aklesso Y. G. Egbendewe L'accès des jeunes au marché du travail au Togo et au bénin: Une évidence paramétrique et semi‐paramétrique, African Development Review 32, no.S1S1 (Jan 2021).https://doi.org/10.1111/1467-8268.12482Francis Menjo Baye, Boniface Ngah Epo, Jean Ndenzako Female education and full-time employment in Guinea: an ambiguous relationship, Labor History 11 (Jan 2020): 1–19.https://doi.org/10.1080/0023656X.2020.1714019Miracle Ntuli, Prudence Kwenda Gender Gaps in Employment and Wages in Sub-Saharan Africa: A Review, (Jun 2019): 183–203.https://doi.org/10.1007/978-3-030-14935-2_11Goitseone Khanie Education and labor market activity of women: The case of Botswana, Journal of Labor and Society 22, no.44 (Nov 2019): 791–805.https://doi.org/10.1111/wusa.12455Sandhya Mahapatro Female employment in India: determinants of choice of sector of activity, Journal of Economic Studies 46, no.33 (Aug 2019): 748–759.https://doi.org/10.1108/JES-04-2017-0108Catalina Herrera, David E Sahn, Kira M Villa Teen Fertility and Female Employment Outcomes: Evidence from Madagascar, Journal of African Economies 28, no.33 (Feb 2019): 277–303.https://doi.org/10.1093/jae/ejy024Giulia La Mattina, Gabriel Picone, Alban Ahoure, Jose Carlos Kimou Female leaders and gender gaps within the firm: Evidence from three Sub-Saharan African countries, Review of Development Economics 22, no.44 (Aug 2018): 1432–1460.https://doi.org/10.1111/rode.12403Jordene Hale “For a Future Tomorrow”, (Sep 2018): 301–319.https://doi.org/10.1002/9781118931837.ch18Melaku Abegaz, Gibson Nene Gender Wage and Productivity Gaps in the Manufacturing Industry. The Case of Ghana, Economic Papers: A journal of applied economics and policy 37, no.33 (Aug 2018): 313–326.https://doi.org/10.1111/1759-3441.12224Fatma Guven-Lisaniler, Gulcay Tuna, Ikechukwu Darlington Nwaka Sectoral choices and wage differences among Nigerian public, private and self-employees, International Journal of Manpower 39, no.11 (Apr 2018): 2–24.https://doi.org/10.1108/IJM-01-2016-0002Solomon Asfaw, Giacomo Pallante, Alessandro Palma Diversification Strategies and Adaptation Deficit: Evidence from Rural Communities in Niger, World Development 101 (Jan 2018): 219–234.https://doi.org/10.1016/j.worlddev.2017.09.004Carlijn Bussemakers, Kars van Oosterhout, Gerbert Kraaykamp, Niels Spierings Women’s Worldwide Education–employment Connection: A Multilevel Analysis of the Moderating Impact of Economic, Political, and Cultural Contexts, World Development 99 (Nov 2017): 28–41.https://doi.org/10.1016/j.worlddev.2017.07.002Ana Carolina Ogando, Sally Roever, Michael Rogan Gender and informal livelihoods, International Journal of Sociology and Social Policy 37, no.7/87/8 (Jul 2017): 435–451.https://doi.org/10.1108/IJSSP-06-2016-0077Catarina Nascimento Moreira, Man Wai Rabenevanana, David Picard Boys go fishing, girls work at home: gender roles, poverty and unequal school access among semi-nomadic fishing communities in South Western Madagascar, Compare: A Journal of Comparative and International Education 47, no.44 (Dec 2016): 499–511.https://doi.org/10.1080/03057925.2016.1253456Ouraich Ismail, Lowenberg-Deboer Jess, Soumah Alseny, Diallo Diawo Employment Prospects for Agricultural Graduates in Guinea Conakry, Journal of Agricultural Extension and Rural Development 9, no.11 (Jan 2017): 5–13.https://doi.org/10.5897/JAERD2016.0804Ikechukwu Darlington Nwaka, Fatma Guven-Lisaniler, Gulcay Tuna Gender wage differences in Nigerian self and paid employment: Do marriage and children matter?, The Economic and Labour Relations Review 27, no.44 (Nov 2016): 490–510.https://doi.org/10.1177/1035304616677655Francis Menjo Baye, Boniface Ngah Epo, Jean Ndenzako Wage Differentials in Cameroon: A Gendered Analysis , African Development Review 28, no.11 (Mar 2016): 75–91.https://doi.org/10.1111/1467-8268.12168Mathias Kuépié Determinants of labour market gender inequalities in Cameroon, Senegal and Mali: the role of human capital and fertility burden, Canadian Journal of Development Studies / Revue canadienne d'études du développement 37, no.11 (Mar 2016): 66–82.https://doi.org/10.1080/02255189.2016.1122580David E. Sahn, Kira Villa The Role of Personality, Cognition, and Shocks in Determining Labor Outcomes of Young Adults in Madagascar, SSRN Electronic Journal (Jan 2015).https://doi.org/10.2139/ssrn.2702415Niels Spierings The Influence of Patriarchal Norms, Institutions, and Household Composition on Women's Employment in Twenty-Eight Muslim-Majority Countries, Feminist Economics 20, no.44 (Nov 2014): 87–112.https://doi.org/10.1080/13545701.2014.963136Abou Kane Dynamique de l'emploi au Sénégal : un suivi de cohortes sur la période 1992-2011, Revue d'économie du développement Vol. 22, no.11 (Apr 2014): 75–105.https://doi.org/10.3917/edd.281.0075D.E. Sahn Nutrition, Health, and Economic Performance, (Jan 2014): 392–398.https://doi.org/10.1016/B978-0-12-375678-7.00107-3Anne E. Calvès, Jean-François Kobiané, Afiwa N’Bouké Privatization of Education and Labor Force Inequality in Urban Francophone Africa: The Transition from School to Work in Ouagadougou, World Development 47 (Jul 2013): 136–148.https://doi.org/10.1016/j.worlddev.2013.03.001M. Ntuli, M. Wittenberg Determinants of Black Women's Labour Force Participation in Post-Apartheid South Africa, Journal of African Economies 22, no.33 (Jan 2013): 347–374.https://doi.org/10.1093/jae/ejs039Tim B Heaton Religion and socioeconomic status in developing nations: A comparative approach, Social Compass 60, no.11 (Mar 2013): 97–114.https://doi.org/10.1177/0037768612471772Angela Luci, Johannes Jütting, Christian Morrisson Why Do So Many Women End Up in ‘Bad Jobs’? A Cross-country Assessment for Developing Countries, The European Journal of Development Research 24, no.44 (Dec 2011): 530–549.https://doi.org/10.1057/ejdr.2011.54Christophe J. Nordman, Anne-Sophie Robilliard, François Roubaud Gender and ethnic earnings gaps in seven West African cities, Labour Economics 18 (Dec 2011): S132–S145.https://doi.org/10.1016/j.labeco.2011.09.003Sarah Bridges, David Lawson, Sharifa Begum Labour Market Outcomes in Bangladesh: The Role of Poverty and Gender Norms, The European Journal of Development Research 23, no.33 (May 2011): 459–487.https://doi.org/10.1057/ejdr.2011.14Sarah Bridges, David Lawson Health and Female Labour Market Participation: The Case of Uganda, (Jan 2011): 174–192.https://doi.org/10.1057/9780230304673_9Sanjaya DeSilva, Mohammed Mehrab Bakhtiar Women, Schooling, and Marriage in Rural Philippines, SSRN Electronic Journal (Jan 2011).https://doi.org/10.2139/ssrn.1976259Monica Fisher, Jeffrey J. Reimer, Edward R. Carr Who Should be Interviewed in Surveys of Household Income?, World Development 38, no.77 (Jul 2010): 966–973.https://doi.org/10.1016/j.worlddev.2009.11.024Maria Minniti, Wim Naudé What Do We Know About The Patterns and Determinants of Female Entrepreneurship Across Countries?, The European Journal of Development Research 22, no.33 (May 2010): 277–293.https://doi.org/10.1057/ejdr.2010.17Salma Ahmed, Pushkar Maitra Gender Wage Discrimination in Rural and Urban Labour Markets of Bangladesh, Oxford Development Studies 38, no.11 (Mar 2010): 83–112.https://doi.org/10.1080/13600810903551611Mathias Kuepie, Christophe J. Nordman, François Roubaud Education and earnings in urban West Africa, Journal of Comparative Economics 37, no.33 (Sep 2009): 491–515.https://doi.org/10.1016/j.jce.2008.09.007Scott T. Yabiku, Sarah Schlabach Social Change and the Relationships Between Education and Employment, Population Research and Policy Review 28, no.44 (Nov 2008): 533–549.https://doi.org/10.1007/s11113-008-9117-2Christophe J. Nordman / François Roubaud Reassessing the Gender Wage Gap in Madagascar: Does Labor Force Attachment Really Matter? Nordman and Roubaud, Economic Development and Cultural Change 57, no.44 (Jul 2015): 785–808.https://doi.org/10.1086/598762S. Bridges, D. Lawson A Gender-based Investigation into the Determinants of Labour Market Outcomes: Evidence from Uganda, Journal of African Economies 18, no.33 (Oct 2008): 461–495.https://doi.org/10.1093/jae/ejn017Paul Kagundu, Olga Pavlova Gender Wage Differentials in Uganda: Evidence from the Uganda National Household Survey, SSRN Electronic Journal (Jan 2007).https://doi.org/10.2139/ssrn.990013Garth Frazer Learning the master's trade: Apprenticeship and human capital in Ghana, Journal of Development Economics 81, no.22 (Dec 2006): 259–298.https://doi.org/10.1016/j.jdeveco.2005.06.006Lire Ersado Child Labor and Schooling Decisions in Urban and Rural Areas: Comparative Evidence from Nepal, Peru, and Zimbabwe, World Development 33, no.33 (Mar 2005): 455–480.https://doi.org/10.1016/j.worlddev.2004.09.009Peter Glick, David Sahn Intertemporal female labor force behavior in a developing country: what can we learn from a limited panel?, Labour Economics 12, no.11 (Feb 2005): 23–45.https://doi.org/10.1016/j.labeco.2004.03.001Deon Filmer Gender and wealth disparities in schooling: Evidence from 44 countries, International Journal of Educational Research 43, no.66 (Jan 2005): 351–369.https://doi.org/10.1016/j.ijer.2006.06.012Justin van der Sluis, Mirjam van Praag, Wim P.M. Vijverberg Entrepreneurship Selection and Performance: A Meta-analysis of the Impact of Education in Less Developed Countries, SSRN Electronic Journal (Jan 2004).https://doi.org/10.2139/ssrn.625903 Human Capital, Household Welfare, and Children’s Schooling in Mozambique, (Jan 2004).https://doi.org/10.2499/0896291375rr134Ma´ire´ad Dunne, Rudith King Outside Theory: An exploration of the links between education and work for Ghanaian market traders, Journal of Education and Work 16, no.11 (Mar 2003): 27–44.https://doi.org/10.1080/1363908022000032876 G. Reza Arabsheibani and Lamine Manfor From Farashia to Military Uniform: Male‐Female Wage Differentials in Libya G. Reza Arabsheibani and Lamine Manfor, Economic Development and Cultural Change 50, no.44 (Jul 2015): 1007–1019.https://doi.org/10.1086/342847Willem Naudé, Philip Serumaga-Zake An analysis of the determinants of labour force participation and unemployment in South Africa's North-West province, Development Southern Africa 18, no.33 (Sep 2001): 261–278.https://doi.org/10.1080/03768350120041929T. Paul Schultz Chapter 8 Women's roles in the agricultural household: Bargaining and human capital investments, (Jan 2001): 383–456.https://doi.org/10.1016/S1574-0072(01)10011-3Danielle de Lame Genre et développement : bibliographie sélective 1, Bulletin de l’APAD , no.2020 (Dec 2000).https://doi.org/10.4000/apad.257G. Reza Arabsheibani Male–Female Earnings Differentials Among the Highly Educated Egyptians, Education Economics 8, no.22 (Jul 2010): 129–138.https://doi.org/10.1080/096452900410703Peter Glick, David E. Sahn Schooling of girls and boys in a West African country: the effects of parental education, income, and household structure, Economics of Education Review 19, no.11 (Feb 2000): 63–87.https://doi.org/10.1016/S0272-7757(99)00029-1T. Paul Schultz Health and Schooling Investments in Africa, Journal of Economic Perspectives 13, no.33 (Aug 1999): 67–88.https://doi.org/10.1257/jep.13.3.67Kathleen M. Fallon Education and Perceptions of Social Status and Power among Women in Larteh, Ghana, Africa Today 46, no.22 (Apr 1999): 66–91.https://doi.org/10.2979/AFT.1999.46.2.66 Simon Appleton , John Hoddinott , and Pramila Krishnan The Gender Wage Gap in Three African Countries Appleton et al., Economic Development and Cultural Change 47, no.22 (Jul 2015): 289–312.https://doi.org/10.1086/452402Harold Alderman, Elizabeth M. King Gender differences in parental investment in education, Structural Change and Economic Dynamics 9, no.44 (Dec 1998): 453–468.https://doi.org/10.1016/S0954-349X(98)00040-XPeter Glick, David E. Sahn Health and productivity in a heterogeneous urban labour market, Applied Economics 30, no.22 (Oct 2010): 203–216.https://doi.org/10.1080/000368498326001 Bibliographie, (): 423–449.https://doi.org/10.4000/books.irdeditions.9679
openalex: W2027805793 mag: 2027805793
Keywords: openalex:import

Rethinking the Status of Early Childhood Care and Education (ECCE) in Rural and Urban Areas of South Africa - Goduka, Ivy N. (Early Education and Development, 1997)
The purpose of this study was to document the current status of, and to determine the need for, early childhood care and education in South Africa. The study included an assessment of the training needs of child carers and other individuals interested in working with young children in urban and rural areas of the region. A total of 373 African men and women with varied occupations and educational attainment were recruited in the study. A survey methodology was employed to obtain desired information. The study showed that families and communities, who have previously responded to the needs of young children including education, health, and nutrition, could no longer meet these needs because of social and economic dynamics. Training, training centers, infrastructure, and the integration of African culture in early childhood are perceived to be compelling needs. Several recommendations for policy and programs are presented.
openalex: W2015284617 mag: 2015284617
Keywords: openalex:import

Population and Education Prospects in the Western Mediterranean Region (Jordan, Lebanon, Syria, the West Bank and the Gaza Strip) - Goujon, Anne (RePEc: Research Papers in Economics, 1997)
This report studies the demographic and educational futures of Jordan, Lebanon, Syria, the West Bank and the Gaza Strip. These are areas of potential and existing conflicts, where population growth has many political dimensions. The report, however, abstains from discussing these political issues and focuses on future demographic aspects. It is clear that this report could raise some questions on the sensitivity of the region to future population prospects. Assumptions for the population projections are based on the analysis of past and present trends in changes in population growth, age structure, fertility levels and trends, contraceptive use, marriage and child bearing patterns, mortality, migration, education, and enrollment levels. Based on this analysis, three population projection paths - low, central, and high - were designed and lead to three population figures for each area in 2044. Educational levels of the population were judged determinant to the future level of population growth. In all scenarios, the levels of enrollment varied consistently with fertility and mortality assumptions to change the levels of education in the population. Results were then analyzed to provide a demographic picture of the region in 2044. This study provides interesting insights into the demography of these countries, especially with regard to the momentum of population growth and education levels. Jordan and Syria have experienced high rates of population growth in the recent past. In Jordan, these rates have been reinforced by the migration of Palestinian refugees from the West Bank and the Gaza Strip into the country. The first signs (important fertility reductions and gains in life expectancy) of a demographic transition became visible in the late 1980s in the two countries. The population in Jordan and Syria will continue to grow rapidly in the future. The central scenario, which gives the most likely path under current conditions, implies a tripling of the population of Jordan and almost a tripling of the population in Syria. Still these countries have a high potential for lesser population growth. Lebanon will remain a country of low population growth, with the annual growth rate ranging on average from 1.0 to 1.3 percent per year between 1994 and 2044. The most extreme results in terms of population growth are found in the case of the West Bank and the Gaza Strip. Even under the low scenario, which combines very rapid fertility and mortality declines and rapid educational improvements, the West Bank and the Gaza Strip more than quadruple in population size in the fifty years of the projection period due to the high momentum of past population growth. However, all scenarios show substantial declines in the proportion of people with a low education - less than a primary education - even under the most pessimistic assumptions.
openalex: W1532349282 mag: 1532349282
Keywords: openalex:import

Marginality Theory and the African American Student - Grant, G. Kathleen; Breese, Jeffrey R. (Sociology of Education, 1997)
This article reports on a study of African American students at a state university in a midwestern city. Specifically, a qualitative research design was used to explore the subjective college experiences of these students to determine if marginality can offer a more holistic understanding of the larger substantive phenomenon. The study found that it is the construction of meaning attached to marginality, not the state of being marginal, that has significance for understanding the students' experiences
openalex: W1993170215 mag: 1993170215
Keywords: openalex:import

Questions of Race and Culture: How They Relate to the Classroom for African American Students - Graybill, Susan W. (The Clearing House: A Journal of Educational Strategies, Issues and Ideas, 1997)
(1997). Questions of Race and Culture: How They Relate to the Classroom for African American Students. The Clearing House: A Journal of Educational Strategies, Issues and Ideas: Vol. 70, No. 6, pp. 311-318.
openalex: W148962013 mag: 148962013
Keywords: openalex:import

Irony as objectivity: orientations for history teaching in post-apartheid South Africa - Kissack, Mike (Curriculum studies, 1997)
Abstract This article provides an account of Hayden White's claim that historiographical difference can be explained in terms of the varying narrative forms in which historical depictions are presented, rather than in terms of the data or evidence on which historical representation are based. Narrative form is constructed around particular organising categories, which assemble and present the content (data/evidence) of particular historical portrayals, to provide us with knowledge about the past. White's contention is illustrated through its application to the liberal and revisionist schools of South African historiography. White defines irony as a recognition and deployment of the mutable and protean characteristic of any linguistic articulation and representation, historical or otherwise. This paper argues that curriculum developers and history teachers in post-Apartheid South Africa would benefit from the adoption of irony as a concept of objectivity, because this would liberate them from the futile task of ascertaining which school of South African historiography embodies the Truth about South Africa's past. History teaching would consequently embrace the different perspectives, fostering a new understanding of the relationship between historical concepts and historical data, and encouraging an appreciation of how the process of historical representation situates different people in their relationship to their pasts.
openalex: W1971770247 mag: 1971770247
Keywords: openalex:import

Differences in Ego States, Locus of Control, and Dogmatism between African-American and Anglo-American Undergraduate College Students - Loffredo, Donald A.; Omizo, Michael M. (Transactional Analysis Journal, 1997)
This quasi-experimental study attempted to identify possible differences between African-American (n = 40) and Anglo-American (n = 40) undergraduate college students (ages 17 to 27) relative to per...
openalex: W2556009023 mag: 2556009023
Keywords: openalex:import

Oral health status among secondary school students in Harare, Zimbabwe. - Makoni, F.; Frencken, J.E.F.M.; Sithole, W.D. (PubMed, 1997)
In 1993 a demonstration oral care programme to evaluate the ART procedure for dental caries under field conditions began among secondary school students in Greater Harare. The programme was preceded by an oral epidemiological survey. Of the 569 students examined, with a mean age of 13.9 years, 58.7 per cent were caries free. The mean DMFS and DMFT scores were 1.4 and 1.1, respectively. Very few missing and filled teeth were observed. Excluding those with pulp involvement, small dentinal lesions which could not be penetrated with an excavator at the time of examination, constituted 49 per cent of the mean DMFS score. 84 per cent of dentinal lesions needing treatment were judged to be treatable using the ART procedure. Using the index of Green and Vermillion (1964), the mean plaque score was 5.6 with substantial variation observed between the schools. Calculus was observed among 89.5 per cent of the students examined. 18 per cent of them had a central diastema in the maxilla. Crowding or spacing in the upper and lower anterior region of the jaws was observed in 67.5 per cent and 60.5 per cent of the students, respectively. 15.8 per cent were dissatisfied with the position of their teeth whilst 15 per cent indicated that they would like to undergo corrective treatment. It was concluded that these secondary students lack preventive and curative oral care and that the vast majority of the dentinal lesions observed could be treated using the ART procedure.
openalex: W2413103125 mag: 2413103125
Keywords: openalex:import

Family Environmental Correlates of Students’ Affective Characteristics: a South African study - Marjoribanks, Kevin; Mboya, Mzobanzi M. (Educational studies, 1997)
Summary This study examined the relationships between family environmental contexts, sibling structure, immediate family settings and students’ affective characteristics. Data were collected from 460 (234 female and 226 male) South African senior high school students. Using partial least-squares path modelling the findings suggest that environmental contexts and family immediate settings combine to have modest to large concurrent validities in relation to differing measures of students’ affective characteristics, immediate family settings are related more strongly to measures of student affect than are indicators of family environment contexts and there are gender-related differences in how social-status indicators form environmental context constructs and in the nature of the relationships between students’ family environments and their affective characteristics.
openalex: W1982822968 mag: 1982822968
Keywords: openalex:import

Current poverty, structural adjustment, and drought in Zimbabwe - Marquette, Catherine M. (World Development, 1997)
Considering the impact of economic structural adjustment programs (ESAP) on the poor is not straightforward because ESAP involves changes affecting future poverty as well as the currently poor. In addition, structural adjustment measures occur alongside other events which may have additive as well as interactive effects with ESAP. In Zimbabwe, for example, the initial years of ESAP implementation overlapped with the onset of a major drought in 1991–92. Understanding changes affecting the poor during the period thus involves considering both these events. This paper considers the effects which ESAP and the drought had on the poor in Zimbabwe during the initial years of the structural adjustment process from 1990–94. Relevant background information on structural adjustment and drought in Zimbabwe are presented. The effects which ESAP and drought had on three areas critical to the currently poor: (a) health services, (b) employment and wages, and (c) food security are then considered.
openalex: W2081712606 mag: 2081712606
Keywords: openalex:import

Automobile air pollution in Dar es Salaam City, Tanzania - Mbuligwe, Stephen E.; Kassenga, Gabriel (Science of The Total Environment, 1997)
Automobile air pollution is a growing problem in Dar es Salaam, Tanzania and as such it needs immediate attention before it goes out of control. The problem is most pronounced in the city centre especially during rush hours. This paper starts by citing some environmental effects of air pollution. It then analyses the problem of automobile air pollution in Dar es Salaam. It also goes on to show that vehicles in Dar es Salaam whose number is increasing at the rate of 6.3% annually contribute to the problem. Furthermore, the paper reveals that one of the main reasons for the air pollution problem in the city centre is large traffic volume which is concentrated on just 4.4% of the total road length in the city. Another reason identified in this paper is the increase in number and density of high rise buildings which end up hindering pollutant dilution by natural ventilation. A shortage of parking places also contributes to the problem. This paper further reveals that automobile exhaust gas coefficients for nitrogen oxides and carbon monoxide are 10 times those of the USA. This is mainly attributed to low-energy efficiency of engines of most of the cars plying city roads due to old age. Concentrations of nitrogen oxides and carbon monoxide in the exhaust gas are also found to be high. Finally, this paper forwards legal and administrative as well as technical measures to arrest the problem. Enacting and enforcing of special laws pertaining to control and prevention of air pollution are also emphasised along with other measures.
openalex: W2022065779 mag: 2022065779
Keywords: openalex:import

Moderating the Demand for Primary Education in Malawi - Minnis, John R. (International Journal of Educational Reform, 1997)
openalex: W346910924 mag: 346910924
Keywords: openalex:import

Impairment of Neural Nitric Oxide-mediated Relaxation after Antigen Exposure in Guinea Pig Airways in vitro - Miura, M.; Yamauchi, H.; Ichinose, Masakazu; Ohuchi, Yuzuru; Kageyama, Natsuko; Tomaki, Masafumi; Endoh, N; Shirato, Kunio (American Journal of Respiratory and Critical Care Medicine, 1997)
Nitric oxide (NO), a neurotransmitter of inhibitory nonadrenergic noncholinergic (iNANC) nerves in airways, is a radical with a short half-life, and its function may be modified by airway inflammation. To test this hypothesis, we examined whether airway allergic inflammation affects iNANC responses mediated by NO in guinea pigs in vitro. Animals sensitized with ovalbumin (OA) were challenged with 0.03% OA (OA group) or saline (saline group) by inhalation on 3 consecutive days. On the day after the final challenge, iNANC responses elicited by electrical field stimulation (2 to 16 Hz) or relaxation responses to 3-morpholinosydnonimine (SIN-1), 10− 8 to 10− 4 M, were obtained in the tracheal strips precontracted by histamine (3 × 10− 6 M) in the presence of atropine and propranolol (both 10− 6 M). The iNANC responses of the OA group were significantly attenuated compared with those of the saline group (p < 0.05), and the inhibitory effect of a NO synthase (NOS) inhibitor, Nω-nitro-l-arginine methyl ester, on the iNANC responses was abolished in the OA group. SIN-1-induced tracheal smooth muscle relaxation was also significantly affected by antigen exposure (p < 0.05), the effect of which disappeared in the presence of a NO scavenger, carboxy PTIO (3 × 10− 6 M). The impairment of the iNANC responses after antigen exposure was significantly restored by superoxide dismutase (1,000 U/ml), especially at lower frequencies. Histochemical demonstration of NADPH-diaphorase-positive nerves representing neural NOS density was not different between the two groups. These results suggest that allergic airway inflammation impairs neural NO-induced relaxation, presumably by inhibiting the access of neural NO to the airway smooth muscle.
openalex: W2049079234 mag: 2049079234
Keywords: openalex:import

Trends in prevalence and pattern of substance use among secondary school pupils in Ilorin, Nigeria. - Ml, Adelekan; Rj, Ndom (PubMed, 1997)
We present trends data on the prevalence and pattern of substance use among secondary school pupils in Ilorin, derived from comparing the finding of two consecutive cross-sectional surveys. From a sample of six schools, 1041 and 848 pupils 1988 and 1993 respectively, completed anonymously a 117-item WHO self-report substance-use questionnaire. The analyses cover responses on the current and lifetime use of eleven substances, their frequency of use, and the effect of gender and school location on use trends. Although a significant increase in current use rates was recorded for alcohol, cannabis, mild stimulants and hypnosedatives, all of these substances (except stimulants) showed a shift towards less frequent use in 1993. The only consistent gender effect was found for smoking, which remained significantly a male activity. The significant increases found in the current use of cocaine, organic solvents and hallucinogens are difficult to substantiate, thus prompting the suggestion for further corroborative qualitative studies. There was a trend towards greater involvement of the rural school's respondents in substance use in general. The implications of the findings with respect to policy issues on substance-use prevention programmes for youths in the Ilorin metropolis are discussed within the context of the limitations of the study design.
openalex: W2416543321 mag: 2416543321
Keywords: openalex:import

Transient Impaired Glucose Tolerance in South African Indians Does Not Carry a Risk for Progression to NIDDM - Motala, Ayesha A.; Omar, Mahomed Abdool Khalek; Gouws, Eleanor (Diabetes Care, 1997)
OBJECTIVE To evaluate the significance of transient impaired glucose tolerance (IGT) in terms of the risk of progression to NIDDM and the serum insulin response during oral glucose tolerance test (OGTT) in a prospective study on the natural history of IGT in South African Indians. RESEARCH DESIGN AND METHODS This is a report on 87 subjects who formed part of a 4-year prospective study in 128 subjects classified with IGT at baseline (year 0) using World Health Organization criteria for glucose tolerance. Subjects were reexamined at years 1 and 4. At year 1, based on OGTT results, the subjects were divided into three groups: transient IGT (normal glucose tolerance [trIGT], n = 40), persistent IGT (pIGT, n = 47), and diabetes (n = 41). Analysis was performed on the 87 subjects who were classified as IGT at year 0, but who had not progressed to NIDDM by year 1 of the study At baseline (year 0), a modified OGTT was performed; between years 1 and 4, the OGTT included timed midtest samples for plasma glucose and serum insulin. Analysis of predictive factors for progression to diabetes or reversion to normal glucose tolerance was undertaken using year 0 as baseline. RESULTS By year 4, 72 subjects (82.8%) completed the study Of the 32 subjects in the trIGT group, none (0%) had progressed to NIDDM, 11 (34.4%) had reverted to IGT (N-IGT), and 21 (65.6%) had persisted with normal glucose tolerance (N-N); of the 40 subjects in the pIGT group, 16 (40%) had progressed to NIDDM (IGT-D), 17 (42.5%) had persisted with IGT (IGT-IGT), and 7 (17.5%) had reverted to normal glucose tolerance (IGT-N). Significant predictive factors for reversion to normal glucose tolerance included absence of obesity (P = 0.0131, odds ratio [OR] 4.2, 95% CI 1.4–13.1) and 2-h plasma glucose level (P = 0.027, OR 2.4, 95% CI 1.11–5.13) at baseline (year 0). Intergroup (cross-sectional) analysis showed that the serum insulin response was higher in the pIGT than in the trIGT subgroup (fasting serum insulin: IGT-N vs. N-IGT and N-N, 16.9 ± 1.9 vs. 6.8 ± 2.1 and 6.1 ± 2.4 μU/ml, respectively, P < 0.001; 2-h postload serum insulin: IGT-IGT vs. N-IGT, 116.8 ± 2.2 vs. 60.3 ± 1.7 μU/ml, P < 0.05). By contrast, the insulinogenic index was higher in the trIGT subgroups both at year 1 (90-min: N-N vs. IGT-D, 48.9 ± 3.9 vs. 14.1 ± 2.5; P < 0.05) and at year 4 (N-N vs. remaining four subgroups, P < 0.01 at 60 min and 90 min). Intragroup (prospective) comparisons showed that in the N-IGT subgroup, the mean 2-h insulinogenic index was lower at year 4 than at year 1 (19.9 ± 1.7 vs. 66.0 ± 2.7; P < 0.05). CONCLUSIONS In this 4-year prospective study in South African Indians, transient IGT carries no risk of progression to NIDDM. The significant predictive factors for reversion to normal glucose tolerance include lower baseline obesity prevalence and 2-h postload plasma glucose level. Moreover, in this group, β-cell secretory function appeared to deteriorate with worsening of glucose tolerance.
openalex: W2068862741 mag: 2068862741
Keywords: openalex:import

Approaches to Teaching Practice and their Implications for Teacher Education Programmes in Zimbabwe - Moyo, P. (1997)
Several approaches to teaching practice are possible. Much current discussions on the ways and means of improving teacher education is focused on this practical element of teacher preparation. (Stones and Morris, 1972). Some approaches to teaching practice will be examined in this paper. The meaning, impact on colleges of education and schools, merits and demerits and the feasibility for Zimbabwe of these approaches to teaching practice will be examined. It is hoped that the paper will generate discussion among teacher educators and all those interested in teacher education.
openalex: W2303295680 mag: 2303295680
Keywords: openalex:import

The recognition of meteoric-hydrothermal and supergene processes in volcanic carbonatites, Nyanza Rift, western Kenya, using carbon and oxygen isotopes - Onuonga, Isaac Oriechi; Fallick, Anthony E.; Bowden, Peter (Journal of African Earth Sciences, 1997)
Carbon and O isotopic compositions were determined for calcite and siderite from the Buru and Kuge carbonatite centres. Wide ranges in the isotopic compositions of these minerals were observed with values of δ13C and δ18O for the Buru calcites ranging from +1.3 to −3.2% (PDB) and + 11.3 to +26.2% (SMOW), respectively. The δ13C and δ18O ranges for the Kuge calcites are −3.1 to −8.4% (PDB) and +18.1 to + 25.7% (SMOW). The Buru siderites plot in a narrow and restricted range at −3.1 to −4.4% (PDB) and +12.6 to + 16.1% (SMOW). Calcite and siderite from the Buru and Kuge volcanic carbonatite centres do not retain their isotope signatures expected for primary magmatic carbonatites. Most of the variations in CO isotope composition can be attributed to secondary processes involving low-temperature hydrothermal alteration and isotope exchange between carbonatites and meteoric water. Higher δ18O values (+21.9 to +26.2%) with a significant increase in δ13C values (−1.5 to + 1.3%) shown by the most oxidised samples from the Buru carbonatite may indicate the involvement of supergene exchange with atmospheric CO2 at surface temperatures. Les compositions isotopiques du C et de l'O ont été déterminées pour la calcite et la sidérite des massifs de carbonatite de Buru et de Kuge. De larges écarts ont été observés. Les δ13C et δ18O des calcites vont à Buru de 1.3 à 3.2% (PDB) et de +11.3 à +26.2% (SMOW) respectivement, et à Kuge de −3.1 à −8.4% (PDB) et de +18.1 à 25.7% (SMOW). Les valeurs des sidérites de Buru se situent dans une gamme étroite allant de −3.1 à −4.4% (PDB) et de +12.6 à 16.1% (SMOW). Les compositions isotopiques du C et de l'O des carbonatites de Buru et de Kuge n'ont pas la signature isotopique attendue pour des carbonatites magmatiques primaires. La plupart des variations de composition isotopique peuvent être attribuées à des processus secondaires impliquant une altération hydrothermale de basse température et un échange isotopique entre les carbonatites et l'eau météorique. Les valeurs plus élevées de δ18O (+21.9 à + 26.2%) s'accompagnant d'un accroissement significatif des valeurs de δ13C (−1.5 à + 1.3%) présentées par les échantillons les plus oxydés de la carbonatite de Buru peuvent indiquer l'implication d'échange supergène avec le CO2 atmosphérique aux températures de surface.
openalex: W2053897506 mag: 2053897506
Keywords: openalex:import

SEXUAL ACTIVITY AMONG JUNIOR SECONDARY SCHOOL GIRLS IN ZAMBIA - Pillai, Vijayan K.; Barton, Thomas R.; Benefo, Kofi D. (Journal of Biosocial Science, 1997)
This paper proposes a causal model of sexual activity among a randomly selected sample of 305 Junior secondary school girls in Zambia. The results indicate that liberal sexual attitudes influence romantic involvement with boys. Emotional involvement is likely to result in sexual activity. Traditional courtship forms are slowly being replaced by modern patterns of courtship behaviour. Policy and programme implications are discussed.
openalex: W2122328752 mag: 2122328752
Keywords: openalex:import

Outcome of African American Men Screened for Prostate Cancer: The Detroit Education and Early Detection Study - Powell, Isaac J.; Heilbrun, Lance K.; Littrup, Peter; Franklin, Archilind; Parzuchowski, Jean; Gelfand, Donald E.; Sakr, Wael (The Journal of Urology, 1997)
Will early detection impact on stage of disease and recurrence of prostate cancer in a high risk population? We initiated a community based study to educate and recruit African American men for early diagnosis of prostate cancer, that is the Detroit Education and Early Detection (DEED) study. Our objective was to evaluate our recruitment process for this target population, examine the percentage of organ confined prostate cancer in men undergoing radical prostatectomy and measure recurrence biochemically.A community based study from February 1993 to February 1995 through the African American churches in metropolitan Detroit was initiated. We compared the early detection group treated with radical prostatectomy to the population presenting to our urological clinic during the same period. We tested and followed 1,105 African American men using the prostate specific antigen blood test.Pathologically organ confined prostate cancer was diagnosed in 11 of 17 men (65%) who underwent radical prostatectomy in the DEED project. Within the clinic population 35% of the African American men were diagnosed with pathologically organ confined prostate cancer. The difference between the 2 populations was statistically significant (p = 0.033). Disease recurred in 1 of 15 (7%) and 39 of 157 (25%) men in the DEED and clinic populations, respectively (p = 0.97).We demonstrated our ability to recruit African American men into a prostate cancer early detection program. We diagnosed early but clinically significant prostate cancers among African American men with characteristics similar to prostate cancers diagnosed in other early detection studies in which the overwhelming majority of men were white.
openalex: W2061243220 mag: 2061243220
Keywords: openalex:import

Response of serum leptin concentrations to 7 d of energy restriction in centrally obese African Americans with impaired or diabetic glucose tolerance - Racette, Susan B.; Kohrt, Wendy M.; Landt, Michael; Holloszy, John O. (The American journal of clinical nutrition, 1997)
The aim of this study was to determine whether serum leptin concentrations are reduced in response to short-term energy restriction in centrally obese individuals with impaired glucose tolerance or non-insulin-dependent diabetes mellitus. Twenty African Americans [16 females and 4 males, 44 +/- 7 y (x +/- SD), 107.2 +/- 23.8 kg, 39 +/- 7% body fat] consumed a 7-d energy-restricted diet (4.03 +/- 0.72 MJ/d) of whole foods. Oral-glucose-tolerance tests (OGTTs) were performed before and immediately after the diet to assess changes in serum leptin, glucose, and insulin concentrations. Baseline leptin concentration correlated significantly with percentage body fat (r = 0.80), body mass index (r = 0.72), fat mass (4 = 0.64), waist-height ratio (r = 0.6), body weight (r = 0.59, all P < 0.01), waist circumference (r = 0.49), and basal insulin concentration (r = 0.48, both P < 0.05). Seven days of energy restriction resulted in significant reductions (P < 0.005) in leptin (-6.1 +/- 8.4 micrograms/L), basal glucose (-0.9 +/- 0.8 mmol/L), OGTT glucose area under the curve (-158 +/- 164 mmol/L), and basal insulin concentration (-34 +/- 69 pmol/L, P < 0.05). In addition, there was a trend for a reduction in OGTT insulin area under the curve (-15,567 +/- 3,658 pmol/L, P = 0.05), and a tendency for basal insulin and leptin to change together (r = 0.41, P = 0.07). Despite the weight loss of 3.1 +/- 1.3 kg (P < 0.0001), the loss of fat mass was calculated to be only -1.0 +/- 0.1 kg. These results suggest that negative energy balance or improved insulin action was responsible for the changes in leptin, glucose, and insulin concentrations. In summary, short-term energy restriction effectively reduced serum leptin concentrations and improved glucose tolerance and insulin action in obese individuals with impaired or diabetic glucose tolerance.
openalex: W2338527510 mag: 2338527510
Keywords: openalex:import

A basic education programme in Africa: The people's own? - Robinson, Clinton; Gfeller, Elisabeth (International Journal of Educational Development, 1997)
This paper examines the issue of community ownership with reference to an adult literacy and basic education programme in NW Zaire. After a discussion of community ownership, stressing the need for local control and relevance to local needs, it outlines the context and development of the programme in NW Zaïre and considers the degree to which ownership is manifested in the design of technical aspects of the programme and its structures. Finally it identifies some key issues for continued progress, particularly the shape of partnerships between external agencies and strengthened local structures.
openalex: W2025642683 mag: 2025642683
Keywords: openalex:import

Knowledge Base and Reflective Practice in Teacher Education in Zimbabwe: Curriculum Continuity or Ideological Confusion? - Shumba, Overson (1997)
This is a contribution and critique of the debate initiated by Dzvimbo's (1991) article on the nature of knowledge and discourse practices in Zimbabwe's teacher training colleges (Zimbabwe Bulletin of Teacher Education, Volume 1, Issue 1). Dzvimbo's paper is important in that it underscores the importance of teacher education to educational and social reform. That teacher education is significant is obviated by the fact that in many countries in the Third World, schools, classrooms and teachers are among the most important determinants of pupil learning and achievement often more significant than socio-economic status (Riddell, 1989). While thebasic thesis of the Dzvimbo paper that discourse and reflective action are necessary for professional growth in teacher education is supported, certain substantive assumptions in the paper are controversial. This paper is an attempt to highlight some of the substantive aspects afflicting the potential for professional growth in teacher education. It proposes that ideological confusion as well as historical precedent rather than simple curriculum continuity are the chief determinants of the present status of teacher education. The assumption of ideological consciousness transferring, inducing or supporting professional growth is not supported.
openalex: W1928717402 mag: 1928717402
Keywords: openalex:import

Schooling Attainment, Parental Education, and Gender in Côte d'Ivoire and Ghana - Tansel, Aysıt (Economic Development and Cultural Change, 1997)
Previous articleNext article No AccessSchooling Attainment, Parental Education, and Gender in Côte d'Ivoire and GhanaAysit Tansel Aysit TanselMiddle East Technical University, Ankara, and Yale University Search for more articles by this author Middle East Technical University, Ankara, and Yale UniversityPDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Economic Development and Cultural Change Volume 45, Number 4July 1997 Article DOIhttps://doi.org/10.1086/452309 Views: 278Total views on this site Citations: 58Citations are reported from Crossref © 1997 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Adebayo Mohammed Ojuolape, Saidatulakmal Mohd Dataset of Child schooling/ Out-of-school children in households in Kwara State, Nigeria, Data in Brief 45 (Dec 2022): 108654.https://doi.org/10.1016/j.dib.2022.108654Mafaizath Fatoké Dato Medium-Term Impact of the Elimination of School Fees on Girls’ Education in Benin, West Africa, Economic Development and Cultural Change 71, no.11 (Aug 2022): 261–294.https://doi.org/10.1086/714064Clifford Afoakwah, Isaac Koomson How does school travel time impact children’s learning outcomes in a developing country?, Review of Economics of the Household 19, no.44 (Jan 2021): 1077–1097.https://doi.org/10.1007/s11150-020-09533-8Anjan Ray Chaudhury, Madhabendra Sinha Gradual Disappearance of Gender Disparity in Human Capital Accumulation: Evidence from India, Journal of Asian and African Studies 55, no.88 (Mar 2020): 1108–1127.https://doi.org/10.1177/0021909620909492Clifford Afoakwah, Xin Deng, Ilke Onur Women’s Bargaining Power and Children’s Schooling Outcomes: Evidence From Ghana, Feminist Economics 26, no.33 (Feb 2020): 1–29.https://doi.org/10.1080/13545701.2019.1707847Catalina Herrera Almanza, David E. Sahn Childhood determinants of internal youth migration in Senegal, Demographic Research 43 (Nov 2020): 1335–1366.https://doi.org/10.4054/DemRes.2020.43.45Phillip Haynes The impact of home-based educational multi-correlates on academic achievement: an analysis of gender discrepancies in Rwanda, International Journal of Inclusive Education 24, no.55 (Apr 2018): 561–577.https://doi.org/10.1080/13603116.2018.1466929Glenn P. Jenkins, Hope Amala Anyabolu, Pejman Bahramian Family decision-making for educational expenditure: new evidence from survey data for Nigeria, Applied Economics 51, no.5252 (May 2019): 5663–5673.https://doi.org/10.1080/00036846.2019.1616075Akanksha Choudhary, Ashish Singh Do Indian daughters shadow their mothers?, International Journal of Social Economics 46, no.99 (Aug 2019): 1095–1118.https://doi.org/10.1108/IJSE-10-2018-0499Charlotte Janssens, Goedele Van den Broeck, Miet Maertens, Isabel Lambrecht What if mothers are entrepreneurs? Non-farm businesses and child schooling in rural Ghana, Journal of Rural Studies 66 (Feb 2019): 95–103.https://doi.org/10.1016/j.jrurstud.2019.01.004Akanksha Choudhary, Ashish Singh, Vijayaprasad Gopichandran Effect of intergenerational educational mobility on health of Indian women, PLOS ONE 13, no.99 (Sep 2018): e0203633.https://doi.org/10.1371/journal.pone.0203633Paola Ballón, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, Journal of African Economies 27, no.44 (Mar 2018): 483–512.https://doi.org/10.1093/jae/ejy001Shaleen Khanal Gender Discrimination in Education Expenditure in Nepal: Evidence from Living Standards Surveys, Asian Development Review 35, no.11 (Mar 2018): 155–174.https://doi.org/10.1162/adev_a_00109 References, (Jan 2018): 307–468.https://doi.org/10.1016/B978-0-12-805371-3.16001-7Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, SSRN Electronic Journal (Jan 2018).https://doi.org/10.2139/ssrn.3175368Long Thanh Giang, Cuong Viet Nguyen, Tuyen Quang Tran, Vu Thieu Does Firm Agglomeration Matter to Labor and Education of Local Children? Evidence in Vietnam, Child Indicators Research 10, no.44 (Aug 2016): 1015–1041.https://doi.org/10.1007/s12187-016-9409-8Akanksha Choudhary, Ashish Singh Are Daughters Like Mothers: Evidence on Intergenerational Educational Mobility Among Young Females in India, Social Indicators Research 133, no.22 (Jun 2016): 601–621.https://doi.org/10.1007/s11205-016-1380-8Abdul Malik Iddrisu, Michael Danquah, Peter Quartey Paying for education among households in Ghana, International Journal of Development Issues 16, no.22 (Jul 2017): 214–226.https://doi.org/10.1108/IJDI-02-2017-0017Tesfaye Alemayehu Gebremedhin, Itismita Mohanty, Jacobus P. van Wouwe Child Schooling in Ethiopia: The Role of Maternal Autonomy, PLOS ONE 11, no.1212 (Dec 2016): e0167639.https://doi.org/10.1371/journal.pone.0167639Alberto Posso, Simon Feeny Beyond enrolments: the determinants of primary-school attendance in Melanesia, Journal of the Asia Pacific Economy 21, no.44 (Mar 2016): 531–548.https://doi.org/10.1080/13547860.2016.1153205Sharon Wolf, Dana C McCoy, Erin B Godfrey Barriers to school attendance and gender inequality: Empirical evidence from a sample of Ghanaian schoolchildren, Research in Comparative and International Education 11, no.22 (Jun 2016): 178–193.https://doi.org/10.1177/1745499916632424Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Monetary and Multidimensional Child Poverty: Why They Differ, SSRN Electronic Journal (Jan 2016).https://doi.org/10.2139/ssrn.3164307Gina A.N. Chowa, Rainier D. Masa, Yalitza Ramos, David Ansong How do student and school characteristics influence youth academic achievement in Ghana? A hierarchical linear modeling of Ghana YouthSave baseline data, International Journal of Educational Development 45 (Nov 2015): 129–140.https://doi.org/10.1016/j.ijedudev.2015.09.009KAKOLI BORKOTOKY, SAYEED UNISA FEMALE EDUCATION AND ITS ASSOCIATION WITH CHANGES IN SOCIO-DEMOGRAPHIC BEHAVIOUR: EVIDENCE FROM INDIA, Journal of Biosocial Science 47, no.55 (Oct 2014): 687–706.https://doi.org/10.1017/S002193201400039XJane Arnold Lincove Improving Identification of Demand-Side Obstacles to Schooling: Findings from Revealed and Stated Preference Models in Two SSA Countries, World Development 66 (Feb 2015): 69–83.https://doi.org/10.1016/j.worlddev.2014.07.018Juan Yang, Terry SICULAR, Desheng LAI The changing determinants of high school attainment in rural China, China Economic Review 30 (Sep 2014): 551–566.https://doi.org/10.1016/j.chieco.2013.10.001Miet Maertens, Ellen Verhofstadt Horticultural exports, female wage employment and primary school enrolment: Theory and evidence from Senegal, Food Policy 43 (Dec 2013): 118–131.https://doi.org/10.1016/j.foodpol.2013.07.006Ashish Singh, Sarthak Gaurav, Upasak Das Household Headship and Academic Skills of Indian Children: A Special Focus on Gender Disparities, European Journal of Population / Revue européenne de Démographie 29, no.44 (Apr 2013): 445–466.https://doi.org/10.1007/s10680-013-9288-3S. Mani, J. Hoddinott, J. Strauss Determinants of Schooling: Empirical Evidence from Rural Ethiopia, Journal of African Economies 22, no.55 (May 2013): 693–731.https://doi.org/10.1093/jae/ejt007Daniel Mont, Cuong Nguyen Does Parental Disability Matter to Child Education? Evidence from Vietnam, World Development 48 (Aug 2013): 88–107.https://doi.org/10.1016/j.worlddev.2013.04.001Anders Breidlid, Halldis Breidlid Women in South Sudan, (Jan 2013): 99–115.https://doi.org/10.1007/978-94-6209-137-5_7Jane Arnold Lincove The influence of price on school enrollment under Uganda's policy of free primary education, Economics of Education Review 31, no.55 (Oct 2012): 799–811.https://doi.org/10.1016/j.econedurev.2012.04.007Manisha Chakrabarty, Sumon Kumar Bhaumik Whither human capital? The woeful tale of transition to tertiary education in India, Applied Economics Letters 19, no.99 (Jun 2012): 835–838.https://doi.org/10.1080/13504851.2011.607109Michèle Smith, Angeline M. Barrett Capabilities for learning to read: An investigation of social and economic effects for Grade 6 learners in Southern and East Africa, International Journal of Educational Development 31, no.11 (Jan 2011): 23–36.https://doi.org/10.1016/j.ijedudev.2010.06.006Jane Arnold Lincove Determinants of schooling for boys and girls in Nigeria under a policy of free primary education, Economics of Education Review 28, no.44 (Aug 2009): 474–484.https://doi.org/10.1016/j.econedurev.2008.10.001Subha Mani, John Hoddinott, John Strauss Determinants of Schooling Outcomes: Empirical Evidence from Rural Ethiopia, SSRN Electronic Journal (Jan 2009).https://doi.org/10.2139/ssrn.1508898Theresa Tuwor, Marie‐Antoinette Sossou Gender discrimination and education in West Africa: strategies for maintaining girls in school, International Journal of Inclusive Education 12, no.44 (Jul 2008): 363–379.https://doi.org/10.1080/13603110601183115H.-A. Dang, F. H. Rogers The Growing Phenomenon of Private Tutoring: Does It Deepen Human Capital, Widen Inequalities, or Waste Resources?, The World Bank Research Observer 23, no.22 (May 2008): 161–200.https://doi.org/10.1093/wbro/lkn004Tassew Woldehanna, Nicola Jones, Bekele Tefera The Invisibility of Children's Paid and Unpaid Work, Childhood 15, no.22 (May 2008): 177–201.https://doi.org/10.1177/0907568207088421Peter Glick Policy Impacts on Schooling Gender Gaps in Developing Countries: The Evidence and a Framework for Interpretation, SSRN Electronic Journal (Jan 2008).https://doi.org/10.2139/ssrn.891256jane kabubo-mariara, domisiano k. mwabu DETERMINANTS OF SCHOOL ENROLMENT AND EDUCATION ATTAINMENT: EMPIRICAL EVIDENCE FROM KENYA, The South African Journal of Economics 75, no.33 (Sep 2007): 572–593.https://doi.org/10.1111/j.1813-6982.2007.00138.xPeter F. Orazem, Elizabeth M. King Chapter 55 Schooling in Developing Countries: The Roles of Supply, Demand and Government Policy, (Jan 2007): 3475–3559.https://doi.org/10.1016/S1573-4471(07)04055-7Anastasia Gage The Interrelationship between Fosterage, Schooling, and Children’s Labor Force Participation in Ghana, Population Research and Policy Review 24, no.55 (Oct 2005): 431–466.https://doi.org/10.1007/s11113-005-4290-zSilvia Pasqua Gender Bias in Parental Investments in Children’s Education: A Theoretical Analysis, Review of Economics of the Household 3, no.33 (Sep 2005): 291–314.https://doi.org/10.1007/s11150-005-3459-xKofi D. Benefo Child schooling and contraceptive use in rural Africa: A Ghanaian case study, Population Research and Policy Review 24, no.11 (Jan 2005): 1–25.https://doi.org/10.1007/s11113-005-8986-xT. Paul Schultz School subsidies for the poor: evaluating the Mexican Progresa poverty program, Journal of Development Economics 74, no.11 (Jun 2004): 199–250.https://doi.org/10.1016/j.jdeveco.2003.12.009Peter Glick, Rumki Saha, Stephen D. Younger Integrating Gender into Benefit Incidence and Demand Analysis, SSRN Electronic Journal (Jan 2004).https://doi.org/10.2139/ssrn.590822 Human Capital, Household Welfare, and Children’s Schooling in Mozambique, (Jan 2004).https://doi.org/10.2499/0896291375rr134Jessica Holmes Measuring the determinants of school completion in Pakistan: analysis of censoring and selection bias, Economics of Education Review 22, no.33 (Jun 2003): 249–264.https://doi.org/10.1016/S0272-7757(02)00024-9 Esther Redmount Cyclical Patterns in School Attrition and Attendance: A Study in the Labor‐Market Behavior of Children Esther Redmount, Economic Development and Cultural Change 51, no.11 (Jul 2015): 135–160.https://doi.org/10.1086/344629Aysit Tansel Determinants of school attainment of boys and girls in Turkey: individual, household and community factors, Economics of Education Review 21, no.55 (Oct 2002): 455–470.https://doi.org/10.1016/S0272-7757(01)00028-0T Paul Schultz Why Governments Should Invest More to Educate Girls, World Development 30, no.22 (Feb 2002): 207–225.https://doi.org/10.1016/S0305-750X(01)00107-3Katharina Michaelowa Primary Education Quality in Francophone Sub-Saharan Africa: Determinants of Learning Achievement and Efficiency Considerations, World Development 29, no.1010 (Oct 2001): 1699–1716.https://doi.org/10.1016/S0305-750X(01)00061-4T. Paul Schultz Chapter 8 Women's roles in the agricultural household: Bargaining and human capital investments, (Jan 2001): 383–456.https://doi.org/10.1016/S1574-0072(01)10011-3Danielle de Lame Genre et développement : bibliographie sélective 1, Bulletin de l’APAD , no.2020 (Dec 2000).https://doi.org/10.4000/apad.257Peter Glick, David E. Sahn Schooling of girls and boys in a West African country: the effects of parental education, income, and household structure, Economics of Education Review 19, no.11 (Feb 2000): 63–87.https://doi.org/10.1016/S0272-7757(99)00029-1T. Paul Schultz Health and Schooling Investments in Africa, Journal of Economic Perspectives 13, no.33 (Aug 1999): 67–88.https://doi.org/10.1257/jep.13.3.67Kathleen M. Fallon Education and Perceptions of Social Status and Power among Women in Larteh, Ghana, Africa Today 46, no.22 (Apr 1999): 66–91.https://doi.org/10.2979/AFT.1999.46.2.66
openalex: W2089314510 mag: 2089314510
Keywords: openalex:import

Schooling Attainment, Parental Education, and Gender in Côte d'Ivoire and Ghana - Tansel, Aysıt (Economic Development and Cultural Change, 1997)
Previous articleNext article No AccessSchooling Attainment, Parental Education, and Gender in Côte d'Ivoire and GhanaAysit Tansel Aysit TanselMiddle East Technical University, Ankara, and Yale University Search for more articles by this author Middle East Technical University, Ankara, and Yale UniversityPDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Economic Development and Cultural Change Volume 45, Number 4July 1997 Article DOIhttps://doi.org/10.1086/452309 Views: 278Total views on this site Citations: 58Citations are reported from Crossref © 1997 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Adebayo Mohammed Ojuolape, Saidatulakmal Mohd Dataset of Child schooling/ Out-of-school children in households in Kwara State, Nigeria, Data in Brief 45 (Dec 2022): 108654.https://doi.org/10.1016/j.dib.2022.108654Mafaizath Fatoké Dato Medium-Term Impact of the Elimination of School Fees on Girls’ Education in Benin, West Africa, Economic Development and Cultural Change 71, no.11 (Aug 2022): 261–294.https://doi.org/10.1086/714064Clifford Afoakwah, Isaac Koomson How does school travel time impact children’s learning outcomes in a developing country?, Review of Economics of the Household 19, no.44 (Jan 2021): 1077–1097.https://doi.org/10.1007/s11150-020-09533-8Anjan Ray Chaudhury, Madhabendra Sinha Gradual Disappearance of Gender Disparity in Human Capital Accumulation: Evidence from India, Journal of Asian and African Studies 55, no.88 (Mar 2020): 1108–1127.https://doi.org/10.1177/0021909620909492Clifford Afoakwah, Xin Deng, Ilke Onur Women’s Bargaining Power and Children’s Schooling Outcomes: Evidence From Ghana, Feminist Economics 26, no.33 (Feb 2020): 1–29.https://doi.org/10.1080/13545701.2019.1707847Catalina Herrera Almanza, David E. Sahn Childhood determinants of internal youth migration in Senegal, Demographic Research 43 (Nov 2020): 1335–1366.https://doi.org/10.4054/DemRes.2020.43.45Phillip Haynes The impact of home-based educational multi-correlates on academic achievement: an analysis of gender discrepancies in Rwanda, International Journal of Inclusive Education 24, no.55 (Apr 2018): 561–577.https://doi.org/10.1080/13603116.2018.1466929Glenn P. Jenkins, Hope Amala Anyabolu, Pejman Bahramian Family decision-making for educational expenditure: new evidence from survey data for Nigeria, Applied Economics 51, no.5252 (May 2019): 5663–5673.https://doi.org/10.1080/00036846.2019.1616075Akanksha Choudhary, Ashish Singh Do Indian daughters shadow their mothers?, International Journal of Social Economics 46, no.99 (Aug 2019): 1095–1118.https://doi.org/10.1108/IJSE-10-2018-0499Charlotte Janssens, Goedele Van den Broeck, Miet Maertens, Isabel Lambrecht What if mothers are entrepreneurs? Non-farm businesses and child schooling in rural Ghana, Journal of Rural Studies 66 (Feb 2019): 95–103.https://doi.org/10.1016/j.jrurstud.2019.01.004Akanksha Choudhary, Ashish Singh, Vijayaprasad Gopichandran Effect of intergenerational educational mobility on health of Indian women, PLOS ONE 13, no.99 (Sep 2018): e0203633.https://doi.org/10.1371/journal.pone.0203633Paola Ballón, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, Journal of African Economies 27, no.44 (Mar 2018): 483–512.https://doi.org/10.1093/jae/ejy001Shaleen Khanal Gender Discrimination in Education Expenditure in Nepal: Evidence from Living Standards Surveys, Asian Development Review 35, no.11 (Mar 2018): 155–174.https://doi.org/10.1162/adev_a_00109 References, (Jan 2018): 307–468.https://doi.org/10.1016/B978-0-12-805371-3.16001-7Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, SSRN Electronic Journal (Jan 2018).https://doi.org/10.2139/ssrn.3175368Long Thanh Giang, Cuong Viet Nguyen, Tuyen Quang Tran, Vu Thieu Does Firm Agglomeration Matter to Labor and Education of Local Children? Evidence in Vietnam, Child Indicators Research 10, no.44 (Aug 2016): 1015–1041.https://doi.org/10.1007/s12187-016-9409-8Akanksha Choudhary, Ashish Singh Are Daughters Like Mothers: Evidence on Intergenerational Educational Mobility Among Young Females in India, Social Indicators Research 133, no.22 (Jun 2016): 601–621.https://doi.org/10.1007/s11205-016-1380-8Abdul Malik Iddrisu, Michael Danquah, Peter Quartey Paying for education among households in Ghana, International Journal of Development Issues 16, no.22 (Jul 2017): 214–226.https://doi.org/10.1108/IJDI-02-2017-0017Tesfaye Alemayehu Gebremedhin, Itismita Mohanty, Jacobus P. van Wouwe Child Schooling in Ethiopia: The Role of Maternal Autonomy, PLOS ONE 11, no.1212 (Dec 2016): e0167639.https://doi.org/10.1371/journal.pone.0167639Alberto Posso, Simon Feeny Beyond enrolments: the determinants of primary-school attendance in Melanesia, Journal of the Asia Pacific Economy 21, no.44 (Mar 2016): 531–548.https://doi.org/10.1080/13547860.2016.1153205Sharon Wolf, Dana C McCoy, Erin B Godfrey Barriers to school attendance and gender inequality: Empirical evidence from a sample of Ghanaian schoolchildren, Research in Comparative and International Education 11, no.22 (Jun 2016): 178–193.https://doi.org/10.1177/1745499916632424Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Monetary and Multidimensional Child Poverty: Why They Differ, SSRN Electronic Journal (Jan 2016).https://doi.org/10.2139/ssrn.3164307Gina A.N. Chowa, Rainier D. Masa, Yalitza Ramos, David Ansong How do student and school characteristics influence youth academic achievement in Ghana? A hierarchical linear modeling of Ghana YouthSave baseline data, International Journal of Educational Development 45 (Nov 2015): 129–140.https://doi.org/10.1016/j.ijedudev.2015.09.009KAKOLI BORKOTOKY, SAYEED UNISA FEMALE EDUCATION AND ITS ASSOCIATION WITH CHANGES IN SOCIO-DEMOGRAPHIC BEHAVIOUR: EVIDENCE FROM INDIA, Journal of Biosocial Science 47, no.55 (Oct 2014): 687–706.https://doi.org/10.1017/S002193201400039XJane Arnold Lincove Improving Identification of Demand-Side Obstacles to Schooling: Findings from Revealed and Stated Preference Models in Two SSA Countries, World Development 66 (Feb 2015): 69–83.https://doi.org/10.1016/j.worlddev.2014.07.018Juan Yang, Terry SICULAR, Desheng LAI The changing determinants of high school attainment in rural China, China Economic Review 30 (Sep 2014): 551–566.https://doi.org/10.1016/j.chieco.2013.10.001Miet Maertens, Ellen Verhofstadt Horticultural exports, female wage employment and primary school enrolment: Theory and evidence from Senegal, Food Policy 43 (Dec 2013): 118–131.https://doi.org/10.1016/j.foodpol.2013.07.006Ashish Singh, Sarthak Gaurav, Upasak Das Household Headship and Academic Skills of Indian Children: A Special Focus on Gender Disparities, European Journal of Population / Revue européenne de Démographie 29, no.44 (Apr 2013): 445–466.https://doi.org/10.1007/s10680-013-9288-3S. Mani, J. Hoddinott, J. Strauss Determinants of Schooling: Empirical Evidence from Rural Ethiopia, Journal of African Economies 22, no.55 (May 2013): 693–731.https://doi.org/10.1093/jae/ejt007Daniel Mont, Cuong Nguyen Does Parental Disability Matter to Child Education? Evidence from Vietnam, World Development 48 (Aug 2013): 88–107.https://doi.org/10.1016/j.worlddev.2013.04.001Anders Breidlid, Halldis Breidlid Women in South Sudan, (Jan 2013): 99–115.https://doi.org/10.1007/978-94-6209-137-5_7Jane Arnold Lincove The influence of price on school enrollment under Uganda's policy of free primary education, Economics of Education Review 31, no.55 (Oct 2012): 799–811.https://doi.org/10.1016/j.econedurev.2012.04.007Manisha Chakrabarty, Sumon Kumar Bhaumik Whither human capital? The woeful tale of transition to tertiary education in India, Applied Economics Letters 19, no.99 (Jun 2012): 835–838.https://doi.org/10.1080/13504851.2011.607109Michèle Smith, Angeline M. Barrett Capabilities for learning to read: An investigation of social and economic effects for Grade 6 learners in Southern and East Africa, International Journal of Educational Development 31, no.11 (Jan 2011): 23–36.https://doi.org/10.1016/j.ijedudev.2010.06.006Jane Arnold Lincove Determinants of schooling for boys and girls in Nigeria under a policy of free primary education, Economics of Education Review 28, no.44 (Aug 2009): 474–484.https://doi.org/10.1016/j.econedurev.2008.10.001Subha Mani, John Hoddinott, John Strauss Determinants of Schooling Outcomes: Empirical Evidence from Rural Ethiopia, SSRN Electronic Journal (Jan 2009).https://doi.org/10.2139/ssrn.1508898Theresa Tuwor, Marie‐Antoinette Sossou Gender discrimination and education in West Africa: strategies for maintaining girls in school, International Journal of Inclusive Education 12, no.44 (Jul 2008): 363–379.https://doi.org/10.1080/13603110601183115H.-A. Dang, F. H. Rogers The Growing Phenomenon of Private Tutoring: Does It Deepen Human Capital, Widen Inequalities, or Waste Resources?, The World Bank Research Observer 23, no.22 (May 2008): 161–200.https://doi.org/10.1093/wbro/lkn004Tassew Woldehanna, Nicola Jones, Bekele Tefera The Invisibility of Children's Paid and Unpaid Work, Childhood 15, no.22 (May 2008): 177–201.https://doi.org/10.1177/0907568207088421Peter Glick Policy Impacts on Schooling Gender Gaps in Developing Countries: The Evidence and a Framework for Interpretation, SSRN Electronic Journal (Jan 2008).https://doi.org/10.2139/ssrn.891256jane kabubo-mariara, domisiano k. mwabu DETERMINANTS OF SCHOOL ENROLMENT AND EDUCATION ATTAINMENT: EMPIRICAL EVIDENCE FROM KENYA, The South African Journal of Economics 75, no.33 (Sep 2007): 572–593.https://doi.org/10.1111/j.1813-6982.2007.00138.xPeter F. Orazem, Elizabeth M. King Chapter 55 Schooling in Developing Countries: The Roles of Supply, Demand and Government Policy, (Jan 2007): 3475–3559.https://doi.org/10.1016/S1573-4471(07)04055-7Anastasia Gage The Interrelationship between Fosterage, Schooling, and Children’s Labor Force Participation in Ghana, Population Research and Policy Review 24, no.55 (Oct 2005): 431–466.https://doi.org/10.1007/s11113-005-4290-zSilvia Pasqua Gender Bias in Parental Investments in Children’s Education: A Theoretical Analysis, Review of Economics of the Household 3, no.33 (Sep 2005): 291–314.https://doi.org/10.1007/s11150-005-3459-xKofi D. Benefo Child schooling and contraceptive use in rural Africa: A Ghanaian case study, Population Research and Policy Review 24, no.11 (Jan 2005): 1–25.https://doi.org/10.1007/s11113-005-8986-xT. Paul Schultz School subsidies for the poor: evaluating the Mexican Progresa poverty program, Journal of Development Economics 74, no.11 (Jun 2004): 199–250.https://doi.org/10.1016/j.jdeveco.2003.12.009Peter Glick, Rumki Saha, Stephen D. Younger Integrating Gender into Benefit Incidence and Demand Analysis, SSRN Electronic Journal (Jan 2004).https://doi.org/10.2139/ssrn.590822 Human Capital, Household Welfare, and Children’s Schooling in Mozambique, (Jan 2004).https://doi.org/10.2499/0896291375rr134Jessica Holmes Measuring the determinants of school completion in Pakistan: analysis of censoring and selection bias, Economics of Education Review 22, no.33 (Jun 2003): 249–264.https://doi.org/10.1016/S0272-7757(02)00024-9 Esther Redmount Cyclical Patterns in School Attrition and Attendance: A Study in the Labor‐Market Behavior of Children Esther Redmount, Economic Development and Cultural Change 51, no.11 (Jul 2015): 135–160.https://doi.org/10.1086/344629Aysit Tansel Determinants of school attainment of boys and girls in Turkey: individual, household and community factors, Economics of Education Review 21, no.55 (Oct 2002): 455–470.https://doi.org/10.1016/S0272-7757(01)00028-0T Paul Schultz Why Governments Should Invest More to Educate Girls, World Development 30, no.22 (Feb 2002): 207–225.https://doi.org/10.1016/S0305-750X(01)00107-3Katharina Michaelowa Primary Education Quality in Francophone Sub-Saharan Africa: Determinants of Learning Achievement and Efficiency Considerations, World Development 29, no.1010 (Oct 2001): 1699–1716.https://doi.org/10.1016/S0305-750X(01)00061-4T. Paul Schultz Chapter 8 Women's roles in the agricultural household: Bargaining and human capital investments, (Jan 2001): 383–456.https://doi.org/10.1016/S1574-0072(01)10011-3Danielle de Lame Genre et développement : bibliographie sélective 1, Bulletin de l’APAD , no.2020 (Dec 2000).https://doi.org/10.4000/apad.257Peter Glick, David E. Sahn Schooling of girls and boys in a West African country: the effects of parental education, income, and household structure, Economics of Education Review 19, no.11 (Feb 2000): 63–87.https://doi.org/10.1016/S0272-7757(99)00029-1T. Paul Schultz Health and Schooling Investments in Africa, Journal of Economic Perspectives 13, no.33 (Aug 1999): 67–88.https://doi.org/10.1257/jep.13.3.67Kathleen M. Fallon Education and Perceptions of Social Status and Power among Women in Larteh, Ghana, Africa Today 46, no.22 (Apr 1999): 66–91.https://doi.org/10.2979/AFT.1999.46.2.66
openalex: W2089314510 mag: 2089314510
Keywords: openalex:import

Schooling Attainment, Parental Education, and Gender in Côte d'Ivoire and Ghana - Tansel, Aysıt (Economic Development and Cultural Change, 1997)
Previous articleNext article No AccessSchooling Attainment, Parental Education, and Gender in Côte d'Ivoire and GhanaAysit Tansel Aysit TanselMiddle East Technical University, Ankara, and Yale University Search for more articles by this author Middle East Technical University, Ankara, and Yale UniversityPDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Economic Development and Cultural Change Volume 45, Number 4July 1997 Article DOIhttps://doi.org/10.1086/452309 Views: 278Total views on this site Citations: 58Citations are reported from Crossref © 1997 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Adebayo Mohammed Ojuolape, Saidatulakmal Mohd Dataset of Child schooling/ Out-of-school children in households in Kwara State, Nigeria, Data in Brief 45 (Dec 2022): 108654.https://doi.org/10.1016/j.dib.2022.108654Mafaizath Fatoké Dato Medium-Term Impact of the Elimination of School Fees on Girls’ Education in Benin, West Africa, Economic Development and Cultural Change 71, no.11 (Aug 2022): 261–294.https://doi.org/10.1086/714064Clifford Afoakwah, Isaac Koomson How does school travel time impact children’s learning outcomes in a developing country?, Review of Economics of the Household 19, no.44 (Jan 2021): 1077–1097.https://doi.org/10.1007/s11150-020-09533-8Anjan Ray Chaudhury, Madhabendra Sinha Gradual Disappearance of Gender Disparity in Human Capital Accumulation: Evidence from India, Journal of Asian and African Studies 55, no.88 (Mar 2020): 1108–1127.https://doi.org/10.1177/0021909620909492Clifford Afoakwah, Xin Deng, Ilke Onur Women’s Bargaining Power and Children’s Schooling Outcomes: Evidence From Ghana, Feminist Economics 26, no.33 (Feb 2020): 1–29.https://doi.org/10.1080/13545701.2019.1707847Catalina Herrera Almanza, David E. Sahn Childhood determinants of internal youth migration in Senegal, Demographic Research 43 (Nov 2020): 1335–1366.https://doi.org/10.4054/DemRes.2020.43.45Phillip Haynes The impact of home-based educational multi-correlates on academic achievement: an analysis of gender discrepancies in Rwanda, International Journal of Inclusive Education 24, no.55 (Apr 2018): 561–577.https://doi.org/10.1080/13603116.2018.1466929Glenn P. Jenkins, Hope Amala Anyabolu, Pejman Bahramian Family decision-making for educational expenditure: new evidence from survey data for Nigeria, Applied Economics 51, no.5252 (May 2019): 5663–5673.https://doi.org/10.1080/00036846.2019.1616075Akanksha Choudhary, Ashish Singh Do Indian daughters shadow their mothers?, International Journal of Social Economics 46, no.99 (Aug 2019): 1095–1118.https://doi.org/10.1108/IJSE-10-2018-0499Charlotte Janssens, Goedele Van den Broeck, Miet Maertens, Isabel Lambrecht What if mothers are entrepreneurs? Non-farm businesses and child schooling in rural Ghana, Journal of Rural Studies 66 (Feb 2019): 95–103.https://doi.org/10.1016/j.jrurstud.2019.01.004Akanksha Choudhary, Ashish Singh, Vijayaprasad Gopichandran Effect of intergenerational educational mobility on health of Indian women, PLOS ONE 13, no.99 (Sep 2018): e0203633.https://doi.org/10.1371/journal.pone.0203633Paola Ballón, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, Journal of African Economies 27, no.44 (Mar 2018): 483–512.https://doi.org/10.1093/jae/ejy001Shaleen Khanal Gender Discrimination in Education Expenditure in Nepal: Evidence from Living Standards Surveys, Asian Development Review 35, no.11 (Mar 2018): 155–174.https://doi.org/10.1162/adev_a_00109 References, (Jan 2018): 307–468.https://doi.org/10.1016/B978-0-12-805371-3.16001-7Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, SSRN Electronic Journal (Jan 2018).https://doi.org/10.2139/ssrn.3175368Long Thanh Giang, Cuong Viet Nguyen, Tuyen Quang Tran, Vu Thieu Does Firm Agglomeration Matter to Labor and Education of Local Children? Evidence in Vietnam, Child Indicators Research 10, no.44 (Aug 2016): 1015–1041.https://doi.org/10.1007/s12187-016-9409-8Akanksha Choudhary, Ashish Singh Are Daughters Like Mothers: Evidence on Intergenerational Educational Mobility Among Young Females in India, Social Indicators Research 133, no.22 (Jun 2016): 601–621.https://doi.org/10.1007/s11205-016-1380-8Abdul Malik Iddrisu, Michael Danquah, Peter Quartey Paying for education among households in Ghana, International Journal of Development Issues 16, no.22 (Jul 2017): 214–226.https://doi.org/10.1108/IJDI-02-2017-0017Tesfaye Alemayehu Gebremedhin, Itismita Mohanty, Jacobus P. van Wouwe Child Schooling in Ethiopia: The Role of Maternal Autonomy, PLOS ONE 11, no.1212 (Dec 2016): e0167639.https://doi.org/10.1371/journal.pone.0167639Alberto Posso, Simon Feeny Beyond enrolments: the determinants of primary-school attendance in Melanesia, Journal of the Asia Pacific Economy 21, no.44 (Mar 2016): 531–548.https://doi.org/10.1080/13547860.2016.1153205Sharon Wolf, Dana C McCoy, Erin B Godfrey Barriers to school attendance and gender inequality: Empirical evidence from a sample of Ghanaian schoolchildren, Research in Comparative and International Education 11, no.22 (Jun 2016): 178–193.https://doi.org/10.1177/1745499916632424Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Monetary and Multidimensional Child Poverty: Why They Differ, SSRN Electronic Journal (Jan 2016).https://doi.org/10.2139/ssrn.3164307Gina A.N. Chowa, Rainier D. Masa, Yalitza Ramos, David Ansong How do student and school characteristics influence youth academic achievement in Ghana? A hierarchical linear modeling of Ghana YouthSave baseline data, International Journal of Educational Development 45 (Nov 2015): 129–140.https://doi.org/10.1016/j.ijedudev.2015.09.009KAKOLI BORKOTOKY, SAYEED UNISA FEMALE EDUCATION AND ITS ASSOCIATION WITH CHANGES IN SOCIO-DEMOGRAPHIC BEHAVIOUR: EVIDENCE FROM INDIA, Journal of Biosocial Science 47, no.55 (Oct 2014): 687–706.https://doi.org/10.1017/S002193201400039XJane Arnold Lincove Improving Identification of Demand-Side Obstacles to Schooling: Findings from Revealed and Stated Preference Models in Two SSA Countries, World Development 66 (Feb 2015): 69–83.https://doi.org/10.1016/j.worlddev.2014.07.018Juan Yang, Terry SICULAR, Desheng LAI The changing determinants of high school attainment in rural China, China Economic Review 30 (Sep 2014): 551–566.https://doi.org/10.1016/j.chieco.2013.10.001Miet Maertens, Ellen Verhofstadt Horticultural exports, female wage employment and primary school enrolment: Theory and evidence from Senegal, Food Policy 43 (Dec 2013): 118–131.https://doi.org/10.1016/j.foodpol.2013.07.006Ashish Singh, Sarthak Gaurav, Upasak Das Household Headship and Academic Skills of Indian Children: A Special Focus on Gender Disparities, European Journal of Population / Revue européenne de Démographie 29, no.44 (Apr 2013): 445–466.https://doi.org/10.1007/s10680-013-9288-3S. Mani, J. Hoddinott, J. Strauss Determinants of Schooling: Empirical Evidence from Rural Ethiopia, Journal of African Economies 22, no.55 (May 2013): 693–731.https://doi.org/10.1093/jae/ejt007Daniel Mont, Cuong Nguyen Does Parental Disability Matter to Child Education? Evidence from Vietnam, World Development 48 (Aug 2013): 88–107.https://doi.org/10.1016/j.worlddev.2013.04.001Anders Breidlid, Halldis Breidlid Women in South Sudan, (Jan 2013): 99–115.https://doi.org/10.1007/978-94-6209-137-5_7Jane Arnold Lincove The influence of price on school enrollment under Uganda's policy of free primary education, Economics of Education Review 31, no.55 (Oct 2012): 799–811.https://doi.org/10.1016/j.econedurev.2012.04.007Manisha Chakrabarty, Sumon Kumar Bhaumik Whither human capital? The woeful tale of transition to tertiary education in India, Applied Economics Letters 19, no.99 (Jun 2012): 835–838.https://doi.org/10.1080/13504851.2011.607109Michèle Smith, Angeline M. Barrett Capabilities for learning to read: An investigation of social and economic effects for Grade 6 learners in Southern and East Africa, International Journal of Educational Development 31, no.11 (Jan 2011): 23–36.https://doi.org/10.1016/j.ijedudev.2010.06.006Jane Arnold Lincove Determinants of schooling for boys and girls in Nigeria under a policy of free primary education, Economics of Education Review 28, no.44 (Aug 2009): 474–484.https://doi.org/10.1016/j.econedurev.2008.10.001Subha Mani, John Hoddinott, John Strauss Determinants of Schooling Outcomes: Empirical Evidence from Rural Ethiopia, SSRN Electronic Journal (Jan 2009).https://doi.org/10.2139/ssrn.1508898Theresa Tuwor, Marie‐Antoinette Sossou Gender discrimination and education in West Africa: strategies for maintaining girls in school, International Journal of Inclusive Education 12, no.44 (Jul 2008): 363–379.https://doi.org/10.1080/13603110601183115H.-A. Dang, F. H. Rogers The Growing Phenomenon of Private Tutoring: Does It Deepen Human Capital, Widen Inequalities, or Waste Resources?, The World Bank Research Observer 23, no.22 (May 2008): 161–200.https://doi.org/10.1093/wbro/lkn004Tassew Woldehanna, Nicola Jones, Bekele Tefera The Invisibility of Children's Paid and Unpaid Work, Childhood 15, no.22 (May 2008): 177–201.https://doi.org/10.1177/0907568207088421Peter Glick Policy Impacts on Schooling Gender Gaps in Developing Countries: The Evidence and a Framework for Interpretation, SSRN Electronic Journal (Jan 2008).https://doi.org/10.2139/ssrn.891256jane kabubo-mariara, domisiano k. mwabu DETERMINANTS OF SCHOOL ENROLMENT AND EDUCATION ATTAINMENT: EMPIRICAL EVIDENCE FROM KENYA, The South African Journal of Economics 75, no.33 (Sep 2007): 572–593.https://doi.org/10.1111/j.1813-6982.2007.00138.xPeter F. Orazem, Elizabeth M. King Chapter 55 Schooling in Developing Countries: The Roles of Supply, Demand and Government Policy, (Jan 2007): 3475–3559.https://doi.org/10.1016/S1573-4471(07)04055-7Anastasia Gage The Interrelationship between Fosterage, Schooling, and Children’s Labor Force Participation in Ghana, Population Research and Policy Review 24, no.55 (Oct 2005): 431–466.https://doi.org/10.1007/s11113-005-4290-zSilvia Pasqua Gender Bias in Parental Investments in Children’s Education: A Theoretical Analysis, Review of Economics of the Household 3, no.33 (Sep 2005): 291–314.https://doi.org/10.1007/s11150-005-3459-xKofi D. Benefo Child schooling and contraceptive use in rural Africa: A Ghanaian case study, Population Research and Policy Review 24, no.11 (Jan 2005): 1–25.https://doi.org/10.1007/s11113-005-8986-xT. Paul Schultz School subsidies for the poor: evaluating the Mexican Progresa poverty program, Journal of Development Economics 74, no.11 (Jun 2004): 199–250.https://doi.org/10.1016/j.jdeveco.2003.12.009Peter Glick, Rumki Saha, Stephen D. Younger Integrating Gender into Benefit Incidence and Demand Analysis, SSRN Electronic Journal (Jan 2004).https://doi.org/10.2139/ssrn.590822 Human Capital, Household Welfare, and Children’s Schooling in Mozambique, (Jan 2004).https://doi.org/10.2499/0896291375rr134Jessica Holmes Measuring the determinants of school completion in Pakistan: analysis of censoring and selection bias, Economics of Education Review 22, no.33 (Jun 2003): 249–264.https://doi.org/10.1016/S0272-7757(02)00024-9 Esther Redmount Cyclical Patterns in School Attrition and Attendance: A Study in the Labor‐Market Behavior of Children Esther Redmount, Economic Development and Cultural Change 51, no.11 (Jul 2015): 135–160.https://doi.org/10.1086/344629Aysit Tansel Determinants of school attainment of boys and girls in Turkey: individual, household and community factors, Economics of Education Review 21, no.55 (Oct 2002): 455–470.https://doi.org/10.1016/S0272-7757(01)00028-0T Paul Schultz Why Governments Should Invest More to Educate Girls, World Development 30, no.22 (Feb 2002): 207–225.https://doi.org/10.1016/S0305-750X(01)00107-3Katharina Michaelowa Primary Education Quality in Francophone Sub-Saharan Africa: Determinants of Learning Achievement and Efficiency Considerations, World Development 29, no.1010 (Oct 2001): 1699–1716.https://doi.org/10.1016/S0305-750X(01)00061-4T. Paul Schultz Chapter 8 Women's roles in the agricultural household: Bargaining and human capital investments, (Jan 2001): 383–456.https://doi.org/10.1016/S1574-0072(01)10011-3Danielle de Lame Genre et développement : bibliographie sélective 1, Bulletin de l’APAD , no.2020 (Dec 2000).https://doi.org/10.4000/apad.257Peter Glick, David E. Sahn Schooling of girls and boys in a West African country: the effects of parental education, income, and household structure, Economics of Education Review 19, no.11 (Feb 2000): 63–87.https://doi.org/10.1016/S0272-7757(99)00029-1T. Paul Schultz Health and Schooling Investments in Africa, Journal of Economic Perspectives 13, no.33 (Aug 1999): 67–88.https://doi.org/10.1257/jep.13.3.67Kathleen M. Fallon Education and Perceptions of Social Status and Power among Women in Larteh, Ghana, Africa Today 46, no.22 (Apr 1999): 66–91.https://doi.org/10.2979/AFT.1999.46.2.66
openalex: W2089314510 mag: 2089314510
Keywords: openalex:import

Schooling Attainment, Parental Education, and Gender in Côte d'Ivoire and Ghana - Tansel, Aysıt (Economic Development and Cultural Change, 1997)
Previous articleNext article No AccessSchooling Attainment, Parental Education, and Gender in Côte d'Ivoire and GhanaAysit Tansel Aysit TanselMiddle East Technical University, Ankara, and Yale University Search for more articles by this author Middle East Technical University, Ankara, and Yale UniversityPDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Economic Development and Cultural Change Volume 45, Number 4July 1997 Article DOIhttps://doi.org/10.1086/452309 Views: 278Total views on this site Citations: 58Citations are reported from Crossref © 1997 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Adebayo Mohammed Ojuolape, Saidatulakmal Mohd Dataset of Child schooling/ Out-of-school children in households in Kwara State, Nigeria, Data in Brief 45 (Dec 2022): 108654.https://doi.org/10.1016/j.dib.2022.108654Mafaizath Fatoké Dato Medium-Term Impact of the Elimination of School Fees on Girls’ Education in Benin, West Africa, Economic Development and Cultural Change 71, no.11 (Aug 2022): 261–294.https://doi.org/10.1086/714064Clifford Afoakwah, Isaac Koomson How does school travel time impact children’s learning outcomes in a developing country?, Review of Economics of the Household 19, no.44 (Jan 2021): 1077–1097.https://doi.org/10.1007/s11150-020-09533-8Anjan Ray Chaudhury, Madhabendra Sinha Gradual Disappearance of Gender Disparity in Human Capital Accumulation: Evidence from India, Journal of Asian and African Studies 55, no.88 (Mar 2020): 1108–1127.https://doi.org/10.1177/0021909620909492Clifford Afoakwah, Xin Deng, Ilke Onur Women’s Bargaining Power and Children’s Schooling Outcomes: Evidence From Ghana, Feminist Economics 26, no.33 (Feb 2020): 1–29.https://doi.org/10.1080/13545701.2019.1707847Catalina Herrera Almanza, David E. Sahn Childhood determinants of internal youth migration in Senegal, Demographic Research 43 (Nov 2020): 1335–1366.https://doi.org/10.4054/DemRes.2020.43.45Phillip Haynes The impact of home-based educational multi-correlates on academic achievement: an analysis of gender discrepancies in Rwanda, International Journal of Inclusive Education 24, no.55 (Apr 2018): 561–577.https://doi.org/10.1080/13603116.2018.1466929Glenn P. Jenkins, Hope Amala Anyabolu, Pejman Bahramian Family decision-making for educational expenditure: new evidence from survey data for Nigeria, Applied Economics 51, no.5252 (May 2019): 5663–5673.https://doi.org/10.1080/00036846.2019.1616075Akanksha Choudhary, Ashish Singh Do Indian daughters shadow their mothers?, International Journal of Social Economics 46, no.99 (Aug 2019): 1095–1118.https://doi.org/10.1108/IJSE-10-2018-0499Charlotte Janssens, Goedele Van den Broeck, Miet Maertens, Isabel Lambrecht What if mothers are entrepreneurs? Non-farm businesses and child schooling in rural Ghana, Journal of Rural Studies 66 (Feb 2019): 95–103.https://doi.org/10.1016/j.jrurstud.2019.01.004Akanksha Choudhary, Ashish Singh, Vijayaprasad Gopichandran Effect of intergenerational educational mobility on health of Indian women, PLOS ONE 13, no.99 (Sep 2018): e0203633.https://doi.org/10.1371/journal.pone.0203633Paola Ballón, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, Journal of African Economies 27, no.44 (Mar 2018): 483–512.https://doi.org/10.1093/jae/ejy001Shaleen Khanal Gender Discrimination in Education Expenditure in Nepal: Evidence from Living Standards Surveys, Asian Development Review 35, no.11 (Mar 2018): 155–174.https://doi.org/10.1162/adev_a_00109 References, (Jan 2018): 307–468.https://doi.org/10.1016/B978-0-12-805371-3.16001-7Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, SSRN Electronic Journal (Jan 2018).https://doi.org/10.2139/ssrn.3175368Long Thanh Giang, Cuong Viet Nguyen, Tuyen Quang Tran, Vu Thieu Does Firm Agglomeration Matter to Labor and Education of Local Children? Evidence in Vietnam, Child Indicators Research 10, no.44 (Aug 2016): 1015–1041.https://doi.org/10.1007/s12187-016-9409-8Akanksha Choudhary, Ashish Singh Are Daughters Like Mothers: Evidence on Intergenerational Educational Mobility Among Young Females in India, Social Indicators Research 133, no.22 (Jun 2016): 601–621.https://doi.org/10.1007/s11205-016-1380-8Abdul Malik Iddrisu, Michael Danquah, Peter Quartey Paying for education among households in Ghana, International Journal of Development Issues 16, no.22 (Jul 2017): 214–226.https://doi.org/10.1108/IJDI-02-2017-0017Tesfaye Alemayehu Gebremedhin, Itismita Mohanty, Jacobus P. van Wouwe Child Schooling in Ethiopia: The Role of Maternal Autonomy, PLOS ONE 11, no.1212 (Dec 2016): e0167639.https://doi.org/10.1371/journal.pone.0167639Alberto Posso, Simon Feeny Beyond enrolments: the determinants of primary-school attendance in Melanesia, Journal of the Asia Pacific Economy 21, no.44 (Mar 2016): 531–548.https://doi.org/10.1080/13547860.2016.1153205Sharon Wolf, Dana C McCoy, Erin B Godfrey Barriers to school attendance and gender inequality: Empirical evidence from a sample of Ghanaian schoolchildren, Research in Comparative and International Education 11, no.22 (Jun 2016): 178–193.https://doi.org/10.1177/1745499916632424Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Monetary and Multidimensional Child Poverty: Why They Differ, SSRN Electronic Journal (Jan 2016).https://doi.org/10.2139/ssrn.3164307Gina A.N. Chowa, Rainier D. Masa, Yalitza Ramos, David Ansong How do student and school characteristics influence youth academic achievement in Ghana? A hierarchical linear modeling of Ghana YouthSave baseline data, International Journal of Educational Development 45 (Nov 2015): 129–140.https://doi.org/10.1016/j.ijedudev.2015.09.009KAKOLI BORKOTOKY, SAYEED UNISA FEMALE EDUCATION AND ITS ASSOCIATION WITH CHANGES IN SOCIO-DEMOGRAPHIC BEHAVIOUR: EVIDENCE FROM INDIA, Journal of Biosocial Science 47, no.55 (Oct 2014): 687–706.https://doi.org/10.1017/S002193201400039XJane Arnold Lincove Improving Identification of Demand-Side Obstacles to Schooling: Findings from Revealed and Stated Preference Models in Two SSA Countries, World Development 66 (Feb 2015): 69–83.https://doi.org/10.1016/j.worlddev.2014.07.018Juan Yang, Terry SICULAR, Desheng LAI The changing determinants of high school attainment in rural China, China Economic Review 30 (Sep 2014): 551–566.https://doi.org/10.1016/j.chieco.2013.10.001Miet Maertens, Ellen Verhofstadt Horticultural exports, female wage employment and primary school enrolment: Theory and evidence from Senegal, Food Policy 43 (Dec 2013): 118–131.https://doi.org/10.1016/j.foodpol.2013.07.006Ashish Singh, Sarthak Gaurav, Upasak Das Household Headship and Academic Skills of Indian Children: A Special Focus on Gender Disparities, European Journal of Population / Revue européenne de Démographie 29, no.44 (Apr 2013): 445–466.https://doi.org/10.1007/s10680-013-9288-3S. Mani, J. Hoddinott, J. Strauss Determinants of Schooling: Empirical Evidence from Rural Ethiopia, Journal of African Economies 22, no.55 (May 2013): 693–731.https://doi.org/10.1093/jae/ejt007Daniel Mont, Cuong Nguyen Does Parental Disability Matter to Child Education? Evidence from Vietnam, World Development 48 (Aug 2013): 88–107.https://doi.org/10.1016/j.worlddev.2013.04.001Anders Breidlid, Halldis Breidlid Women in South Sudan, (Jan 2013): 99–115.https://doi.org/10.1007/978-94-6209-137-5_7Jane Arnold Lincove The influence of price on school enrollment under Uganda's policy of free primary education, Economics of Education Review 31, no.55 (Oct 2012): 799–811.https://doi.org/10.1016/j.econedurev.2012.04.007Manisha Chakrabarty, Sumon Kumar Bhaumik Whither human capital? The woeful tale of transition to tertiary education in India, Applied Economics Letters 19, no.99 (Jun 2012): 835–838.https://doi.org/10.1080/13504851.2011.607109Michèle Smith, Angeline M. Barrett Capabilities for learning to read: An investigation of social and economic effects for Grade 6 learners in Southern and East Africa, International Journal of Educational Development 31, no.11 (Jan 2011): 23–36.https://doi.org/10.1016/j.ijedudev.2010.06.006Jane Arnold Lincove Determinants of schooling for boys and girls in Nigeria under a policy of free primary education, Economics of Education Review 28, no.44 (Aug 2009): 474–484.https://doi.org/10.1016/j.econedurev.2008.10.001Subha Mani, John Hoddinott, John Strauss Determinants of Schooling Outcomes: Empirical Evidence from Rural Ethiopia, SSRN Electronic Journal (Jan 2009).https://doi.org/10.2139/ssrn.1508898Theresa Tuwor, Marie‐Antoinette Sossou Gender discrimination and education in West Africa: strategies for maintaining girls in school, International Journal of Inclusive Education 12, no.44 (Jul 2008): 363–379.https://doi.org/10.1080/13603110601183115H.-A. Dang, F. H. Rogers The Growing Phenomenon of Private Tutoring: Does It Deepen Human Capital, Widen Inequalities, or Waste Resources?, The World Bank Research Observer 23, no.22 (May 2008): 161–200.https://doi.org/10.1093/wbro/lkn004Tassew Woldehanna, Nicola Jones, Bekele Tefera The Invisibility of Children's Paid and Unpaid Work, Childhood 15, no.22 (May 2008): 177–201.https://doi.org/10.1177/0907568207088421Peter Glick Policy Impacts on Schooling Gender Gaps in Developing Countries: The Evidence and a Framework for Interpretation, SSRN Electronic Journal (Jan 2008).https://doi.org/10.2139/ssrn.891256jane kabubo-mariara, domisiano k. mwabu DETERMINANTS OF SCHOOL ENROLMENT AND EDUCATION ATTAINMENT: EMPIRICAL EVIDENCE FROM KENYA, The South African Journal of Economics 75, no.33 (Sep 2007): 572–593.https://doi.org/10.1111/j.1813-6982.2007.00138.xPeter F. Orazem, Elizabeth M. King Chapter 55 Schooling in Developing Countries: The Roles of Supply, Demand and Government Policy, (Jan 2007): 3475–3559.https://doi.org/10.1016/S1573-4471(07)04055-7Anastasia Gage The Interrelationship between Fosterage, Schooling, and Children’s Labor Force Participation in Ghana, Population Research and Policy Review 24, no.55 (Oct 2005): 431–466.https://doi.org/10.1007/s11113-005-4290-zSilvia Pasqua Gender Bias in Parental Investments in Children’s Education: A Theoretical Analysis, Review of Economics of the Household 3, no.33 (Sep 2005): 291–314.https://doi.org/10.1007/s11150-005-3459-xKofi D. Benefo Child schooling and contraceptive use in rural Africa: A Ghanaian case study, Population Research and Policy Review 24, no.11 (Jan 2005): 1–25.https://doi.org/10.1007/s11113-005-8986-xT. Paul Schultz School subsidies for the poor: evaluating the Mexican Progresa poverty program, Journal of Development Economics 74, no.11 (Jun 2004): 199–250.https://doi.org/10.1016/j.jdeveco.2003.12.009Peter Glick, Rumki Saha, Stephen D. Younger Integrating Gender into Benefit Incidence and Demand Analysis, SSRN Electronic Journal (Jan 2004).https://doi.org/10.2139/ssrn.590822 Human Capital, Household Welfare, and Children’s Schooling in Mozambique, (Jan 2004).https://doi.org/10.2499/0896291375rr134Jessica Holmes Measuring the determinants of school completion in Pakistan: analysis of censoring and selection bias, Economics of Education Review 22, no.33 (Jun 2003): 249–264.https://doi.org/10.1016/S0272-7757(02)00024-9 Esther Redmount Cyclical Patterns in School Attrition and Attendance: A Study in the Labor‐Market Behavior of Children Esther Redmount, Economic Development and Cultural Change 51, no.11 (Jul 2015): 135–160.https://doi.org/10.1086/344629Aysit Tansel Determinants of school attainment of boys and girls in Turkey: individual, household and community factors, Economics of Education Review 21, no.55 (Oct 2002): 455–470.https://doi.org/10.1016/S0272-7757(01)00028-0T Paul Schultz Why Governments Should Invest More to Educate Girls, World Development 30, no.22 (Feb 2002): 207–225.https://doi.org/10.1016/S0305-750X(01)00107-3Katharina Michaelowa Primary Education Quality in Francophone Sub-Saharan Africa: Determinants of Learning Achievement and Efficiency Considerations, World Development 29, no.1010 (Oct 2001): 1699–1716.https://doi.org/10.1016/S0305-750X(01)00061-4T. Paul Schultz Chapter 8 Women's roles in the agricultural household: Bargaining and human capital investments, (Jan 2001): 383–456.https://doi.org/10.1016/S1574-0072(01)10011-3Danielle de Lame Genre et développement : bibliographie sélective 1, Bulletin de l’APAD , no.2020 (Dec 2000).https://doi.org/10.4000/apad.257Peter Glick, David E. Sahn Schooling of girls and boys in a West African country: the effects of parental education, income, and household structure, Economics of Education Review 19, no.11 (Feb 2000): 63–87.https://doi.org/10.1016/S0272-7757(99)00029-1T. Paul Schultz Health and Schooling Investments in Africa, Journal of Economic Perspectives 13, no.33 (Aug 1999): 67–88.https://doi.org/10.1257/jep.13.3.67Kathleen M. Fallon Education and Perceptions of Social Status and Power among Women in Larteh, Ghana, Africa Today 46, no.22 (Apr 1999): 66–91.https://doi.org/10.2979/AFT.1999.46.2.66
openalex: W2089314510 mag: 2089314510
Keywords: openalex:import; openalex:yes

Schooling Attainment, Parental Education, and Gender in Côte d'Ivoire and Ghana - Tansel, Aysıt (Economic Development and Cultural Change, 1997)
Previous articleNext article No AccessSchooling Attainment, Parental Education, and Gender in Côte d'Ivoire and GhanaAysit Tansel Aysit TanselMiddle East Technical University, Ankara, and Yale University Search for more articles by this author Middle East Technical University, Ankara, and Yale UniversityPDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Economic Development and Cultural Change Volume 45, Number 4July 1997 Article DOIhttps://doi.org/10.1086/452309 Views: 278Total views on this site Citations: 58Citations are reported from Crossref © 1997 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Adebayo Mohammed Ojuolape, Saidatulakmal Mohd Dataset of Child schooling/ Out-of-school children in households in Kwara State, Nigeria, Data in Brief 45 (Dec 2022): 108654.https://doi.org/10.1016/j.dib.2022.108654Mafaizath Fatoké Dato Medium-Term Impact of the Elimination of School Fees on Girls’ Education in Benin, West Africa, Economic Development and Cultural Change 71, no.11 (Aug 2022): 261–294.https://doi.org/10.1086/714064Clifford Afoakwah, Isaac Koomson How does school travel time impact children’s learning outcomes in a developing country?, Review of Economics of the Household 19, no.44 (Jan 2021): 1077–1097.https://doi.org/10.1007/s11150-020-09533-8Anjan Ray Chaudhury, Madhabendra Sinha Gradual Disappearance of Gender Disparity in Human Capital Accumulation: Evidence from India, Journal of Asian and African Studies 55, no.88 (Mar 2020): 1108–1127.https://doi.org/10.1177/0021909620909492Clifford Afoakwah, Xin Deng, Ilke Onur Women’s Bargaining Power and Children’s Schooling Outcomes: Evidence From Ghana, Feminist Economics 26, no.33 (Feb 2020): 1–29.https://doi.org/10.1080/13545701.2019.1707847Catalina Herrera Almanza, David E. Sahn Childhood determinants of internal youth migration in Senegal, Demographic Research 43 (Nov 2020): 1335–1366.https://doi.org/10.4054/DemRes.2020.43.45Phillip Haynes The impact of home-based educational multi-correlates on academic achievement: an analysis of gender discrepancies in Rwanda, International Journal of Inclusive Education 24, no.55 (Apr 2018): 561–577.https://doi.org/10.1080/13603116.2018.1466929Glenn P. Jenkins, Hope Amala Anyabolu, Pejman Bahramian Family decision-making for educational expenditure: new evidence from survey data for Nigeria, Applied Economics 51, no.5252 (May 2019): 5663–5673.https://doi.org/10.1080/00036846.2019.1616075Akanksha Choudhary, Ashish Singh Do Indian daughters shadow their mothers?, International Journal of Social Economics 46, no.99 (Aug 2019): 1095–1118.https://doi.org/10.1108/IJSE-10-2018-0499Charlotte Janssens, Goedele Van den Broeck, Miet Maertens, Isabel Lambrecht What if mothers are entrepreneurs? Non-farm businesses and child schooling in rural Ghana, Journal of Rural Studies 66 (Feb 2019): 95–103.https://doi.org/10.1016/j.jrurstud.2019.01.004Akanksha Choudhary, Ashish Singh, Vijayaprasad Gopichandran Effect of intergenerational educational mobility on health of Indian women, PLOS ONE 13, no.99 (Sep 2018): e0203633.https://doi.org/10.1371/journal.pone.0203633Paola Ballón, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, Journal of African Economies 27, no.44 (Mar 2018): 483–512.https://doi.org/10.1093/jae/ejy001Shaleen Khanal Gender Discrimination in Education Expenditure in Nepal: Evidence from Living Standards Surveys, Asian Development Review 35, no.11 (Mar 2018): 155–174.https://doi.org/10.1162/adev_a_00109 References, (Jan 2018): 307–468.https://doi.org/10.1016/B978-0-12-805371-3.16001-7Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Child Monetary Poverty and Multidimensional Deprivations: Why They Differ, SSRN Electronic Journal (Jan 2018).https://doi.org/10.2139/ssrn.3175368Long Thanh Giang, Cuong Viet Nguyen, Tuyen Quang Tran, Vu Thieu Does Firm Agglomeration Matter to Labor and Education of Local Children? Evidence in Vietnam, Child Indicators Research 10, no.44 (Aug 2016): 1015–1041.https://doi.org/10.1007/s12187-016-9409-8Akanksha Choudhary, Ashish Singh Are Daughters Like Mothers: Evidence on Intergenerational Educational Mobility Among Young Females in India, Social Indicators Research 133, no.22 (Jun 2016): 601–621.https://doi.org/10.1007/s11205-016-1380-8Abdul Malik Iddrisu, Michael Danquah, Peter Quartey Paying for education among households in Ghana, International Journal of Development Issues 16, no.22 (Jul 2017): 214–226.https://doi.org/10.1108/IJDI-02-2017-0017Tesfaye Alemayehu Gebremedhin, Itismita Mohanty, Jacobus P. van Wouwe Child Schooling in Ethiopia: The Role of Maternal Autonomy, PLOS ONE 11, no.1212 (Dec 2016): e0167639.https://doi.org/10.1371/journal.pone.0167639Alberto Posso, Simon Feeny Beyond enrolments: the determinants of primary-school attendance in Melanesia, Journal of the Asia Pacific Economy 21, no.44 (Mar 2016): 531–548.https://doi.org/10.1080/13547860.2016.1153205Sharon Wolf, Dana C McCoy, Erin B Godfrey Barriers to school attendance and gender inequality: Empirical evidence from a sample of Ghanaian schoolchildren, Research in Comparative and International Education 11, no.22 (Jun 2016): 178–193.https://doi.org/10.1177/1745499916632424Paola Ballon, John Cockburn, Sylvain Dessy, Setou Diarra Monetary and Multidimensional Child Poverty: Why They Differ, SSRN Electronic Journal (Jan 2016).https://doi.org/10.2139/ssrn.3164307Gina A.N. Chowa, Rainier D. Masa, Yalitza Ramos, David Ansong How do student and school characteristics influence youth academic achievement in Ghana? A hierarchical linear modeling of Ghana YouthSave baseline data, International Journal of Educational Development 45 (Nov 2015): 129–140.https://doi.org/10.1016/j.ijedudev.2015.09.009KAKOLI BORKOTOKY, SAYEED UNISA FEMALE EDUCATION AND ITS ASSOCIATION WITH CHANGES IN SOCIO-DEMOGRAPHIC BEHAVIOUR: EVIDENCE FROM INDIA, Journal of Biosocial Science 47, no.55 (Oct 2014): 687–706.https://doi.org/10.1017/S002193201400039XJane Arnold Lincove Improving Identification of Demand-Side Obstacles to Schooling: Findings from Revealed and Stated Preference Models in Two SSA Countries, World Development 66 (Feb 2015): 69–83.https://doi.org/10.1016/j.worlddev.2014.07.018Juan Yang, Terry SICULAR, Desheng LAI The changing determinants of high school attainment in rural China, China Economic Review 30 (Sep 2014): 551–566.https://doi.org/10.1016/j.chieco.2013.10.001Miet Maertens, Ellen Verhofstadt Horticultural exports, female wage employment and primary school enrolment: Theory and evidence from Senegal, Food Policy 43 (Dec 2013): 118–131.https://doi.org/10.1016/j.foodpol.2013.07.006Ashish Singh, Sarthak Gaurav, Upasak Das Household Headship and Academic Skills of Indian Children: A Special Focus on Gender Disparities, European Journal of Population / Revue européenne de Démographie 29, no.44 (Apr 2013): 445–466.https://doi.org/10.1007/s10680-013-9288-3S. Mani, J. Hoddinott, J. Strauss Determinants of Schooling: Empirical Evidence from Rural Ethiopia, Journal of African Economies 22, no.55 (May 2013): 693–731.https://doi.org/10.1093/jae/ejt007Daniel Mont, Cuong Nguyen Does Parental Disability Matter to Child Education? Evidence from Vietnam, World Development 48 (Aug 2013): 88–107.https://doi.org/10.1016/j.worlddev.2013.04.001Anders Breidlid, Halldis Breidlid Women in South Sudan, (Jan 2013): 99–115.https://doi.org/10.1007/978-94-6209-137-5_7Jane Arnold Lincove The influence of price on school enrollment under Uganda's policy of free primary education, Economics of Education Review 31, no.55 (Oct 2012): 799–811.https://doi.org/10.1016/j.econedurev.2012.04.007Manisha Chakrabarty, Sumon Kumar Bhaumik Whither human capital? The woeful tale of transition to tertiary education in India, Applied Economics Letters 19, no.99 (Jun 2012): 835–838.https://doi.org/10.1080/13504851.2011.607109Michèle Smith, Angeline M. Barrett Capabilities for learning to read: An investigation of social and economic effects for Grade 6 learners in Southern and East Africa, International Journal of Educational Development 31, no.11 (Jan 2011): 23–36.https://doi.org/10.1016/j.ijedudev.2010.06.006Jane Arnold Lincove Determinants of schooling for boys and girls in Nigeria under a policy of free primary education, Economics of Education Review 28, no.44 (Aug 2009): 474–484.https://doi.org/10.1016/j.econedurev.2008.10.001Subha Mani, John Hoddinott, John Strauss Determinants of Schooling Outcomes: Empirical Evidence from Rural Ethiopia, SSRN Electronic Journal (Jan 2009).https://doi.org/10.2139/ssrn.1508898Theresa Tuwor, Marie‐Antoinette Sossou Gender discrimination and education in West Africa: strategies for maintaining girls in school, International Journal of Inclusive Education 12, no.44 (Jul 2008): 363–379.https://doi.org/10.1080/13603110601183115H.-A. Dang, F. H. Rogers The Growing Phenomenon of Private Tutoring: Does It Deepen Human Capital, Widen Inequalities, or Waste Resources?, The World Bank Research Observer 23, no.22 (May 2008): 161–200.https://doi.org/10.1093/wbro/lkn004Tassew Woldehanna, Nicola Jones, Bekele Tefera The Invisibility of Children's Paid and Unpaid Work, Childhood 15, no.22 (May 2008): 177–201.https://doi.org/10.1177/0907568207088421Peter Glick Policy Impacts on Schooling Gender Gaps in Developing Countries: The Evidence and a Framework for Interpretation, SSRN Electronic Journal (Jan 2008).https://doi.org/10.2139/ssrn.891256jane kabubo-mariara, domisiano k. mwabu DETERMINANTS OF SCHOOL ENROLMENT AND EDUCATION ATTAINMENT: EMPIRICAL EVIDENCE FROM KENYA, The South African Journal of Economics 75, no.33 (Sep 2007): 572–593.https://doi.org/10.1111/j.1813-6982.2007.00138.xPeter F. Orazem, Elizabeth M. King Chapter 55 Schooling in Developing Countries: The Roles of Supply, Demand and Government Policy, (Jan 2007): 3475–3559.https://doi.org/10.1016/S1573-4471(07)04055-7Anastasia Gage The Interrelationship between Fosterage, Schooling, and Children’s Labor Force Participation in Ghana, Population Research and Policy Review 24, no.55 (Oct 2005): 431–466.https://doi.org/10.1007/s11113-005-4290-zSilvia Pasqua Gender Bias in Parental Investments in Children’s Education: A Theoretical Analysis, Review of Economics of the Household 3, no.33 (Sep 2005): 291–314.https://doi.org/10.1007/s11150-005-3459-xKofi D. Benefo Child schooling and contraceptive use in rural Africa: A Ghanaian case study, Population Research and Policy Review 24, no.11 (Jan 2005): 1–25.https://doi.org/10.1007/s11113-005-8986-xT. Paul Schultz School subsidies for the poor: evaluating the Mexican Progresa poverty program, Journal of Development Economics 74, no.11 (Jun 2004): 199–250.https://doi.org/10.1016/j.jdeveco.2003.12.009Peter Glick, Rumki Saha, Stephen D. Younger Integrating Gender into Benefit Incidence and Demand Analysis, SSRN Electronic Journal (Jan 2004).https://doi.org/10.2139/ssrn.590822 Human Capital, Household Welfare, and Children’s Schooling in Mozambique, (Jan 2004).https://doi.org/10.2499/0896291375rr134Jessica Holmes Measuring the determinants of school completion in Pakistan: analysis of censoring and selection bias, Economics of Education Review 22, no.33 (Jun 2003): 249–264.https://doi.org/10.1016/S0272-7757(02)00024-9 Esther Redmount Cyclical Patterns in School Attrition and Attendance: A Study in the Labor‐Market Behavior of Children Esther Redmount, Economic Development and Cultural Change 51, no.11 (Jul 2015): 135–160.https://doi.org/10.1086/344629Aysit Tansel Determinants of school attainment of boys and girls in Turkey: individual, household and community factors, Economics of Education Review 21, no.55 (Oct 2002): 455–470.https://doi.org/10.1016/S0272-7757(01)00028-0T Paul Schultz Why Governments Should Invest More to Educate Girls, World Development 30, no.22 (Feb 2002): 207–225.https://doi.org/10.1016/S0305-750X(01)00107-3Katharina Michaelowa Primary Education Quality in Francophone Sub-Saharan Africa: Determinants of Learning Achievement and Efficiency Considerations, World Development 29, no.1010 (Oct 2001): 1699–1716.https://doi.org/10.1016/S0305-750X(01)00061-4T. Paul Schultz Chapter 8 Women's roles in the agricultural household: Bargaining and human capital investments, (Jan 2001): 383–456.https://doi.org/10.1016/S1574-0072(01)10011-3Danielle de Lame Genre et développement : bibliographie sélective 1, Bulletin de l’APAD , no.2020 (Dec 2000).https://doi.org/10.4000/apad.257Peter Glick, David E. Sahn Schooling of girls and boys in a West African country: the effects of parental education, income, and household structure, Economics of Education Review 19, no.11 (Feb 2000): 63–87.https://doi.org/10.1016/S0272-7757(99)00029-1T. Paul Schultz Health and Schooling Investments in Africa, Journal of Economic Perspectives 13, no.33 (Aug 1999): 67–88.https://doi.org/10.1257/jep.13.3.67Kathleen M. Fallon Education and Perceptions of Social Status and Power among Women in Larteh, Ghana, Africa Today 46, no.22 (Apr 1999): 66–91.https://doi.org/10.2979/AFT.1999.46.2.66
openalex: W2089314510 mag: 2089314510
Keywords: openalex:import

AIDS related knowledge and behaviours among college students, Gondar, Ethiopia: a comparative study. - Teka, Telahun (PubMed, 1997)
AIDS-related knowledge and behaviours among students at the Gondar College of Medical Sciences, Gondar, Ethiopia were evaluated based on identical surveys conducted in 1990 and 1992. One hundred three second year students provided information in 1992. Analysis indicated that 49% were engaged in sexual intercourse and only a third of these group used condom despite their improved knowledge and belief on condom compared to their previous position in 1990 (p < 0.004). On the other hand, their sexual behaviours regarding sexual contact with high risk individuals decreased compared to 1990 (p < 0.0005). Their general level of AIDS-related preventive knowledge increased over time (p < 0.002), although there was no significant difference in knowledge observed among different sexes and departments. Among the sexually active, a large proportion of students (22%) still had sexual contact with high risk individuals and only 33% of them were using safer methods. Continuing efforts, including peer education, specific health education interventions are still crucially needed to bring a positive change in sexual behaviour.Results of identical surveys administered to 164 students before their admission (1990 survey) to the Gondar College of Medical Sciences in Ethiopia and the 103 of these students who completed their second year at the school (1992 survey) were compared to investigate trends in AIDS-related knowledge and practices. The proportion of students aware that AIDS can be prevented by condom use increased from 69% in 1990 to 84% in 1992, and the percentage who considered themselves knowledgeable about current methods of AIDS prevention rose from 62% to 80%. In terms of sexual behavior, only 24% of students who were sexually active in 1990 used condoms at most recent sexual intercourse compared with 33% in 1992. The proportion whose most recent sexual partner was from a high-risk group (i.e., prostitutes) decreased from 47% in 1990 to 34% in 1992. These changes occurred in the absence of a sex education or AIDS prevention program at the university. There was no association between AIDS knowledge and condom use in either survey. The gap between Ethiopian students' knowledge of the protective effect of condom use and their actual use of condoms requires an extensive health education campaign, including peer education.
openalex: W2276495948 mag: 2276495948
Keywords: openalex:import

Narrative Insights into African American School Experiences: Combating the Culture of Defeatism - Thomas, Cornell (International Journal of Educational Reform, 1997)
openalex: W233568707 mag: 233568707
Keywords: openalex:import

Seismic discrimination between earthquakes and explosions in the Middle East and North Africa - Walter, William R.; Harris, David B.; Myers, S. C. (1997)
The recently signed Comprehensive Test Ban Treaty provides for an international network of primary and auxiliary seismic monitoring stations (IMS) to verify its compliance. Calibration is required to confidently use these stations to identify and discriminate between earthquakes, mine-related events and clandestine nuclear explosions, particularly for small to moderate seismic events recorded regionally at only a few stations. Given the lack of regional recordings of underground nuclear tests in most of the world, we are making use of mining and industrial explosions to test discriminants. For example we use the Multimax compiled dataset of small earthquakes and quarry explosions in Israel to test regional discriminants at local distances with mixed results. Further complicating calibration is the fact that many INK sites have not yet been installed and others have very short operating histories. When IMS data is available, there is often a lack of independent information (ground truth ) on the seismic sources. Here we describe a procedure for calibrating stations with limited data and apply it to the IMS auxiliary station MDT in Morocco. Data was initially available for three months in 1990 when MDT was operated as part of MEDNET. An event detector was run over the continuousmore » data and regional events identified and roughly located using S-P time and back azimuth. The procedure uses spatial and temporal clustering to identify ''known'' mine blasts. The spatial clustering is done using the waveform correlation technique of Harris (1991) to find events with similar sources and locations. Temporal clustering looks at the time of day and repetition in time of events with the mine blasts occurring during working hours and days repeatedly over a period of time. A set of ''known'' earthquakes is also determined using location, time of day, distribution in time and size criteria. With these independent libraries of identified seismic events, we evaluate promising regional discriminants such as high frequency P/Lg. We also examine distance and path effects on the discriminants. Preliminary results indicate high frequency P/Lg provides some separation between mine blasts and earthquakes at MDT.« less
openalex: W1481814734 mag: 1481814734
Keywords: openalex:import

The African experience with higher education - Watson, Keith (International Journal of Educational Development, 1997)
openalex: W2941374088 mag: 2941374088
Keywords: openalex:import

Comparison of albendazole and levamisole chemotherapy on prevalence and intensity of common soil-transmitted helminth infections in school children, Sierra Leone. - Williams, Roderick; Koroma, Mohamed; Hodges, Mary H. (PubMed, 1997)
A comparison of two studies performed in Sierra Leone on the effect of anthelmintic, chemotherapy, levamisole, albendazole or a placebo in children aged 6 to 10 years on the prevalence and intensity of common soil transmitted helminths (S-THs) infections is presented. In total 501 children were screened, and 394 successfully follow-up. At baseline their overall prevalence and intensity (epg) of Ascaris, Necator and Trichuris were 34% (2,877), 22% (284) and 39% (266) respectively. At baseline there was no significant difference in the intensity of S-THs infections in the different treatment groups but the prevalence of Necator was significantly higher in the levamisole than the albendazole group (p < 0.05). At follow-up both albendazole and levamisole significantly reduced prevalence and intensity of Ascaris and Trichuris. Only albendazole significantly reduced those of Necator. The placebo group had no significant change in prevalence but a significant increase in intensity of all S-THs.
openalex: W46466056 mag: 46466056
Keywords: openalex:import

Prevalence of NIDDM and impaired glucose tolerance in a rural and an urban population in Cameroon - Mbanya, Jean Claude; Ngogang, Jeanne; Salah, J. N.; Minkoulou, EM; Balkau, Beverley (Diabetologia, 1997)
The adoption of Western lifestyles is known to lead to increasing prevalence of non-insulin-dependent diabetes mellitus in Africa, yet epidemiological studies using standardised methods are rare. The prevalence of diabetes and impaired glucose tolerance was determined in a rural and an urban community in Cameroon using the 75-g oral glucose tolerance test and the World Health Organization diagnostic criteria in 719 rural (292 men, 427 women) and 1048 urban (458 men, 590 women) subjects aged 24–74 years. The response rate was 95 and 91 % for the rural and urban population, respectively. The age-standardized prevalence of diabetes in the rural and urban population was respectively 0.9 % (95 % confidence interval (0.2–2.7)) and 0.8 % (0.2–1.8) for men and 0.5 % (0.1–1.6) and 1.6 % (0.7–3.1) for women, and that of impaired glucose tolerance was 5.8 % (3.3–9.4) and 1.8 % (0.9–3.2) for men, and for women, 2.2 % (1.0–4.0) and 2.0 % (0.6–4.5). Although for both men and women the body mass index was higher at all ages in the urban than in the rural area, the 2-h plasma glucose, even after adjustment for age and body mass index, was significantly higher in the rural than in the urban area (p < 0.005, p < 0.002 for men and women, respectively). There was a female excess of diabetes in the urban area and an equal sex distribution in the rural area. In the rural area 67 % (4 of 6) of diabetic subjects were unknown before the survey, compared with 57 % (8 of 14) in the urban area. These data indicate a low prevalence of diabetes in Cameroon; however, the prevalence of impaired glucose tolerance suggests an early stage of a diabetes epidemic. [Diabetologia (1997) 40: 824–829]
openalex: W1984718244 mag: 1984718244
Keywords: openalex:import

The relevance of a needs analysis of life-skills in tertiary students in the current South African milieu - Raijmakers, L. R.; Scholtz, Patsy (Sa Journal of Industrial Psychology, 1997)
This study encompasses a needs analysis of life-skills in 1992, first-year full time students at the Vaal Triangle Technikon, Vanderbijlpark. To evaluate the hypotheses, respondents who completed the self-assessment Life Skills and Competencies: General Questionnaire on Life Competencies and Skills, were divided into language groups (Afrikaans, English, African). Data indicates differences between the needs of the language groups themselves and between male and female respondents. A literature review reveals that first-time entrants into the job market have defective life- and job-skills. The findings of this study confirms the necessity of a life- and job-skills training programme for tertiary students which takes cognizance of language and cultural differences.| Opsomming Die studie behels die uitvoer van 'n behoeftebepaling ten opsigte van, lewenskundighede en vaardighede van voltydse 1992 ingeskrewe eerstejaarstudente aan die Vaaldriekhoekse Technikon, Vanderbijipark. Ten einde die hipotese te evalueer, is respondente wat die self-evaluering Lewenskundighede en Vaardighede: Algemene Vraelys oor Lewenskundighede en Vaardighede, voltooi het, in taalgroepe opgedeel (Afrikaans, Engels en Afrika). Dataverky, dui daarop dat daar wel 'n verskil is tussen die behoeftes van die groepe onderling, asook tussen die behoeftes van manlike en vroulike respondente. 'n Literatuuroorsig toon dat daar leemtes bestaan met betrekking tot lewens- en werkvaardighede van persone wat die arbeidsmark vir die eerste keer betree. Bevindinge bevestig die noodsaaklikheid van lewens- en werkvaardighede-opleidingsprogramme vir tersiere studente wat kennis neem van kultuur- en taalverskille.
openalex: W1999422063 mag: 1999422063
Keywords: openalex:import

A survey of microbial pollution of rural domestic water supply in Ghana - Ampofo, Joseph A. (International Journal of Environmental Health Research, 1997)
A short term, baseline study was undertaken to determine the occurrence and levels of microbial pollution in three major rivers in Ghana- the Birim river, Kakum river and the Nakwa river. Routine bacteriological examinations were made to determine the levels of total coliforms (TC), faecal coliforms (FC) and faecal streptococci (FS). Results obtained showed that TC, FC and FS counts were high in all the three rivers thus making them unsafe to drink untreated water from those sources. Eight of the 10 stations sampled on the Birim river had their source of pollution from human waste while two stations had a livestock source of pollution. Maximum levels of 4448 TC/100 ml, 1848 FC/100 ml and 214 FS/100 ml were obtained in the Birim river. Two of the seven stations sampled on the Kakum river had their source of pollution from human waste with one station having a predominance of human waste in a mixed source of pollution. Two stations had their source of pollution from livestock and poultry and another two predominance of livestock and poultry in a mixed pollution. Livestock and poultry source dominate pollution in the Nakwa river, with two stations recording purely livestock and poultry source and two other stations showing mixed pollution with livestock and poultry source dominating. Two stations showed human source of contamination. There was no correlation between TC and FS levels on one hand, and FC and FS levels on the other hand, at 95% confidence limit. There was significant correlation, however, between TC and FC levels. High socioanthropological activities in the basins of the three rivers were identified as a contributory factor to the later situation.
openalex: W1975239459 mag: 1975239459
Keywords: openalex:import

Diagnostic performance of red cell sorbitol assay in a Nigerian teaching hospital - Anaja, HP (Clinica Chimica Acta, 1997)
The analytical linearity, detection limit, precision and accuracy, as well as diagnostic sensitivity, specificity and predictive values of red cell sorbitol (RCS) assay were evaluated using the fluorimetric enzymatic technique with the available laboratory facilities in a Nigerian Teaching Hospital. The assay was linear up to 40.0 nmol/ml. The detection limit was 0.55 nmol/ml. The within-assay coefficients of variation (CV) from low to high concentrations were in the range of 2.82% to 5.48% while the corresponding values for the between-assay variation were 3.60% to 6.05%. The mean recovery was 90.4%. High concentrations of some common blood constituents and drugs did not cause significant interference. An evaluation of the diagnostic sensitivity and specificity of RCS in 102 out-patients revealed a sensitivity of 94.4%, specificity of 98.8% and efficiency of 98.0%. The predictive value of a positive test was 94.4% while that of a negative test was 98.8%. The mean value of red cell sorbitol in patients confirmed to have diabetes mellitus (23.1 +/- 1.13 SE nmol/g Hb) was significantly higher (P < 0.001) than the corresponding value (11.0 +/- 0.0.27 SE nmol/g Hb) for those without diabetes and for control subject. A similar observation was also made for plasma glucose and fructosamine. These observations demonstrate that RCS assay could be adopted in a third world laboratory for clinical applications.
openalex: W2010533884 mag: 2010533884
Keywords: openalex:import

HIV-related stress at school and at home in Zambia. - Baggaley, R; Sulwe, James; Chilala, Michael; Mashambe, Christine (PubMed, 1997)
There are an estimated 140,000 orphans in Zambia, with 600,000 likely by the year 2000. 19 randomly sampled schoolteachers from Lusaka were interviewed to learn how the HIV epidemic affects their professional and personal lives. HIV has a wide-ranging impact upon teachers in the classroom. Each teacher had students who had lost both parents to AIDS, many teachers had several orphans in their class, and student absenteeism to care for sick adults and younger siblings at home interferes with the ongoing in-school learning process. Some students have even become ill and died from what has often thought to be AIDS-related causes. Outside of the classroom, many teachers were troubled by the loss of relatives, friends, and colleagues due to AIDS, and concerned that they and/or their children may become infected or are already infected with HIV. Schoolteachers need to be given support, trained to manage the emotional consequences of HIV, and provided with educational materials to help them cope with HIV-related stress.
openalex: W2295427287 mag: 2295427287
Keywords: openalex:import

Creating a legal framework to support the provision of high quality education in South Africa - Beckmann, Johan (Education And The Law, 1997)
(1997). Creating a legal framework to support the provision of high quality education in South Africa. Education and the Law: Vol. 9, No. 2, pp. 123-143.
openalex: W2000708395 mag: 2000708395
Keywords: openalex:import

Their Highest Potential: An African American School Community in the Segregated South. - Berkeley, Kathleen C.; Walker, Vanessa Siddle (The Journal of American History, 1997)
Journal Article Their Highest Potential: An African American School Community in the Segregated South. By Vanessa Siddle Walker. (Chapel Hill: University of North Carolina Press, 1996. xvi, 259 pp. Cloth, $34.95, ISBN 0-8078-2276-0. Paper, $14.95, ISBN 0-8078-4581-7.) Get access Kathleen Berkeley Kathleen Berkeley University of North Carolina, Wilmington, North Carolina Search for other works by this author on: Oxford Academic Google Scholar Journal of American History, Volume 84, Issue 1, June 1997, Pages 286–287, https://doi.org/10.2307/2952854 Published: 01 June 1997
openalex: W2906032337 mag: 2906032337
Keywords: openalex:import

Groundwater Management in Drought-prone Areas of Africa - Calow, Roger; Robins, Nick; MacDonald, Alan; Macdonald, David; Gibbs, B.R.; Orpen, W. R. G.; Mtembezeka, P.; Andrews, Anita; Appiah, Samson Obed (International Journal of Water Resources Development, 1997)
Abstract The issues pertaining to groundwaterdrought are reviewed with particular regard to the historical and present situations in Malawi, northern Ghana and the Northern Province of South Africa. These three quite different examples highlight some of the major difficulties facing respective governmentsand donor agencies, not least the shortcomingsof drought-reliefdrilling programmes,the general lack of routine monitoring and the need for longer term analysis and assessment of groundwatersystems than is currently possible. The distinct character of groundwater systems and their reaction to prevailing and changing environmentalconditions is discussed, and it is argued that essentially predictable variations in groundwater drought vulnerability are rarely planned for or acted upon. Managementissues arising are discussed and it is suggested that governments,and particularly donors, should place more emphasis on longer term, pre-droughtmitigation measures to reduce the need for costly and sometimes ineffective emergency interventions.
openalex: W2055891067 mag: 2055891067
Keywords: openalex:import

Responses to Descriptions of Bias against African Americans among Euro-American Students Enrolled in Colleges of Education and Journalism - Carroll, Jane J. (Perceptual and Motor Skills, 1997)
Responses to descriptions of racial bias toward African Americans by 84 Euro-Americans did not differ among Euro-American upper level students enrolled in Colleges of Education and Journalism.
openalex: W2314890557 mag: 2314890557
Keywords: openalex:import

Assessment of environmental pollution by PCBs, DDT and its metabolites using human milk of mothers in Zimbabwe - Chikuni, Ordias; Nhachi, Charles; Nz, Nyazema; Polder, Anuschka; Nafstad, Inger; Skaare, Janneche Utne (Science of The Total Environment, 1997)
The milk samples were collected from mothers who had lived in the area for at least 5 years, healthy and breast feeding their first, second or third child. Of the 175 mothers' milk samples analysed, the organochlorine pesticide residues were detected in the following order of frequency: pp-DDE, 100%; pp-DDT, 98%; and sum PCB, 53%. Of all the seven areas analysed the Kariba area had the highest mean level of sum DDT—25 259 ng/g milk fat and the lowest mean level of sum DDT of 1607 ng/g milk fat was found in Esigodini which is a rural area. The major DDT metabolite was pp-DDE. The ratio of pp-DDTpp-DDE was highest in Kariba (0.6) suggesting recent pollution by DDT in that area. The results show that the vector control programmes (extensive pesticide spraying of disease-carrying pests, such as mosquitoes and tsetse files), agricultural activities and dietary habits were the main contributing factors towards the high levels of pesticides in most of the areas. Kadoma area had the highest mean level of sum-PCB (60 ng/g milk fat).
openalex: W1968883547 mag: 1968883547
Keywords: openalex:import

Achievement in School in Relation to Simultaneous and Sequential Cognitive Processes among Young Egyptian Students - Elwan, Fadia (Perceptual and Motor Skills, 1997)
The present study was designed to examine whether a relationship exists between scores on simultaneous and sequential cognitive processes, on one hand, and performance on the Reading Decoding and Arithmetic subtests of the Kaufman Assessment Battery for Children (K–ABC), on the other hand, using a sample of 170 Egyptian school children in Grades 1, 3, and 5. To examine the differential magnitudes of the relationship between scores for cognitive processing and school achievement a two by two (simultaneous × sequential) analysis of variance was calculated with reading decoding and arithmetic scores as dependent variables. The results indicated that cognitive processing, especially simultaneous synthesis, is related to arithmetic as well as decoding during reading. Scores on sequential processing were not significantly related to scores for decoding reading and may not be important as simultaneous processing for mathematical skills. The findings were interpreted in the context of the Arabic orthographic system and in view of the nature of the cognitive and mathematical tasks employed in this study.
openalex: W2029102013 mag: 2029102013
Keywords: openalex:import

Challenges of Education for Library and Information Work in Nigeria in the 21st Century - Fayose, Philomena O. (Information Development, 1997)
Edited version of a paper presented at the 48th FID/ET Conference, Graz, Austria, 21st–25th October, 1996. Attempts a critical analysis of current library and information services and education for library and information work in Nigeria. Provides a short history of library education and Western library orientation. Examines the information environment of Nigeria and proposes a new philosophy for library and information services in the country based on its sociocultural conditions. Discusses the programmes of the Department of Library, Archival and Information Studies, University of Ibadan and suggests modifications to existing courses and some entirely new courses. Emphasizes the need to provide adequate funding and infrastructures for tertiary education in general and for education for library and information work in particular. Librarianship is a practical profession, therefore opportunities for practical activities at various levels ought to be provided.
openalex: W2150786843 mag: 2150786843
Keywords: openalex:import

The Costs and Benefits of Doctoral Education in Economics in South Africa - Hosking, Stephen (South African Journal of Economics, 1997)
South African Journal of EconomicsVolume 65, Issue 2 p. 112-117 The Costs and Benefits of Doctoral Education in Economics in South Africa S G HOSKING, S G HOSKING Associate Professor, Department of Economics and Economic History, PO Box 1600, University of Port Elizabeth, Port Elizabeth, South Africa. This paper is drawn from Chapter 4 of an unpublished report commissioned by the African Economic Research Consortium on “Doctoral Education in Economics: South Africa” (December, 1995), by Black, P.A., Horton, C.M. and Hosking, S.G. The assistance provided by the University of Port Elizabeth and the comments of Prof. P. Black, the anonymous referees and the editor of the South African Journal of Economics are gratefully acknowledged.Search for more papers by this author S G HOSKING, S G HOSKING Associate Professor, Department of Economics and Economic History, PO Box 1600, University of Port Elizabeth, Port Elizabeth, South Africa. This paper is drawn from Chapter 4 of an unpublished report commissioned by the African Economic Research Consortium on “Doctoral Education in Economics: South Africa” (December, 1995), by Black, P.A., Horton, C.M. and Hosking, S.G. The assistance provided by the University of Port Elizabeth and the comments of Prof. P. Black, the anonymous referees and the editor of the South African Journal of Economics are gratefully acknowledged.Search for more papers by this author First published: 22 August 2005 https://doi.org/10.1111/j.1813-6982.1997.tb01362.xAboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinked InRedditWechat Volume65, Issue2June 1997Pages 112-117 RelatedInformation
openalex: W2002496714 mag: 2002496714
Keywords: openalex:import

Critical pedagogy and the public sphere: Comparative perspectives in education in South Africa and the United States - Jackson, Shannon M. (Social Dynamics, 1997)
(1997). Critical pedagogy and the public sphere: Comparative perspectives in education in South Africa and the United States. Social Dynamics: Vol. 23, No. 2, pp. 19-56.
openalex: W2128180647 mag: 2128180647
Keywords: openalex:import

Fatigue performance of 6261-T6 aluminium alloy – constant and variable amplitude loading of parent plate and welded specimens 1This work was performed while M.N.J. was with the School of Process and Materials Engineering, University of the Witwatersrand, WITS 2050, South Africa. 1 - James, M.N.; Paterson, Anthony H.J. (International Journal of Fatigue, 1997)
The work reported in this paper is a summary of the results obtained from several projects run over a five year period. A number of thrusts were encompassed in the project scope, which was to examine the fatigue strength of extruded 6261-T6 I-beams with centrally located, welded cover plates under constant amplitude (CA) and variable (two-level repeated block) amplitude (VA) loading. The CA part of the work examined the effect of cover plate geometry, specimen size, thermal and vibratory stress relief, and differences in fabrication quality on fatigue performance. A number of cases were identified which gave rise to cross-overs in performance in moving from shorter to longer fatigue lives. The aim of the VA part of the work was to identify situations which might give rise to fatigue lives shorter than predicted by linear damage summation models, such as Miner's rule. Two such cases were identified: specimens which had been subjected to vibratory stress relief; and specimens in which weld `quality' (as assessed by profile, heat affected zone hardness, extent and microstructure) varied. Explanations for these observations are proposed and supported by interpretation of a two-level block of small fatigue crack growth.
openalex: W2155616637 mag: 2155616637
Keywords: openalex:import

Mathematics Achievement and Attitudes of Senior Secondary-School Students in Transkei, South Africa - Kulubya, Mathlas M.; Glencross, Michael J. (Psychological Reports, 1997)
In a study of mathematics achievement and attitudes toward mathematics, a sample of 266 Standard 10 (Grade 12) students (98 boys and 168 girls) from 10 senior secondary schools in the Umtata district of Transkei, South Africa, were administered a mathematics achievement test and an attitude questionnaire. Contrary to other studies analysis showed no significant relationship between students' scores on measures of mathematics achievement and attitudes.
openalex: W2036722524 mag: 2036722524
Keywords: openalex:import

Towards a New Multilingual Language Policy in Education in South Africa: different approaches to meet different needs - Martin, Douglas L. (Educational review, 1997)
Abstract This paper discusses some of the issues involved in developing a multilingual language policy in education in South Africa: the influence of the historical context, the language demography and patterns of language use in South Africa, the attitudes of learners, parents and teachers towards the multilingual language policy in education, the range of multilingual education models operating in other countries and the influence of resources in the debate. It draws on two research projects carried out in KwaZulu Natal and in North West Province. The paper argues that for a multilingual language policy in education developed at government level within a national framework, there needs to be the flexibility for each province and each school and classroom to implement the policy to meet the needs of their learners within their resources.
openalex: W2010606182 mag: 2010606182
Keywords: openalex:import

Volcanic and nonvolcanic rifted margins of the Red Sea and Gulf of Aden: Crustal cooling and margin evolution in Yemen - Menzies, Martin; Gallagher, Kerry; Yelland, Andrew; Hurford, Anthony J. (Geochimica et Cosmochimica Acta, 1997)
New apatite fission track (AFT) data from the southern Red Sea volcanic and the Gulf of Aden nonvolcanic margins provide important constraints on the timing of crustal cooling relative to periods of volcanism and lithosphere extension. The AFT data define several regions of extension immediately adjacent to the Red Sea margin with AFT ages < 25 Ma and track-length distributions consistent with rapid cooling. Elevated Precambrian basement highs on the rift shoulder have AFT ages ⪢ 100 Ma and track-length distributions indicative of a complex pre-rift history. An intervening area along the Red Sea and Gulf of Aden margins, and inland along the Balhaf graben (Jurassic rift), has AFT ages of 25–100 Ma. and track-length distributions indicative of rapid cooling. Elevated Precambrian basement highs are juxtaposed against topographically lower extended coastal terranes with sharp contrasts in AFT ages and track-length distributions, pointing to possible reactivation in the Tertiary of lineaments of Precambrian and Jurassic age. Integration of field observations with AFT data and 40Ar/ 39Ar data indicates that, on the Red Sea volcanic margin, surface uplift was initiated immediately prior to volcanism and that cooling was synchronous with widespread extension and an apparent hiatus in voluminous volcanic activity.
openalex: W2003812756 mag: 2003812756
Keywords: openalex:import

Social Acceptance of Children with Intellectual Disabilities in an Integrated School Setting in Zambia: a pilot study - Nabuzoka, Dabie; Rønning, John A. (International journal of disability, development and education, 1997)
Abstract The social acceptance of a group of Zambian primary school children with intellectual disabilities by two groups of nondisabled children was examined. One group were in direct contact with the children with disabilities over a period of six months while the other was not. Nondisabled boys who had been in contact with children with disabilities had more positive attitudes than boys who had no direct contact, while no exposure effects were observed amongst girls. Gender differences amongst nondisabled children who had contact with peers with disabilities were not significant. Amongst the nondisabled children who had no contact with children with disabilities, girls had more positive attitudes than boys. The findings are preliminary, but offer directions for further research and have some implications for integrating children with disabilities into mainstream schools.
openalex: W2003394465 mag: 2003394465
Keywords: openalex:import

Use of Acetylcholinesterase in Perna perna and Mytilus galloprovincialis as a Biomarker of Pollution in Agadir Marine Bay (South of Morocco) - Najimi, S.; Bouhaimi, Abdellah; Daubèze, M.; Zekhnini, A.; Pellerin, J.; Narbonne, J.; Moukrim, Abdellatif (Bulletin of Environmental Contamination and Toxicology, 1997)
openalex: W2039546008 mag: 2039546008
Keywords: openalex:import

Education and development in Africa - Nwomonoh, J. N. (1997)
openalex: W2798795497 mag: 2798795497
Keywords: openalex:import

Structural Adjustment and Gender Access to Education in Nigeria - Obasi, Emma (Gender and Education, 1997)
ABSTRACT The article reports on relative gender access to secondary (grammar) school education from 1977 to 1990 in Imo State, Nigeria. To this end, time series data on secondary (grammar) school enrolment in Imo State from 1977/78 to 1989/90 were analysed. The findings are: (i) the existence of a gender imbalance in access to grammar school education in which the participation rate for girls was less than 40% up to 1980/81. This is discussed with reference to the prevalence of a gender-biased tradition which restricts girls' access to education; (ii) the dramatic overturning of the gender enrolment imbalance, in favour of girls, from 1981/82 when girls' participation rate in secondary education reached a peak of 56%. This is attributed to the nationwide implementation of a 6-year programme of free and compulsory Universal Primary Education (UPE) in Nigeria from 1976. The free and compulsory UPE scheme (which removed the traditional constraints on female education)had the immediateeffect of causing a phenomenal growth in primary school enrolment that was paralleled in the secondary sector in 1981/82; and (iii) the decline in access to grammar school education, more marked for girls than for boys, since 1986 when free market reform structural adjustment policies (SAP) prescribed by the International Monetary Fund (IMF) and the World Bank were introduced in Nigeria. The SAP was accompanied by enormous financial and economic hardship which militate against access to education for the majority of poor Nigerians and for girls in particular. These findings are consistent with reported findings elsewhere in 'adjusting' countries. It is concluded that the financial rigours of the structural adjustments that havebeen imposed on such countries militate against the United Nations Children's Fund and United Nations Educational, Scientific and Cultural Organisation commitments to the elimination of all policies that hinder gender access to education in Africa and the global vision of education for all by the year 2000.
openalex: W2050524156 mag: 2050524156
Keywords: openalex:import

Profile of dementia in a Nigerian community–types, pattern of impairment, and severity rating. - Ogunniyi, Adesola; Gureje, Oyewusi; Baiyewu, Olusegun; Unverzagt, Fred; Hall, Kathleen; Oluwole, Steve; Osuntokun, B. O.; Hendrie, Hugh C. (PubMed, 1997)
Out of 2494 subjects screened in a Nigerian community, 28 patients with dementia were identified. Alzheimer's disease was diagnosed in 18 patients (64.3%), 16 of whom had probable Alzheimer's disease. Eight patients (28.6%) had vascular dementia while one patient each had parkinsonism with dementia and depression with dementia. Patients with Alzheimer's disease were significantly older, predominantly females and illiterates. Cognitive deficit commonly took the form of memory and judgment impairment while financial mismanagement was the most frequent impaired activity of daily living. More than half of the cases had mild disease on severity rating and were comprised mainly of Alzheimer's disease subjects. These results confirm the higher frequency of Alzheimer's disease over the other types as reported in other communities.
openalex: W148040010 mag: 148040010
Keywords: openalex:import

Geochemistry and mineralization of Buru and Kuge volcanic carbonatite centres, Western Kenya - Onuonga, Isaac Oriechi (1997)
openalex: W2917504538 mag: 2917504538
Keywords: openalex:import

The Dreamkeepers: Successful Teachers of African American Children - Peele, Tryphenia B. (Anthropology & Education Quarterly, 1997)
The Dreamkeepers: Successful Teachers of African American Children. Gloria Ladson‐Billings. San Francisco: Jossey‐Bass Publishers, 1994. 187 pp.
openalex: W1852816657 mag: 1852816657
Keywords: openalex:import

Inheritance Patterns of Morphological Traits Related to Drought Tolerance in New Guinea Impatiens - Quene, Robert J.; Strefeler, Mark S. (Hortscience, 1997)
Three drought-tolerant and four drought-susceptible breeding lines from the Univ. of Minnesota's New Guinea impatiens breeding program were crossed in all combinations (reciprocals and selfs) using a complete diallel crossing scheme. Progeny of each cross were grown using standard cultural practices and data was taken on the morphological traits shown to be related to drought tolerance in previous studies. Data was taken on leaf thickness, leaf width, leaf length, leaf area, and leaf dry weight. From these data the leaf length:width ratio and leaf dry weight/unit area (g·cm –2 ) were calculated. Mean squares for general and specific combining ability were estimated using Griffing's Model 1, Method 4. Differences between crosses were highly significant ( P < 0.001) for all traits examined. Means squares for specific (SCA) and general (GCA) combining ability were significant indicating that both additive and non-additive gene effects are important in the inheritance patterns of these characters. For all traits, GCA was greater than SCA indicating that the additive component had the greatest influence on gain from selection for these traits. These findings agree with other estimates of GCA and SCA for these characters in other crops species. The importance of non-additive effects (SCA) on inheritance of these traits explains why we were able to make rapid improvement in drought tolerance in New Guinea impatiens and the role of additive effects (GCA) on drought tolerance indicates that we can continue to make substantial progress improving drought tolerance in New Guinea impatiens. The impact of these findings on strategies to improve drought tolerance in New Guinea impatiens will be discussed in this presentation.
openalex: W2586985733 mag: 2586985733
Keywords: openalex:import

Blindness and visual impairment in a region endemic for onchocerciasis in the Central African Republic - Schwartz, Ellen C; Huss, Richard W.; Hopkins, Adrian; Dadjim, B; Madjitoloum, P; Hénault, C; Klauß, Volker (British Journal of Ophthalmology, 1997)
AIMS A population based survey of blindness and visual impairment was conducted in the district of Bossangoa, Central African Republic. Methods—A total of 48 communities were randomly selected, and 6086 people examined. RESULTS The prevalence of blindness (visual acuity in the better eye less than 3/60) was 2.2%, and visual impairment 3.0% (6/24 to 3/60 in the better eye). The major causes of blindness were onchocerciasis (73.1%), cataract (16.4%), trachoma (4.5%), and glaucoma (2.2%). CONCLUSION Around 95.5% of all blindness could potentially have been prevented or treated. Ivermectin mass distribution is hoped to prevent 50% of all forms of visual loss in the future.
openalex: W1986317516 mag: 1986317516
Keywords: openalex:import

A comparison of AIDS-related sexual risk behaviors among African-American college students. - Se, Taylor; Dilorio, Colleen; Tt, Stephens; Je, Soet (PubMed, 1997)
This article compares the sexual practices and risk-taking behaviors of African-American male and female college students (n = 649) attending 4-year institutions in a major southeastern metropolitan area. It is a descriptive study of the kinds of practices that put African-American college students at a high risk of contracting the human immunodeficiency virus (HIV). Overall, the reported practices indicate that the college students studied are exposed to risk by certain sexual behaviors, with males reporting significantly higher frequency of risk behaviors than females. The percentages of male students reporting they engage in an array of risky sexual practices (including sex without condoms and anal intercourse) suggest the invulnerability to HIV apparently perceived by this group. Although the students overall adhere to some HIV-preventive behaviors, they also violate important HIV prevention practices. The findings illuminate the need for designing and conveying messages for African-American college students, and particularly for males, that impress the realities of acquired immunodeficiency syndrome (AIDS) as an indiscriminant disease on this group.
openalex: W54883353 mag: 54883353
Keywords: openalex:import

Formal vs. Non-Formal Vernacular Education: The Education Reform in Papua New Guinea - Siegel, Jeff (Journal of Multilingual and Multicultural Development, 1997)
A community-based non-formal education movement in Papua New Guinea has led to hundreds of the country's more than 800 languages being used to teach initialliteracy in local preschool and adult education programmes. The central government, with the help of overseas aid donors, has now embarked on a massive reform of the English-only formal education system. The first three years of formal education will be in vernacular languages at newly established Elementary Schools, run by local communities. But there is a great deal of controversy about the feasibility of the reform and its potential effects on the highly successful non-formal vernacular education movement. This paper describes this movement, the proposed reform and the conflicts between them, demonstrating the importance of community support and non-government organisations in educational language planning initiatives.
openalex: W2129593456 mag: 2129593456
Keywords: openalex:import

A medical school in Zambia - Sims, Peter A. (Journal of public health (Print), 1997)
The Medical School in Zambia was founded in 1968, some four years after independence. The first graduates qualified in 1973, and over the intervening 23 years there have been some 700 medical graduates, 600 of them Zambian.These doctors are now working all over the world, and the standard of their training compares favourably with that at medical schools of North America and Europe. This story of success, against a worsening financial situation and with deteriorating amenities, has to be tempered by the fact that only 100 Zambian graduates are today working in the country and 50 of those are in private practice. Thus the idea of training Zambian doctors in Zambia for the Zambian health care system has been found unworkable. How many doctors and what sorts of doctor does Zambia need now? These are crucial questions. WHO estimates for this type of country and at this stage of development would suggest one doctor per 5000-10000 people, and with a population of 9 million this argues for some 1000-1500 doctors for the country, with the necessary support of clinical officers, nurses and other health professionals. There are some 800 doctors working in Zambia today and registered with the Zambian Medical Council. Thus there is a considerable shortfall. Many of the doctors working are non-Zambian and are on short-term contracts. It has been very difficult to retain Zambian graduates within the country, largely owing to poor conditions of service, lack of career structure and an unsatisfactor y professional experience. The Medical School in Lusaka is in the process of examining its own contribution to redressing this balance. It is reviewing the suitability of the teaching and learning provided, and its emphasis upon primary care and community based education. It is even asking the hard question - do we need a medical school? Assuming the answer is yes, then what sort of school and what sort of curriculum will be most effective in providing the Zambian doctors for the twenty-first century? Does the sort and style of medical school make a difference? Ten years after qualifying, is it possible to tell the difference between the doctor educated at McMaster and the one in Lusaka? The essential
openalex: W2145970718 mag: 2145970718
Keywords: openalex:import

The School Improvement Project of the Aga Khan Education Service: Uganda. Evaluation Report Prepared for the Aga Khan Foundation. - Siraj‐Blatchford, Iram; Odada, Matthew; Omagor, Martin (1997)
openalex: W334492344 mag: 334492344
Keywords: openalex:import

Quality Assurance with Respect to University Teaching in South Africa: a narrative analysis - Webbstock, Denyse (Assessment & Evaluation in Higher Education, 1997)
Abstract In this paper, national research projects underway which are aimed at establishing national standards on lecturing capabilities within a new national qualifications framework, are argued to typify a policy narrative informed by functionalist understandings of education, curriculum and evaluation. This narrative is counter‐posed with two others, found largely but not exclusively in the historically white liberal English‐speaking universities, which critique that narrative, arguing that curriculum development, the evaluation of courses and programmes, and the assessment of teaching, are complex activities which are context‐bound, and incapable of being reduced to the measurement of the performance of certain capabilities. In the analysis undertaken in the paper, the two critiques identified are argued to be at odds with the dominant policy narrative partly because, although much of the language and the intentions are similar, at base lie fundamentally different concepts of quality. The dominant narrative is argued to regard quality as ‘fitness for purpose’, where the overall purpose of higher education is assumed to be singular and uncontested, and as meeting certain pre‐specified standards. The critiques understand quality either in the liberal sense as an absolute to be aspired to, or in a more constructivist way, as significantly adding to existing levels of development in particular sectors, thereby contributing to greater justice and equality in South African society. These different understandings have different implications for the assurance of quality in university teaching. The power differentials between the narratives are explored and it is argued that unless a way is found to accommodate the different perspectives, resistance to the dominant narrative might undermine its implementation. In this paper a metanarrative ‘told’ by the comparison of the three narratives, which attempts to take into account the conceptual dissonance examined, is put forward. It is suggested that, in order to lead to a policy‐relevant narrative on quality assurance with respect to university teaching, a conceptual distinction between ‘quality’ and ‘standards’ be made. With this conceptual separation, policies may be developed to assure both standards and quality, using different methodologies and different implementing bodies in such a way that potential resistance to the dominant narrative may be averted.
openalex: W2020837312 mag: 2020837312
Keywords: openalex:import

The talented ten: Supporting African American male college students - Wright, Richard C.; McCreary, Micah L. (Journal of African American men, 1997)
openalex: W2074007049 mag: 2074007049
Keywords: openalex:import

The Need for Leadership and Management Training for Community Nurses: Results of a Ugandan District Health Nurse Survey - Ziegler, Priscilla B.; Anyango, Henerika; Ziegler, Henry (Journal of Community Health Nursing, 1997)
A joint Ugandan-American team conducted a nonrandom convenience survey of 14 Ugandan district health nurses from 12 of Uganda's 39 districts. The survey was designed to (a) identify what senior nursing personnel are actually doing in Ugandan districts, (b) determine whether these nurses believe that their nursing education prepared them for their roles, and (c) discover what these nurses believe should be added to the basic nursing curriculum to better prepare district nurses for their jobs. Supervision and general management made up the largest portion of the current district health nurse's actual and perceived roles. The nurses varied on how well their nursing education prepared them for their roles, but the majority voiced a need for further training in management skills. None of the nurses perceived herself to be a leader, and most displayed an inability to prioritize within their work settings.
openalex: W2035536263 mag: 2035536263
Keywords: openalex:import

An assessment of the quality of care given to, and hygiene on patients at a teaching hospital in Namibia - Dyk, Agnes Van; Small, LF (Curationis, 1997)
An assessment was done during 1991 to evaluate the quality of care with regard to mouth hygiene rendered to patients in a teaching hospital in Namibia. The sample was drawn from nine wards. By means of a type of quota sampling, the patients were categorised as dependent, interdependent or independent. The nursing process was used as a framework for the study. From the assessment it became evident that no policies existed with regard to oral hygiene. Planning was not in every case based on assessment, and it seemed that when planning(s) were done, it was not always implemented. Record keeping was the aspect most poorly attended to.
openalex: W1963923007 mag: 1963923007
Keywords: openalex:import

The October 30, 1994, seismic disturbance in South Africa: Earthquake or large rock burst? - Bowers, David (Journal of Geophysical Research, 1997)
The relative amplitude method is applied to body waves recorded at teleseismic distances from the October 30, 1994, m b 5.6 seismic disturbance, in South Africa, to determine the source depth and moment tensor. The results indicate that the source is shallow and that moment tensors with a positive volume change component are inconsistent with the observations. Observations of R g in the frequency range 0.5–2.0 Hz at two regional distance stations also indicate that the source is shallow (less than about 3 km deep). Three‐component broadband and long‐period seismograms recorded at regional distances show strong Love wave excitation and a lobed Rayleigh radiation pattern, observations that are inconsistent with collapse mechanisms recently proposed for some large rock bursts (mine tremors). Modeling of teleseismic broadband P and regional distance surface waves shows that the source depth is shallow (2–3 km) and that the observed source radiation is consistent with that expected from a 45° normal dip‐slip fault. The results of the modeling are confirmed by reports from the mining region that the disturbance was a mine tremor caused by slip on the Stuirmanspan Fault in the President Brand mine at a depth of between 2 and 3 km. The close match between observed and synthetic P and Rayleigh wave amplitudes suggests that the explosion‐like m b : M s of the mine tremor ( m b 5.6, M s 4.7) is attributable to the effect of the mechanism and the shallow depth of the source. The above results are at odds with those of Fan and Wallace [1995], who interpreted this disturbance as an earthquake at a depth of 12 km, based on a broadband inversion of three‐component waveforms from two regional distance stations. This study confirms the need to interpret both broadband waveforms (to match amplitude and polarity) and short‐period waveforms (to confirm (relative) onset times in the model structure) if inversion of regional broadband waveforms is to provide a reliable estimate of the moment tensor and source depth.
openalex: W2087618732 mag: 2087618732
Keywords: openalex:import

Factors Influencing African Americans To Select Teaching Careers In Vocational Education And Experiences That Relate To Their Progress In Vocational Teacher Licensure Programs - Evans, Jewel Lynn (1997)
openalex: W2587514265 mag: 2587514265
Keywords: openalex:import

Comprehensive timber harvest planning for plantation forests on difficult terrain : Sokoine University of Agriculture Training Forest, Tanzania - Shemwetta, Dunstan T. K. (1997)
openalex: W1498565184 mag: 1498565184
Keywords: openalex:import

Blood demand in a teaching Hospital in Ghana. - Acquaye, Jane; Aryee, M E (PubMed, 1997)
The blood requirement per acute hospital bed and the pattern of the supply were determined using the number of units of blood supplied to the various wards of the Korle Bu Teaching Hospital between 1987 to 1993. The mean yearly supply and mean monthly supply and their standard deviations were determined. The former was used to calculate the blood needs per bed in the clinical departments and also per adult and paediatric bed respectively. The rainfall figures in mm per month and year were used to determine the mean rainfall for the various months and years under study. This was superimposed over the blood requirement. There were 1143 adult acute beds with blood requirement of 5.16 units per bed compared with 231 paediatric beds needing 9.2 units per bed. The mean blood requirement per acute hospital bed which is found to be applicable also to regional hospitals is 5.5. Paediatric blood usage was extremely high in July to September after the April to July rains and also very high in the years with the highest rainfall.
openalex: W47721472 mag: 47721472
Keywords: openalex:import

The Perception of Ability Scale for Students (PASS) in Africa and New Zealand - Akande, Adebowale (School psychology international, 1997)
The present study investigates the Perception of Ability Scale for Students (PASS) which is purported to measure six academic self-concept dynamic factors evident in children. Although previous analyses of PASS among New Zealand children have suggested only Penmanship/Neatness subscale did not yield a significant effect, corresponding analyses among non-Western children have not yet been undertaken in any satisfactory manner. To this end, the present article, reports the treatment by two-way analyses of variance for the PASS on an African sample of 204 Form 2 or Grade 6 students enrolled in various elementary schools. The results suggest the scale does not appear to have a ceiling effect which prevents differentiation of normally-achieving and learning-disabled groups from those of gifted ones. The results also indicate that in comparison with normally-achieving children, the learning-disabled (LD) children are characterized by significantly more negative perceptions of ability and negative academic self-concept, along with tendencies towards learned helplessness and lower achievement expectations for future success in school. The Perception ofAbility Scale for Students is not only a new addition to the field of academic selfconcept measurement, but also a major breakthrough for assessing children's cognitive-motivational variables without the difficulties associated with self-report questionnaires. Nevertheless, the degree of variation across both studies and samples suggests that further refinement of the PASS is required in order to improve its reliability and robustness.
openalex: W2088745973 mag: 2088745973
Keywords: openalex:import

Relatorio Final Sobre o Ensino Bilingue: Resultados da Avaliacao Externa da Experiencia de Escolarizacao Bilingue em Mocambique (PEBIMO) (Final Report on Bilingual Education: Results of External Evaluation of an Experiment in Bilingual Education in Mozambique). - Benson, Carolyn J. (1997)
openalex: W67423675 mag: 67423675
Keywords: openalex:import

Safe Houses in the Contact Zone: Coping Strategies of African-American Students in the Academy - Canagarajah, A. Suresh (College Composition and Communication, 1997)
gage in what Mary Louise Pratt calls the literate arts of the contact zone. Inspired by the extraordinary intercultural tour de force of a 17th century autoethnographic text from the non-literate Quechua community which expresses opposition against Spanish imperialism (34), Pratt celebrates the creative modes of text construction taking place in situations of cultural contact both inside and outside the academy. But, while acknowledging such fascinating examples of linguistic/literary resistance, we must remember that minority communities also inherit traditions of accommodation deriving from legacies of domination. Henry Giroux reminds us that subordinate cultures are situated and recreated within relations of domination
openalex: W38371969 mag: 38371969
Keywords: openalex:import

Relaxation is impaired in the diaphragm muscle of the cardiomyopathic Syrian hamster. - Coirault, Catherine; Chemla, Denis; Pourny, J. C.; Lambert, Francine; Riou, Bruno; Lecarpentier, Yves (American Journal of Respiratory and Critical Care Medicine, 1997)
Relaxation was examined in diaphragm muscle strips of cardiomyopathic Syrian hamsters and control hamsters. Isotonic lengthening velocity and isometric tension decay were analyzed over the load continuum in response to twitch. For each load level (P), we measured the maximum extent of shortening (deltaL), the peak lengthening velocity (VL), and the peak rate of tension decline (-dP/dtmax). The kinetics of sarcomere length (SL) were simultaneously measured by laser diffraction. In an attempt to account for the influence of shortening and/or load on relaxation, we calculated the slopes of the VL - deltaL and -dP/dtmax - P relationships. In both groups, there was a direct relationship between (1) VL and deltaL and (2) -dP/dtmax and P. In myopathic hamsters, we observed a decrease in the slope of the VL - deltaL relationship (p < 0.05), a decrease in VL at any common value of both muscle and sarcomere extent of shortening, and an increase in the duration of overall lengthening. Isometric tension decay was significantly prolonged in myopathic muscle strips, while the -dP/dtmax - P relationship was not significantly different than in controls. At low-to-medium loads, SLs at the onset of tension decline were greater in myopathy. These data indicate that relaxation of the diaphragm was both slowed and prolonged in myopathic Syrian hamsters.
openalex: W2167367869 mag: 2167367869
Keywords: openalex:import

South Africa revolutionises HIV prevention and education strategies - Crowe, Sam (The Lancet, 1997)
Based on the results of surveys that screened women attending prenatal clinics in November 1996 for human immunodeficiency virus (HIV), it is estimated that 2-4 million people in South Africa are HIV-positive and that 90,000 of them will develop acquired immunodeficiency syndrome (AIDS) by the end of 1997. According to Rose Smart, director of the national AIDS control program of South Africa's Ministry of Health, a pilot project developed in KwaZulu-Natal by the African Medical Research Foundation (AMREF) would be incorporated into the national AIDS strategy. In KwaZulu-Natal, 27.5% of prenatal-care clients tested positive for HIV in 1996, an increase from 14.4% in 1994. Based on the AMREF model, peer education groups among local sex workers in each South African province and campaigns in truck firms will be employed to increase use of condoms and knowledge of the disease. William Okedi, head of AMREF South Africa, said that the pilot had sprouted from earlier ideas developed at Kibwezi and Machineng in Kenya, where truckers and sex workers had been targeted along the Mombassa-Miabe highway and in Mwanza, Tanzania. Since a randomized, controlled trial conducted in Mwanza, Tanzania demonstrated that simple management of sexually transmitted diseases (STDs) decreased HIV seroprevalence by 42%, STD treatment will also be incorporated into the prevention measures. According to Okedi, the new strategy will aid the human rights of sex workers, who can be arrested for carrying condoms. He added that adolescents in schools would be the next targets.
openalex: W1992400527 mag: 1992400527
Keywords: openalex:import

The phenomenon of studying while working in Nigerian universities: preliminary report on NCE teachers - Duyilemi, B.O. (International Journal of Lifelong Education, 1997)
This study examined the phenomenon of studying while working (SWW) as curriculum development programmes in three Nigerian universities. The three universities which were randomly selected are among those which admit Nigeria Certificate in Education (NGE) teachers as direct entrants to study for their first degrees (BScEd, BAEd, or BEd). The research design used was the Analytical Survey type. All the final‐year sandwich‐degree education students in the three universities for the 1992‐93 vacation period formed the population for the study. The research instrument was Questionnaire for Studying While Working (QSWW). Constructed and validated by the author, the instrument exhibited a reliability coefficient of 0.74 at the 0.05 level of significance. Five hundred randomly selected participants were used for the analysis. This figure was made up of 340 males and 160 females from science and non‐science disciplines. In descending order of magnitude, reasons which prompt people to choose to study while they work are 85.43 % for improvement of academic qualifications, > 76.25 % for accomplishing self‐actualisation, > 68.16% for usefulness to the society, > 58.44% for effective performance of teaching job, > 57.0% for mental and social development, > 53.50% for job security, > 52.08% for overcoming inferiority complex, etc. Findings also show that NCE holders teach more courses in senior secondary school classes than they teach in junior secondary school. This is especially so in Science and Mathematics. Andragogical and pedagogical problems as encountered and reported by the sandwich students came mainly from courses handled by lecturers who are not professionally qualified. Suggestions for further research point to those areas which need more clarification in order to elucidate some facts and variables connected with current issues in SWW.
openalex: W1994543414 mag: 1994543414
Keywords: openalex:import

[Influence of socioeconomic conditions on the occurrence of intestinal helminthiases. Study of 1001 students in Abidjan (Ivory Coast)]. - Ei, Menan; Ng, Nebavi; Ta, Adjetey; Nn, Assavo; Ba, Deddy; Pc, Barro-Kiki; Koné, Mariatou (PubMed, 1997)
We report the results of epidemiological research carried out using a sample of 1,001 children between the ages of 4 and 15 in the city of Abidjan. The aim of the study was to explore the relationship between socioeconomic conditions and the occurrence of intestinal helminthiasis. The variables evaluated in this study were the monthly income of the parents, daily food budget per person, number of people sharing accommodation, availability of running water and electricity, availability of food near schools and regular anti-parasite treatment.
openalex: W2409490829 mag: 2409490829
Keywords: openalex:import

[Influence of socioeconomic conditions on the occurrence of intestinal helminthiases. Study of 1001 students in Abidjan (Ivory Coast)]. - Ei, Menan; Ng, Nebavi; Ta, Adjetey; Nn, Assavo; Ba, Deddy; Pc, Barro-Kiki; Koné, Mariatou (PubMed, 1997)
We report the results of epidemiological research carried out using a sample of 1,001 children between the ages of 4 and 15 in the city of Abidjan. The aim of the study was to explore the relationship between socioeconomic conditions and the occurrence of intestinal helminthiasis. The variables evaluated in this study were the monthly income of the parents, daily food budget per person, number of people sharing accommodation, availability of running water and electricity, availability of food near schools and regular anti-parasite treatment.
openalex: W2409490829 mag: 2409490829
Keywords: openalex:import

Brain aging in a sample of normal Egyptians cognition, education, addiction and smoking - Elwan, Osamah; Hassan, Azza; Naseer, Maged Abdel; Elwan, Fadia; Deif, Randa; Serafy, Omar El; Banhawy, Eman El; Fatatry, Medhat El (Journal of the Neurological Sciences, 1997)
The impact of duration of education, cannabis addiction and smoking on cognition and brain aging is studied in 211 normal Egyptian volunteers with mean age 46.4+/-3.6 years (range: 20-76 years). Subjects were classified into two groups: Gr I (non-addicts) with 174 subjects, mean age 49.9+/-3.8 years (range 20-76 years), smokers and non-smokers, educated and non-educated and Gr II (cannabis addicts) with 37 subjects, mean age 43.6+/-2.6 years (range 20-72 years) all smokers, educated and non-educated. Outcome measures included the Paced Auditory Serial Addition test (PASAT) for testing attention and the Trailmaking test A, and B (TMa and TMb) for testing psychomotor performance. Age correlated positively with score of Trailmaking test (TMb) in the non-addict group and in the addict group (TMa and TMb). Years of education correlated negatively with scores of Trialmaking test (TMb) in the non-addict group (Gr I) but not the addict group (Gr II). However, in both groups mean scores of the Trailmaking test (TMa) were significantly lower in subjects with a primary level of education than those with higher levels of education. No significant difference was detected between male smokers and nonsmokers of Gr I (non-addicts) regarding any of the neuropsychological tests. Yet, smokers and the non-educated group had poorer attention compared to non-smokers of the same group. Cannabis addicts (Gr II) had significantly poorer attention than non-addict normal volunteers (Gr I). It is concluded that impairment of psychomotor performance is age related whether in normal non-addicts or in cannabis addicts. A decline in attention was detected in cannabis addicts and has been considered a feature of pathological aging. Education in early life as well as the duration of education are neuroprotectors for brain aging more so in the non-addict than addict group. Though cigarette smoking per se has no effect on cognitive abilities in normal aging, it becomes evident that its association with lack of education impairs attention.
openalex: W2009700829 mag: 2009700829
Keywords: openalex:import

Scientific Experiences as Predictors of Choice of Science among Female High School Students in Nigeria - Erinosho, Stella Y. (Research in Science & Technological Education, 1997)
Abstract This study was undertaken to ascertain the interplay between scientific experiences and participation in school science among girls in the first year of senior‐level classes in four secondary schools (two all‐girls and two mixed) in Nigeria. The outcomes indicate that: ft) girls in science tend to participate in activities which relate to living aspects of science and those which are academic, but only occasionally in tinkering activities; (ii) experience in academic and physical activities in science promotes participation in school science among them; and (iii) these girls tend to be more active than their peers in non‐science. Finally, the paper highlights the implication of these outcomes for a school programme that is designed to stimulate interest in science among girls.
openalex: W2089169008 mag: 2089169008
Keywords: openalex:import

[Student nurses' and nurse midwives' behavior concerning sexuality and prevention of sexually transmitted diseases in Cotonou (Benin)]. - Fourn, Léonard; Be, Fayomi; Massougbodji, M; Zohoun, T. (PubMed, 1997)
Sexually-transmitted diseases (STDs) remain a public health problem in Benin. However, few studies have focused on the future educators, the student nurses. We studied a cross-section of the population of student nurses at the Institut National Médico-Social at Cotonou in December, 1995. The aim of the study was to describe nurses' sexual behavior and their views on STD transmission and prevention. Information was obtained from 141 students by means of an anonymous questionnaire. We found that first sexual relationships often occurred at a young age (12 years old). Sexual relations generally began between 0.25 and 60 months after meeting the partner for the first time. Men were more likely to have multiple partners than women (P < 0.05). The students' views on STD transmission and the use of condoms indicated that they lacked information. About half the students said that they use condoms during sexual intercourse. We identified four groups of students, based on condom-use. This may make more effective student education possible in the future. We suggest improved education of student nurses, greater emphasis in the school curriculum on sexually-transmitted diseases and the creation of a counseling service at the Institute.
openalex: W122362895 mag: 122362895
Keywords: openalex:import

Cross-Cultural Mentor Effectiveness and African American Male Students - Grant-Thompson, Sheila; Atkinson, Donald R. (Journal of Black Psychology, 1997)
This study examined the effects of mentor ethnicity, cultural sensitivity, and student level of cultural mistrust on perceptions of mentor credibility and cultural competence. African American men attending west coast community colleges listened to a tape-recorded mentoring session in which the faculty mentor was described as eitherAfrican American or European American and was portrayed as either culturally responsive or culturally unresponsive. Mentor ethnicity, as well as an interaction between mentor ethnicity and participant level of cultural mistrust, were found to be related to perceptions of mentor credibility/effectiveness. In addition, mentor ethnicity and cultural sensitivity were found to be related to perceptions of mentor cross-cultural competence.
openalex: W2047900358 mag: 2047900358
Keywords: openalex:import

Teacher Practices and Student Motivation in a Middle School Program for African American Males - Hudley, Cynthia (Urban Education, 1997)
An instructional program emphasizing African American history and culture was examined to determine the classroom experiences that were present as well as the program's impact on achievement motivation. Ethnic minority middle school students (N = 18) and their teacher participated. Data included a semi structured teacher interview and student measures of self-perceptions of competence and intrinsic motivation. Students displayed average levels of perceived competence and intrinsic motivation; however, these two constructs were weakly related. The teacher endorsed moderate levels of student autonomy and academic competition. Findings were discussed in relationship to cognitive evaluation theory and the motivation-enhancing elements of this program.
openalex: W2077391038 mag: 2077391038
Keywords: openalex:import

Effects of aerobic training on exaggerated blood pressure response to exercise in African-Americans with severe systemic hypertension treated with indapamide ± verapamil ± enalapril - Kokkinos, Peter; Narayan, Puneet; Fletcher, Ross D.; Tsagadopoulos, Demetrios; Papademetriou, Vasilios (The American Journal of Cardiology, 1997)
Hypertensive patients are likely to have an exaggerated blood pressure (BP) response during physical exertion. When moderate aerobic exercise was added to medical antihypertensive therapy in patients with severe hypertension, excessive elevations in BP during physical exertion were attenuated even with a modest reduction in BP at rest.
openalex: W2007853756 mag: 2007853756
Keywords: openalex:import

Cross-cultural training in southern africa: A call for psychoecological pluralism - Levers, Lisa López (International Journal of Intercultural Relations, 1997)
This article provides a description of counseling services in one southern African nation and documents the results of a qualitative investigation of that nation's counselor training needs. Implications for cross-cultural training are drawn from the study, and related complexities are elaborated. The findings of the study are synthesized with the outcomes of a follow-up study and with the results of subsequent related research on indigenous healing practices in three southern African nations. The synthesis supports a rationale for considering psychoecological pluralism in designing cross-cultural training in human services.
openalex: W2045482448 mag: 2045482448
Keywords: openalex:import

The Effectiveness of Interactive Maps in the Classroom: A Selected Example in Studying Africa - Linn, Sophia Emmanouilides (The Journal of geography, 1997)
Abstract As computers become commonplace in the nation's schools, interactive maps are finding their way into the geography classroom. Students can use electronic atlases to access information as well as use authoring software to produce their own interactive maps. Does this change in media correspond to better geography education for our children? This article addresses whether using interactive maps for gathering and presenting information can have a positive influence on learning geography content. A two-week experiment was conducted in five 7th grade classrooms. Students in four of the classes researched and produced map products using both traditional and computer-assisted techniques. The fifth class was a control group. A pretest and two post-tests were given to quantitatively assess student learning after each project. Also, students were given a qualitative questionnaire to determine their attitude towards the different techniques. Quantitative results of the study indicate that there was no significant difference in student post-test performance after using each of the techniques, but qualitative results suggest that students prefer using the computer techniques over the traditional methods for gathering and presenting information.
openalex: W1991144497 mag: 1991144497
Keywords: openalex:import

Childhood hearing loss in sub-Saharan Africa: a review and recommendations - McPherson, Bradley; Swart, Susan M. (International Journal of Pediatric Otorhinolaryngology, 1997)
Nearly 10% of the world's population lives in sub-Saharan Africa, a region comprised of many countries with least developed nation status. The region has a predominantly young population and many children in the region are at risk of pathologies associated with hearing loss. Despite the constraints associated with low socioeconomic levels, a number of valuable studies have been carried out into the prevalence and etiology of childhood hearing loss in the sub-Saharan region. A review of the published literature related to childhood hearing loss in sub-Saharan Africa is presented and recommendations made on possible future research directions that could assist hearing loss prevention and management.
openalex: W2053914973 mag: 2053914973
Keywords: openalex:import

Pegging bridewealth to an African woman's education - Mwamwenda, Tuntufye S.; Monyooe, Lebusa A. (Research in Education, 1997)
openalex: W2742147647 mag: 2742147647
Keywords: openalex:import

Human intestinal parasites in primary school children in Kampala, Uganda. - Nb, Kabatereine; Kemijumbi, J.; Kazibwe, Francis; Aw, Onapa (PubMed, 1997)
A cross sectional survey on intestinal parasite infections was carried out in 5,313 pupils between the ages of ten and fifteen years in 98 primary schools in Kampala. The aim was to identify the types and distribution of intestinal parasites and to estimate the prevalence in school children. Trichuris trichiura (28%), Ascaris lumbricoides (17%) and hookworms (12.9%) were common infections among the children. Other less commonly found parasites were S.mansoni, Strongyloides stercolaris, Taenia sp, Enterobius vermicularis, Giardia lamblia, Entamoeba coli and E. histolytica. Refuse dumps are probably a significant source of transmission of intestinal helminthic infections in Kampala.
openalex: W54446306 mag: 54446306
Keywords: openalex:import

Correlates of job motivation of physical education teachers in Northern Ghana secondary schools - Ndago, Alfred Abugre (1997)
openalex: W2783931415 mag: 2783931415
Keywords: openalex:import

Schistosomiasis infection in relation to the ABO blood groups among school children in Zimbabwe - Ndamba, J.; Gomo, Exnevia; Nz, Nyazema; Makaza, N.; Kaondera, K (Acta Tropica, 1997)
The study aimed to establish if there was any relationship between the blood group of the human host and schistosomiasis prevalence, intensity, incidence and related organ pathology. Urine and stool specimens were collected from the 735 school children attending a rural school in Zimbabwe to determine the Schistosoma haematobium and S. mansoni infection status of the children. The parasitology results were used to calculate prevalence and intensity of schistosomiasis infection. All the children, irrespective of infection status, were examined for signs of organ damage using ultrasonography before those that were infected were treated using a single dose of praziquantel. A blood specimen was taken from each child for blood group determination. Exactly 1 year later, parasitology was repeated to allow calculation of annual incidence of schistosomiasis infection. Of the children studied, 212 (28.8%) were of blood group 'A', 156 (21.2%) were of blood group 'B' while 367 (49.9%) belonged to blood group 'O'. The prevalence of S. haematobium was 59.6% (n = 438) while that of S. mansoni was 15.60% (n = 115). S. haematobium infection was detected among 129 (60.8%) children belonging to blood group 'A': 225 (61.30%) of blood group 'O' and 84 (53. 80%) of those belonging to blood group 'B'. S. mansoni infection was detected among 65 (30.70%) blood group 'A' children while 37 (10.10%) blood group 'O' and 13 (8.30%) blood group 'B' children were infected. Intensity, annual incidence of S. haematobium infection and related organ pathology was significantly higher among children of blood group 'A' and lowest among blood group 'O' children (P < 0.01, F-value = 6.13). Similarly, S. Mansoni intensity and incidence of infection and related liver lesions were highest among children of blood group 'A' (P < 0.005, F-value = 11.45).
openalex: W2086373485 mag: 2086373485
Keywords: openalex:import

A TOPOSEQUENCE OF SOILS DERIVED FROM VOLCANIC MATERIALS IN RWANDA: MORPHOLOGICAL, CHEMICAL, AND PHYSICAL PROPERTIES - Nizeyimana, Egide (Soil Science, 1997)
Soils in the northwestern region of Rwanda developed from volcanic materials that originated from eruptions of six volcanoes during the Quaternary period. This study assessed primarily soil morphological, chemical, and physical property differences along a toposequence on the slopes of these volcanoes. Three representative soil pedons were described in the field and sampled for laboratory analyses from sites located at 2700-m, 2400-m, and 2000-m elevations on the slopes of one of the volcanic peaks. The sampling site locations varied in rainfall and temperature regimes. All soils were characterized by thick and dark A horizons and dark brown or grayish brown cambic horizons. The soil structure was primarily weak fine granular in surface horizons and weak fine subangular blocky in subsurface horizons. All three soils appeared to be similar in morphological properties. Organic C was high in all three soils, particularly in the soil at the 2700-m elevation, and decreased with decreasing elevation. The Cation Exchange Capacity varied with elevation in the same manner as organic C but appeared to be affected also by amorphous constituents. Phosphate retention, exchangeable acidity, and exchangeable Al were lower in the soil at the lowest elevation. Soil bulk density increased whereas water retentions at −33 kPa and −1500 kPa tension and Water Retention Difference decreased with decreasing elevation. Although soils at the upper two locations fitted the order of Andisols, that at the lower location was classified as an Inceptisol because of the lack of andic soil properties. The variations in soil properties, and hence in soil taxonomic classes, with elevation were attributed primarily to changes in organic matter, and probably allophane, and the 10-Å ; halloysite induced by rainfall and temperature differences that existed between sites. In general, variations in soil properties with elevation were similar to those found in soils derived from volcanic materials in other parts of the world.
openalex: W2333832460 mag: 2333832460
Keywords: openalex:import

AN ASSESSMENT OF COLLOIDAL CONSTITUENTS AND CLAY MINERALOGY OF SOILS DERIVED FROM VOLCANIC MATERIALS ALONG A TOPOSEQUENCE IN RWANDA - Nizeyimana, Egide; Bicki, Thomas J.; Agbu, P. A. (Soil Science, 1997)
Colloidal constituents and clay mineralogical composition of soils derived from volcanic materials were determined in relation to climate along the slopes of an extinct volcano in northwestern Rwanda. Three representative soil pedons were sampled from sites located at 2700 m, 2400 m, and 2000 m to represent differences in rainfall and temperature regimes. Allophane was present in all three soils but tended to be higher in subsurface than in surface horizons. The lower allophane content in surface horizons was attributed to high organic C content. Organic C forms strong bonds with Al originating from the weathering of volcanic ash, thus inhibiting the coprecipitation of Al and Si needed for the formation of amorphous constituents in these horizons. Ferrihydrite was also present in the soils. The 10-Å ; halloysite was also present in high amounts, particularly in subsurface horizons. All soils contained substantial amounts of mica, feldspar, and iron-based crystalline clay minerals. In general, percentages of allophane and Al- and Fe-humus complexes were higher in the soil at the 2700-m elevation and decreased with decreasing elevation. Furthermore, the Al/Si ratio of allophane was approximately 2 in this soil and decreased to about 1 in the soil at the 2000-m elevation. The 10-Å ; halloysite, however, increased with decreasing elevation. The lower allophane content and Al/Si ratio in allophane and the higher halloysite content in the soil at the lowest elevation may have resulted from higher Si concentration in the soil solution associated with the lower rainfall regime at this location. Variations in metal-humus complexes, amorphous constituents, and the 10-Å ; halloysite appeared to be a function of the differences in rainfall regimes that existed between sites.
openalex: W2314940902 mag: 2314940902
Keywords: openalex:import

Remote sensing of heat, lava and fumarole emissions from Erta 'Ale volcano, Ethiopia - Oppenheimer, Clive; Francis, P. W. (International Journal of Remote Sensing, 1997)
Abstract Erta 'Ale volcano, sited within the Afar Triangle of Ethiopia, is one of the least frequented, perennially active, subaerial volcanoes. By compiling a time series of Landsat MSS and TM, JERS-1, SPOT, and AVHRR digital imagery, and space-borne photographic data, we have been able to constrain the activity of this volcano, important for its geodynamic setting, during the long period since 1974 when volcanological investigations effectively ceased. Existing techniques for infrared thermometry have been modified to cope with saturation of the short wavelength infrared Landsat TM band 5 and 7 sensors, enabling derivation of thermal fluxes from Erta 'Ale's active lava lakes. Lake levels have been estimated from measurements of shadow lengths cast by the crater rim. Changes in caldera and flank reflectances identify new lava flows whose areas and volumes we have constrained in order to derive eruption magnitudes and effusion rates. Between 1968 and 1974, approximately 3 1010 kg of lava was erupted at peak discharge rates exceeding 400kg s -1, though much of this subsequently drained back or subsided rigidly. No post-1974 overflows were detected in the imagery, although thermal (100-400 MW) output from the lava lakes, and gas emissions appear to have been sustained up to the time of writing. The longevity of the lava lakes provides evidence for convective circulation between the lakes and a deeper magma reservoir. The high heat flux and low exogenous growth rates ( 10kg s -1 integrated over the last thirty years) are indicative of a volcano that 'grows' largely by magmatic intrusion, which is consistent with the formation of new igneous crust in the extensional tectonic environment of northern Afar.
openalex: W2139652884 mag: 2139652884
Keywords: openalex:import

The Conscience of Society: The Social Teaching of the Catholic Bishops of Kenya 1960-1995 - Pirouet, M. Louise; Mejía, Rodrigo Ocampo (Journal of Religion in Africa, 1997)
openalex: W1979387279 mag: 1979387279
Keywords: openalex:import

Do African American Students' Perceptions Of Their Needs Have Implications For Retention? - Rowser, Jacqueline F. (Journal of Black Studies, 1997)
African American student retention on predominantly White campuses continues to be one of the greatest challenges for many colleges and universities. In addition to the impact of student attrition on the economic well-being of the university, the image of the university is at risk when African American students' attrition rates far exceed those of White students. Researchers, when studying factors related to retention, found that high GPA and test scores predict academic performance differently for African American students than for White students (Farver, Sedlacek, & Brooks, 1975; Lunneborg & Lunneborg, 1986). Even when academic preparation was considered, disparity still resulted. Steele (1992) observed that
openalex: W1565697348 mag: 1565697348
Keywords: openalex:import

INTRODUCTION TO DRIVER TRAINING AND LICENSING IN GHANA. - Salifu, Mohammed (1997)
openalex: W384584537 mag: 384584537
Keywords: openalex:import

Paediatric neurologic emergencies at the University of Nigeria Teaching Hospital, Enugu. - So, Iloeje (PubMed, 1997)
Four hundred and sixty-seven children, aged from birth to 16 years (mean age:35.9 months), presented with emergency neurological problems to the Children's Emergency Unit (CHER) of the University of Nigeria Teaching Hospital, Enugu over a 12-month period. This accounted for 11.1% of all the cases seen in the Unit during that period. There was a male:female ratio of 1.55:1. A significantly higher number of cases presented during the rainy season (May to October) than during the other months of the year. Febrile convulsion was the most common problem, with 132 cases (28.3%), followed by meningitis (18.2%) and afebrile seizures (15.8%). One hundred and ninety-two patients (37.7%) were discharged home, while 36 (7.7%) died. The findings from the study are discussed and compared with data from other centres. Recommendations that may help to reduce mortality from neurologic emergencies in children, are made.
openalex: W1672709636 mag: 1672709636
Keywords: openalex:import

African American College Students' Experiences in HBCUs and PWIs and Learning Outcomes. - Terenzini, Patrick T.; Yaeger, Patricia M.; Bohr, Louise; Pascarella, Ernest T.; Nora, Amaury (1997)
This study examined whether African-American students who attend historically black colleges and universities (HBCUs) have different experiences and perceive the campus climate differently than African American students who attend predominantly white institutions (PWIs). The study also examined whether differences in experiences and perceptions of the environment are linked to differential gains in cognitive abilities. The study used data from the National Study of Student Learning, a three-year longitudinal study of about 4,000 students who entered 23 institutions in 1992. Data were gathered in the fall of 1992 and the spring of 1993 and included demographic characteristics, scores on the Collegiate Assessment of Academic Proficiency, and responses on the College Student Experience Questionnaire. Students in HBCUs differed from their peers in both entering characteristics and college experiences in a variety of areas. These experiences, however, were not associated with differences in first year cognitive gains. (Contains 38 references and 3 tables.) (DB) ******************************************************************************** * Reproductions supplied by EDRS are the best that can be made * * from the original document. * ******************************************************************************** AFRICAN AMERICAN COLLEGE STUDENTS' EXPERIENCES IN HBCUs AND PWIs AND LEARNING OUTCOMES PERMISSION TO REPRODUCE AND DISSEMINATE THIS MATERIAL HAS BEEN GRANTED BY Patrick Terenzini TO THE EDUCATIONAL RESOURCES INFORMATION CENTER (ERIC) by Patrick T. Terenzini Professor and Senior Scientist Center for the Study of Higher Education The Pennsylvania State University 403 South Allen Street, Suite 104 University Park, PA 16801-5252 Telephone: (814) 865-6346 E-Mail: ptt2@psu.edu Patricia M. Yaeger Research Assistant Center for the Study of Higher Education The Pennsylvania State University Louise Bohr Assistant Professor of Reading 'Northeastern Illinois University Ernest T. Pascarella Professor of Higher Education University of Illinois-Chicago Amaury Nora Professor of Higher Education University of Houston U.S. DEPARTMENT OF EDUCATION Office of Educational Research and Improvement EDUCATIONAL RESOURCES INFORMATION CENTER (ERIC) 117this document has been reproduced as received from the person or organization originating it. Minor changes have been made to improve reproduction quality. Points of view or opinions stated in this document do not necessarily represent official OERI position or policy. Paper presented at the meeting of the Association for Institutional Research, Orlando, FL, May 1997. This study was supported by the National Center on Postsecondary Teaching, Learning, and Assessment, funded in part by the U.S. Department of Education, Office of Educational Research and Improvement (OERI) under Grant No. R117G10037. The opinions herein do not necessarily reflect the position or policies of OERI, and no official endorsement should be inferred.
openalex: W2727523125 mag: 2727523125
Keywords: openalex:import

Changing South African schools?: an analysis and critique of post‐election government policy - Tikly, Leon (Journal of Education Policy, 1997)
This article provides an exposition, analysis and critique of post‐election policy concerning state schooling in South Africa. In particular the article focuses on the White Paper on the Organisation, Governance and Funding of Schools. Policy is analysed at three levels, namely the economic, ideological/discursive and the political. At the economic level it is argued that although the White Paper makes provision for redress of past inequalities, limitations in government expenditure are limiting the possibilities for reform. It will also be argued that the White Paper must be seen as the outcome of contestation between different discourses concerned with race, culture and education. Finally the White Paper has been shaped by the interim constitution as well as by political struggles within the state and civil society.
openalex: W2004927708 mag: 2004927708
Keywords: openalex:import

Earthquake swarms of Mt Cameroon, West Africa - Ubangoh, Richard U.; Ateba, Bekoa; Ayonghe, Samuel N.; Ekodeck, Georges Emmanuel (Journal of African Earth Sciences, 1997)
Historical and recent instrumental studies of the central region of the Cameroon Volcanic Line clearly indicate the occurrence of earthquake swarms of volcanic origin. Analyses of more than 3000 micro-earthquakes recorded between 1985 and 1992 show a well-defined seismic pattern characterised by single and swarm events with duration magnitudes between 2 and 3 at depths down to 20 km. On average, the earthquakes here occur at the rate of about 2 events every 3 days with occasional earthquake swarms, which greatly increase this number. The seismic swarms comprising felt earthquakes are shown to be sometimes preceded by, simultaneous with, or followed by swarms from Bimbia and Equatorial Guinea. Mapped epicentres of some of these swarms correspond to regions of volcanic gas emissions and are parallel to the fissures on Mt Cameroon and to the inferred direction of the underlying shear zone. The quiescent periods between swarms are seen to double each year since 1986. This observation was used to predict a major seismic swarm which occurred in 1993. The data coupled with historical data, are used to infer the involvement of a magma chamber in the generation of the earthquake swarms in the region. Since the installation of the network, no eruption has been observed on Mt Cameroon. This warrants more observation in order to study the seismicity that may precede, accompany or follow an eruption of the mountain. Les études historiques et instrumentales récentes de la région centrale de la Ligne Volcanique du Cameroun indiquent clairement ('existence d'essaims de tremblements de terre d'origine volcanique. L'analyse de plus de 3000 micro-séïsmes enregistrés entre 1985 et 1992 montre un ensemble sismique bien défini caractésé par des événements isolés et en essaim avec des magnitudes de 2 à 3 à des profondeurs jusqu'à 20 km. En moyenne, les tremblements de terre se déclenchent au rythme de 2 événements tous les 3 jours avec des essaims occasionnels qui augmentent ce nombre. Les essaims sismiques comprennent des tremblements de terre ressentis et sont parfois précédés par, simultanés de, ou suivis par des essaims en Bimbia et Guinée Équatoriale. Les épicentres de certains essaims correspondent aux régions d'émission de gaz volcaniques et sont parallèes aux fissures du Mont Cameroun et à la direction supposée de la zone de cisaillement profonde. Les périodes de repos doublent chaque année depuis 1986. Cette observation a été utilisée pour prédire ('essaim sismique majeur qui se produisit en 1993. Les données couplées avec l'histoire sont utilisées pour définir le rôle de la chambre magmatique dans l'origine des essaims de tremblements de terre de la région. Depuis l'installation du réseau, aucune éruption n'a été observée au Mont Cameroun. Ceci justifie le besoin de plus de données avant d'être capable d'étudier la sismicité qui peut précéder, accompagner ou suivre une éruption dans la montagne.
openalex: W2027928115 mag: 2027928115
Keywords: openalex:import

Tracing Graduates Through Reunion Parties: Secondary Technical Education in Mozambique - Ziderman, Adrian (Comparative Education Review, 1997)
Previous articleNext article No AccessFocus on Adult SkillsTracing Graduates Through Reunion Parties: Secondary Technical Education in MozambiqueAdrian ZidermanAdrian Ziderman Search for more articles by this author PDFPDF PLUS Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinkedInRedditEmail SectionsMoreDetailsFiguresReferencesCited by Comparative Education Review Volume 41, Number 2May, 1997 Sponsored by the Comparative and International Education Society Article DOIhttps://doi.org/10.1086/447427 Views: 1Total views on this site Citations: 2Citations are reported from Crossref Copyright 1997 The Comparative and International Education SocietyPDF download Crossref reports the following articles citing this article:Denise Jarratt, Tom Murphy, Diannah Lowry Building customer relationships: a model for vocational education and training delivery, Journal of Vocational Education and Training 49, no.44 (Dec 1997): 591–615.https://doi.org/10.1080/13636829700200038Jørgen Billetoft, Technical and Vocational Education and Training in Mozambique: Better than Its Reputation, (): 309–328.https://doi.org/10.1007/1-4020-3034-7_7
openalex: W1999625589 mag: 1999625589
Keywords: openalex:import

[South Africa–student nurse among the Zulus. Interview by Eli M. Bjørkan]. - Gundersen, Malene Wøhlk (1997)
openalex: W2467878904 mag: 2467878904
Keywords: openalex:import

Black English and education in South Africa : an investigation - Nwaila, Charles (1997)
openalex: W330199495 mag: 330199495
Keywords: openalex:import

Volcanological features of a low-viscosity melt: the carbonatitic Gross Brukkaros Volcanic Field, Namibia - Kurszlaukis, S.; Lorenz, Volker (Bulletin of Volcanology, 1997)
openalex: W2068557062 mag: 2068557062
Keywords: openalex:import

A study of the procedures and their perceived effectiveness in the recruitment of African American teachers in city school divisions in Virginia - Hobbs, Betty E. (1997)
openalex: W2582413592 mag: 2582413592
Keywords: openalex:import

Breast cancer education, self-efficacy, and screening in older African American women. - Adderley-Kelly, Beatrice; Green, P M (PubMed, 1997)
Breast cancer is the second leading cause of cancer mortality in African American women. Low rates of cancer screening participation have been documented in inner-city elderly African American populations. Knowledge and beliefs about breast cancer and screening, and self-efficacy in performing breast self-examinations, are important components in an educational program aimed at increasing participation in breast cancer screening. The objectives of this study were to determine the breast cancer knowledge of subjects, their level of confidence when performing breast self-examination, and if individual instruction, one-to-one practice, and feedback on performance made a difference in screening practices. The findings suggest that a more intensive training intervention sustains breast examination self-efficacy.
openalex: W2400617776 mag: 2400617776
Keywords: openalex:import

Glove Utilization and Reasons for Poor Compliance by Health Care Workers in a Nigerian Teaching Hospital - Adegboye, Ajibola A.; Roy, Praveen K.; Emeka, Chukwubuike Kevin (Tropical doctor, 1997)
openalex: W2418344693 mag: 2418344693
Keywords: openalex:import

Glove Utilization and Reasons for Poor Compliance by Health Care Workers in a Nigerian Teaching Hospital - Adegboye, Ajibola A.; Roy, Praveen K.; Emeka, Chukwubuike Kevin (Tropical doctor, 1997)
openalex: W2418344693 mag: 2418344693
Keywords: openalex:import

Thermal and geodynamic setting of the Buem volcanic rocks near Tiélé, Northwest Bénin, West Africa - Affaton, Pascal; Aguirre, Luis; Ménot, René-Pierre (Precambrian Research, 1997)
The mafic volcanic rocks of Tiélé occur as intercalations within very low-grade metasediments, mainly metapelites and meta-arenites. These Proterozoic supracrustal rocks are considered as part of the Buem Structural Unit (BSU) which is the most external tectonic unit of the Pan-African Dahomeyide fold belt. The geodynamic significance of the BSU is still debated: it could represent either a portion of the West-African passive margin during the rifting and the drifting of the Pan-African ocean (Affaton, 1990), or a continental rift-zone (Jones, 1990) or the Pan-African oceanic crust itself (Burke and Dewey, 1972 and Burke and Dewey, 1973; Shackleton, 1976). The mafic lavas derived from tholeiitic magmas, which originated by partial melting of the lithospheric mantle with a possible asthenospheric contribution. They are quite similar to MORBs and free of any crustal contamination. They are related to a strongly attenuated continental lithosphere, and a passive margin would be the most likely tectonic environment for the coeval volcanic and sedimentary activities. On the other hand, these rocks demonstrate effects of early static recrystallizations related to a very low grade metamorphism of the prehnite-pumpellyite facies developed under temperatures of 200 to 300°C. Such a thermal imprint clearly marks an extensional tectonic stage. Later, the early parageneses were re-equilibrated under slightly higher pressures during the Pan-African collision. Both magmatic features and early metamorphic characters of these metavolcanic rocks are in good agreement with a context of lithospheric thinning characterized by mantle-derived magmatism and high thermal-gradient. These results fit with previous interpretations mainly based on sedimentary and structural features: the BSU represents a portion of a Proterozoic passive margin which suffered strong lithospheric stretching, with deep seated normal faults and mantle derived magmatism, and a subsequent severe subsidence evidenced by the prominent detrital sedimentation. Such a tectonic setting developed during the Pan-African oceanic drifting
openalex: W2072764207 mag: 2072764207
Keywords: openalex:import

Management training and development within its environment: the case of Libyan industrial companies - Agnaia, Almehdi A. (Journal of European Industrial Training, 1997)
Discusses the state of management training and development in Libya. Investigates the Libyan management environment and examines the influence of a variety of factors on the management training and development programmes (MTDPs). Presents an empirical study and uses descriptive statistical methods to analyse the collected data and information. Finds that Libyan industrial companies, like those in many other developing countries, are owned, managed and supervised by government institutions. The MTD units in these companies are influenced negatively by the surrounding environment (e.g. social, economic and political factors) which imposes some constraints on MTD, and hampers the achievement of their goals. Suggests that more attention needs to be given to the environmental effects on the companies and their employees.
openalex: W2094187838 mag: 2094187838
Keywords: openalex:import

The Effect of Using Rapping To Teach Selected Musical Forms to Urban African American Middle School Students. - Akintunde, Omowale (1997)
A study determined the effects of a pedagogical approach using rap music on the learning of musical forms among urban African American youth and whether there were differential effects among students of different levels of self-esteem. Urban African American youth (n=66) from the St. Louis County Public Schools who were enrolled in general music classes at Brittany-Woods Middle School served as participants. Two randomly chosen classes formed the control group and 2 randomly chosen classes formed the experimental group. All participants were in grades 6 through 8. Participants were divided into high, middle, and low self-esteem groups. For the control group, traditional procedures (lecture, listening, etc.) were used to teach students binary, ternary, and verse-refrain forms. The researcher also composed 3 songs in binary, ternary, and verse/refrain form respectively. The experimental group was instructed in the same manner as the control group with the exception that the 3 researcher-composed examples were rapped to a pre-recorded rhythm soundtrack, and students were allowed to move rhythmically to the beat and perform as a human beat box. A researcher-designed test was then administered to those in both experimental and control groups, and students made written comments regarding rap as a pedagogical device. Results indicated no significant differences between the experimental and control groups, but student comments suggest that the use of rap music was highly appealing. (Contains 18 references and 2 tables of data. Appendixes present the researcher-composed songs and students' comments.) (Author/RS) ******************************************************************************** Reproductions supplied by EDRS are the best that can be made from the original document. ********************************************************************************
openalex: W227383376 mag: 227383376
Keywords: openalex:import

Prevalence and incidence rates of HIV-1 infection in Rwandan students. - Baganizi, Énias; Saah, A. J.; Bulterys, Marc; Dr, Hoover; Celentano, David D.; Alary, Michel (PubMed, 1997)
A study was conducted between October 1992 and June 1993 to determine the prevalence and incidence of HIV-1 infection and associated risk factors among secondary school and university students in Rwanda. All single students aged 15-35 years from the National University and six secondary schools in Butare were eligible to participate. 1348 of the 1807 students invited to participate agreed to enroll. The proportion of non-participation increased with age with the median age of students in the study being 21 years. 23 of 1345 (1.7%) students were diagnosed as infected with HIV-1. Nine of these HIV-seropositive students denied being sexually active and reported no other HIV risk factor. The level of HIV-1 infection was significantly higher among university students than among secondary school students with HIV-1 seroprevalence increasing from 0.6% among those under age 22 years to 5.0% among those over age 25. Students who had their first sexual intercourse before age 18 years were more likely to be HIV-positive than those who had their first sexual experience at age 18 years or older. Multivariate logistic regression found only age to be independently associated with the prevalence of HIV-1 infection. 6 months after the beginning of the study blood specimens were taken from 1120 seronegative students at baseline to determine HIV incidence. There was an overall incidence density of 0.74 per 100 person-years. However among the 97 female university students aged 20-24 years the incidence density was 6.34 per 100 person-years. The observed HIV-1 seroprevalence rate among the students was far lower than that reported among women attending prenatal clinics in the same area as the study population. Self-selection bias may have affected the study findings.
openalex: W2185798027 mag: 2185798027
Keywords: openalex:import

Knowledge and attitudes to HIV and AIDS and sexual practices among university students in Lusaka, Zambia and London, England: are they so different? - Baggaley, Rachel; Drobniewski, Francis; Pozniak, A.; Chipanta, David; Tembo, Mavuto; Godfrey‐Faussett, Peter (The journal of the Royal Society of Health, 1997)
Surveys conducted among university students in Lusaka, Zambia, and London, England, in 1993-94 revealed comparable AIDS-related knowledge, attitudes, and sexual practices, despite vast differences between the two countries in AIDS prevalence. Questionnaires were completed by 946 seniors and 294 new students from the University of Zambia in 1993 and 1994 and by 100 seniors and 117 new students from London University in 1994. Both groups of students were quite knowledgeable about transmission of HIV through semen, blood, and vaginal fluid; however, 50% in both settings believed saliva transmits HIV. Although more than two-thirds of Lusaka students, compared with one-fourth of London students, knew or had known someone with HIV, British students had more compassionate, less judgmental attitudes toward AIDS patients. 90% of Lusakan but under 50% of London students worried about catching HIV. By their senior year, 61% of female and 85% of male students in Zambia had had one or more sexual partner compared with 73% and 76%, respectively, in London. 66% of Lusakan and 75% of London students used condoms most of the time with casual partners; with regular partners, these rates were only 23% and 35%, respectively. Lusakan students were less likely than their London counterparts to discuss HIV with their partners. 75% of students in both countries had received some type of AIDS education, but the majority expressed an interest in additional counseling. Recommended, in both settings, are university-based AIDS education programs, with particular emphasis on the importance of condom use with all sexual partners.
openalex: W2073596274 mag: 2073596274
Keywords: openalex:import

Langues et education en Afrique noire (Language and Education in Black Africa). - Bearth, Thomas (1997)
openalex: W39892759 mag: 39892759
Keywords: openalex:import

Professional Development for Educators through Travel to Zimbabwe: One-Year Follow-up. - Betts, Sherry C.; Norquest, Jan (Journal of Family and Consumer Sciences, 1997)
openalex: W232976461 mag: 232976461
Keywords: openalex:import

[Medical education in Algeria: opinion of the students at the end of their curriculum]. - Bouziani, M; Mebtoul, M (PubMed, 1997)
A cohort of 120 medical stents who have nearly completed their medical training have been surveyed in Oran, Algeria. Most of them are not satisfied concerning their medical training (82%). However, they accept the conventional pattern of medical learning which allows little room to active participation from the trainees. The most appreciated scientific disciplines are cardiology for men and gynecology for women. In most cases, priority is given to clinical disciplines. Community medicine and public health are rather neglected. Similarly, at the end of their training, medical students' knowledge is rather tiny regarding teamwork or health promotion. Clearly, most of them consider themselves as care providers, not health builders.
openalex: W2436910992 mag: 2436910992
Keywords: openalex:import

Education Policy and Language Learning for a Multilingual Society. Proceedings of a Conference (Hartebeespoort, South Africa, October 30-November 1, 1996). - Brown, David (1997)
openalex: W1582356253 mag: 1582356253
Keywords: openalex:import

Prevalence of transmissible blood infections among blood donors at the University of Maiducuri Teaching Hospital, Maiduguri, Nigeria. - Chikwem, John; Mohammed, Idris; Okara, G. C.; Ukwandu, N. C. D.; Ola, Thomas O. (PubMed, 1997)
Before the advent of the Acquired Immune Deficiency Syndrome (AIDS), many countries of the world transfused blood without seriously considering the potential risks of transmission of infectious agents. Even after it was shown that the Human Immunodeficiency virus(HIV) could be transmitted through blood and blood products, many hospitals and clinics in Nigeria still continue to transfuse unscreened blood. This study was therefore initiated to highlight the risks of transmitting infectious agents through blood transfusion and the category of infectious agents which could be transfused in blood in this area. A total of 364 healthy blood donors were counselled, bled and screened for HIV-1, HIV-2, HBsAg, Treponema pallidum, Plasmodium falciparum and microfilaria. The results show that the three most common infections transmissible through blood transfusion are Hepatitis B(14.9%), HIV-1 (5.8%) and P.falciparum (4.1%). Thirteen of the 364 blood donors (3.6%) and antibodies to T. pallidum. There were no donors with HIV-2 or filarial infection. Infection of donors by hepatitis B virus (HBV), T. pallidum and HIV-1 was not significant dependent on promiscuity, polygamy, previous blood transfusion or local surgery. However, there was a significant difference between donors with no risk factors and those with risk factors with regard to seroprevalence to HBV, T. pallidum and HIV-1 (p = 0.0053). The results confirm that transfusion of unscreened blood carries severe risks of transmitting serious infectious agents and that is a need to enforce laws for transfusing blood in Nigeria. Meanwhile, in the absence of screening facilities, proper counselling of blood donors in order to ascertain their risk behaviour should be used to select donors and reduce this risk.
openalex: W1596059316 mag: 1596059316
Keywords: openalex:import

An approach using SAR ERS images to relate extension fractures to volcanic vents: examples from iceland and Madagascar - Chorowicz, J.; Bardintzeff, Jacques-Marie; Rasamimanana, Georges; Chotin, P.; Thouin, C.; Rudant, Jean-Paul (Tectonophysics, 1997)
A new approach to the study of geometric relationships between tectonic structures and volcanic vents is presented. It is based on the mapping of tectonic and volcanic features using high-resolution imagery, including Synthetic Aperture Radar (SAR) images of the European Remote Sensing satellite number one (ERS-1). We have evidenced new faults: (1) N-striking normal faults in the Husavik fault zone of the North Atlantic ridge, and (2) NW-striking faults belonging to the Husavik transform fault zone, associated to drag folds which testify to a dextral strike-slip movement component. We show that most of the volcanic edifices are located on extension fractures responsible for fissure eruptions, volcanic linear clusters and elongated volcanoes. This relationship is studied first in Iceland where the geodynamics is well known, using SAR ERS-1 imagery. Applied to the Montagne d'Ambre, in northern Madagascar, using aerial photographs, this approach makes it possible to identify faults and the regional Plio-Quaternary direction of extension, i.e. N65°E to N85°E. Volcanoes forming linear clusters, together with elongated volcanoes, are interpreted to be located on extension fractures. S- or Z-shape of the linear clusters allowed us to determine the tips of extension fractures, and consequently the orientation of the regional tension. Alignments of extension fractures, depending on their S- or Z-shape, permitted us to infer conjugated faults.
openalex: W1976462099 mag: 1976462099
Keywords: openalex:import

Energy intakes, anthropometry and body composition of Nigerian adolescent girls: a case study of an institutionalized secondary school in Ibadan - Cole, A. H.; Taiwo, Omowumi O.; Nwagbara, Ngozi I.; Cole, Cornelia E. (British Journal of Nutrition, 1997)
Twenty-two apparently healthy Nigerian adolescent girls aged 11-17 years residing in a hostel, were studied over five consecutive days in order to assess their energy intake (EI), energy cost of specific activities and body composition (BC). The mean characteristics of the group were: height 1.58 (SD 0.1, range 1.42-1.68) m, body weight 49.1 (SD 7.9, range 34.0-61.0) kg and BMI 19.5 (SD 2.0, range 16.0-23.0) kg/m2. The food intake of each subject was assessed by direct weighing and its energy value was determined by means of a ballistic bomb calorimeter. BMR values were calculated according to Food and Agriculture Organization/World Health Organization/United Nations University (FAO/WHO/UNU) (1985) equations. Percentage body fat (BF%) values were derived from three skinfold thickness measurements, using population-specific equations. The adolescents' mean daily EI was found to be 6510 (SD 855) kJ/d (138.3 (SD 27.8) kJ/kg body weight per d) which is lower than the FAO/WHO/UNU (1985) calculated energy requirement of 8800 kJ/d for adolescent girls aged 12-14 years. The contributions of specific nutrients and individual meals to the total EI were: carbohydrate, protein and fat, 59.2, 12.5 and 28.3% of energy respectively and breakfast, lunch and supper, 21.5, 41.0 and 37.4% respectively. However, the mean BMR was 5627 kJ/d, which is comparable with that given by FAO/WHO/UNU (1985) for adolescent girls aged 13-14 years. The mean BF% was found to be 21.7. The comparatively low EI of the participants in the present study may be indicative of energy deficiency in their meals. This assumption is also reflected in their BC values. Nevertheless, further studies of this kind on adolescents in Nigeria are needed to confirm these observations.
openalex: W2164740596 mag: 2164740596
Keywords: openalex:import

Isotopic constraints on the age and formation of a Palaeoproterozoic volcanic arc complex in the Kedougou Inlier, eastern Senegal, West Africa - Dia, Anta Tal; Schmus, W. R. Van; Kröner, Alfred (Journal of African Earth Sciences, 1997)
The Palaeoproterozoic Kedougou basement in the Mako area in eastern Senegal consists of four major rock complexes: 1) high-grade amphibolitic and gneissic rocks occuring as large xenoliths (the Sandikounda amphibolite-gneiss complex); 2) voluminous bimodal volcanic rocks (the Mako volcanic-plutonic complex); 3) the Sandikounda layered plutonic complex; and 4) trondhjemitic to calc-alkaline intrusive granitoids (the Laminia-Kaourou plutonic complex). Zircons from xenoliths of the Sandikounda amphibolite-gneiss complex yielded ages of ∼2200 Ma, which are slightly older than those of the Mako Supergroup volcanic rocks. These xenoliths also have ɛNd(t) values ranging from +2.4 to +4.1. The volcanic sequence represents an important bimodal volcanic event with Mg-tholeiites and subordinate felsic calc-alkaline lavas having ɛNd(t) values ranging from +2.6 to 3.8. The plutonic intrusions yield ages between 2158 and 2079 Ma with positive ɛNd(t) values of +2.6 to +4.7. Isotopic evidence indicates that the Mako Palaeoproterozoic crust is a juvenile, arc-related terrain derived from a depleted mantle source, emplaced between 2300 and 2079 Ma and subsequently accreted to the growing West African Craton. An early magmatic event, represented by the protolith of the amphibolite and the gneiss, is inferred to represent the initial stage of this Palaeoproterozoic crustal growth and may represent the root of the Mako volcanic-plutonic complex. Thus, the Birimian-Eburnian development of the western part of the Kedougou Inlier is constrained to the interval 2300-2079 Ma; this is slightly older than other parts of the Birimian-Eburnian domains elsewhere in western Africa. Le socle paléoprotérozoïque de Kédougou dans la région de Mako consiste en quatre unités majeures: 1) amphibolites et gneiss de degréélevéen grands panneaux formant le complexe amphibolite-gneiss de Sandikounda; 2) volcanisme bimodal important formant le complexe volcano-plutonique de Mako; 3) complexe plutonique litéde Sandikounda; et 4) granitoïdes trondhjémitiquesàcalco-alcalins du complexe plutonique de Laminia-Kaourou. Les zircons des panneaux du complexe amphibolite-gneiss de Sandikounda donnent desaˆges autour de 2200 Ma, légèrement plus anciens que ceux des roches volcaniques du Supergroupe de Mako, et des valeurs eNd(t) comprises entre +2,4 et +4,1. La séquence volcanique provient d'unévénement volcanique bimodal important avec des tholéïtes magnésiennes et des laves felsiques calco-alcalines moins abondantes avec des valeurs eNd(t) entre +2,6 et +3,8. Les intrusions plutoniques fournissent desaˆges entre 2158 et 2079 Ma avec de faibles valeurs positives eNd(t) de +2,6à+4,7. Les données isotopiques indiquent que la crouˆte paléoprotérozoïque de Makoétait un terrain d'arc juvénile dérivéd'une source mantellique appauvrie et mis en place de 2300à2079 Ma, puis accoléau craton ouest-africain. Unévénement magmatique précoce, représentépar le protolite des amphibolites et des gneiss, a duˆconstituer l'épisode initial de la croissance crustale paléoprotérozoïque et pourrait représenter la racine du complexe volcano-plutonique de Mako. Ainsi, le développement au cours du Birimien-Eburnéen de la partie occidentale du socle de Kédougou s'est produit dans l'intervalle 2300-2079 Ma, ce qui est légèrement plus ancien que les autres terrains birimiens-éburnéens ailleurs en Afrique de l'Ouest.
openalex: W1983303965 mag: 1983303965
Keywords: openalex:import

White-Collar or Hoe Handle? African Education under British Colonial Policy 1920-1945. - Falọla, Toyin; Sivonen, Seppo (The American Historical Review, 1997)
openalex: W1991779806 mag: 1991779806
Keywords: openalex:import

Lessons for life—Past and present modes of sexuality education in Tanzanian society - Fuglesang, Minou (Social Science & Medicine, 1997)
The provision of sexuality education and contraceptive services to unmarried adolescents has became a key issue in the era of AIDS. International health organizations are promoting action worldwide. In Tanzania the Ministry of Health has started policy work, while the NGO sector is spearheading activities in the field. Yet there is a lot of public scepticism and resistance to launching such programmes, as many believe that these will promote promiscuity among the young. This article explores the efforts of the Family Planning Association of Tanzania (UMATI), collaborating with the Swedish Association of Sex Education (RFSU), to develop appropriate and sensitive programme activities, drawing on the experiences of other countries as well as on local customs tied to traditional initiation rites. Capacity building involving the provision of techniques for training, research, advocacy and outreach has been the focus of the exchange between the two NGOs. The aim has been to take a broad but integrated perspective on the issue, including an understanding of adolescent sexuality as well as that of reproduction. Most of the data presented here were generated during a follow-up study of the UMATI/RFSU collaboration.
openalex: W2042193256 mag: 2042193256
Keywords: openalex:import

Dental emergence among urban Zambian school children: An assessment of the accuracy of three methods in assigning ages - Gillett, Rhonda M. (American Journal of Biological Anthropology, 1997)
In situations where birth records are unavailable and stated ages are unreliable, the emergence of the permanent dentition can serve as an indicator of age. Due to substantial variation in the timing of tooth emergence, a sample (n = 721) of Zambian school children, with known ages, was examined to provide a tooth emergence reference standard for the area. Three methods for assigning ages were utilized and their accuracy assessed. A random test sample was withheld from the original study in order to further evaluate the methods' accuracy. The three methods-1) number of teeth, 2) regression and 3) probit analysis-were applied to Zambian children, and estimates of age were made. Predicted ages were compared to actual ages to determine the percentage of accuracy in three categories-(+/-) .5, +/- 1.0 and +/- 2.0 years- and paired t-tests were conducted. Each of the three methods was then applied to the test sample, and their accuracy was evaluated in the same manner. Methods 1 and 2 were found to provide the higher percentage of correct ages within +/- .5 years, assigning roughly 39% of both male and female children within this increment. This was also the case at the next increment, with methods 1 and 2 assigning a higher percentage (66-76%) of children to the +/- 1.0 year category, while the accuracy of method 3 was quite a bit lower. The results for the test sample were very similar to those of the main sample. The overall accuracy of methods 1 and 2 was very similar in both the main and test samples, while method 3 had lower accuracy and t-tests indicated significant differences. Therefore, due to ease of application in the field setting, method 1, mean age per number of teeth emerged, is the method of choice.
openalex: W2056816315 mag: 2056816315
Keywords: openalex:import

Dental emergence among urban Zambian school children: An assessment of the accuracy of three methods in assigning ages - Gillett, Rhonda M. (American Journal of Biological Anthropology, 1997)
American Journal of Physical AnthropologyVolume 102, Issue 4 p. 447-454 Dental emergence among urban Zambian school children: An assessment of the accuracy of three methods in assigning ages Rhonda M. Gillett, Corresponding Author Rhonda M. Gillett University of Arizona, Tucson, Arizona 85721Carolina Population Center, University of North Carolina at Chapel Hill, CB# S120, University Square, Chapel Hill, NC 27516-3997.Search for more papers by this author Rhonda M. Gillett, Corresponding Author Rhonda M. Gillett University of Arizona, Tucson, Arizona 85721Carolina Population Center, University of North Carolina at Chapel Hill, CB# S120, University Square, Chapel Hill, NC 27516-3997.Search for more papers by this author First published: 06 December 1998 https://doi.org/10.1002/(SICI)1096-8644(199704)102:4<447::AID-AJPA2>3.0.CO;2-PCitations: 17AboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinked InRedditWechat Abstract In situations where birth records are unavailable and stated ages are unreliable, the emergence of the permanent dentition can serve as an indicator of age. Due to substantial variation in the timing of tooth emergence, a sample (n = 721) of Zambian school children, with known ages, was examined to provide a tooth emergence reference standard for the area. Three methods for assigning ages were utilized and their accuracy assessed. A random test sample was withheld from the original study in order to further evaluate the methods' accuracy. The three methods—1) number of teeth, 2) regression and 3) probit analysis—were applied to Zambian children, and estimates of age were made. Predicted ages were compared to actual ages to determine the percentage of accuracy in three categories—±.5, ±1.0 and ±2.0 years—and paired t-tests were conducted. Each of the three methods was then applied to the test sample, and their accuracy was evaluated in the same manner. Methods 1 and 2 were found to provide the higher percentage of correct ages within ±.5 years, assigning roughly 39% of both male and female children within this increment. This was also the case at the next increment, with methods 1 and 2 assigning a higher percentage (66–76%) of children to the ±1.0 year category, while the accuracy of method 3 was quite a bit lower. The results for the test sample were very similar to those of the main sample. The overall accuracy of methods 1 and 2 was very similar in both the main and test samples, while method 3 had lower accuracy and t-tests indicated significant differences. Therefore, due to ease of application in the field setting, method 1, mean age per number of teeth emerged, is the method of choice. Am J Phys Anthropol 102:447–454, 1997. © 1997 Wiley-Liss, Inc. Citing Literature Volume102, Issue4April 1997Pages 447-454 RelatedInformation
openalex: W4246713979
Keywords: openalex:import

Dental emergence among urban Zambian school children: An assessment of the accuracy of three methods in assigning ages - Gillett, Rhonda M. (American Journal of Biological Anthropology, 1997)
American Journal of Physical AnthropologyVolume 102, Issue 4 p. 447-454 Dental emergence among urban Zambian school children: An assessment of the accuracy of three methods in assigning ages Rhonda M. Gillett, Corresponding Author Rhonda M. Gillett University of Arizona, Tucson, Arizona 85721Carolina Population Center, University of North Carolina at Chapel Hill, CB# S120, University Square, Chapel Hill, NC 27516-3997.Search for more papers by this author Rhonda M. Gillett, Corresponding Author Rhonda M. Gillett University of Arizona, Tucson, Arizona 85721Carolina Population Center, University of North Carolina at Chapel Hill, CB# S120, University Square, Chapel Hill, NC 27516-3997.Search for more papers by this author First published: 06 December 1998 https://doi.org/10.1002/(SICI)1096-8644(199704)102:4<447::AID-AJPA2>3.0.CO;2-PCitations: 17AboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinked InRedditWechat Abstract In situations where birth records are unavailable and stated ages are unreliable, the emergence of the permanent dentition can serve as an indicator of age. Due to substantial variation in the timing of tooth emergence, a sample (n = 721) of Zambian school children, with known ages, was examined to provide a tooth emergence reference standard for the area. Three methods for assigning ages were utilized and their accuracy assessed. A random test sample was withheld from the original study in order to further evaluate the methods' accuracy. The three methods—1) number of teeth, 2) regression and 3) probit analysis—were applied to Zambian children, and estimates of age were made. Predicted ages were compared to actual ages to determine the percentage of accuracy in three categories—±.5, ±1.0 and ±2.0 years—and paired t-tests were conducted. Each of the three methods was then applied to the test sample, and their accuracy was evaluated in the same manner. Methods 1 and 2 were found to provide the higher percentage of correct ages within ±.5 years, assigning roughly 39% of both male and female children within this increment. This was also the case at the next increment, with methods 1 and 2 assigning a higher percentage (66–76%) of children to the ±1.0 year category, while the accuracy of method 3 was quite a bit lower. The results for the test sample were very similar to those of the main sample. The overall accuracy of methods 1 and 2 was very similar in both the main and test samples, while method 3 had lower accuracy and t-tests indicated significant differences. Therefore, due to ease of application in the field setting, method 1, mean age per number of teeth emerged, is the method of choice. Am J Phys Anthropol 102:447–454, 1997. © 1997 Wiley-Liss, Inc. Citing Literature Volume102, Issue4April 1997Pages 447-454 RelatedInformation
openalex: W4246713979
Keywords: openalex:import

THE MOROCCAN AIRPORTS BECOME PART OF THE WORLD TRAINING NETWORK. - Hamon, Didier (Aeroports Magazine, 1997)
openalex: W659518833 mag: 659518833
Keywords: openalex:import

Reversible hearing impairment induced by lithium in the guinea pig - Horner, Kathleen C.; Huang, Zhiwu; Higuerie, Denise; Cazals, Yves (NeuroReport, 1997)
LITHIUM salts remain one of the most widely used treatments for depressive illness. The mechanisms involved probably include reduction in free inositol. Visual perceptive disturbances can be a side effect of the treatment. We report here for the first time that chronic lithium treatment in the guinea pig induces a predominantly low frequency hearing loss and, in the longer term, loss of sensitivity is observed across the whole audiogram. The changes are reversed when treatment is arrested. The observations could be accounted for, at least partially, by a lithium-induced perturbation of the phosphoinositide cascade within the inner ear.
openalex: W2020467135 mag: 2020467135
Keywords: openalex:import

Reassessing public expenditure priorities: The case of education in South Africa - Khuumalo, Bongani; Wright, Anthony J (Development Southern Africa, 1997)
This paper highlights one of the central challenges facing the present South African government ‐ meeting the strong demands for increased and more equitable provisions of education and maintaining fiscal discipline. This task need not be daunting, as theory and evidence suggest that there is considerable scope for rationalising the existing state provision of social services in South Africa to make them more equitable and efficient. We employ an economic theory of clubs and argue that the provision of basic education should be prioritised while the subsidisation of sophisticated and higher levels of education should be reconsidered. More specifically, the qualitative upgrading of basic schooling deserves more priority from the state while subsidies to exclusive schools and to university students need review. Such rationalisations should encourage sustained economic growth and enable the state to meet its RDP objectives without compromising its commitment to fiscal discipline. However, to achieve this the state will have to resist the strong pressures for the continued provision of services which bestow large private benefits on privileged groups.
openalex: W1984608677 mag: 1984608677
Keywords: openalex:import

Cooperative Research Project "ACACIA" (Arid Climate, Adaptation and Cultural Innovation in Africa) 1995-2010 - Kroepelin, S. (Pages (Bern), 1997)
Report of the workshopThis two-day workshop was convened with the twin aims of reviewing the state of water and climate research in Canada using isotope tracers and investigating the establish- ment of a revitalized "Canadian Network for Isotopes in Precipitation", as a contribution to the international GNIP program (Global Network for Isotopes in Precipitation), which is the well-known offspring of long-standing IAEA/Ii\MO efforts to document the distribu- tion of water isotopes in the global water ryde.
openalex: W2890339513 mag: 2890339513
Keywords: openalex:import

Linguistic and Cultural Comparisons: Middle School African American Students Learning Arabic. - Moore, Zena; English, Mark (1997)
openalex: W348619259 mag: 348619259
Keywords: openalex:import

Stress of Secondary School Teachers in Transkei, South Africa - Mwamwenda, Tuntufye S.; Monyooe, Lebusa A.; Glencross, Michael J. (Psychological Reports, 1997)
The purpose of this study was to explore self-reported stress experienced by secondary school teachers in Transkei, South Africa using a local unstandardized scale. Contrary to the literature on western teachers, an average rating of stress of 93.5 was reported by the 134 teachers, and no differences were noted between the 66 men and 68 women.
openalex: W2004839766 mag: 2004839766
Keywords: openalex:import

Education for all by the year 2000 (EFA 2000) in some countries in Africa: Can teacher education ensure the quantity, quality and relevance of that education? - Ndawi, Obert Paradzai (International Journal of Educational Development, 1997)
This paper identifies and explores three basic challenges which EFA 2000 poses to teacher education in Africa, viz: quality, quantity and relevance. Researched data is used to show the extent of the problems and to argue for some possible solutions suggested as to how teacher education in Africa could best prepare to meet these problems. There are many (even more fundamental) factors that will affect the quality, quantity and relevance of any education system. This paper focuses specifically on how teacher education could make its limited contribution towards ensuring a better EFA 2000. Significantly, educationists in general, and teacher educators in particular, are challenged to take the responsibility of ensuring that the education, which it is the business of their profession to give, measures up to the demands of quantity, quality and relevance to the needs of every learner, not just to the needs of those few who will continue to university.
openalex: W2077758619 mag: 2077758619
Keywords: openalex:import

Can research into the development of education in post-colonial Africa shape education policies in South Africa? - Nieuwenhuis, F. J. (International Journal of Educational Development, 1997)
This article is based on the premise that the globalisation of education impacts directly on the development of education policy in developing countries. Internationally, in both developed and developing countries, the focus within policy development in education has shifted over time. It seems obvious that these shifts in focus would have a direct impact on educational planning in developing countries and on the flow of donor aid. This assumption was analyzed in a study that was conducted in eight African countries (Botswana, Kenya, Malawi, Lesotho, Swaziland, Tanzania, Zambia and Zimbabwe) during the first part of 1995. Two important aspects of policy development that were reviewed, are discussed in this article: The process of education policy formulation and the implementation of education policy. It appeared that, in the past, educational policy formulation in Africa was guided by the conviction that education was the way to ensure economic growth, to restructure the social order, and to reduce the social ills of society in general. The study revealed the disparity between the formulation of educational policy and the implementation thereof in the context of the wider socio-economic and political development process. Turning to South Africa, the author reflects on the possible influence that research on educational development in Africa may have on policy development in South Africa. Based on the findings of this study, it is concluded that decision makers and implementers of education policy in South Africa can indeed benefit from studies of educational development in Africa.
openalex: W2058012086 mag: 2058012086
Keywords: openalex:import

Can research into the development of education in post-colonial Africa shape education policies in South Africa? - Nieuwenhuis, F. J. (International Journal of Educational Development, 1997)
This article is based on the premise that the globalisation of education impacts directly on the development of education policy in developing countries. Internationally, in both developed and developing countries, the focus within policy development in education has shifted over time. It seems obvious that these shifts in focus would have a direct impact on educational planning in developing countries and on the flow of donor aid. This assumption was analyzed in a study that was conducted in eight African countries (Botswana, Kenya, Malawi, Lesotho, Swaziland, Tanzania, Zambia and Zimbabwe) during the first part of 1995. Two important aspects of policy development that were reviewed, are discussed in this article: The process of education policy formulation and the implementation of education policy. It appeared that, in the past, educational policy formulation in Africa was guided by the conviction that education was the way to ensure economic growth, to restructure the social order, and to reduce the social ills of society in general. The study revealed the disparity between the formulation of educational policy and the implementation thereof in the context of the wider socio-economic and political development process. Turning to South Africa, the author reflects on the possible influence that research on educational development in Africa may have on policy development in South Africa. Based on the findings of this study, it is concluded that decision makers and implementers of education policy in South Africa can indeed benefit from studies of educational development in Africa.
openalex: W2058012086 mag: 2058012086
Keywords: openalex:import

Book Review: Encyclopedia of African‐American Education - Peelle, Carolyn C. (Equity & excellence in education, 1997)
openalex: W2072930271 mag: 2072930271
Keywords: openalex:import

Two education projects in Yemen - Petrucci, Stefano (1997)
This Precis entitled, Two education projects in Yemen, complements the Bank's Operations and Evaluation Department (OED), Performance audit report, Yemen : Fifth and sixth education projects, Report No. 15667, dated May 28, 1996. The audit concludes that fewer or simpler projects, with a stronger focus on sector analysis, might have been more successful. More emphasis on monitoring and evaluation would also have guided the projects towards cost-effective outcomes and sound policy development.
openalex: W385524605 mag: 385524605
Keywords: openalex:import

Not Out of Africa: How Afrocentrism became an Excuse to Teach Myth as History. - Roth, Ann Macy; Lefkowitz, Mary R.; Rogers, Guy MacLean (The American Historical Review, 1997)
* Introduction * Myths of African Origins * Ancient Myths of Cultural Dependency * The Myth of the Egyptian Mystery System * The Myth of the Stolen Legacy * Conclusion * Epilogue
openalex: W2075395842 mag: 2075395842
Keywords: openalex:import

Management of Higher Education with Special Reference to Financial Management in African Institutions. IIEP Contributions, No. 28. - Sanyal, Bikas C.; Martin, Michaela (1997)
openalex: W162086505 mag: 162086505
Keywords: openalex:import

Controlling teachers' work: The South African state and curriculum control - Sebakwane, Shirley M. (International Journal of Qualitative Studies in Education, 1997)
This paper focuses on factors a ecting women teachers' work in Lebowa secondary schools. It discusses whether teachers are aware of being ideologically controlled by a centralized curriculum and the structure of apartheid by focusing on languages (i.e., Sepedi, English, and Afrikaans). Since there is a serious lack of any material of a qualitative nature in the country on teachers' work, the paper hopes to contribute to the debate on language issues (as well as policy issues) from the teachers' perspectives, especially in this period of restructuring the South African education system. Furthermore, by using the symbolic interactionist concept of ''self,'' the paper employs teachers' individual coping strategies to illustrate how women teachers respond to and resist these controls in di erent work contexts.
openalex: W2051434715 mag: 2051434715
Keywords: openalex:import

Successful Pedagogy in Urban Schools: Perspectives of Four African American Teachers - Stanford, Grace Cureton (Journal of Education for Students Placed at Risk (JESPAR), 1997)
Despite numerous attempts in the 1990s to reform urban schools, little attention has been given to understanding the beliefs and practices of successful African American urban teachers and applying the resulting knowledge to reform proposals. This article attempts to build on previous studies of exemplary African American teachers through its portrayal of the beliefs and practices of four successful urban African American teachers within the context of existing research. The persistence of common themes across numerous studies suggests that successful African American pedagogy is not idiosyncratic. This interpretative study provides a way to recognize and understand such pedagogy.
openalex: W2000647297 mag: 2000647297
Keywords: openalex:import

Abnormal eating attitudes in secondary-school girls in South Africa–a preliminary study. - Szabo, Christopher Paul; Hollands, Clare (PubMed, 1997)
To document the existence of eating attitudes that may reflect current, pre- or subclinical eating disorders. To establish preliminary prevalence figures for abnormal eating attitudes.Cross-sectional survey of eating attitudes.Non-clinical, community-based.Female high-school pupils.Total score derived from a self-report questionnaire, Eating Attitudes Test (EAT-26), which measures eating attitudes. Factor profile describing dimensions of eating-related psychopathology, derived from the clustering of questions on the EAT-26.An overall prevalence figure of abnormal eating attitudes of 21.66% was documented. Black pupils had a higher prevalence than white pupils (37.5% v. 20.67%). The factor profile of respondents with abnormal eating attitudes did not differ between the race groups, although within the total sample, black respondents had a significantly stronger drive toward thinness. A significant developmental continuum was established, with prevalence figures for abnormal eating attitudes increasing with each standard from Standard 7 onward. The study provides preliminary epidemiological data on the prevalence of adolescent girls either suffering from or at risk of the development of an eating disorder. In addition, the study also provides evidence of the need for intervention strategies that commence in the pre-teen years.
openalex: W2471636184 mag: 2471636184
Keywords: openalex:import

Factors influencing eating attitudes in secondary-school girls in South Africa–a preliminary study. - Szabo, Christopher Paul; Hollands, Clare (PubMed, 1997)
To establish factors in the environment, e.g. family, peer or media, as well as individual factors, e.g. self-perception, which may influence eating attitudes.Cross-sectional survey.Non-clinical, community-based.Female high-school pupils.Responses to questions pertaining to environmental as well as individual factors for each respondent ('dieting questionnaire'; self report). Total scores derived from a self-report questionnaire pertaining to eating attitudes (Eating Attitudes Test (EAT-26)). Statistical analysis, using analysis of variance procedures, to determine significant associations between the two questionnaires.Specific individual wishes, perceptions, behaviours and topics of conversation appear to influence as well as predict eating attitudes. Family, especially maternal, factors play a role in determining eating attitudes. Peer and media (television) factors are not significantly influential. The findings provide preliminary data on factors that influence eating attitudes in a group at risk for the development of eating disorders. The findings have implications for the formulation of preventive strategies within a comprehensive treatment approach.
openalex: W108744079 mag: 108744079
Keywords: openalex:import

Pedagogical classroom practice and the social context: The case of Botswana - Tabulawa, Richard (International journal of educational development, 1997)
Abstract Attempts have been made in Botswana to change teachers' didactic classroom practices. These attempts, however, have not been successful. More often than not, this lack of success is attributed to technical problems associated with the innovation delivery system. In this paper I argue that this technicist approach to problems of pedagogical change is faulty in that it treats pedagogical innovations as value-neutral. I argue that pedagogical innovations are social constructions influenced by the wider social context. By adopting a socio-historical approach, this paper traces the genesis of authoritarian classroom practices that studies have reported in Botswana classrooms. A number of factors are outlined as having influenced classroom practices in Botswana. These include the imported bureaucratic—authoritarian educational model of nineteenth century Britain, the missionaries/colonialists' belief in the supremacy of Western civilisation, the authoritarianism inherent in Tswana society, and the human resource development policy of post-independence Botswana. Today these interact with technical issues in complex ways to impede pedagogic change.
openalex: W2079159819 mag: 2079159819
Keywords: openalex:import

‘They are the government's children’. School and community relations in a Remote Area Dweller (Basarwa) settlement in Kweneng District, Botswana - Tshireletso, Lucky (International Journal of Educational Development, 1997)
Observations are made on how socio-economic background and culture of the Basarwa in the settlement influences their children's progress in schooling and their career aspirations. A further consideration is made on parents' participation in the school and what they consider to be the contribution of schooling to the development of life in their settlement. The study also looks at the perception of teachers, who are non-Basarwa, towards Basarwa pupils. The findings of the study show positive attitudes to schooling by both the parents and the pupils. In particular there is a general belief in the community that schooling can enable children to get employment in the future. The general view held by most Basarwa parents that as a result of poor socio-economic life conditions in the settlement they are left dependent on government to assist in the schooling of their children is explored to explain school and community interplay in the Basarwa settlement. The difference between the cultural background of Basarwa pupils and the school with its authoritarian set up alien to Basarwa culture provides the cultural dimension for this study in revealing school and community relations in a minority group of a remote rural community.
openalex: W2019613172 mag: 2019613172
Keywords: openalex:import

Requiem for the Sudan: War, Drought and Disaster Relief on the Nile - Waldron, Sidney R.; Burr, James; Collins, Robert O.; Eltigani, Eltigani E.; Keen, David; Ruay, Deng D. Akol (African studies review, 1997)
openalex: W2316011417 mag: 2316011417
Keywords: openalex:import

Evaluation of a Peer Health Education Project in the Gambia, West Africa - Wong, Tinadale; Travers, Kim D. (The International Quarterly of Community Health Education, 1997)
The purpose of this study was to evaluate a peer health education program among high school students in The Gambia, West Africa. Using convenience sampling, two of the ten high schools targeted by the program (one urban and one rural) were selected for evaluation. A total of eighty respondents, forty from each school, were randomly selected for participation. A validated questionnaire with both open and closed-ended questions was the data collection instrument which was subject to qualitative content analysis and quantitative descriptive analysis. Altogether, seventy-four participants completed the questionnaire for a response rate of 92.5 percent. Respondents' almost universal awareness of the peer health education program and their ability to recall the presentations suggested that peer education is an effective and acceptable means of disseminating information among youths. Over 90 percent of respondents applied the health information to their own lives, suggesting that peer health education can also have an influence on health behaviors of youths. Within the context of a developing country, peer health education was found to be culturally appropriate and allowed for the efficient utilization of local resources.
openalex: W2139947592 mag: 2139947592
Keywords: openalex:import

African-Americans' Participation in Teacher Education Programs - Sianjina, Rayton R.; Cage, Bob N.; Allen, Vikki (The Educational Forum, 1997)
openalex: W1966987104 mag: 1966987104
Keywords: openalex:import

Dilemmas of Student Identity and Academic Success in Post-Colonial Papua New Guinea. - Demerath, Peter (1997)
This study investigated how and why high school students in Papua New Guinea may resist education, particularly as these factors affect individual identity and academic success. The study was in response to concern over declining student achievement. In a coastal village and two schools in the provincial capital, informal interviews were conducted with elementary and high school students (grade 6 and 10 graduates), parents, teachers, administrators, and board members; structured group and individual interviews were conducted with 38 high school students at various achievement levels; high school students were observed within and outside school over 7 months; and a questionnaire was administered to 320 secondary school students. Results indicate that a critical mass of students who felt they would return to their villages on graduation preferred social experiences in town and school over academic success, and valued a village-based identity within the student culture. These students policed their peers for signs of Western-based identities and unacceptable levels of academic effort. This anti-academic culture posed dilemmas for higher-achieving students, many of whom curtailed their own academic efforts and hid their aspiration to a job in the modern economy. Contains 20 references. (MSE) ******************************************************************************** * Reproductions supplied by EDRS are the best that can be made * * from the original document. * ******************************************************************************** DILEMMAS OF STUDENT IDENTITY AND ACADEMIC SUCCESS IN POSTCOLONIAL PAPUA NEW GUINEA Paper presented at the Annual Meeting of the American Educational Research Association, Chicago, IL March 25, 1997 Peter Demerath Department of Educational Policy, Research, and Administration University of Massachusetts / Amherst
openalex: W291204636 mag: 291204636
Keywords: openalex:import

Assistance for African Higher Education: The Association for the Development of African Education (DAE) - Saint, William (International higher education, 1997)
International Higher Education (IHE) publishes insightful, informed, and high-quality commentary and analysis on trends and issues of importance to higher education systems, institutions, and stakeholders around the world.
openalex: W2108532998 mag: 2108532998
Keywords: openalex:import

Assistance for African Higher Education: The Association for the Development of African Education (DAE) - Saint, William (International higher education, 1997)
International Higher Education (IHE) publishes insightful, informed, and high-quality commentary and analysis on trends and issues of importance to higher education systems, institutions, and stakeholders around the world.
openalex: W2108532998 mag: 2108532998
Keywords: openalex:import

Education in Egypt : Forcusing on the Educational System and Pre-imiversity Education - Sato, Yu (年報いわみざわ : 初等教育・教師教育研究, 1997)
openalex: W2904034093 mag: 2904034093
Keywords: openalex:import

Relations Among Racial Identity Attitudes, Perceived Stressors, and Coping Styles in African American College Students - Neville, Helen A.; Heppner, P. Paul; Wang, Lifei (Journal of Counseling & Development, 1997)
This study expanded on previous research with African American college students at predominantly White institutions by examining the theoretically relevant but unexplored relations among racial identity attitudes and (a) both general and culture‐specific stressors and (b) problem‐focused coping styles. Ninety African American college students at a predominantly White university completed the Black Racial Identity Attitudes Scale, Black Student Stress Inventory, Problem Solving Inventory, and Problem‐Focused Style of Coping Scale. A series of multivariate regression analyses revealed that specific racial identity attitudes were statistically significant predictors of both general and culture‐specific stressors. In addition, one racial identity attitude status (immersion/emersion) was a unique predictor of general perceived stressors and problem solving. Results suggest the importance of racial identity schemata as a critical factor in predicting stress and coping responses of African American students at predominantly White institutions. The findings also underscore the utility in distinguishing between general and culture‐specific stressors, which traditionally have been ignored in the psychological literature.
openalex: W2150373875 mag: 2150373875
Keywords: openalex:import

African-American Culture,Classroom Rituals,and Conflict in the Classroom - Abe, G.O.; Bond-Jefferson, H. (徳島文理大学研究紀要, 1997)
openalex: W316971394 mag: 316971394
Keywords: openalex:import

Professionalism in process: mathematics teacher as researcher from a South African perspective - Adler, Jill (Educational action research, 1997)
Abstract The ‘teacher as researcher’ movement highlights the concept of ‘teacher as researcher’ and claims a key role for teachers in the production of knowledge about teaching. It constitutes teaching as an inquiring process, and as a powerful context and practice for professional development. This paper explores the potential of the teacher as researcher movement for the professional development of mathematics teachers in South Africa. It argues that themovement has particular historical roots in contexts of professionalism very different from South Africa. It proposes that the notion ‘teacher as inquirer’ is more inclusive of the very diverse teaching conditions in South Africa. It also argues that such a conception of the teacher could contribute to a more general theorisation of the teacher as researcher movement.
openalex: W2061528275 mag: 2061528275
Keywords: openalex:import

A Philosophy for Health Informatics Education in Developing Countries: Nigeria as a Case Study - Akinde, Adebayo D.; Soriyan, Hettie Abimbola; Adagunodo, Emmanuel R. (Methods of Information in Medicine, 1997)
The use of computers in the health sector has increased significantly during the last few years in Nigeria. This paper addresses the integration of health and informatics education, or health education and informatics education, or informatics education in health care delivery. It gives an introduction to the status of a health informatics programme in the daily practice of computer use. The essence of a health informatics curriculum, the planning and administration of the programme in medical schools, and what informatics education offers the health sector, even in a developing country, are presented. The problems of administering an informatics programme in a conventional medical training curriculum are highlighted. The article describes the philosophy which should underline the framework for the formulation of appropriate national policies and curricula for health informatics education in developing countries, using Nigeria as a case study.
openalex: W1491119330 mag: 1491119330
Keywords: openalex:import

Sexual Activity and Contraceptive Knowledge and Use Among In-School Adolescents in Nigeria - Amazigo, Uche; Silva, Nancy; Kaufman, Joan; Obikeze, D. S. (International family planning perspectives, 1997)
Among 2460 secondary school students surveyed in two southeastern Nigerian states only 36% could correctly identify the most likely time for conception to occur. Female students were considerably more likely than males to understand the timing of conception (46% vs. 25%); less dramatic differences emerged by students residence and grade in school. Among students who supplied information about their sexual activity 40% had had intercourse; the proportion who were sexually experienced climbed from 26% of 14-year-olds to 54-55% of 18- to 19-year-olds. While 36% of the young women had had sexual partners who were roughly their age 25% had been involved with older businessmen; the young women said they have intercourse more frequently and are less likely to restrict intercourse to the safe period of their cycle when they are involved with older partners than when they have boyfriends their own age. Only 17% of sexually active students had ever used a contraceptive method other than abstinence. In focus groups and in-depth discussions students expressed a strong desire for better education about contraception and the consequences of sexual intercourse and recommended that both schools and parents participate in educating young people about reproductive health. (authors)
openalex: W2077992500 mag: 2077992500
Keywords: openalex:import

Theatre for Reconciliation: Desire and South African Students - Barnes, Hazel E. (Theatre Journal, 1997)
Theatre for Reconciliation: Desire and South African Students Hazel Barnes (bio) It is imperative that the first democratically elected government in South Africa enable South Africans to come to terms with the injustice of their past. Such is the enormity of the impact of apartheid policies that the present government cannot grant individual and specific compensation to all. Instead, its representatives have created the Truth and Reconciliation Commission as a site and a vehicle for bearing witness to the individual and collective acts of violence and suffering under apartheid. 1 This witnessing has two functions. One is to encourage the confession of crimes by the perpetrators in order to make the truth public. This is essential in a country where press censorship and clandestine and unaccountable government operations withheld verifiable information about state violence and its antagonists from the public eye. This truth is reinforced by the testimony of the victims, which makes public and therefore legitimate the suffering formerly officially denied. The second function of the Commission is that of effecting reconciliation. The Commission hopes to bring about reconciliation through the public acknowledgment of a common humanity, which the apartheid state denied officially to blacks, thus compromising the humanity of all South Africans. In the words of the Commission’s principal officer, former Anglican Archbishop and Nobel Prize winner, Desmond Tutu, “African jurisprudence is restorative, rather than retributive.” 2 This common humanity is publicly affirmed ideally (but not always in practice) through the ability of ordinary citizens to understand the sufferings of others. The South African Truth and Reconciliation Commission has chosen to make hearings public, thus accentuating its ritualistic aspect, but it may also grant amnesty to perpetrators who make a public confession of apartheid crimes. 3 This choice has provoked controversy but affirms the belief of the [End Page 41] government and many citizens that forgiveness and reconciliation are prerequisites for a united nation and that transparency is the basis for trust. The Truth and Reconciliation Commission illustrates for South Africans the significance of public, ritualistic, and symbolic representation of pressing social tensions in order to acknowledge their emotional consequences and to facilitate the understanding and analysis of their impact. Symbolic representation of social conflict is also what theatre does. Both processes can be described, in Victor Turner’s terms, as “social drama.” 4 His identification of four phases in the evolution of social drama (namely: “breach of normal social relations”; “crisis”; “redressive action”; and “reintegration” or “irreparable schism”) could indeed apply to the drama of apartheid and its demise. Turner’s definition of the third phase, “redressive action,” includes legal processes as well as the performance of public ritual “in order to resolve certain kinds of crisis or legitimate other modes of resolution.” 5 In favoring, for the moment at least, a restorative rather than retributive jurisprudence, the Truth and Reconciliation Commission has mixed the conventions of a court of law with those of a ritual of collective cleansing. Rather than vainly attempt to analyze the nationwide processes of the ongoing Commission, this article will focus on a particular but, I think, exemplary fusion of theatrical practice and the public ritual of confession and reconciliation: the performance of David Lan’s play Desire by drama students at the University of Natal in Pietermaritzburg (UNP), in the heart of KwaZulu-Natal, the province most affected by civil war in recent years. 6 The play uses scenes of legal and ritual enactment to represent the processes of truth-telling and reconciliation and in so doing it shows the theatrical nature of these processes. In particular, the dramatic climax of the play is effected through public confession, which makes possible the healing of Rosemary, the central character, her realization of her power, and the reunification and reconciliation of members of her village. Our production of Lan’s play harnessed the subject matter of the drama as well as the processes of theatrical enactment and, through the process of rehearsal and public presentation, enabled students in our department to understand and affirm local practices of healing and reconciliation as well as to develop new skills of dramatic interpretation. Desire is set in a village in the Zambezi valley immediately after...
openalex: W2003097063 mag: 2003097063
Keywords: openalex:import

I Teach You the Way I See Us: Concepts of Self and Teaching of African-American Women Teachers Committed to Social Justice. - Beauboeuf–Lafontant, Tamara (1997)
This paper reports findings from a qualitative study of the nature of teachers' connections with their African American students. It is based on three rounds of interviews with six African American women teachers who had used the social justice curriculum Facing History and Ourselves. The teachers ranged in age from the mid-twenties to the mid-fifties, and had between 2 and 23 years of classroom teaching experience. All had taught in urban junior and senior high schools, and three were currently employed as teacher educators. The most striking aspect of their self-concepts as teachers was the way in which they brought maternal urgency to teaching. They compared teaching to parenting and saw themselves in a maternal role. They did not consider their gender a liability, but saw it as a touchstone for their insights as educators. Their pedagogy was also derived from their political attitudes and their recognition that there are relationships between schools and society that differentially structure the successes and failures of groups of children. The maternal interest the women had in their students and the political understandings they had of society were supported by their visions of moral justice and their beliefs that social justice is a matter of students coming to have the choice to determine and realize their potentials for themselves. In their pedagogy, these teachers did not distinguish among maternal, political, and moral aspects of teaching. Nor did they shy away from issues of race and gender in their lives or those of their students. (Contains 11 references.) (SLD) ******************************************************************************** * Reproductions supplied by EDRS are the best that can be made * * from the original document. * ******************************************************************************** I teach you the way I see us: Concepts of self and teaching of AfricanAmerican women teachers committed to social justice Tamara Beauboeuf-Lafontant Harvard Graduate School of Education
openalex: W119827334 mag: 119827334
Keywords: openalex:import

Rethinking school sanitation and hygiene education curriculum in rural and peri-urban communities in South Africa. - Bility, Khalipha M.; Burkhalter, Stephanie; Shaker, Abdulrazaq Oudah; Ahmed, Nasar Uddin; Onya, Hans; Masinyana, N (PubMed, 1997)
The provision of appropriate water, sanitation, and hygiene education, especially in schools, is very weak in some areas of South Africa. Inadequate education is one of the biggest obstacles to providing sufficient water in the country. The South African Hygiene Education Project (SASHEP) will be implemented during 1996-98 with the goal of developing a child-oriented sanitation and hygiene education curriculum informed by the perceptions of children and adolescents in primary schools. In the first phase of the project, researchers and educators in the Western Cape, Eastern Cape, Northern, and possibly KwaZulu Natal Provinces will investigate children's perceptions of water, sanitation, and hygiene practices. Child-friendly research approaches, such as the draw-and-write method and focus group discussions, will be used. The perceived needs for water, sanitation, and hygiene education among primary school students will later be used in the development, implementation, and evaluation of the school hygiene education curriculum and extracurricular activities. Curriculum activities will use methods such as the child-to-child approach.
openalex: W33408056 mag: 33408056
Keywords: openalex:import

Deaf Culture in Zimbabwe: Existence, Reality and Implication for Education - Chimedza, Robert (1997)
A ZBTE article on the importance of an educational system tailor made for the convenience of deaf children in Zimbabwe.
openalex: W2538115879 mag: 2538115879
Keywords: openalex:import

The O' Level Mathematics Curriculum for Zimbabwe: Does it Meet the Expectations for Quality Mathematics Education in Zimbabwe? - Chinhanu, Charles (1997)
A ZBTE article on the need to revamp the O-level Mathematics curriculum in Zimbabwe to make it more balanced between intuitive thinking and analytical thinking in Mathematics.
openalex: W2532647592 mag: 2532647592
Keywords: openalex:import

The Teacher, the School and Education Effectiveness in Zimbabwe: a Pilot Study - Chivore, Boniface Runesu Samuel (1997)
Education is about teaching and learning. This is the case at school level. At the center of learning are pupils. The effectiveness of education is measured in terms of the amount of learning acquired by the pupils. In any society children go to school to acquire academic skills. At primary school level, children go to school to learn reading, writing and mathematics. At secondary level children go to school to acquire academic skills based on various subjects broadly categorized as mathematics and science, arts and humanities, practical and commercial subjects. To acquire these skills pupils need teachers and schools. It is against this background that a study on secondary teacher effectiveness in Zimbabwe was undertaken.
openalex: W1886207684 mag: 1886207684
Keywords: openalex:import

HIV Risk Among Low-Income African American Mothers of Elementary School Children - Cummings, Gayle L.; Battle, Robynn S.; Barker, Judith C.; Krasnovsky, Flora (Journal of health and social policy, 1997)
Abstract Data from 119 African American low-income mothers of school aged children in Oakland, California show that 38% engaged in behavior that might place them at risk of exposure to the human immunodeficiency virus (HIV). Risk behaviors that were investigated included having multiple partners and having a partner with an incarceration history. Of women studied, 23% were at risk because of multiple partners, while 15% were at risk as a result of having had an incarcerated partner. Women who were < 35 years of age were three times more likely to report having had an incarcerated partner compared to women > 36 years of age (22% vs. 6%) (X<sp>2</sp> = 5.59, P < .01). Single women were also more likely to report having had a partner who had been incarcerated, 21% compared to 9% of married women (X<sp>2</sp> = 3.73, P < .05). Although no significant relationships were found with respect to condom use, a larger proportion of women with an incarcerated partner reported never using condoms (71%) compared to women without an incarcerated partner (63%); whereas, fewer women with multiple partners reported never using condoms (56%) compared to women without multiple partners (67%). Findings suggest that low-income African American women outside of traditional high-risk groups (i.e., generally studied in high-risk settings such as drug treatment centers, sexually transmitted disease [STD] clinics, hospitals or from the sex industry) may be at risk and should be targeted in HIV risk prevention programs. These women may not consider themselves to be at risk and are not generally targeted in HIV risk prevention programs because they are mothers, housewives, and working women.
openalex: W2092298094 mag: 2092298094
Keywords: openalex:import

Adapting to climate change in Africa - Downing, Thomas E.; Ringius, Lasse; Hulme, Mike; Waughray, Dominic (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W4255880686
Keywords: openalex:import

Adapting to climate change in Africa - Downing, Thomas E.; Ringius, Lasse; Hulme, Mike; Waughray, Dominic (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W4255880686
Keywords: openalex:import

Adapting to climate change in Africa - Downing, Thomas E.; Ringius, Lasse; Hulme, Mike; Waughray, Dominic (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W4255880686
Keywords: openalex:import

Adapting to climate change in Africa - Downing, Thomas E.; Ringius, Lasse; Hulme, Mike; Waughray, Dominic (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W4255880686
Keywords: openalex:import

Adapting to climate change in Africa - Downing, Thomas E.; Ringius, Lasse; Hulme, Mike; Waughray, Dominic (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W4255880686
Keywords: openalex:import; openalex:yes

Adapting to climate change in Africa - Downing, Thomas E.; Ringius, Lasse; Hulme, Mike; Waughray, Dominic (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W4255880686
Keywords: openalex:import

Demographic Responses to Ecological Degradation and Food Insecurity: Drought Prone Areas in Northern Ethiopia - Ezra, Markos (1997)
openalex: W201210633 mag: 201210633
Keywords: openalex:import

Descriptions of Motivation among African American High School Students for Their Favorite and Least Favorite Classes. - Gladney, Lawana Shirelle.; Greene, Barbara A. (1997)
The motivation to learn of African American high school students was examined by asking them about their favorite and least favorite classes. Two hundred and seventy-five students attending three urban high schools were randomly selected from their history classes to respond to a questionnaire on their perceptions of ability, goals, and reasons for disliking their least favorite class. There was a positive motivational pattern reported for their favorite classes. The students scored high on three variables that have been found to be most important for engagement and achievement: learning goals, future consequences, and perceived ability. Their reason for disliking the least favorite class was usually that the teacher was boring, and not because of perception of ability. Analysis of interview data for these students showed that teacher attitudes and methods of instruction were the significant reasons for liking and disliking the favorite and least favorite classes. Students also reported that the race of the teacher affected motivation in the classroom. These results show positive motivational orientations among students when their favorite classes were an
openalex: W72673940 mag: 72673940
Keywords: openalex:import

Returns to Education in Tie Manufacturing Sector in Zimbabwe: Some Empirical Evidence. - Godana, Tekaligne (South African Journal of Economics, 1997)
South African Journal of EconomicsVolume 65, Issue 1 p. 48-55 Returns to Education in Tie Manufacturing Sector in Zimbabwe: Some Empirical Evidence. TEKALIGNE GODANA, TEKALIGNE GODANA Professor of Economics, Universitv of Zimbabwe, Harare. The author would like to thank Rob Davies and Gene Grossman for their detailed comments on an earlier draft. He is also grateful to two referees for their valuable comments and suggestions. The usual disclaimer applies.Search for more papers by this author TEKALIGNE GODANA, TEKALIGNE GODANA Professor of Economics, Universitv of Zimbabwe, Harare. The author would like to thank Rob Davies and Gene Grossman for their detailed comments on an earlier draft. He is also grateful to two referees for their valuable comments and suggestions. The usual disclaimer applies.Search for more papers by this author First published: 22 August 2005 https://doi.org/10.1111/j.1813-6982.1997.tb01353.xAboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinkedInRedditWechat Volume65, Issue1March 1997Pages 48-55 RelatedInformation
openalex: W2038809485 mag: 2038809485
Keywords: openalex:import

Development of Library and Information Science Education in Africa - Gupta, Shanti S.; Gupta, D. K. (International Information & Library Review, 1997)
This paper gives a comprehensive account of the development of library and information science education in Africa. Ghana was first to start any kind of library education in 1944 but the formal education started at Ibadan, Nigeria in 1959. By 1970 there were six library schools; four new schools started during 1970s and another six during 1980s. Two Regional Schools with Master's programme in Information Science started in 1990. Two new schools are likely to start soon. Nigeria alone has eight schools providing professional education at all levels including PhD (which is only available in Nigeria) and an exclusive programme of Master in Information Science at ARCIS, Ibadan. Several schools, realizing the importance of new developments in information science and technology, are planning to incorporate this component into their curriculae. The existing programmes need to be assessed in context of information needs of Africa.
openalex: W2031789597 mag: 2031789597
Keywords: openalex:import

Development of Library and Information Science Education in Africa - Gupta, Shanti S.; Gupta, Dinesh K. (International Information & Library Review, 1997)
This paper gives a comprehensive account of the development of library and information science education in Africa. Ghana was first to start any kind of library education in 1944 but the formal education started at Ibadan, Nigeria in 1959. By 1970 there were six library schools; four new schools started during 1970s and another six during 1980s. Two Regional Schools with Master's programme in Information Science started in 1990. Two new schools are likely to start soon. Nigeria alone has eight schools providing professional education at all levels including PhD (which is only available in Nigeria) and an exclusive programme of Master in Information Science at ARCIS, Ibadan. Several schools, realizing the importance of new developments in information science and technology, are planning to incorporate this component into their curriculae. The existing programmes need to be assessed in context of information needs of Africa.
openalex: W2464910563 mag: 2464910563
Keywords: openalex:import

A STUDY OF THE WHO/GHANA GOVERNMENT HEALTH EDUCATION PROGRAMME FOR ENHANCING THE HEALTH STATUS OF WOMEN IN THE DANGME EAST DISTRICT - Gyening, P.A. (1997)
openalex: W2271816951 mag: 2271816951
Keywords: openalex:import

Structure, Standpoint and Practices: The Construction and Meaning of the Boundaries of Blackness for African-American Female High School Seniors in the College Choice Process. - Horvat, Erin McNamara (1997)
This qualitative study examined the role played by race in the college choice behavior of a group of minority females. It examines the college aspirations and decision making processes of Black female college-bound students and the influences of their parents, friends, college counselors, teachers, and school staff. Subjects were 50 students at 3 urban California high schools. Data collection included transcribed and coded interviews as well as extensive ethnographic observational data and review of documents. The schools were chosen for their ethnic and social differences and included: a predominantly African-American public school with predominantly lower class families; a racially mixed public school of diverse social class composition; and a predominantly white, private school with upper class families. It was found that the students chose colleges where they could see students like themselves who already attended the college. The high schools they attended had acted as templates that encouraged particular kinds of action with the role of Blackness having a different meaning at each of the three schools. The study supported the importance of race and class in defining students' choice behavior with race a clear marker of class membership and class distinction that greatly impacts decision making. Appended are a summary of the data and descriptions of the school settings. (Contains 15 references.) (JLS) ******************************************************************************** * Reproductions supplied by EDRS are the best that can be made * * from the original document. * ********************************************************************************
openalex: W337210624 mag: 337210624
Keywords: openalex:import

A Gendered Look at the Academic Achievement of Low Income African-American High School Students: Strategies of Success. - Hubbard, Lea (1997)
openalex: W159206941 mag: 159206941
Keywords: openalex:import

Teaching physics to large classes: the Botswana experience - Jain, Pushpendra K. (European Journal of Physics, 1997)
Some of the skills required to teach large classes are very different from the skills used for smaller classes. Good planning, coordination and team work are essential to the success of the course. In developing countries, there are also limitations of resources which include lack of manpower, laboratory equipment, facilities for their repair and maintenance, classroom and laboratory space, and audio-visual materials and equipment. This paper discusses the teaching of a physics course at the University of Botswana to a class of over 450 students. The lectures are held in two groups, and the class is divided into groups of 25 to 30 students for tutorials. Laboratories are conducted for groups of 50 to 60 students. The frequency of tests, different assessment components, and procedures and strategies for fair marking are also discussed. The experience gained from the case of Botswana can be applied to other countries of Africa, many of which have similar socio-economic conditions with a similar academic background of students. Une partie du savoir faire necessaire a l'enseignement de grandes classes est tres differente de celui utilisee dans le cas de classes plus petites. Bonne planification, coordination et travail d'equipe sont essentiels au succes du cours. Dans les pays en voie de developpement, interviennent aussi la faiblesse de moyens, ce qui inclus le manque de personnel, de materiel de laboratoires et d'equipements necessaires a leurs entretient, de locaux pour les cours et travaux pratiques, ansi que de materiels audio-visuels. Cet article discute de l'enseignement d'un cours de physique a l'Universite du Botswana a une classe de plus de 450 etudiants. Les etudiants sont divises en deux groupes pour les cours magistraux, et en groupes de 25 a 30 pour les travaux diriges. Les travaux pratiques sont dispenses a des groupes de 50 a 60 etudiants. La frequence des devoirs surveilles, les differentes composantes de l'evaluation des etudiants, et les strategies utilisees pour evaluation juste des etudiants sont aussi discutes. L'experience acquise dans le cas du Botswana peut etre appliquee a d'autres pays d'Afrique, dont beaucoup ont des conditions socio economiques semblables, ainsi des etudiants de niveau accademiques similaires.
openalex: W2064784735 mag: 2064784735
Keywords: openalex:import

The United Nations Convention to Combat Desertification in those Counties Experiencing Serious Drought and/or Desertification, Particularly in Africa; Implementing Agenda 21 - Jamal, Alia (Review of European Community and International Environmental Law, 1997)
Review of European Community & International Environmental LawVolume 6, Issue 1 p. 1-6 The United Nations Convention to Combat Desertification in those Counties Experiencing Serious Drought and/or Desertification, Particularly in Africa; Implementing Agenda 21 Alia Jamal, Alia Jamal Interim Secretariat of the Convention to Combat Desertification, Geneva Executive Center, 11/13 Chemin des Anemones, CH-1219 Chatelaine, Geneva, SwitzerlandSearch for more papers by this author Alia Jamal, Alia Jamal Interim Secretariat of the Convention to Combat Desertification, Geneva Executive Center, 11/13 Chemin des Anemones, CH-1219 Chatelaine, Geneva, SwitzerlandSearch for more papers by this author First published: 17 December 2002 https://doi.org/10.1111/1467-9388.00068Citations: 2AboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onFacebookTwitterLinkedInRedditWechat Citing Literature Volume6, Issue1March 1997Pages 1-6 RelatedInformation
openalex: W1993753161 mag: 1993753161
Keywords: openalex:import

Systemic Lupus Erythematosus in Relation to Environmental Pollution: An Investigation in an African-American Community in North Georgia - Kardestuncer, Tarik; Frumkin, Howard (Archives of Environmental Health, 1997)
The etiology of systemic lupus erythematosus is not well understood, although gender, race, genetic predisposition, and certain drugs are risk factors. Several environmental exposures have been implicated. In this study, we examined the prevalence and incidence of lupus in an African-American community that experienced long-standing exposures to industrial emissions. We hypothesized that lupus was elevated among residents of a specific community in Gainesville, Georgia. We included both a retrospective cohort study and a cross-sectional study designed to assess the incidence and prevalence, respectively, of lupus. The prevalence of lupus was 3 cases/300 persons (1000/100,000). Compared with the highest reported prevalence, this represents a 6-fold increase. The incidence of lupus was 3 cases/4709 person-years (63.7 cases/100,000 person-years). Compared with the highest reported incidence, this represents a 9-fold increase. The hypothesis that environmental toxins may induce lupus is consistent with the known ability of certain medications to do the same. The results suggest that long-standing exposure to industrial emissions may be associated with an increased risk of lupus.
openalex: W2002758269 mag: 2002758269
Keywords: openalex:import

Stress Balance and Emotional Life Complexes in Students in a Historically African American College - Launier, Raymond A. (The Journal of Psychology, 1997)
Abstract Emotional complexes can be found within the constellation of emotional experiences occurring and recurring around particular existential conditions or psychological themes operant within the life of an individual. Data from a sample of 200 African American college students were used to describe the emotional complexes of racial discrimination, financial strain, and optimism–pessimism. The Emotology Q-Deck, based on the Q-sort method (Block, 1978), was used to assess emotional life through self-report ratings of 26 positive and 26 negative emotions. More comprehensive than the traditional focus on singular emotional states or traits, the focus on emotional life complexes provides a more realistic understanding of the challenges and necessities of promoting community mental health, emotional well-being, and healthy intergroup relationships through educational, socioeconomic, and cultural interventions.
openalex: W2073595830 mag: 2073595830
Keywords: openalex:import

Effects of a randomized health education intervention on aspects of peproductive health knowledge and reported behaviour among adolescents in Zimbabwe - Mbizvo, Michael T.; Kasule, J.; Gupta, Vandana Ayyar; Rusakaniko, S; Kinoti, Stephen N.; Mpanju-Shumbushu, W; Sebina-Zziwa, Abby; Mwateba, R; Padayachy, Jude (Social Science & Medicine, 1997)
Unwanted teenage pregnancy and the attendant morbidity and mortality necessitate an understanding of the factors influencing adolescent sexuality and the implementation of programmes designed to improve their knowledge and reproductive behaviour. A randomized controlled study on reproductive health knowledge and behaviour was undertaken among adolescent pupils drawn from a multi-stage random cluster sample. A self-administered questionnaire was used to assess aspects of reproductive health knowledge and behaviour at baseline followed by a health education intervention, except for control schools. Results are based on 1689 responses made up of 1159 intervention and 530 control respondents. There was a significant increase in correct knowledge about aspects of menstruation in intervention as compared with control schools [odds ratio (OR) = 4.5, 95% confidence interval (CI) = 3.4–6.1). Significantly, (OR = 2.0, 95%CI = 1.1–3.9) more pupils from intervention than control schools scored correctly on practice relating to menstruation. Pupils from intervention schools were more likely (P < 0.001) to know that a boy experiencing wet dreams could make a girl pregnant and that a girl could get pregnant at her first sexual intercourse (OR = 1.4, 95%CI = 1.1–1.9). Knowledge of family planning was low in both groups at baseline but was high at five months follow-up in the intervention schools. The findings point to the need for early school-based reproductive health education programmes, incorperating correct information on reproductive biology and the subsequent prevention of reproductive ill health.
openalex: W2109602916 mag: 2109602916
Keywords: openalex:import

Children's Social Acceptance and Academic Achievement in Zimbabwean Multicultural School Settings - Mpofu, Elias (The Journal of Genetic Psychology, 1997)
Abstract Children's social acceptance as measured by sociometric ratings was examined in relation to their grade point averages. The sample consisted of 376 upper-middle-class, 12- to 13-year-old Zimbabwe Black and White school children and their teachers (N = 13). Multiple regression analysis indicated that, taking into account ethnicity, sex, family size, and number of languages spoken, social acceptance measures accounted for a significant proportion of the variance in the children's academic achievement. Within social acceptance measures, the children's actual rather than perceived social acceptance explained a greater proportion of the variance in their academic achievement.
openalex: W2150451911 mag: 2150451911
Keywords: openalex:import

Globalization, endogenous development and education in Africa - Ndoye, Mamadou (PROSPECTS, 1997)
openalex: W1988303714 mag: 1988303714
Keywords: openalex:import

African-American Students' Perceptions of Caring Teacher Behaviors in Catholic and Public Schools of Choice. - Nelson, Mark D.; Bauch, Patricia A. (1997)
The perceptions of students about caring teachers were studied in secondary Catholic and public magnet schools. Both types of schools were schools of choice, attended through student and family choice and not assignment by neighborhood. The sample for the study came from a national, federally funded project that studied the relationship between family choice and school responsiveness. The larger sample consisted of interviews with 300 high school seniors and their parents and 100 school teachers, counselors, and administrators. For this study, interviews from 88 African American students were used. The students attended four urban Catholic high schools, two public single-focus (one theme) urban magnet high schools, and two public multifccus (several areas of concentration) urban magnet high schools. Data were analyzed separately based on school type. The concept groups of expectations, encouraging, and challenging were emphasized in the conversations of students from all three types of schools, suggesting that these behaviors are consistent in defining caring for students in all the school types. Students from Catholic schools tended to associate helping and involving with caring teacher behavior more often than students in the public schools. The concept of relationship was mentioned more by Catholic school students and students from single-focus magnets. Concern was mentioned more often by Catholic and multifocus school students. It is suggested that students in Catholic high schools may have more personal interaction with parents and teachers and may expect and value such interaction more as indicative of caring. (Contains 4 tables and 30 references.) (SLD) ******************************************************************************** Reproductions supplied by EDRS are the best that can be made from the original document. ******************************************************************************** AFRICAN-AMERICAN STUDENTS' PERCEPTIONS OF CARING TEACHER BEHAVIORS IN CATHOLIC AND PUBLIC SCHOOLS OF CHOICE U.S. DEPARTMENT OF EDUCATION Office of Educational Research and Improvement EDUCATIONAL RESOURCES INFORMATION CENTER (ERIC) This document has been reproduced as received from the person or organization originating it. Minor changes have been made to improve reproduction quality. Points of view or opinions stated in this document do not necessarily represent official OERI position or policy. by Mark D. Nelson College of Communication The University of Alabama Patricia A. Bauch College of Education The University of Alabama PERMISSION TO REPRODUCE AND DISSEMINATE THIS MATERIAL HAS BEEN GRANTED BY Pedrico Baud() TO THE EDUCATIONAL RESOURCES INFORMATION CENTER (ERIC) Paper presented at the annual meeting of The American Educational Research Association, Chicago, 1997 BEST COPY AVAILABLE 2
openalex: W105355039 mag: 105355039
Keywords: openalex:import

Rheumatic disorders at a Zambian Teaching Hospital - Njobvu, Panganani (British journal of rheumatology, 1997)
openalex: W2052221308 mag: 2052221308
Keywords: openalex:import

The Environment of Crises in the Nigerian Education System - Nwagwu, Cordelia C. (Comparative Education, 1997)
ABSTRACT The Nigerian education system witnessed tremendous expansion between independence in 1960 and 1995. However, the rate declined after 1986 when economic depression resulted in the introduction of the Structural Adjustment Programme. A population explosion, frequent changes in the government due to military coups, a depressed economy and unplanned and uncontrolled educational expansion all created an environment of crisis in the education system. The crises included those of poor funding, inadequate facilities, admission and certificate racketeering, examination malpractices, general indiscipline and the emergence of secret cults. Personnel management problems resulted in frequent strikes and closures and the abandonment of academic standards. The thesis is that any society which stimulates the uncoordinated growth of its education system and then fails to provide the necessary dedicated teachers, teaching and learning facilities and operating funds for staff and student welfare services, is creating an environment within which all types of problems and crises will flourish. Lessons for other developing nations include the need for democratically elected stable governments instead of military regimes and better planning, funding and management of the education system.
openalex: W1973083384 mag: 1973083384
Keywords: openalex:import

Pathogenetic Mechanisms of Impaired Glucose Tolerance and Type II Diabetes in African-Americans: The significance of insulin secretion, insulin sensitivity, and glucose effectiveness - Osei, Kwame; Gaillard, Trudy; Schuster, Dara (Diabetes care, 1997)
OBJECTIVE To examine the significance of alterations in insulin sensitivity index (S1), glucose effectiveness (Sg), and β-cell function in the pathogenesis of type II diabetes in African-Americans with varying degrees of glucose intolerance. RESEARCH DESIGN AND METHODS A total of 154 African-Americans residing in Franklin County, Ohio, were studied. There were 101 subjects with normal glucose tolerance (NGT), 36 with impaired glucose tolerance (IGT), and 17 with type II diabetes. An oral glucose tolerance test (OGTT) was performed on each subject. S1 and Sg were measured by insulin-modified, frequently sampled intravenous glucose tolerance test (FSIGT). RESULTS The mean fasting and postprandial serum glucose levels were significantly greater in the diabetic groups when compared with the IGT and NGT groups. In contrast, while fasting serum insulin and C-peptide levels tended to be greater in the type II diabetic and IGT groups, the postprandial responses were blunted at 30 min in the IGT and type II diabetic groups when compared with the NGT group. The mean acute first-phase insulin release after intravenous glucose was blunted also in the IGT and type II diabetic groups when compared with the NGT group. The S1 was significantly lower in the IGT (1.51 ± 0.19) and type II diabetic (0.61 ± 0.15) groups when compared with the NGT group (2.94 ± 0.20 × 10−4 · min−1 · μU−1 · ml−1). The Sg was not significantly different in the NGT (2.90 ± 0.20), IGT (2.47 ± 0.19), and the type II diabetic (2.35 ± 0.15 × 10−2/min) groups. The glucose effectiveness at theoretical zero insulin concentration (GEZI) followed similar patterns as the Sg. Furthermore, the basal insulin effect (BIE) was significantly lower in the IGT and type II diabetic groups compared with the NGT group. In addition, the glucose decay constant (Kg) was significantly lower (P < 0.001) in the IGT (1.21 ± 0.13) and the type II diabetic (1.07 ± 0.12) groups when compared with the NGT group (2.03 ± 0.10% per minute). CONCLUSIONS Our present study demonstrates that African-American patients with IGT and mild type II diabetes have significant reduction in β-cell function, insulin sensitivity, and BEI but have normal and intact Sg and GEZI when compared with NGT subjects. We conclude the following: 1) a reduction in Sg does not appear to play a significant role in the pathogenetic mechanism of IGT and type II diabetes in African-American patients, and 2) the intact Sg in the IGT and type II diabetic groups could serve as a compensatory mechanism for hyperglycemia in African-Americans.
openalex: W2017881732 mag: 2017881732
Keywords: openalex:import

Mate Selection Preferences Among African American College Students - Ross, Lone (Journal of Black Studies, 1997)
All cultures have rules regarding mate selection. Many societies encourage either homogamy or heterogamy. Homogamy refers to marriage between individuals with similar social and personal characteristics, whereas heterogamy refers to marriage between individuals with different social or personal characteristics. Although there is some freedom in mate selection in American society, the United States is still basically a society whose norms encourage homogamy. Some of the major factors that influence mate selection include socioeconomic status, race, age, and parental and peer pressures. The purpose of this article is to examine the attitudes and preferences of African American college students toward physical and social status related variables regarding dating and future mate selection. Several social status and attractiveness related variables, along with selected background variables (including gender), were analyzed to note relationship patterns. Of particular interest was the importance of skin color or skin tone and social status as mate selection preferences among African American college students. There may be vast differences between attitudes toward mate selection and actual behaviors when selecting mates for marriage. Attitudinal research on skin color and social status preferences as they relate to mate selection on African American populations is lacking.
openalex: W1970606349 mag: 1970606349
Keywords: openalex:import

In-service teacher training programmes: the case of Palestine - Sabri, Khawla Shakhshir (Journal of in-service education, 1997)
Abstract This research aims to assess the effectiveness of the in-service teacher training programme in Palestine, based on the opinion of the teacher participants in order to improve future in-service programmes. The Spearman's coefficient of rank correlation p test has been used to examine the stated null hypotheses. It indicates that the participants considered the concept of planning a lesson plan as the most important competency. The research found that there is a positive association among all groups of teachers (except onc group) concerning the importance of the listed objectives of the in-service programme, at a significant level of .05. Finally, the study recommended that in-service teacher programmes should place more emphasis on class applications and teaching techniques using different training programmes.
openalex: W2070659905 mag: 2070659905
Keywords: openalex:import

Impacts of global climate change in a hydrologically vulnerable region: challenges to South African hydrologists - Schulze, R. E. (Progress in Physical Geography: Earth and Environment, 1997)
South Africa is already hydrologically vulnerable and this is likely to be exacerbated by both nonpermanent ENSO-related as well as more permanently greenhouse-gas forced climate changes. Climate change effects are explained by way of the hydrological equation. This serves as a backdrop to a brief review, in a hydrological context, of projected perturbations to temperature, rainfall and potential evaporation, over southern Africa. Methodologies for simulating hydro logical responses to climate change are assessed. These include more direct GCM-derived output, with some emphasis on recent advances in climatic downscaling, and the application of appro priate hydrological models for use in impact studies. Scale problems of importance to hydrologists are highlighted. Directions to which climate change-related hydrological research efforts should be expended in South Africa are summarized, before two case study simulations, one a general sensitivity study of hydrological responses to changes in rainfall over southern Africa, the other a more specific hydrological response study to the El Niño of the 1982-83 season, are presented. The article concludes with a discussion on whether or not water resources practitioners in South Africa should respond to climate change.
openalex: W1986708318 mag: 1986708318
Keywords: openalex:import

Autobiographical Stories of Rites of Passage of Caucasian and African-American Female Doctoral Students in Educational Administration - Shapiro, Joan Poliner (Journal of School Leadership, 1997)
This paper focuses on the autobiographical stories of one Caucasian and three African-American female doctoral students during their rites of passage in departments of educational administration. A rite of passage has been defined as the student's journey toward the completion of the dissertation. While not generalizable, the four stories offer different perspectives and experiences of nontraditional doctoral students and may provide new insights for those who advise and teach diverse graduate students.
openalex: W2728449825 mag: 2728449825
Keywords: openalex:import

Variables that Impact the Education of African American Students: Parental Involvement, Religious Socialization, Socioeconomic Status, Self-Concept, and Gender. - Sojourner, Jeannette; Kushner, Susan N. (1997)
openalex: W157343230 mag: 157343230
Keywords: openalex:import

Deaf Adults' Emic Views on Deaf Education in South Africa: Looking Back To Improve the Future. - Störbeck, Claudine (1997)
openalex: W193624757 mag: 193624757
Keywords: openalex:import

How We Got Over: The Moral Teachings of The African–American Church on Business Ethics - Trimiew, Darryl M.; Greene, Michael B. (Business Ethics Quarterly, 1997)
Abstract: An analysis of the business ethics of the African-American church during and after Reconstruction reveals that it is a conflicted ethic, oscillating between two poles. The first is the sacralization of the business ethic of Booker T. Washington, in which self-help endeavors which valorize American capitalism but are preferentially oriented to the African-American community are advanced as the best and only options for economic uplift. The second is the “Blackwater” tradition, which rejects any racial discrimination and insists upon social justice. The inability of the Washingtonian business ethic to address the needs of the Black underclass are explored. A new business ethic is called for, which would be committed to meeting the basic needs of the most disadvantaged members of American society and those of the “international poor.”
openalex: W1979509791 mag: 1979509791
Keywords: openalex:import

Classroom Instruction and Learning Environment Differences between Effective and Ineffective Urban Elementary Schools for African American Students - Waxman, Hersholt C.; Huang, Shwu‐Yong L. (Urban Education, 1997)
The purpose of this study was to investigate whether there are significant differences between effective and ineffective urban schools based on (a) students' classroom behavior and (b) students' motivation and perceptions of their classroom learning environment. Students from four effective and four ineffective urban elementary schools that served predominantly African American students were systematically observed during the school year and completed three surveys about 6 weeks before the end of the school year. Students from effective schools were observed significantly more (a) working in an individualized setting, (b) interacting with their teacher, and (c) working on written assignments. Students from effective schools also reported significantly higher achievement motivation, academic self-concept, task orientation, rule clarity, and student aspiration scores than students from the ineffective schools.
openalex: W2010950585 mag: 2010950585
Keywords: openalex:import

El Niño and Drought Early Warning in Ethiopia - Wolde–Georgis, Tsegay (Social Science Research Network, 1997)
El Nino (EN) is the increase in the surface temperatures (SST) in the central and eastern equatorial Pacific Ocean. EN results from changes in the pattern and direction of winds and ocean currents in the region, which have potentially catastrophic effects. Many researchers now believe that the occurrence of various droughts in Africa, especially in Southern Africa and the Horn, are caused by physical processes related to the occurrence of ENSO events thousands of miles away. If valid and reliable information about the linkages between these occurrences becomes available, it could help to forecast Sub-Saharan African droughts. ENSO-based drought early warning could send a wake-up call to governments to prepare for national food shortages. With such information, policies that reduce the impact of drought could be introduced. An early warning with many months of lead time, such as could be provided by ENSO information, would eliminate the excuse of national governments who claim to be unaware of the advent of drought. When drought causes famine, and a reliable drought early warning was available, it becomes a man-made disaster.
openalex: W172355085 mag: 172355085
Keywords: openalex:import

Public Policy and the Management of Higher Education in Sub-Saharan Africa: The Case of Kenya - Gray, Kenneth R.; Credle, Sid Howard (Journal of Marketing for Higher Education, 1997)
openalex: W2039642266 mag: 2039642266
Keywords: openalex:import

Encyclopedia of African-American education (Choice Reviews Online, 1997)
openalex: W1490791419 mag: 1490791419
Keywords: openalex:import

Integration of Environmental Education in Social Science Curricula at the Secondary School Level in Nigeria: problems and prospects - Adedayo, Adebisi; Olawepo, J. A. (Environmental Education Research, 1997)
Summary Nigeria is one of the developing world countries that are committing themselves to the importance of environmental education (EE) as a means of improving the environment, which has suffered from considerable pollution and degradation. As part of the strategies’ for raising the level of awareness and engendering attitudes amongst the population through the formal school system, the Federal government has designed curricula with strong EE elements for a brand new subject called citizenship education to be introduced at the primary and secondary levels. As a response to this situation, this paper examines the existing elements in and the various approaches to integrating EE in social science with reference to Nigeria. This is followed by an analysis of the constraints and the support systems which are likely to be helpful to EE at the secondary school level. Some measures and guidelines that could enhance the effective integration of EE at the secondary school, if practised, are suggested.
openalex: W2087236447 mag: 2087236447
Keywords: openalex:import

The School Improvement Programme of the Aga Khan Education Service, Kenya at Kisumu, Western Kenya: Evaluation Report. - Capper, Joanne; Nderitu, Shelomith; Ogula, Paul (1997)
openalex: W135890236 mag: 135890236
Keywords: openalex:import

Plasma fatty acid levels in South African interethnic male high school pupils at different ultimate risks of coronary heart disease - Chetty, N; Naran, Nitien H.; Walker, Alexander; Seftel, H. C.; Joffe, B. I.; Raal, Frederick J. (Clinica Chimica Acta, 1997)
While coronary heart disease (CHD) is responsible for about a quarter of deaths in South African white, coloured and Indian populations, the rate is very low in the black population. Dietary risk factors for CHD include high intakes of saturated fatty acids and cholesterol, with low intakes of mono and polyunsaturated fatty acids. In a characterization study, plasma fatty acid profiles have been determined in seven groups of high school pupils aged 16–18 years, namely, white, rural black, urban black and middle-class and lower socio-economic class coloureds and Indians. Plasma fatty acids were measured by gas liquid chromatography in 20 subjects from each group. Contrary to expectation, urban and rural black pupils had the highest mean molar percentage composition of saturated fatty acids, largely myristic (14:0) and palmitic (16:0) acids. Rural blacks and middle-class coloureds the highest molar percentage composition of monounsaturated fatty acids, primarily oleic acid (18:1). Again unexpectedly, white, coloured and Indian groups had the highest level of polyunsaturated fatty acids, due entirely to linoleic acid (18:2). As the findings are unrelated to proneness to CHD mortality in the particular communities studied, plasma fatty acid levels are not predictive of the disease. Epidemiologically, there are many examples of lack of correlation in serum lipid levels and proneness to CHD.
openalex: W1967814655 mag: 1967814655
Keywords: openalex:import

Apartheid and the Socio-Political Context of Education in South Africa: A Narrative Account - Constas, Mark A. (Teachers College Record, 1997)
Historically, education in South Africa formed an important part of the government's plan to develop a racially segregated society. While there is a significant amount of research that describes the widespread problems of schooling in South Africa, there are few reports about the subjective qualities of education. The primary purpose of the present article is to provide a more personalized account of what it has meant to be educated as a student and to work as a teacher under the conditions of apartheid. In order to accomplish this objective, a life history approach was combined with an archival review to construct a narrative account of selected aspects of the education provided for black South Africans. Because of the long-standing political oppression of South Africa's black population, it was considered important to develop such a record by listening to the voices of individuals who, as students, endured poor educational conditions only to find themselves, as teachers, practicing under circumstances that were largely unchanged. Within the life-history approach, interview data were obtained from two teachers, who attended schools and began their respective teaching careers during different periods of South Africa's sociopolitical history. In order to contextualize the findings, the participants’ experiences were considered in relation to selected elements of the legislative and political history of South Africa. The empirical result of the research is an historical description of education in South Africa, illustrated by the personal stories and professional experiences of two practicing teachers. The article concludes by considering the way in which selected theories of oppression and resistance explain or fail to explain the experiences of the two participants.
openalex: W161061564 mag: 161061564
Keywords: openalex:import

The gathering storm that is the HIV epidemic in Papua New Guinea - Dwyer, Jennifer B.; Lovell-Jones, S. (Australian and New Zealand Journal of Medicine, 1997)
Australian and New Zealand Journal of MedicineVolume 27, Issue 1 p. 3-5 Free Access The gathering storm that is the HIV epidemic in Papua New Guinea J. M. DWYER, J. M. DWYER Head of Division of MedicineSearch for more papers by this authorS. LOVELL-JONES, S. LOVELL-JONES Executive Assistant, AIDS Society for Asia and the Pacific, Division of Medicine, Prince of Wales Hospital, Sydney, NSWSearch for more papers by this author J. M. DWYER, J. M. DWYER Head of Division of MedicineSearch for more papers by this authorS. LOVELL-JONES, S. LOVELL-JONES Executive Assistant, AIDS Society for Asia and the Pacific, Division of Medicine, Prince of Wales Hospital, Sydney, NSWSearch for more papers by this author First published: 25 March 2008 https://doi.org/10.1111/j.1445-5994.1997.tb00905.xCitations: 2AboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL References 1 Dwyer JM, Mahathir M, Nath LM. The epidemic of HIV infections in Asia and die Pacific. Med J Aust 1996; 165: 489– 93. 2 O'Leary MJ, Van Der Meijden WI, Malau C, Delamare O, Pyakalyia T. HIV serosurveillance in Papua New Guinea. PNG Med J 1993; 36: 187– 91. 3 Seaton RA, Wembri JP, Armstrong P, Ombiga J, Naraqi S, Kevau I. Symptomatic human immunodeficiency virus (HIV) infection in Papua New Guinea. Aust NZ J Med 1996; 26: 783– 8. 4 Cooke R. The colorful people of Papua New Guinea: Some of their habits and some diseases which result from these habits. Pathol Annu 1986; 21: 311– 46. 5 Jenkins C, Pataki-Schweizer K. Knowledge of AIDS in Papua New Guinea. PNG Med J 1993; 36: 192– 204. 6 Jenkins CL. Sex as work in Papua New Guinea. Proceedings of the Tenth International Conference on AIDS. Yokohama, Japan: 1994, 712 August. 7 Bleibtreu-Ehrenberg G. Pederasty among primitives: Institutionalized initiation and cultic prostitution. J Homosex 1990; 20: 13– 30. 8 Baldwin JD, Baldwin JI. The socialization of homosexuality and heterosexuality in a Non-Western Society. Arch Sex Behav 1989; 18: 13– 29. Citing Literature Volume27, Issue1February 1997Pages 3-5 ReferencesRelatedInformation
openalex: W1965764997 mag: 1965764997
Keywords: openalex:import

Achievement Motivation in Rural African-American Female High School Honor Graduates. Preliminary Report. - Grant, Dale F. (1997)
openalex: W2729218905 mag: 2729218905
Keywords: openalex:import

School quality, achievement bias, and dropout behaviour in Egypt - Hosni, Djehane (Economics of Education Review, 1997)
One of the major educational challenges in the United States is ensuring that all students graduate from high school. This article reviews research evidence on four facets of this issue: (1) the magnitude of the problem and trends over time; (2) the economic and social consequences of dropping out; (3) the causes of the problem, including individual factors and institutional factors associated with families, schools, and communities; and (4) solutions to the problem, ranging from smaller-scale programmatic solutions to larger-school systemic solutions.
openalex: W2052855692 mag: 2052855692
Keywords: openalex:import

Mathematics and Science Performance in the Middle School Years in South Africa: A Summary Report on the Performance of South African Students in the Third International Mathematics and Science Study (TIMSS). - Howie, Sarah J. (1997)
openalex: W5873116 mag: 5873116
Keywords: openalex:import

Guidelines on training and credentialling for the the practice of minimal access surgery (MAS). Recommendations of the South African Society of Endoscopic Surgeons (SASES). - Jamieson, J. R. (PubMed, 1997)
openalex: W2416893366 mag: 2416893366
Keywords: openalex:import

Dental education in Africa with special reference to Nigeria - Jeboda, Sonny Olukayode (International Dental Journal, 1997)
Over the years, the dental profession in most of the developing countries of the world has given the education of the dentist greater priority over the education of dental auxiliaries. There has also been a great tendency on the part of the profession in these countries to think that dental education involves the training of dentists alone. The training of dental auxiliaries forms an important core of dental education for the training of oral health workers in the developing countries. The training of dentists in the developing countries, especially Africa, seems to have been lopsided with excessive emphasis on restorative procedures. The dental undergraduate training programme in a representative Nigerian dental school is investigated and suggestions made on the appropriate mode of training needed for the future Nigerian, and indeed the future African dentist. The need for effective parallel training of dental auxiliaries, especially in large numbers, is also emphasised.
openalex: W2025040178 mag: 2025040178
Keywords: openalex:import

Non-grid electrification of 45 schools in the Eastern Cape, South Africa: An assessment - Leitch, A.W.R.; Scott, B.J.; Adams, John J. (Renewable Energy, 1997)
This paper reports on the electrification using photovoltaic power of 45 schools in the rural areas near Queenstown, in the Eastern Cape region of South Africa. The project was funded by the state, coordinated by Eskom and implemented by Siemens Limited (Solar Division). The University of Port Elizabeth (Department of Physics) independently monitored the electrification process. As solar power is a relatively new concept for many of the rural people in South Africa, the University also gauged the opinion of the school teachers and local community on this new form of electricity.
openalex: W2026149813 mag: 2026149813
Keywords: openalex:import

Staff training aspects of automation in a Nigerian university library - Olorunsola, Richard (Aslib proceedings, 1997)
Automated systems, like manual systems, will not be successful without adequate training and preparation on the part of the staff. Some problems will arise where adequate training is lacking. The article discusses the structure and organisation of on‐site training of staff in the use of TINLIB software at the University of Ilorin Library. Particular attention is paid to the content of the training, trainers and what the programme is out to achieve. The article discusses some pitfalls in the training exercise and offers suggestions for future training programmes.
openalex: W2060582976 mag: 2060582976
Keywords: openalex:import

The Overrepresentation of African American Children in Special Education - Russo, Charles J.; Talbert-Johnson, Carolyn (Education and Urban Society, 1997)
openalex: W2006144056 mag: 2006144056
Keywords: openalex:import

[Male breast cancer in Africa, Apropos of 5 cases at the Ouagadougou University Teaching Hospital (Burkina Faso)]. - Sano, D.; Dao, Blamy; Lankoandé, J.; Touré, Boubacar Mami; Sakandé, B.; Traoré, Si Simon; Wandaogo, A; Dakouré, Raphaël; Sanou, Amadou (PubMed, 1997)
A retrospective study of male breast cancer was undertaken at Ouagadougou University Teaching Hospital over a 3 year period (1993-1996). Authors report 5 cases representing 4.16% of all breast cancers. The patients' mean age was 61 years. The average duration of signs and symptoms before the diagnosis was 13 months. Clinically all the 5 cases presented advanced cancers (4 T4N2M0, 1 T4N2M1 according to UICC TNM System) with size ranging from 5.5, to 11.5 cm. Histology found: 2 medullary infiltrating carcinoma, 1 canalar infiltrating carcinoma, 1 colloid mucous carcinoma and 1 lobular infiltrating carcinoma. All patients had mastectomy associated with axillary clearance in 4 cases. Radiotherapy, chemotherapy and hormonotherapy were not associated because unavailable in Burkina Faso. Three patients died: the first, 10 days after surgical treatment and the 2 others respectively after 14 and 17 months. We have lost sight 1 patients. The last one is still alive. Authors find that to get better prognosis, it is important to improve medical and technical means, to increase information and to promote early detection.
openalex: W1585077563 mag: 1585077563
Keywords: openalex:import

Goal Discrepancy in African American Male Student-Athletes' Unrealistic Expectations for Careers in Professional Sports - Sellers, Robert M.; Kuperminc, Gabriel P. (Journal of Black Psychology, 1997)
The present study investigated whether African American male college student-athletes unrealistically focus their career goals on professional athletics to the detriment of their academic pursuits. The study considered the professional athleticaspirations of 702 AfricanAmerican male student-athletesfrom42 NCAA Division I universities using the concept of goal discrepancy to identify individuals whose professional athletic aspirations were inconsistent with their current status asfirst team members of theirfootball or basketball programs. The results found only 5% of the sample to be goal discrepant and that among goal discrepant student-athletes, the majority were underclassmen. Institutional characteristics, such as intensity of the athletic program and segregation of athletes from nonathletic students, were stronger predictors of goal discrepancy than personal characteristics, such as socioeconomic status or precollege academic preparation. The results are discussed in relation to social policy that influences access to educational opportunity for African Americans.
openalex: W2152846865 mag: 2152846865
Keywords: openalex:import

Marine Pollution as Indicated by Oil Accumulated on Clams Collected from the Western Coasts of the Red Sea, Egypt - Shimy, Thouraya M. (Energy Sources, 1997)
In order to save our environment from pollution, many techniques are used for identifying oil accumulated on clams along the western coast of the Red Sea. Gas chromatography (GCr, infrared (IR), and ultraviolet (UV) absorption spectrophotometry are three different techniques used to analyze the collected samples, GC chromatograms for oil extracted from these animals indicate that the source of pollution is petroleum, and a few peaks reveal a mixture of biogenic and petrogenic hydrocarbons. These results are confirmed by the characteristic IR spectra profiles, high concentrations of the aromatic compounds, and the UV absorption spectra of these samples.
openalex: W1999767485 mag: 1999767485
Keywords: openalex:import

[Dermatology for Africa. The Regional Dermatology Training Center in Tanzania]. - Stingl, Peter (PubMed, 1997)
openalex: W2413939390 mag: 2413939390
Keywords: openalex:import

DROUGHTS, RAINFALL AND RURAL WATER SUPPLY IN NORTHERN NIGERIA - Tarhule, Augustine Aondover (1997)
openalex: W1650040484 mag: 1650040484
Keywords: openalex:import

The impact of the manual vacuum aspiration (MVA) technique on health care services at Queen Elizabeth Central Teaching Hospital, Blantyre, Malawi. - Vm, Leme; La, Mtimavalye; Gc, Thole; Mt, Mvula (PubMed, 1997)
To assess the impact of the manual vacuum aspiration (MVA) technique on health care services and its acceptability to patients and staff.Prospective descriptive survey.The university teaching hospital, Blantyre, Malawi.All 456 patients who had MVA for treatment or investigation between 10 January and 9 April 1994, the nurses and doctors working in the unit and hospital administrators.Proportion of incomplete abortion patients who had MVA, the need for pain relief, patients' reactions, staff opinion, and reduction in ward occupancy rates and duration of hospitalisation.Of the total, 97.4% had MVA for treatment of incomplete abortion; these comprised 81.2% of all incomplete abortion patients treated during the study period. The mean volume of uterine contents was 33.4 ml. There was no relationship between the volume and either the gestational age or uterine size (P > 0.05). Only 10.7% of patients required pain relief. The bed occupancy rates in the gynaecological ward dropped from an average of 150% before to 130% after the introduction of MVA, and the mean hospital stay was reduced from 3 days, with 78.4% staying for more than 2 days, to 2 days, with 52% staying for less than 24 hours (P < 0.05). Most patients expressed general satisfaction with the method, while the staff were happler because their work had been made easier. There were no major complications associated with the procedure.The findings show that MVA is a safe, reliable, effective and acceptable method of treating incomplete abortion, and can conserve hospital resources.
openalex: W79859239 mag: 79859239
Keywords: openalex:import

Randomised clinical trial to determine optimum initiation time of norgestrel-progestin only contraception in Eldoret Teaching Hospital, Kenya. - Were, Edwin; Kendall, Jessica; Nyongesa, Paul (PubMed, 1997)
In a randomised controlled trial to determine the optimum time of initiation of Ovrette, a progestin only oral contraceptive among postpartum women, who fully or nearly fully breast-fed their infants in the first six months, no difference was found between group 1 (initiating at six weeks postpartum) and group 2 (initiating the pill at return of menses or 6 months postpartum). There were no pregnancies in either group during the 18 month follow-up. There were no significant differences in the continuation rates between the two group.The optimal time for initiation of progestin-only oral contraception (POC) among fully or nearly fully breast-feeding women was investigated in a comparative study conducted among 200 women delivering at Kenya's Eldoret Teaching Hospital in a 2-year period during 1992-94. 100 women were randomly assigned to initiate POC use at 6 weeks' postpartum (group 1), while the remaining 100 women deferred POC initiation until the onset of menses or 6 postpartum months (whichever event occurred first) (group 2). At 12 months postpartum, 53.57% of mothers in group 1 and 56.67% in group 2 were still taking Ovrette; at 18 months, these rates were 46.10% and 43.59%, respectively. The mean duration of use was 7.6 months in group 1 and 7.5 months in group 2. There were 178 episodes of adverse experiences with Ovrette, 16.9% of which involved menstrual disturbances. Adverse experiences were more likely to be perceived as serious and related to Ovrette in group 1 than in group 2. There were no pregnancies recorded, suggesting that initiation of Ovrette use at 6 months postpartum or when menses reappears is a feasible strategy. However, postpartum women should be provided with counseling on the efficacy of the lactational amenorrhea method.
openalex: W1577810023 mag: 1577810023
Keywords: openalex:import

Attitudes of Zimbabwean medical students to future practice - Woelk, Godfrey (The Central African journal of medicine, 1997)
A medical research paper on the need for newly graduated medical students to engage in medical rural development in Zimbabwe.
openalex: W2465075042 mag: 2465075042
Keywords: openalex:import

politically sensitive teacher development in South Africa: guidelines for personal empowerment - Wouters, Anniek; Naude, G. N. (Changes, 1997)
openalex: W1966195732 mag: 1966195732
Keywords: openalex:import

Computer assisted curriculum analysis, design and evaluation for science education in Africa - McKenney, Susan; Akker, Jan van den (1997)
openalex: W2737866990 mag: 2737866990
Keywords: openalex:import

A School-Based Approach to HIV Prevention for Inner-City African-American and Hispanic Adolescent Females - Workman, Gloria M.; Robinson, W. LaVome; Cotler, Sheldon; Harper, Gary W. (Journal of Prevention & Intervention in the Community, 1997)
This study examined the efficacy of a school-based HIVIAIDS prevention intervention for African-American and Hispanic adolescent females. Participants, 60 high school freshmen enrolled in an inner-city parochial high school, were randomly assigned to either HIVIAIDS prevention or attention-placebo womanhood interventions. Significant ethnic differences were found, with African- American adolescents reporting notably higher levels of sexual assertiveness and comfort discussing AIDS preventivc behaviors, as compared to Hispanic adolesccnt females. Further, both African-American and Hispanic participants who received the HIV/AIDS prevention intervention increased their knowledge of AIDS, more so than participants in the attention-placebo condition. These findings highlight the importance of culture in the design of relevant and sensitive HIV/AIDS prevention interventions for ethnic minority youth.
openalex: W2044195754 mag: 2044195754
Keywords: openalex:import

Prevalence of congenital heart disease among school children of Sahafa Town, Sudan - Khalil, Siddiq Ibrahim; Gharieb, Khalid; haj, Mohamed El; Khalil, Mohammed; Hakeim, Suzan (Eastern Mediterranean health journal, 1997)
The prevalence of congenital heart disease among schoolchildren aged 5-15 years was studied as part of Phase 1 of the WHO Global Rheumatic Fever/Rheumatic Heart Disease Prevention Programme in Sudan. A total of 13 322 schoolchildren in Sahafa Town, Khartoum, was examined from 1986 to 1990 representing 70% of the total target population. There were 27 cases of congenital heart disease giving a prevalence rate of 2.0 per 1000. Ventricular septal defect, atrial septal defect [ASD], patent ductus arteriosus [PDA] and tetralogy of Fallot made up 85% of the cases. PDA and ASD were twice as common in females as in males. The prevalence rate is comparable to that of similar African countries but lower than European and north American rates
openalex: W2884709608 mag: 2884709608
Keywords: openalex:import

Iodine deficiency disorders among primary-school children in Kafr El-Sheikh, Egypt - Sayed, Nawal A. El; Gad, Zahlra M.; Nofal, Lalla H.; Ismail, Hassan; Sahn, Fikrat F. El; Gad, Ashry (Eastern Mediterranean health journal, 1997)
The prevalence of iodine deficiency in primary-school children in Kafr El-Sheikh governorate was assessed. A total of 2250 primary-school children aged 8-10 years were selected by a two-stage cluster sampling technique. The results revealed that the prevelance rate of goitre was 27.1% and it was significantly higher in females [29.2%] than males [25.1%]. The median urinary iodine level was 6.7 micro g/dl and 3.9 micro g/dl for grade 1 and grade 2 goitre respectively. It was concluded that iodine deficiency is a public health problem of moderate severity in primary-school children in Kafr El-Sheikh governorate. This necessitates an intervention programme through salt iodization
openalex: W3201402888 mag: 3201402888
Keywords: openalex:import

Socio-Economic Issues in the Education of Children of Migrant Fishermen in Nigeria - Fatunla, Grace T. (Journal of sustainable agriculture, 1997)
ABSTRACT The fishing industry contributes immensely to the agricultural sector which is the mainstay of the Nigerian economy. The industry is the foundation of all facets of development, particularly the effective provision and management of the productive resources. The migrant fishermen of the Nigerian coastal and riverine areas are greatly educationally disadvantaged. For sustainable development of the fishing industry, it is important to pay attention to the education of the fishermen and their children. Yet the migration of fishermen from one area to another, a concomitant of ecological and socio-economic factors, has profound effects on the education of their children. The study identifies the seasonal patterns of migrations of the fishermen and discusses the problems these migrations pose to the children's education. Then it discusses how their socio-economic conditions such as occupations, family structure and size, fishing organization and technology, fish marketing, income level and living standards aggravate the problems. Finally, recommendations are made to mitigate the problems and also provide viable alternative non-formal but functional education for the fishermen's children. Such recommendations also include physical provisions and special curriculum suited to the needs and demands of their peculiar circumstance.
openalex: W1971470176 mag: 1971470176
Keywords: openalex:import

A Quarter-Century of Strong African-American Progress in Medical School Education May Be Coming to an Abrupt Halt (Journal of Blacks in Higher Education, 1997)
openalex: W4241023244
Keywords: openalex:import

African Americans are Overdue at Graduate Schools of Library Science (Journal of Blacks in Higher Education, 1997)
openalex: W4239870272
Keywords: openalex:import

Book Review: Mill Hill Fathers in West Cameroon: Education, Health and Development, 1884–1970 (Missiology, 1997)
openalex: W4234534007
Keywords: openalex:import

"Community ownership" spurs girls' education in Egypt. (PubMed, 1997)
In a town in Upper Egypt, a local committee established by the Coptic Evangelical Organization for Social Services (CEOSS) conducted a door-to-door canvass and discovered about 21 school-age girls who had never been enrolled. The committee persuaded the school district to admit the girls despite the fact that the school year had started. In 10 towns, committees such as these plan, implement, and monitor projects to increase girls' education. Other projects include encouraging adolescent girls to attend family life education classes and discouraging such harmful traditional practices as female genital mutilation and early marriage. Efforts to prevent female genital mutilation are directed to mothers of girls aged 7-10 and to unmarried young men. In five communities, these efforts have led to the voluntary cessation of female genital mutilation within the past 10 years.
openalex: W4299418353
Keywords: openalex:import

Experience with clinical training in postabortion care in Egypt: Improving medical and interpersonal skills (1997)
The Population Council’s Asia and Near East Operations Research and Technical Assistance (ANE OR/TA) Project is collaborating with AVSC International to incorporate the addition of improved postabortion care procedures into the ongoing Safe Reproductive Health Care project. An element in the next phase of the program’s evolution was a two-day seminar held in Alexandria, Egypt. This seminar provided an opportunity for staff from ten hospitals that participated in the 1996–97 expansion program to present their own experience and impressions of the postabortion case-management procedures, and to discuss their strengths and weaknesses. This report presents an overview of this meeting’s presentations and discussions.
openalex: W4238528179
Keywords: openalex:import

Integrated management of childhood illness: field test of the WHO/UNICEF training course in Arusha, United Republic of Tanzania. WHO Division of Child Health and Development & WHO Regional Office for Africa. (PubMed, 1997)
The 11-day training course on integrated management of childhood illness was field tested with three types of first-level facility health workers: medical assistants, rural medical aides, and MCH (maternal and child health) aides. The objective of the field test was to determine whether the materials were effective in preparing participants to manage correctly sick children and to suggest improvements in the course materials and teaching procedures. The course combined classroom work and daily inpatient and outpatient clinical sessions. Each participant individually examined 9-10 inpatients and managed more than 30 sick children as outpatients. Individual feedback from facilitators during clinical practice and module work, combined with data collection documenting the adequacy of the assessment, classification, treatment and counselling carried out by the participants, allowed an assessment of the participants' mastery of key clinical skills. Although some participants had difficulty in reading the modules in English, all three groups overall were able to assess, classify, and treat most sick children by the end of the course, and most of them were able to provide adequate counselling. Specific improvements were suggested and subsequently incorporated into the guidelines and training materials.
openalex: W4298188793
Keywords: openalex:import

Economic efficiency of the secondary and tertiary education and training sector in Tanzania - Abayo, Abdiel; Kaijage, Erasmus (Papers in Education and Development, 1997)
openalex: W1559479392 mag: 1559479392
Keywords: openalex:import

Land husbandry education in agricultural colleges of Eastern Africa. An overview - Abebe, Tesfaye (1997)
openalex: W2753357201 mag: 2753357201
Keywords: openalex:import

Effect of Urbanisation on the Nutritional Status of Primary School Children in Lagos ‐ Nigeria∗ - Abidoye, R.O. (Early Child Development and Care, 1997)
Effect of urbanisation on Nutritional status of 250 primary school children was assessed among the children of working parents. Children involved were those who were dropped early in the morning 6 am by parents and picked up around the school premises later in the evening between 6.30‐7.00pm in the University of Lagos Staff School. Questionnaires were prepared for the parents to fill including the history of the children, time usually spent with the children from Monday through Friday, dietary information including information on whether they were breast‐fed in childhood. These information emanated from the study 193 (77%) were breast‐fed exclusively for two months while 57 (22.8%) were both breast‐fed and bottle‐fed. On feeding habits, children fed on cookies and soft drinks around the school premises with dinner at home around 8.00pm. Food served for dinner was mainly carbohydrates. No time for interaction with parents Monday through Friday. Average Anthropometric measurements obtained from these children (7‐10 years) were 29kg, 132cm for weight and height. Incidence of nutritional anaemia was very high among these children 87 (34.8%) had severe anaemia, below 9gm%, 65 (26% moderate 7‐10gm%) and 98 (39.2%) had their haemoglobin above 10gm%. This study was carried out in Lagos University Staff School. This school is owned and run by the University Authority and admits both staff and non‐staff. Lagos University Staff School is an expensive private school well subsidised by the University for the staff children.
openalex: W2024787814 mag: 2024787814
Keywords: openalex:import

The Influence of Socioeconomic and Nutritional Status on Menarche in Nigerian School Girls - Abioye-Kuteyi, Emmanuel Akintunde; Ojofeitimi, E.O.; Aina, Olabisi I.; Kio, Franklin E.; Aluko, Yetunde A.; Mosuro, O. (Nutrition and Health, 1997)
A study of 352 randomly selected secondary school girls in an urban population in Southern Western Nigeria revealed a mean menarcheal age of 13.94 ± 1.31 years and that 76.8% of girls attained menarche between ages 13 and 15 years. Age-matched pre- and post-menarcheal girls did not differ significantly in biophysical measurements, however, nutritional status was strongly and positively associated with attainment of menarche. School girls from the upper socio-economic class reached menarche 11 months earlier than the lower socio-economic counterparts. A significant finding of this study is that the declaration rate in age at menarche was slowest in girls from high socio-economic households. This deceleration was not influenced by body mass suggesting that socio-economic factors play a unique role in the secular trend widely reported in menarcheal age.
openalex: W2054208021 mag: 2054208021
Keywords: openalex:import

Education and national development in Southern Africa - Abosi, Okechukwu (Mosenodi, 1997)
openalex: W2239152562 mag: 2239152562
Keywords: openalex:import

Collaborative Space in South African Schools: A Comparative Perspective - Abrahams, Mark (Journal of Negro Education, 1997)
This article details a study that investigated both the nature and extent of the conceptual and physical space teachers, principals, and other administrators in South African schools devote to teacher collaboration. The schools selected for the study represented a cross-section of urban and rural, primary and secondary schools administered by several of the nation's previously historically racially divided education departments. Through data gathered from questionnaires, interviews, and observations, the findings generate important comparative information on how teacher collaboration in South Africa has been influenced by numerous historical and political factors, how it manifests within various school cultures, and how it differs across artificial and real organizational divides. INTRODUCTION Teacher collaboration has been identified as a basic characteristic of schools demonstrating improved student achievement (Lieberman, 1990; Little, 1982; Robinson & Collett, 1994), yet it has been conceptualized in numerous ways. According to Firestone and Pennel (1993), teacher collaboration has sociocognitive as well as affective dimensions and provides opportunities for to learn and develop a sense of collegiality or shared endeavor. Little refers to teacher collaboration as a level of collegiality at which in successful schools discuss, design, conduct, analyze, evaluate, and experiment with their teaching. She describes the dimensions of collegiality as strong and weak ties among teachers (p. 511), and places various interactions such as storytelling, sharing, assistance and joint work on a continuum between teacher independence and teacher interdependence. In her view, these interactions empower and prepare them to engage in shared decision making, both of which are vital for school improvement. Smith (1987) points out that such collaboration must move beyond merely trading stories about problems with students into the arena of proactive exchange so that can set school goals and oversee their own professional development. Morrison (1994) defines teacher collaboration as teamwork and promotes its use as a required strategy for planning and implementing cross-curricular themes for the following reasons: * [it] promotes organizational health; * [it] empowers teachers; * [it] rationalizes workload; * [it] builds democracy; * [it provides] an effective strategy for curriculum development; * [it brings into focus] a feature of human interaction; * [it fits] the cross-curricular nature of themes; * [it establishes] that every teacher is affected by the development of the cross-curricular themes; * [it] accords status to the cross-curricular themes. (p. 142) As a strategy for school improvement teacher collaboration is widely accepted, even in the most conservative and authoritarian school settings. Whereas Little (1990a) posits that teacher collaboration can be legislated, she notes that the success or failure of such collaboration depends on the benefits derive from it: Specific forms of induced collaboration.. [include] coaching, mentoring, peer observation, peer support.... The prospects of their influence on individuals and organizations rest in part on their congruence with established norms of interaction and interpretation among colleagues, and with the degree to which they fit or conflict with the meaningful reference groups with which align themselves. (p. 530) A range of studies cite the benefits of teacher collaboration, including improved student behavior and achievement, increased teacher satisfaction and adaptability, increased teacher commitment, and the creation of learning opportunities for teachers. For example, a World Bank (1989) study linked school effectiveness to teacher cooperation in efforts to improve the school and classroom instruction. …
openalex: W1969344566 mag: 1969344566
Keywords: openalex:import

Geologic Evolution of Conjugate Volcanic Rifted Margins - Pelotas Basin (Offshore Brazil) and Offshore Namibia : ABSTRACTS - Abreu, Vitor S. (AAPG Bulletin, 1997)
openalex: W2332788491 mag: 2332788491
Keywords: openalex:import

Innovative Second Language Education in the Middle East and North Africa - Abu-Absi, Samir (1997)
openalex: W190573452 mag: 190573452
Keywords: openalex:import

Openness of Health Professionals about Death and Terminal Illness in a Nigerian Teaching Hospital - Adamolekun, Kemi (OMEGA - Journal of Death and Dying, 1997)
Most physicians in developed countries are reported to have a sense of responsibility to inform a patient about the facts of his or her life-threatening condition. This study reports doctors' and nurses' responsibility to their terminally ill patients in an African environment. Since, by local tradition, doctors are not supposed to convey bad news and the patients do not see themselves as dying of illness, the doctors are not enthusiastic about informing the patients that their disease is terminal. Though doctors and nurses are of the opinion that patients or relatives should be informed of patients' diagnoses, the majority of these professionals do not discuss the prognosis with terminally ill patients. The need to discuss the diagnosis and prognosis according to the desire of each patient was examined. This is more relevant to the practice of medicine in the developing countries with the likelihood that more terminally ill patients would use the hospitals in the face of HIV/AIDS epidemic.
openalex: W1991275273 mag: 1991275273
Keywords: openalex:import

Instability of squall-inducing waves, global sea-surface temperature anomalies and climate change in tropical north Africa - Adedoyin, J. A. (Meteorology and Atmospheric Physics, 1997)
openalex: W1998504097 mag: 1998504097
Keywords: openalex:import

Perspectives of special need in Kenya, Zimbabwe and Nigeria - Adenigbagbe, S.; Osodo, Ogonda Grace; Peresuh, M. (1997)
openalex: W2736591880 mag: 2736591880
Keywords: openalex:import

Literacy education in Nigeria - Aderinoye, Rashid (1997)
openalex: W653536257 mag: 653536257
Keywords: openalex:import

The role of the Cambridge University Syndicate in the development of curriculum and examinations in Nigerian secondary schools, 1910-1960 - Adeyinka, Augustus A. (1997)
openalex: W1530803754 mag: 1530803754
Keywords: openalex:import

Impacts of lagoonal bacterial pollution on an aquacultural site (Ebrié Lagoon, Côte d'Ivoire. - Adingra, A.A.; Guiral, Daniel; Arfi, Robert (1997)
Abidjan, the economic capital of Cote d‘Ivoire, has grown around Ebrie lagoon. There are significant local water pollution problems because of the waste waters that flow untreated into the natural environment (Arfi et al., 1981). These anthropogenic inputs constitute a‘major source of lagoonal contamination by pathogenic germs such as Vibrio cholerae. Moreover, the physical and chemical characteristics of the lagoonal environment appear to be conducive to the survival and multiplication of halophilic or halotolerant pathogen bacteria (Lanusse and Guiral, 1988; Kouassi er al., 1992). Diarrhoeal syndromes have been reported on several occasions since 1970 in the Abidjan area. The main causative agent for these epidemics has been identified as V. cholerae, serotype El Tor Ogawa (Duchassin et al., 1973). A number of choleriform infections involving other vibrionic bacteria (V. parahaemolyricus, Aeromonas spp.) are also periodically reported in the area. Previous research on vibrios (particularly V. cholerae) mainly involved epidemiological studies of hospital cases (Dosso er al., 1984). Little information is therefore available on the ecological conditions and incidence of these germs in the natural environment; in particular no study has been done to determine the relation between vibrio presence in the environment and the hydroclimatic conditions of Ebrie lagoon. In the long term such pollution could undermine aquaculture in the lagoon, as V. cholerae can be transmitted by ingestion of contaminated fish. In 1991, during a routine check of infectious agents likely to provoke fish mortality at Layo aquaculture station on the banks of EbriC lagoon, V. colerae (serotype EI Tor Ogawa) was isolated in the alimentary canal of a Hererobranchus longzjilis fingerling. As tests failed to identify sick or healthy-carrier workers at the station, the presence of this germ in the ponds would indicate a more general state of environmental contamination. This study has been done to provide more reliable information on the real risks incurred at an aquacultural site, and to describe the annual cycle of V. cholerae in the various hydrosystems at Layo station (lagoon, ponds and irrigation channels). ,
openalex: W2159463310 mag: 2159463310
Keywords: openalex:import

The empowerment of South African women through education : a philosophical reflection - Adonis, Bradley Charles (1997)
openalex: W2118503619 mag: 2118503619
Keywords: openalex:import

Higher education in Africa : trends and challenges for the 21st century - Africa, Unesco Regional Office for Education in (1997)
openalex: W576617487 mag: 576617487
Keywords: openalex:import

This project, "First Teachers," studied urban African-American families' perceptions of an after school involvement program - African, Identifiers (1997)
openalex: W2978200158 mag: 2978200158
Keywords: openalex:import

Towards Behavioral Approaches to Library Practice: A Model for Integrating Social Skills Training in Nigerian Library School Curricula. - Agada, John (1997)
Studies indicate that many librarians, including Nigerian librarians, lack strong communication and social skills. The introduction of behavioral science courses in the curriculum of Nigerian library schools is recommended as a remedy. Besides, these courses would enhance the client–centered approach to Nigerian library practice. This article describes the author’s use of cooperative learning strategies to enhance students’ perceptions of the social nature of learning, information seeking, and use. The experience of the author suggests that these strategies could be integrated into library school curricula with positive gains in students’ cognitive and social skills.
openalex: W245833128 mag: 245833128
Keywords: openalex:import

Networking for Environmental Disaster Management: The case of Drought in Kenya - Agwata, Jones F. (1997)
openalex: W2257107036 mag: 2257107036
Keywords: openalex:import

Home Language Instruction for Moroccan and Turkish Children in Primary and Secondary Education - Aissati, A. El; Heer-Dehue, J. de (1997)
openalex: W2107119460 mag: 2107119460
Keywords: openalex:import

The African Experience with Higher Education - Ajayi, J. F. Ade; Goma, Lameck K. H.; Johnson, Ampah G. (International Journal of African Historical Studies, 1997)
Antecedents - before 1900 colonialism and higher education decolonization and higher education 1945-60 the politics of independence and higher education 1960-70 the association of African universities higher education and African development 1970s and 1980s issues and problems of the 1990s towards the 21st century the mission of the university reviewed new expectations and reorientations the outreach.
openalex: W2163339979 mag: 2163339979
Keywords: openalex:import

Teachers and national development in Uganda - Akankwasa, R.R. (1997)
openalex: W2805806548 mag: 2805806548
Keywords: openalex:import

The use of indigenous Kenyan children's songs for the development of a music curriculum and pedagogy for the primary school in Kenya - Akuno, EA (1997)
openalex: W2470883752 mag: 2470883752
Keywords: openalex:import

The use of indigenous Kenyan children's songs for the development of a primary school music curriculum for Kenya - Akuno, Emily Achieng’ (1997)
Music education in Kenya has been characterised by the teaching of Western musical literacy and a curriculum content with a Western classical bias. To date, few students graduate with sufficient music making skills, and even less pursue training at higher levels. The research aimed to formulate a learning programme that would make music education successful for Kenyans, through a curriculum content and pedagogy that would promote Kenya's cultural heritage while ensuring pupils' development of musical knowledge and skills. Firstly, an analytical survey of past and current music teaching practices in Kenya revealed the deficiencies in the music education programmes. Secondly, a critique of the Kodaly, Curwen, Eurythmics, Orff and Music in the National Curriculum (England) programmes identified the elements that contribute to their success. These were evaluated for their suitability to Kenya's educational environment. Field trials with Kenyan pupils used musical elements derived from indigenous Kenyan children's songs to teach musical concepts and skills. The collection of indigenous Kenyan children's songs involved recording live children's performances and iterviews with adults. Transcribing the songs using staff notation facilitated a rhythmic and melodic analysis, while a study of the texts gave insight into the songs' cultural functions. The musical elements characteristic of these songs were used to design the Rhythm-Interval Approach (RIA), a music teaching programme focusing on the use of rhythm and interval to teach musical concepts and skills. The study resulted in the postulation of the elemental theory of music; aesthetic functionalism as a culture-sensitive view of African music; the Rhythm-Interval curriculum model; and a primary school music curriculum based on indigenous Kenyan children's songs.
openalex: W124341191 mag: 124341191
Keywords: openalex:import

Continuous assessment in post-secondary teacher training in Ghana: a case study evaluation - Akyeampong, Kwame (1997)
The importance of and preference for assessing learning outcomes using a variety of assessment techniques and containing data from many sources, rather than the sole dependence on the one-shot examination, has long been recognised worldwide. This has led to major assessment policy changes in both developed and developing countries. In Ghana, this change has led to the introduction of continuous assessment at all levels of secondary schooling and post-secondary teacher training, to operate in parallel with external examinations. Although in Ghana evaluation studies of continuous assessment have been conducted for the secondary school level, none has so far been done for the post-secondary teacher training level. The purpose of this research was therefore, to examine the nature and scope of activities and problems that have to do with the practice of continuous assessment at the postsecondary teacher training level in Ghana. The research also examined the training and guidance provided for those undertaking continuous assessment, and the impact of the new assessments upon teaching and learning. A qualitative case study was conducted in three selected training colleges from the months, February to March of 1996 and January of 1997. The selected colleges were considered to be a fair representation of the teacher training college system in Ghana. The field research also included interviews with key officials associated with the postsecondary teacher training system. Findings from the multi-site case study evidence were presented and analysed for their significance. The findings of the research suggest that, many problems continue to threaten the benefits derivable from using continuous assessment in assessing students in the training colleges. The key findings that emerged as significant includes: operational and structural conditions in the colleges, professional support systems for tutors to carry out continuous assessment, tutor competency in assessment and considerations rooted in the values and beliefs of tutors about assessment which define their assessment culture and agenda. Evidence from those findings was then used as a basis for conclusions about improving continuous assessment in post-secondary teacher training, in Ghana. Recommendations for policy implementation and potential areas for further research were also made.
openalex: W1570155649 mag: 1570155649
Keywords: openalex:import

Attitudes and motivation of Yemeni secondary school students and English language learning - Al-Sohbani, Yehia Ahmed Y. (1997)
openalex: W2790371175 mag: 2790371175
Keywords: openalex:import

Flood and drought: application to the Senegal River management. - Albergel, Jean; J-C, Bader; J-P, Lamagat (1997)
openalex: W3209331857 mag: 3209331857
Keywords: openalex:import

Estimation of evapotranspiration in Libya under the impact of plausible global climate change - Ali, Amjad (Geographia Polonica, 1997)
openalex: W923988564 mag: 923988564
Keywords: openalex:import

Education Language Policy and Bilingual Education: The Impact of French Language Policy in Primary Education in Niger - Alidou, Hassana (1997)
openalex: W2337227204 mag: 2337227204
Keywords: openalex:import

Morbidity and disability in elderly Zimbabweans - Allain, Theresa J.; Wilson, Adrian O.; Gomo, Zvenyika A. R.; Mushangi, E.; Senzanje, B.; Adamchak, Donald J.; Matenga, J. A. (Age and Ageing, 1997)
the population aged over 60 years in Zimbabwe is expanding. Despite the likely increased demand on medical services that this will bring, little is known about the health needs of this elderly population.to record the prevalence of disability (impairment of activities of daily living), subjective morbidity (symptoms), the social circumstances and the utilization of health services in a group of elderly Zimbabweans.cross-sectional community survey.a remote rural area in North Eastern Zimbabwe and two urban townships located approximately 80 km from Harare.278 subjects (154 women, 174 rural), aged > 60 years (range 60-92) living at home.subjects were selected by random cluster sampling. They were assessed in a structured interview and underwent physical examination including visual acuity, inspection for cataracts and assessment of mobility.less than 4% experienced difficulty with self-maintenance activities of daily living, but 30% had difficulty with instrumental activities. The former were all visually impaired and both visual and mobility problems contributed to the latter. Elderly people experienced many symptoms but had inadequate access to health services and used medication infrequently. Subjects were mainly self-sufficient for financial income and 60% still worked. They had declining resources with age and received little help from the social welfare department. Their health and functional abilities deteriorated with age but it was older subjects who had most difficulty getting to the clinic. Simple measures such as cataract surgery and analgesics were available only to the minority or not at all.this study highlights problem areas where simple, low-cost measures could make a difference to the morbidity and disability of elderly Zimbabweans.
openalex: W2158716070 mag: 2158716070
Keywords: openalex:import

Report on an assessment of the impacts of frost and drought in Papua New Guinea - Phase 2. - Allen, Brian K.; Bourke, R. Michael; Burton, J. W.; Flew, Sarah; Gaupu, B.; Heai, S.; Igua, P.; Ivahupa, S.; Kanua, M. B.; Kokoa, P.; Lillicrap, S.; Gou, Ling; et al. (1997)
openalex: W2894645120 mag: 2894645120
Keywords: openalex:import

Estimation of Evapotranspiration in Libya under the Impact of Plausible Global Climate Change - Almabruk, Ali A. (Geographia Polonia, 1997)
openalex: W3143325174 mag: 3143325174
Keywords: openalex:import

Management structure in the European Union and South African Higher Education Systems: the portuguese case - Amaral, Alberto; Magalhães, António M.; Teixeira, Pedro J. (1997)
openalex: W2619770465 mag: 2619770465
Keywords: openalex:import

URINARY SCHISTOSOMIASIS AMONG SCHOOL CHILDREN IN NIGERIA: CONSEQUENCES OF INDIGENOUS BELIEFS AND WATER CONTACT ACTIVITIES - Amazigo, Uche O.; Anago-Amanze, Chukwudi; Okeibunor, Joseph (Journal of Biosocial Science, 1997)
A study of urinary schistosomiasis in Umueze-Anam, Anambra State, Nigeria, showed a Schistosoma haematobium infection of 26% (85) among school children with no significant difference by sex except when age as a variable is introduced. Eleven percent (37) of the 333 children were positive for haematuria; all these 37 children lived within 1·0 km of the water sources. Of the 85 infected children, swimming and laundering accounted for 65% and 48% of all water contact activities, for boys and girls respectively. One-third of the 230 adults interviewed believed haematuria to be a venereal disease and 20% thought it was a sign of maturity. Individual perception of causation and seriousness of haematuria differed by level of education and by sex. Less than 2% of the respondents knew that snails transmitted the disease. The effects of social restrictions on the epidemiology of infection is discussed.
openalex: W2035612095 mag: 2035612095
Keywords: openalex:import

Urinary schistosomiasis among school children in Nigeria : Consequences of indigenous beliefs and water contact activities. - Amazigo; Anago-Amanze; Okeibunor (Journal of Biosocial Science, 1997)
openalex: W3147957846 mag: 3147957846
Keywords: openalex:import

The causes and prevalence of pre-school deafness in Ghana. - Amedofu, GK; Brobby, GW; Ocansey, Grace (PubMed, 1997)
A study to determine the causes of deafness was done in Kumasi in central Ghana. A total of 128 deaf children aged between 1-5 years referred to the Ear, Nose and Throat clinic at the Komfo Anokye Teaching Hospital (KATH) were seen from January 1992 to June 1993. The procedure adopted included exploration and assessment of individual medical history, otoscopy, pre-audiometric and audiometric evaluation. It turns out that 66(51.5%) had congenital sensorineural hearing loss (CSHL), while the remaining 62(48.5%) had acquired sensorineural hearing loss (ASHL). Of the 66 congenital cases, 44 was due to unknown factors, while the rest were due to post-natal convulsion, measles, meningitis, mumps, fever and jaundice. Results of free-field tests were available in 116 children. Of these, 90 cases had a profound SHL while 38 had a severe-profound SHL. Again, of the 90 children with profound SHL, 56 was due to congenital factors, while the remaining 34 originated from acquired causes. Thus, the cases listed under CSHL showed a distinctly higher incidence of profound deafness. Primary prevention measures against diseases that cause deafness would be the most logical and practical way of helping to reduce the incidence of deafness in Ghana.
openalex: W2226805578 mag: 2226805578
Keywords: openalex:import

The Role of Asmara Students in the Eritrean Nationalist Movement: 1958-1968 - Ammar, Wolde-Yesus (1997)
openalex: W2265253225 mag: 2265253225
Keywords: openalex:import

Discipline: An interpersonal approach for elementary school teachers in Ghana - Amponsah-Amfo, Daniel (1997)
openalex: W2754090980 mag: 2754090980
Keywords: openalex:import

The academic and nonacademic characteristics of science and nonscience majors in Yemeni high schools - Anaam, Mahyoub Ali (1997)
openalex: W1564258954 mag: 1564258954
Keywords: openalex:import

A study of training programmes for school mathematics teachers in Nigeria - Anakwue, Festus Onyeama (1997)
This research set out to examine initial teacher training programmes for school mathematics in institutions in Nigeria with the aim of establishing their characteristics, quality and appropriateness. The focus of the study was the curricula of colleges of education and the understandings and expectations of student teachers at the terminal point of their training in these colleges. The study sought to determine: a) the characteristic features of programmes that exist in Nigeria for the initial training of school mathematics teachers; b) the differences among the training programmes; c) the relationship between the training curricula and the school mathematics curriculum in Nigeria; d) the level of understanding of school mathematics subject matter among trainees who have completed the training programmes. Data were collected and analysed from three sources to allow triangulation of findings. The first sought information from curricular provisions in initial training programmes, in terms of the knowledge components expected to be understood by a mathematics teacher. The second, a school mathematics contents test, was used to identify prospective teachers' level of understanding of school mathematics at the end of their training. The third, a questionnaire, was used to seek mathematics teacher trainers' views about the training programmes in their institutions. The research drew the following conclusions: 1) There are differences between mathematics teachers training programmes in Nigeria. The initial teacher qualifications awarded by different colleges of education cannot, therefore, be said to be of the same quality. 2) Mathematics teachers training programmes in Nigeria are not achieving their intended objectives because there are contradictions between their stated aims and the curricular provisions for training. 3) The level of understanding of subject matter by prospective teachers in Nigeria is low. Over 30% of student teachers cannot be relied upon to teach the school mathematics syllabus with confidence. 4) There is low understanding among teacher trainers of the objectives and philosophy of teacher education in Nigeria. Most teacher trainers believe that the main purpose of training is to help student teachers develop enthusiasm and intellectual ability for further mathematics. In summary, it is suggested that the curricula for training school mathematics teachers at colleges of education in Nigeria are not related to the subject matter of school mathematics nor to the needs of trainees and they need substantial revision.
openalex: W775496179 mag: 775496179
Keywords: openalex:import

Staffing and Training the South African Army of the Future - Andersen, Robert (African Security Review, 1997)
openalex: W2296198849 mag: 2296198849
Keywords: openalex:import

Improving primary science teaching in Nigeria: a workshop approach. - Anosike, Cordelia Nwamaka. (1997)
Earlier studies have shown that the majority of the teachers in primary schools in Nigeria are ill-equipped to teach science. It was also established that most of these primary school science teachers had rather poor background and training in science. The present study was therefore designed to establish the efficacy of practical workshops as a way of furthering teachers' professional competency in science. This was done through a field study of these teachers in their teaching environment. The investigation was carried out in three phases. The first phase involved a questionnaire survey covering 180 primary six teachers located in three of the 30 states of Nigeria (Anambra, Kaduna and Plateau). The aim of this survey was to identify the topics in the primary science core curriculum which the teachers found difficult to teach. It was found that the teachers found magnetism a difficult topic to teach. The second phase involved the mounting of a 2-day in-service training workshop on the teaching of magnetism, for fifty teachers located in Anambra state. The workshop was designed as one of the mechanism for improving the knowledge and teaching skills of the teachers in science. The third phase of the study involved post-workshop visits, follow-up interviews and the observation of the teachers in action in their own classrooms. The visits were followed by a 1-day workshop which provided an opportunity for the workshop programme to be evaluated as well as for the teachers to meet for mutual exchanges of experiences. The outcomes of the workshops indicated that the teachers, as a result of their participation in the workshops, had achieved a greater understanding of magnetism and subsequently were able to teach the topic more confidently. The implications of this study for pre-service and in-service teacher education programmes as well as classroom science teaching practice are discussed.
openalex: W821290797 mag: 821290797
Keywords: openalex:import

Leaping into the dark: some reflections on free primary education in Uganda - Appleton, Simon (1997)
openalex: W2277421177 mag: 2277421177
Keywords: openalex:import

The politics of planning culturally relevant AIDS education for African-American women. - Archie‐Booker, Elaine (1997)
openalex: W2588752345 mag: 2588752345
Keywords: openalex:import

Rez. Raffaella Cribiore, 'Writing, Teachers, and Students in Graeco-Roman Egypt'. Atlanta: Scholars Press. 1996 (American Studies in Papyrology 36), XIV, 316 S., 80 Tafeln - Arzt‐Grabner, Peter (1997)
openalex: W2994909634 mag: 2994909634
Keywords: openalex:import

Space science education in the African continent - Aseno, J.O. (Advances in Space Research, 1997)
Through measurement and interpretation of the spectral, spatial and temporal variations in electromagnetic emissions and reflections from the Earth's surface, important information related to natural resources can be acquired. Furthermore, satellite technology has greatly improved the communication and positioning techniques world-wide. Consequently, space science now provides valuable and timely information about natural resources, which has become a major factor in sustainable development. The realization of the full potential of space science in the context of development in Africa requires adequate education and training in order to facilitate project formulation, planning, management and implementation. This, in turn, would lead to the formulation and adoption of national space science policies based on user needs and addressing both the short and long-term needs of a particular country. Space science education in Africa needs to address issues like (i) provision of programmes, (ii) integration of the proposed techniques within the existing infrastructure, and (iii) training in Remote Sensing, Global Positioning System, Geographic Information System and other space science techniques, in order to ensure the successful implementation of space science projects within the continent. In this context, African universities ought to play a major role in space science training, research, consultancy and publication. Through international co-operation, it is possible to develop and support national, regional and international training programmes and international scientific exchange in Africa.
openalex: W2013673060 mag: 2013673060
Keywords: openalex:import

The prospects of enhanced space science training in Kenya - Aseno, J.O.; Obel, J.D. (Advances in Space Research, 1997)
To a limited extent, space exploration has been conducted in Kenya for almost the last two decades through a joint project (San Marco Project) between the Government of Kenya and the Government of Italy. Other space science activities in the country include remote sensing, space communications, meteorology and the use of navigation and positioning satellite systems. To sustain space science activities in Kenya will require specialized training in the various disciplines of space sciences. Currently, there are no well coordinated training programmes in the country. Consequently, there is an urgent need for a well planned and a well coordinated space science training programme. This could be achieved through international co-operation and joint ventures between Kenya and space science institutions/organizations worldwide. The paper justifies the need for training in space science in Kenya and discusses socio-economic as well as environmental gains which would be realized due to increased space science activities arising from such training. Some of these gains would include participation in the launching and tracking, and control of satellite, managing and running a space centre or satellite launching and tracking station, decoding and synthesizing data from satellites and disseminating such data for public and scientific uses. The paper further offers suggestions on how the training requirements cited above could be achieved. It also highlights the level of expertise in space science disciplines and provides specific recommendations on the types of personnel that need to be trained. In addition, various forms and levels of training required to strengthen the role of space science in socioeconomic development in Kenya, are discussed.
openalex: W1994842031 mag: 1994842031
Keywords: openalex:import

Success Related Attributes in Tertiary Training Institutions in Tanzania - Assad, Mussa Juma; Olomi, Donath (Papers in Education and Development, 1997)
openalex: W2236641413 mag: 2236641413
Keywords: openalex:import

Training in Policy Analysis Methods: The Ethiopian Experience - Assefa, Alemayehu (African Administrative Studies, 1997)
openalex: W2255719263 mag: 2255719263
Keywords: openalex:import

Facilitating constructive change in secondary mathematics classrooms in Zimbabwe - Atkinson, Mary (1997)
openalex: W55663040 mag: 55663040
Keywords: openalex:import

Multi variate analysis of academic success factors among accounting and management students at the National University of Lesotho - Ayaya, O. (1997)
openalex: W2287800941 mag: 2287800941
Keywords: openalex:import

Problems and Conflicts in Liberian Education: A Road to National Peace - Azango, Bertha B. (Liberian studies journal, 1997)
openalex: W38472788 mag: 38472788
Keywords: openalex:import

Mitigating the Effects of Drought through Food Security and Nutrition Monitoring: Lessons from Malawi - Babu, Suresh Chandra; Chapasuka, Evance (Food and nutrition bulletin (Tokyo. Print), 1997)
This article uses a case study from Malawi to demonstrate the use of a Food Security and Nutrition Monitoring (FSNM) system for managing and mitigating the effects of drought. The implementation of FSNM during the drought emergency is presented, along with a description of the process of information generation and the use of results in emergency interventions. Presenting the lessons learned from the Malawi experience for the benefit of future drought-management and disaster-prevention efforts in other sub-Saharan African countries, the article concludes that a decentralized system of data collection, processing, and analysis is more likely to be successful in planning interventions for food security and nutritional improvements during periods of drought.
openalex: W2900297957 mag: 2900297957
Keywords: openalex:import

A study of faculty attitudes towards the adoption of university-based distance education in Ghana - Badu-Nyarko, Samuel Kofi (1997)
openalex: W1546231996 mag: 1546231996
Keywords: openalex:import

African American Racial Identity Development in Predominantly White Institutions: Challenges for Student Development Professionals - Bakari, R. Sentwali (1997)
openalex: W294980854 mag: 294980854
Keywords: openalex:import

Implementing Basic Education: An African Experience - Banya, Kingsley; Elu, Juliet U. (1997)
openalex: W4256610153
Keywords: openalex:import

English language teaching in the Kenyan secondary school : policy, training and practice - Barasa, L.P. (1997)
openalex: W785106078 mag: 785106078
Keywords: openalex:import

The education of deaf children in Zimbabwe : the changing roles of non-governmental organisations, the government and international organisations - Barcham, Lesley (1997)
In this thesis I describe and analyse the development of education for deaf children in Zimbabwe, from its beginnings in the 1940s to 1994. I investigate in detail the changing policies and provision of non governmental organisations, the government and international organisations. The thesis is divided into three sections. The first section examines the literature relating to deaf education in Zimbabwe. the role of international organisations and the changes from charity to government provision. I introduce four propositions developed from the literature about, first the internationalisation of the debates about deaf education provision, second the limitation of charitable provision. third the struggles between interest groups and finally the influence of organisations of deaf people. I analyse the case study methodology used to investigate policies and practices. The second section describes the changes in the education for deaf children from the 1940s to 1994. I examine the early role of churches and charities and the gradual increase of government involvement. This section also plots the complex relationships between the government, non governmental and international organisations in the development of policy and practice. In the third and final section I return to the four original propositions and discuss the key findings relating to the changes in international policies and funding, the growing influence of deaf peoples organisations and reactive nature of government policies.
openalex: W2905985847 mag: 2905985847
Keywords: openalex:import

Approaching Change: One School's Approach to Multicultural Education and Raising the Achievement of African Caribbean Students. - Barron, Pat (Multicultural Teaching, 1997)
openalex: W177869394 mag: 177869394
Keywords: openalex:import

The Effects of Preinstructional Activities and Mental Maps in Enhancing Learner Recall and Conceptual Learning of Instructional Materials for Preservice Teachers in Zimbabwe. - Bassoppo-Moyo, Temba C. (International journal of instructional media, 1997)
openalex: W257469673 mag: 257469673
Keywords: openalex:import

A Fulbrighter's Experience with English Language Teaching in Tunisia: The Land of Mosaics - Battenburg, John D.; Obispo, San Luis (1997)
Mosaics—slivers of tile in shades of red, blue, brown, black, and white jigsawed together—are on display throughout Tunisia. Some form geometric designs; others reveal gods and goddesses, warriors, lovers, ships, and, of course, all types of fish. The mosaics are sometimes multilayered. They tell of the waves of civilizations which have come to Tunisia. Punic mosaics with pink stone surfaces flecked with fragments of glass or marble give way to Roman creations with intricate patterns of triangles and diamonds. Native North African mosaics with circular compositions and frequent portrayals of rural and marine scenes are replaced by Christian representations with colored blocklike shapes and later motifs concerning martyrdom and resurrection. Finally, Byzantine mosaics with cut glass and figurative representations appeared. These mosaics are delightful yet haunting because of their ambiguity. They suggest that beneath the dusty surface lie ornately textured and colorful layers which are often hidden from the hurried traveler. They also warn that it is impossible to entirely reconstruct or reconcile all of the experiences of Tunisia. From 1995–1997, I served as a Fulbright senior lecturer in TEFL and applied linguistics at the University of Tunis.1 I applied for a grant to Tunisia because I was interested in discovering how an emerging North African country has successfully encouraged multilingualism. I hoped to apply what I would learn to the language situation in California.
openalex: W2184227286 mag: 2184227286
Keywords: openalex:import

The Relative Effects of Married Versus Divorced Family Configuration and Socioeconomic Status on the Educational Achievement of African American Middle-Grade Students - Battle, Juan (Journal of Negro Education, 1997)
This article reports research examining the relative effects of parental marital status and socioeconomic status (SES) on the educational achievement of African American middle-grade students. Analyses of data from a nationally representative sample (NELS:88) reveal that at lower levels of SES, African American students from divorced households scored significantly higher on a standardized test measure. At the mean and higher levels of SES, no significant difference was found between students from divorced and married households on the test measure. The article concludes with discussion of the reasons behind these findings and the implications of the findings for public policy. INTRODUCTION Regardless of one's personal feeling about divorce, statistics clearly show that it has become popular. They also reveal that the trend toward rising divorce rates is not likely to be reversed in the near future. For example, Norton and Miller's (1992) research projects that 40% of first marriages will eventually end in divorce, while others argue that the dissolution rate is as high as 60% (Bumpass, 1990). Stratifying across race, African American couples have been found more than twice as likely as European American couples to divorce (Saluter, 1992). More recent research suggests that given current rates, as many as two-thirds of all recent African American marriages will end in divorce. By the age of 16, Baca Zinn and Eitzen (1996) maintain, two out of every three African American children, compared to only about one out of every three White children, will experience the dissolution of their parents' marriage. It is more than clear that these racial/ ethnic differences in divorce rates did not occur overnight. Morgan, McDaniel, Miller, and Preston's (1993) research found that even at the turn of the 20th century, African American households were less likely to be nuclear and more likely to be headed by women than were White households. Using census data, McDaniel (1994) compared contemporary African and White American household structures to those that were common during the slavery era and found significant similarities in family organization between the two time periods. After analyzing data from the 1960 through 1980 censuses, Wojtkiewicz (1993) concluded that the increasing number of female-headed African American families-the end-products of divorce, separation, and never marrying-was a factor contributing to the deepening economic inequality noted between Blacks and Whites. The reasons suggested for these differences in African and European American divorce rates are as plentiful as the statistics themselves. For example, Heaton and Jacobson (1994) considered a number of demographic variables and found that none of them satisfactorily explained the disparities noted. They subsequently conclude that the differences are attributable to differences in the ways Black and White families respond to various cultural and structural constraints. Crosbie-Burnett and Lewis's (1993) work focusing on racial differences, coping strategies, and divorce extols the pedi-focal coping strategies used by African American postdivorce families and suggests that these strategies might also be useful for European American postdivorce families. Other researchers, who conducted cultural-ecological analysis using data from the 1987-88 National Survey of Families and Households, found that after controlling for socioeconomic status (SES) and other variables, African American single mothers reported having higher expectations for their children than did their White counterparts (Fine, McKenry, & Chung, 1992; McKenry & Fine, 1993). They further note that the Black single mothers in their sample also reported that their children had a higher quality of life than did White single mothers. Another interesting racial difference concerning divorce was reported by Glenn and Kramer (1987), who note that among their sample of four groups of adult children of divorce-White males, White females, Black males, and Black females-only White females showed statistically significant divorce-proneness as a result of divorce. …
openalex: W2061349399 mag: 2061349399
Keywords: openalex:import

"If You Can Pass Momma's Tests, Then She Knows You're Getting Your Education": A Case Study of Support for Literacy Learning within an African American Family. - Baumann, James F.; Thomas, Deborah L. (The Reading Teacher, 1997)
openalex: W2565418662 mag: 2565418662
Keywords: openalex:import

A status study of the recruitment and retention of African-American students in agricultural education baccalaureate programs / - Bell, Janice Lester (1997)
openalex: W2807942220 mag: 2807942220
Keywords: openalex:import

Interventions for the Promotion of Girls' Education in Tanzania - Bendera, Stella J. (Papers in Education and Development, 1997)
openalex: W2267226549 mag: 2267226549
Keywords: openalex:import

Impaired phosphatidylcholine biosynthesis and ascorbic acid depletion in lung during lipopolysaccharide-induced endotoxaemia in guinea pigs. - Benito, Eva; Bosch, María Asunción (Molecular and Cellular Biochemistry, 1997)
openalex: W63471423 mag: 63471423
Keywords: openalex:import

Education and Technical Training for Africans in India - Bhardwaj, Krishna (Africa quarterly, 1997)
openalex: W2257874570 mag: 2257874570
Keywords: openalex:import

THE ROLE OF OPEN SCHOOLS IN THE PROCESS OF SOCIAL CHANGE IN SOUTH AFRICA - Bhengu, Paulus. (1997)
Submitted in fulfilment of the requirements for the degree MASTER OF EDUCATION in the Department of Sociology of Education of the Faculty of Education at the University of Zululand, 1997
openalex: W2146140910 mag: 2146140910
Keywords: openalex:import

Art Education in South Africa in the Midst of Transition: Township and Private Schools. - Blaikie, Fiona (1997)
openalex: W116878417 mag: 116878417
Keywords: openalex:import

Integrating Literacy and Health Education for a Sustainable Development in Africa - Bodomo, Adams; Agyei‐Mensah, Samuel (Scandinavian journal of development alternatives, 1997)
openalex: W148572444 mag: 148572444
Keywords: openalex:import

Mother Tongue Education in Ethiopia - Boothe, Ken; Walker, Roland W. (Language Problems and Language Planning, 1997)
RESUMEN Educación en lengua materna en Etiopia: De una política a la implementación A pesar de los limitados recursos financieros y humanos, Etiopia esta avanzando rápidamente en la implementación de una política de educación en lengua materna para todos sus ciudadanos en un corto periodo de tiempo. Este artículo es el reporte de un observador participe de los tres primeros años de un ambicioso programa de educación en lengua materna, enfocado en el proceso de creación de materiales en lenguaje materno y en la efectividad del programa. Por décadas las minorías étnicas etíopes fueron dominadas por la política de usar solamente el idioma del emperador en la educación elemental. Luego durante los siguientes 17 años de socialismo el uso de la lengua materna fue permitido solamente en la alfabetización de adultos. Sin embargo desde 1991 el gobierno ha gastado una buena cantidad de recursos para facilitar la educación en lengua materna a los grupos étnicos que asi lo deseen. Diseñar un programa y producir sus materiales es uno de los mayores obstáculos para los paises que tienen varios idiomas y que desean ofrecer un programa universal de educación en lengua madré. En asociación con los grupos locales de individuos y las organizaciones no gubernamentales, el gobierno de Etiopia ha juntado cientos de maestros de escuela para producir materiales en idioma materno en cada una de las areas de estudio, del primero al sexto grado, en los ocho primeros idiomas de los cincuenta hablados en el pais. La estandarización del idioma y el desarrollo de una ortografía han ido de la mano en una forma acelerada. RESUMO Edukado en gepatra lingvo en Etiopio: De politiko gis realigo Spite limigitajn financajn kaj homajn rimedojn, Etiopio rapide transiras el formulado de politiko al ties realigado por liveri al sia tuta popolo edukadon en la gepatra lingvo ene de mallonga tempoperiodo. En tiu ĉi artikolo, partoprenanta observante priskribas la unuajn tri jarojn de la aŭdaca etiopia programo por edukado en la gepatra lingvo, kun fokuso je la procedo por evoluigi materialojn en gepatraj lingvoj, kaj je la efikeco de la programo. Dum jardekoj, la etnaj minoritatoj de Etiopio estis regataj de la politikoj de la Imperiestroj koncerne ekskluzivan utiligon de la amhara lingvo en elementa edukado. Dum la postaj dek sep jaroj da socialismo, la gepatran lingvon oni permesis nur por plenaĝula alfabetigo. Tamen, depost 1991, la Transira Registaro de Etiopio permesas al etnaj grupoj la rajton antaŭenigi la proprajn kulturojn kaj evoluigi siajn lingvojn por elementa edukado. Preterirante politikon al efektiva agado, la registaro elspezas signifajn rimedojn por faciligi edukadon en la gepatra lingvo por ĉiuj etnaj grupoj, kiuj tion deziras. Granda barilo por multlingvaj nacioj, kiuj deziras proponi universalan edukadon en gepatraj lingvoj, estas la kreado de taŭgaj studprogramoj kaj materialoj. Kunlabore kun lokaj enlogantoj kaj neregistaraj organizaĵoj, la registaro de Etiopio jam kunvenigis centojn da instruistoj por krei materialojn por ciu studtemo en la unua gis la sesa klaso, por la unuaj ok el la pli ol kvindek etiopiaj lingvoj. Lingva normigo kaj evoluigo de ortografio okazadas samtempe, ĉiam je granda rapideco.
openalex: W2037429441 mag: 2037429441
Keywords: openalex:import

Development of bilingualism: A study of school-age Moroccan children in the Netherlands - Bos, Petra (1997)
openalex: W2130190337 mag: 2130190337
Keywords: openalex:import

Mission report. Training operations in Africa and Latin America/Caribbean. Training courses for instructors on the use of the STANTECH manual (standardized research techniques for coconut breeding). Ivory Coast, Grand-Bassam, 16th-26th June 1997 ; Jamaica, Kingston, 14th-25th July 1997 - Bourdeix, Roland (1997)
L'objectif de ces deux missions etait de former des chercheurs ou des formateurs aux differentes techniques standardisees d'amelioration du cocotier. Ces deux sessions se sont largement appuyees sur le manuel STANTECH. Apres avoir dresse un rapide bilan concernant le deroulement des deux cours, l'auteur s'est attache a rassembler en annexes du rapport un memorandum des erreurs detectees dans le manuel STANTECH ainsi que les notes prises lors des seminaires dans les deux pays
openalex: W2227962701 mag: 2227962701
Keywords: openalex:import

Policy Action and School Demand in Kenya - Bradshaw, York W.; Fuller, Bruce (1997)
AbstractComparative scholars are beginning to specify the conditions under which central states can act with independence vis-à-vis economic forces to penetrate local cultures and families, influencing parental demands placed on local institutions, such as demand for more schooling. Much less is known about (1) which specific forms of state action are efficacious in manipulating family demands, (2) whether boosting demand for more services can undercut their quality, and (3) why central political capacity to shape family action varies and may erode over time. To inform these issues we focus on two distinct periods in Kenya, stretching over the 1963–1990 post-independence era. We show, using time-series analysis, how the Kenyan regime initially boosted family demand for more schooling through discrete policy initiatives: reducing the private cost of school attendance, offering food supplements at school, and broadening secondary school opportunities for peripheral ethnic and class groups. But after two decades of efficacious state action, local demand for schooling began to falter, quality eroded severely, and stratification has again hardened. After identifying the early effects of these policies we detail how the Kenyan state has grown more fragile, less effective in shaping family demands and delivering quality education against the backdrop of a declining economy. The case of Kenya reveals weaknesses in Western sociological theories that fail to recognize domestic political and organizational constraints besetting centralized Third-World states, even those once considered strong.
openalex: W4231200016
Keywords: openalex:import

The Leland Initiative: Africa Global Information Infrastructure Gateway Project (698-0565) Strategic Objective 3: End-User Applications Internet for Development: Applications and Training School-to-School Partnership Ghana - Breslar, Zoey L. (1997)
openalex: W2184201139 mag: 2184201139
Keywords: openalex:import

Working Together to Develop our Teaching - a report on the in-service workshops for junior secondary English and Mathematics teachers of The Gambia - Brown, Laurinda C; Woodfield, Helen; Hayter, RJ (1997)
openalex: W1749458842 mag: 1749458842
Keywords: openalex:import

Helping African-American Students Prepare for College. Fastback 413. - Brown, O. Gilbert (1997)
openalex: W250411657 mag: 250411657
Keywords: openalex:import

Language in Education in Kenyan Schools - Bunyi, G. (1997)
openalex: W23802900 mag: 23802900
Keywords: openalex:import

Multilingualism and discourse in primary school mathematics in Kenya - Bunyi, G. (Language, Culture and Curriculum, 1997)
The paper very briefly reviews the literature on second language medium of instruction and educational achievement. Classroom discourse data from English, Kiswahili and mother tongue mathematics lessons, and from lessons where code switching occurred are presented. The paper argues that regardless of the medium of instruction, a transmissional model of teaching and learning predominates. The paper underlines the importance of teacher education programmes that are based on the realities of the local situation, and that develop the teachers’ awareness of the impacts that their way of talking and organising learning opportunities have on how pupils learn.
openalex: W2018642716 mag: 2018642716
Keywords: openalex:import

Experiences and Perceptions of Interpersonal, Environmental, and Institutional Racism among African-American Students in Psychology Graduate Training. - Burrell, Tracey (1997)
openalex: W24697221 mag: 24697221
Keywords: openalex:import

The Significance of African American Male Social Skills: Students with and without Disabilities. - Butler, Douglas M. (1997)
openalex: W79143746 mag: 79143746
Keywords: openalex:import

A study of the role perceptins and expectations of the principals of technical training institutes in Kenya - Bwika, Sulelman K (1997)
openalex: W2239975713 mag: 2239975713
Keywords: openalex:import

Disasters, disasters: Association of University English Teachers of South Africa Conference, University of the Western Cape, July 1996 - Byrne, Deirdre (Scrutiny2, 1997)
openalex: W2088397575 mag: 2088397575
Keywords: openalex:import

The implementation of creativity-action-service in South African schools - Cajee, Zeinoul Abedien (1997)
A Research Report submitted to the Faculty of Education, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Education.
openalex: W2591425222 mag: 2591425222
Keywords: openalex:import

Using Mentoring to Improve Academic Programming for African American Male Youths with Mild Disabilities. - Campbell-Whatley, Gloria D.; Algozzine, Bob; Obiakor, Festus E. (The School counselor, 1997)
African Americans represent the largest care, and the mortality rate is high for culturally diverse group in the United African American infants (Kappan Special States (United States Department of ComReport, 1990; National Center for Health merce, Bureau of the Census [USDOC], Statistics, [NCHS], 1990). Additionally, one 1987), yet statistics indicate a high risk out of every two families in this popula factor for the well-being of the African tion lives in poverty (USDOC, 1987). When American population. Economic hardships compared with other cultural groups, Af and the psychological and physiological rican American youth, especially boys, are burden of oppression are lethally comdisproportionately represented among bined to disadvantage African Ameriperpetrators and victims of aggressive cans, adding significant obstacles to their crimes or of violent crimes (Hacker, 1992; successful academic, personal, and social NCHS, 1990). When compared with the development (Barbarin, 1993). Statistics Anglo-American adolescent male popula provide the basis for considerable concern tion, African American male adolescents for the long-term emotional, social, and ecoare at a greater risk in terms of criminal nomic existence of African Americans, esity and death rates at a ratio of 5:1 (NCHS, pecially men. 1990). As a result of the inequities of soci For example, two thirds of the African ety, African American male adolescents are American population have poor health at greater risk for developing frustration and anger (Campbell-Whatley, 1993). Many variables seem to interact with those Gloria D. Campbell-Whatley is art assistant propreviously identified to contribute to poor fessor in the School of Education of Indiana Unieducational development among African versity-Purdue University, Fori Wayne, Indiana. American adolescents as well. Bob Algozzine is a professor and research fellow Research on academic achievement in
openalex: W28662349 mag: 28662349
Keywords: openalex:import

Indoor air pollution and acute lower respiratory infections in young Gambian children. - Campbell, Harry (PubMed, 1997)
openalex: W2397616705 mag: 2397616705
Keywords: openalex:import

Challenges in English Literacy for African-American and Lankan Tamil Learners: Towards a Pedagogical Paradigm for Bidialectal and Bilingual Minority Students - Canagarajah, A. Suresh (Language and Education, 1997)
The paper compares two separate classroom ethnographies in higher educational institutions one, on African-American students learning Academic writing and another on Lankan Tamil students learning English for General Purposes. Explicating the similarities of challenges and responses in English academic literacy for these students, the paper attempts to overcome the separation of the concerns of bilingual and bidialectal minority students in English language teaching. Although both groups of students are initially highly motivated, they experience conflicts for their identity, values, and group membership in internalising an alien discourse. They therefore adopt a formalistic learning approach of mastering the abstract structural rules and ignoring the communicative uses of the language in order to oppose its ideological thrusts. Through this ambivalent strategy, they attempt to attain the English proficiency needed for social mobility while retaining their cultural and ideological integrity. The paper proposes thatwhile minority students should be encouraged to analyse the limitations of their own attitudes and values, the pedagogy should also sustain an interrogation of the ideologies represented by English discourses. Such students should reposition themselves in relation to English and use it according to their own discursive backgrounds in order to empower themselves while pluralising English/academic discourses.
openalex: W2049214635 mag: 2049214635
Keywords: openalex:import

The provision of schools by the DET in South Africa during 1983-1994 - Candiotes, George (1997)
openalex: W3094004418 mag: 3094004418
Keywords: openalex:import

The schooling of African-origin children in Portugal : an analysis of primary school teachers' views. - Cardoso, Neves; Manuel, Carlos (1997)
openalex: W2119429369 mag: 2119429369
Keywords: openalex:import

Foreign Aid in Africa: Learning from Country Experiences - Carlsson, Jerker; Somolekae, Gloria; Walle, Nicolas van de (1997)
This volume reports on the findings of an international research project on aid effectiveness in Africa. Field studies was conducted in Botswana, Burkina Faso, Ghana, Kenya, Senegal, Tanzania and Z ...
openalex: W2144921811 mag: 2144921811
Keywords: openalex:import

Catholic schools in Zambia: whither? - Carmody, Brendan (African Christian Studies, 1997)
openalex: W2230935959 mag: 2230935959
Keywords: openalex:import

A dream deferred? Examining the degree aspirations of African-American and White college students. - Carter, Deborah Faye (Deep Blue (University of Michigan), 1997)
1. Introduction: The Realization or Abandonment of Dreams 2. What are Aspirations?: Definitions and Theoretical Foundations 3. What Affects Aspirations: Empirical Evidence 4. Methodology for the Study 5. College Students Degree Expectations and Plans 6. What Affects College Students Degree Expectations and Plans? 7. Conclusion: Dreams Deferred? Appendices References.
openalex: W593997650 mag: 593997650
Keywords: openalex:import

Attitudes of African American and Caucasian Eighth Grade Students about Praises, Rewards, and Punishments. - Casteel, Clifton A. (Elementary school guidance and counseling, 1997)
Over the last few decades, many problems have surfaced related to teaching in United States schools, partially because of larger class sizes and increased student diversity. One problem that teachers face is an increase in the incidence of rebellious and disruptive behavior by students, which seems to indicate that previous ways of dealing with reward and punishment by teachers have not always been effective (Brophy & Good, 1974; Chance, 1992; Merrett, Wilkins, Houghton, & Wheldall, 1988; Parker, 1978; Smith, 1978). Teachers must learn to become expert managers in the classrooms if they are to optimize learning. As part of this process, teachers should make the effort to identify what children find effective as reward or punishment, and then to adapt the educational environment accordingly (Merrett & Tang, 1994; Pang, 1992). The teacher sets the guidelines for the classroom's educational environment and is inevitably the person to decide the consequences of their students' performance and behavior. According to Merrett and Tang (1994), rewarding consequences (positive reinforcers) are those that follow a desired behavior and serve to increase its frequency. Conversely, punishing consequences follow an undesired behavior and serve to decrease its frequency. Neutral consequences are those that have no measurable effect on behavior. Teachers must recognize that the application of specific rewards or punishments should be reevaluated if such consequences are not effective in directing subsequent behavior, and that the effectiveness of such consequences hinges in part on the opinions of students concerning appropriate reward and punishment. Pursuant to earlier studies of student attitudes about reward and punishment (Caffyn, 1989; Sharpe, Wheldall, & Merrett, 1987; Turco & Elliot, 1984), Merrett and Tang (1994) investigated nearly 1,800 British school students (boys and girls age 8-11) through the use of a written questionnaire (14 probes). The research involved two variables: age level and sex. The researchers found significant differences in the responses of students, according to age or sex, on some items.
openalex: W150225355 mag: 150225355
Keywords: openalex:import

Learner-centered education in Namibia - Chaka, Mubita Villem. (1997)
openalex: W1589183331 mag: 1589183331
Keywords: openalex:import

Learner-centered education in Namibia: a case study - Chaka, Mubita Villem. (1997)
openalex: W2805053428 mag: 2805053428
Keywords: openalex:import

I am a Promise: The School Achievement of British African Caribbeans. - Channer, Yvonne (International Migration Review, 1997)
openalex: W1989435106 mag: 1989435106
Keywords: openalex:import

Handbook of Teachers and Teacher Education in Botswana - Chapman, David W.; Marope, M. (1997)
openalex: W2680577256 mag: 2680577256
Keywords: openalex:import

Teachers’ beliefs about effective teaching: A view from Botswana - Chapman, David W.; Snyder, Conrad W. (1997)
openalex: W2734532151 mag: 2734532151
Keywords: openalex:import

Vulnerability of coastal resources to climate changes in Mozambique: a call for integrated coastal zone management - Chemane, David; Motta, H.; Achimo, Mussa (Ocean & Coastal Management, 1997)
The Earth is affected by the emission of different gases which are largely generated by human activities. The “blanket” these gases form around the planet is likely to affect the climate balance. The resulting warmth could cause partial melting of the polar ice-caps, as well as the thermal expansion of the sea water, with the consequence of harmful degrees of sea-level rise. If global warming becomes a reality, with the consequential sea-level rise Africa's numerous islands and all its low-lying coastal areas, which include large areas of Mozambique, would be severely affected. This paper describes how the projected sea-level rise would affect a particular area in Mozambique, which is just one of the many vulnerable areas. The article also focuses on the broader framework for integrated coastal zone management in Mozambique and its enormous challenges, that aims to accommodate not only the current problems the coastal zone is facing, but also those resulting from the projected accelerated sea level rise.
openalex: W2086945924 mag: 2086945924
Keywords: openalex:import

Famine and Drought: The Question of Food Security in Zimbabwe - Chigodora, Joshua (1997)
openalex: W67835742 mag: 67835742
Keywords: openalex:import

Training future leaders in environment and development: the LEAD Southern Africa Programme - Chiotha, Sosten (1997)
openalex: W403211194 mag: 403211194
Keywords: openalex:import

Attitudes of South African teacher educators in relation to mainstreaming pupils with special needs - Choles, Gwynneth (1997)
A Dissertation Presented to The Division of Specialized Education The University of the Witwatersrand In Partial Fulfillment of the Requirements for the Degree of Master of Education (Educational Psychology)
openalex: W2613283272 mag: 2613283272
Keywords: openalex:import

Distance learning for University Physics in South Africa - Cilliers, J. A.; Basson, Ilsa (AIP Conference Proceedings, 1997)
The University of South Africa (Unisa) is one of the largest distance education universities in the world. Teaching physics at a distance is a complex and multifaceted problem which is compounded in the South African context by the diversity of educational backgrounds of the learners involved. The fact that students are distributed over a vast geographical area, presents unique problems for the incorporation of the practical component into the curriculum. Current research involves a fundamental evaluation of the aims and objectives of the introductory laboratory. The project is based on the notion that practicals, as they have been used in most physics curricula, are not particularly effective or efficient, although they are costly both financially and logistically. Design, development and delivery of efficient study material imply that there should be agreement between what the student knows and can do, and what the material offers. An in depth profile that takes into account biographic as well as cognitive characteristics of the target group, is therefore being compiled. This paper gives an overview of the specific problems and circumstances that were identified for distance education in physics in a multi-cultural society, and proposes a new model for the incorporation of the introductory laboratory into the curriculum.
openalex: W1509608609 mag: 1509608609
Keywords: openalex:import

Breeding groundnut for drought adaptation in Senegal - Clavel, Danièle; Annerose, Daniel (International Arachis Newsletter, 1997)
Face aux risques graves de secheresse durant le cycle vegetatif de l'arachide, les selectionneurs jouent sur la precocite varietale (maximum 80 ou 90 jours selon la partie du bassin arachidier) ainsi que sur la capacite de resistance au manque d'eau. L'amelioration genetique conduite depuis 1985 est de type pluridisciplinaire, incluant des etudes agro-physiologiques sur le systeme racinaire (volume, forme), la regulation stomatique et la resistance membranaire. La precocite est de nature polyfactorielle, d'ou le recours a la selection recurrente, parallelement a la selection genealogique, celle-ci a plus court terme. Des obtentions de valeur interessent le Senegal, le Burkina Faso, le Bostwana et le Bresil, qui composent un reseau d'evaluation multilocale
openalex: W2269406548 mag: 2269406548
Keywords: openalex:import

The infusion of African-American art from eighteen-eighty to the early nineteen-nineties for middle and high school art education / - Claxton, Ronald Wayne (1997)
openalex: W2626303039 mag: 2626303039
Keywords: openalex:import

African Women and Development: A History. The Story of the African Training and Research Centre for Women of the United Nations Economic Commission for Africa - Cockerton, Camilla May; Snyder, Margaret; Tadesse, Mary (International Journal of African Historical Studies, 1997)
openalex: W2263525010 mag: 2263525010
Keywords: openalex:import

School and Community Politics: Issues, Concerns, and Implications When Conducting Research in African-American Communities - Conley, Darlene J.; Debro, Julius (Substance Use & Misuse, 1997)
Since the public exposure of the atrocities associated with the Tuskegee experiment, organizations in the African-American community have become more politically involved in and sophisticated about the agendas of outside researchers and the policy implications of these studies for their residents and communities. Community organizations are now requiring accountability from researchers, regardless of race. This chapter discusses the politics of conducting research in these communities and provides several strategies for involving the community as a partner in the research enterprise.
openalex: W2037305365 mag: 2037305365
Keywords: openalex:import

Sudan: In the Eye of the African Storm - Connell, Dan (1997)
openalex: W1550188703 mag: 1550188703
Keywords: openalex:import

Tanzanian Education in the Nineties: beyond the diploma disease - Cooksey, Brian; Riedmiller, Sibylle (Assessment in Education: Principles, Policy & Practice, 1997)
Abstract In the 1970s, policies restricting the growth of post‐primary education and guaranteeing government employment for the few graduates limited the spread of the ‘diploma disease’ in Tanzania. The economic crisis of the 1980s meant growing underfund‐ing of education, which, combined with bureaucratic inefficiency and corruption, has led to the collapse of educational quality. Consequently, the majority rural poor have increasingly turned away from formal schooling, while the urban middle class continue to compete through education for the limited number of modem‐sector jobs. Liberalisation has resulted in rapid informalisation of the economy and the shrinkage of the public sector. But, just as previous reforms were unsuccessful in promoting rural development, so the present education system is incapable of promoting self‐employment in the informal sector. Dore predicted that, as a ‘late developer’, Tanzania would suffer an acute attack of certification sickness. That the symptoms are only now appearing among a relatively small segment of the population suggests, perhaps, that Tanzania is an even later developer than Dore imagined.
openalex: W2027166324 mag: 2027166324
Keywords: openalex:import

Marginality, Mattering, and the African American Student: Creating an Inclusive College Environment. - Cooper, Jacqueline (The College Student Affairs Journal, 1997)
openalex: W27312593 mag: 27312593
Keywords: openalex:import

New education policy directions in South Africa: shifting the boundaries of worker education - Cooper, Linda (1997)
openalex: W2612632378 mag: 2612632378
Keywords: openalex:import

Understanding African-American students' perceptions of the campus climate at a predominantly White college: A study of student affairs administrators - Costa, Susan Therese (1997)
openalex: W88237973 mag: 88237973
Keywords: openalex:import

The Scenario of Environmental Degradation in the Tell Leilan Region, Ne Syria, During the Late Third Millennium Abrupt Climate Change - Courty, Marie‐Agnès; Weiss, Harvey (1997)
openalex: W41994188 mag: 41994188
Keywords: openalex:import

The role played by environmental education in the secondary school geography syllabus in a future South Africa. - Cowie, Trevor Leslie. (1997)
openalex: W1532744000 mag: 1532744000
Keywords: openalex:import

Turks and Moroccans Learning Possession in Dutch. A Conservation Approach of L2 Acquisition - Craats, I. van de; Corver, Norbert; Hout, R.W.N.M. van (1997)
openalex: W1593140548 mag: 1593140548
Keywords: openalex:import

Rethinking the future of teacher education in South Africa: The role of partnerships - Cross, Tracy L.; Sehoole (South African journal of higher education, 1997)
This paper aims to examine the findings of the National Teacher Education Audit in view to explore the possibilities and limits of interinstitutional cooperation or partnerships between institutions involved -in teacher education in South Africa. This will entail a careful scrutiny of the structure institutional distribution types of programmes offered and the existing linkages involving these institutions. The most pressing problems facing teacher education include duplication of programmes and the quality of training of teachers as well as lack of support systems for teachers in service. In some cases some of these problems have been minimized by coliaboration between institutions particularly between universities arld colleges. The paper will argue that to address these problems institutions involved in teacher education may have to undergo profound restructuring to meet the challenges of the future. A critical factor in this process is the role of partnerships.
openalex: W3021826694 mag: 3021826694
Keywords: openalex:import

Will 'Things' or Will Knowledge and Ideas Fuel South Africa's Growth?: Education in a New South Africa: The Crises of Conflict, the Challenges of Change - Crouch, Luis (1997)
openalex: W2807286448 mag: 2807286448
Keywords: openalex:import

Transformational leadership and the learning organisation : exploring requirements for management of anticipatory organisational change in the South African banking industry - Crow, Andrew Grant (1997)
The purpose of this study is to examine the relationship between transformational leadership, the manner in which these leaders approach their work and a variety of organisational outcomes in the South African banking sector. In particular, the manner and extent to which transformational leaders focus on the management of organisation culture and are able to bring about learning within their organisations was examined. Other areas explored included their sensitivity to the macro environment and extent to which proactive action is taken. These aspects have not been widely researched and provided the opportunity to seek new relationships. The study also replicated previous research by Bass and bis colleagues that established linkages between transformational leadership and outcomes such as subordinates willingness to work harder, perceived leaders effectiveness and satisfaction with the leader. The eight propositions are tested in 10 Strategic Business Units (SBU's) within the 4 largest South African banks. Data was collected using the multifactor leadership and 11 factor learning organisation questionnaires and also through structured open - ended interviews with the executives directly responsible for leadership of these 10 SBU's. Support was found for greater learning taking place within areas led by the relatively more transformational leaders in the sample. The level of appreciation and understanding of the concept of the learning organisation among the executives sampled however, was found to be low throughout the sample. In addition, support was found for the outcome measures, although not in the manner in which previous research had established. Those executives that were relatively more transformational were also found to be more proactive in their actions at the workplace. There was no support found for the proposition that transformational leaders are more sensitive to and aware of the happenings and trends in the macro business environment. The main contribution of the study is the finding that concerted efforts are required if the establishment of the learning organisation as a valid response to environmental changes is to be attained. Relying on individual leadership orientations is unlikely to be sufficient.
openalex: W2981562666 mag: 2981562666
Keywords: openalex:import

Transfer of training: assessing the impact of INSET in Tanzania - Cullen, Richard (1997)
openalex: W2530958227 mag: 2530958227
Keywords: openalex:import

Learning within a social movement: The Chicago African-American experience. - Cunningham, Phyllis M.; Curry, Regina (1997)
openalex: W2584134130 mag: 2584134130
Keywords: openalex:import

Strategies for Enhancing Research and Research Training Programs for African Americans: Viewing Barriers as Opportunities - Curry, Charles L. (Journal of Health Care for the Poor and Underserved, 1997)
Minorities have long been excluded from biomedical research programs, both as researchers and as study participants. One reason for the dearth of minority researchers is their lack of awareness that federal and private financial assistance programs exist on their behalf. To provide opportunities for minorities in biomedical research, minority institutions must be given expanded opportunities to participate in federally sponsored biomedical research programs. Thus both governmental and private agencies need to appraise minority research institutions of the kinds of assistance available and how to access funds. One means of disseminating such information would be to post it on the Internet. Minority institutions, for their part, must make basic research a priority and engage in mentorship programs that encourage minority precollege students to pursue careers in the sciences. Researchers can gain the trust of African Americans through outreach programs, which may lead to the greater inclusion of this population in clinical trials.
openalex: W2007594769 mag: 2007594769
Keywords: openalex:import

Transition from an apartheid education system to a democratic education system in South Africa : a minor field study - Dahlgren, Hans (1997)
Transition from an apartheid education system to a democratic education system in South Africa : a minor field study
openalex: W782001004 mag: 782001004
Keywords: openalex:import

Climate change and environmental assessments: Issues in an African perspective - Dalfelt, Arne; Næss, Lars Otto (1997)
openalex: W2479627389 mag: 2479627389
Keywords: openalex:import

Religion education in South African state schools with special reference to the Kwazulu-Natal region - Dangor, Suleman (1997)
openalex: W2264702400 mag: 2264702400
Keywords: openalex:import

Peer Networks of African American Students in Independent Schools: Affirming Academic Success and Racial Identity - Datnow, Amanda; Cooper, Robert G. (Journal of Negro Education, 1997)
Analysis of qualitative data reveals that the formal and informal peer networks of African American students in predominantly White elite independent schools support these students' academic success, create opportunities for them to reaffirm their racial identities, and facilitate their adjustment to settings that are otherwise difficult for Blacks toit into. Contrasted to research showing that adopting academically successful behaviors leads Black students to being labeled as acting White, the sampled students made social gains within school when they were academically successful. However, this success did not result in full acceptance by African American peers outside the school. The authors conclude that the dynamics and ideologies of African American peer groups are more complex than prior research has suggested. INTRODUCTION A plethora of research documents the educational experiences of African American students. Early research in this area primarily focused on the failures of African American students to achieve at the same academic level as their White counterparts (Coleman et al., 1969; Jencks et al., 1972). More recently, the emphasis in research has shifted from studies of academic failure to studies of the factors that contribute to African American student success (Ladson-Billings, 1990; Lee, Winfield, & Wilson, 1991). Since the 1960s, increasing numbers of African American students have been enrolling in predominantly White elite independent schools known to prepare students for positions of power and leadership (Cookson & Persell, 1985). Much of the increase in enrollment can be attributed to the efforts of a number of organizations, including A Better Chance (ABC), Prep for Prep, Black Student Fund (BSF), and the Baltimore Educational Scholarship Trust (BEST), that have initiated and maintained the presence and participation of African American students in these schools (Cookson & Persell, 1991; Johnson & Anderson,1992). Additionally, the majority of these schools have enacted policies of nondiscrimination, and a growing number actively recruit minority students in their efforts to create more diverse student bodies on their campuses (Speede-Franklin, 1988). Despite these efforts, research shows that predominantly White elite independent schools, with their history of racial exclusion, are often places where African American students find it difficult to fit in (Brookins, 1988; Zweigenhaft & Domhoff, 1991). Moreover, African American students in such institutions have frequently reported that they feel caught between two cultures and consequently doubly marginalized.' They have also indicated that often they feel alienated from the culture of the school and from their own parents and friends, particularly in boarding school environments (Cookson & Persell, 1991). This is not surprising, as NELS:88 data indicate that African American students at predominantly White elite independent schools have substantially fewer family economic resources relative to the school populations as a whole (Schneider & Shouse, 1992). Research also suggests that African American students at these institutions may have weaker social relationships with their teachers than do their peers at the schools, and that this lack of connection may affect their motivation and academic performance (Schneider & Shouse, 1992). Given these findings, it appears that the social bonds that African American students at predominantly White elite independent schools develop with each other may provide an important but as yet unexplored support network that could potentially contribute to their academic performance and sense of identity and belonging. Although African American students in such settings often form their own cliques and clubs (Cookson & Persell, 1991), the functions served by these peer networks are not clearly understood. Thus, the study presented here used qualitative interview data to explore the peer networks developed by African American students enrolled in predominantly White elite independent schools through the Baltimore Educational Scholarship Trust (BEST). …
openalex: W2088593954 mag: 2088593954
Keywords: openalex:import

Teachers needs, culturally-significant teacher education and educational achievement in an African context — the case of Guinea-Bissau - Daun, Holger (International Journal of Educational Development, 1997)
Various studies demonstrate that school and teacher characteristics play an important role in pupil success. This article presents the findings from a study in Guinea-Bissau in which it is shown that the higher educational level and the level of the teacher training and the school buildings and equipment deemed appropriate do not always contribute to better pupil results. Two principal and partially complementary interpretations of these results are made. First, in a society where the technological level is very low and the school is distanced from the local cultures, value-oriented factors count more than technical-material factors in regard to pupil success. Secondly, the standard of living that the teachers have is so low that their basic needs are not met and, consequently, they cannot give teaching tasks priority. Therefore, their level of instruction and training does not make the difference it would make otherwise.
openalex: W2085789214 mag: 2085789214
Keywords: openalex:import

The Determinants of Primary School Enrollment and Household Schooling Expenditures in Kenya: Do They Vary by Income? - Deolalikar, Anil B. (1997)
January 1997*An earlier version of this paper was presented at the Workshop on Determinants ofEducational Attainments in Sub-Saharan Africa held on 2 December 1996 at theAcademy for Educational Development, Washington, D.C. Comments by HaroldAlderman, Ronald Ridker, and other participants at the workshop are gratefullyacknowledged.
openalex: W2339805371 mag: 2339805371
Keywords: openalex:import

Socio-demographic characteristics and indoor air pollution as risk factors for acute lower respiratory infections in under-five children in Addis Ababa, Ethiopia - Derege, K; Willett, Walter C. (Ethiopian Journal of Health Development, 1997)
openalex: W109876536 mag: 109876536
Keywords: openalex:import

The Role of Games as an Aid in Teaching English as a Foreign Language to Preparatory School Pupils in Egyptian Government Schools - Dessouky, Salwa Saad El-Din (Mağallaẗ Al-Adāb wa Al-ʿulūm Al-Insāniyyaẗ (Minia), 1997)
openalex: W3118828571 mag: 3118828571
Keywords: openalex:import

Theoretical conceptions of human movement and their implication for dance instruction in selected Kenyan primary schools - Digolo, B.A. (1997)
openalex: W2232269263 mag: 2232269263
Keywords: openalex:import

FACTORS RELATED TO AGRICULTURE STUDENTS ACADEMIC PERFORMANCE IN SWAZILAND - Dlamini, B.M.; Sithole, Nelisiwe (Journal of International Agricultural and Extension Education, 1997)
openalex: W2330983558 mag: 2330983558
Keywords: openalex:import

Natural Disasters in Africa: Hazards Education for a Hazardous Continent - Dodson, Belinda (The Australian journal of emergency management, 1997)
Africa is considered as one of the more hazardous continents, as its high mortality and low life expectancy, along with misconceptions about natural hazards and contradictions in perceptions of Africa and Africans, attest. However, in recent years, there has been a shift in natural hazards research, revealing that the Africa's natural disasters would contribute to the further sophistication of the new approach to natural hazards.
openalex: W2222429436 mag: 2222429436
Keywords: openalex:import

Higher Education in South Africa: Transforming the System - Donn, Gari (1997)
openalex: W2788231632 mag: 2788231632
Keywords: openalex:import

Education After Apartheid South African Education in Transition. - Donn, Gari; Kallaway, Peter; Donn, Gari (1997)
openalex: W1490299868 mag: 1490299868
Keywords: openalex:import

Geothermal potential of the Alid Volcanic Center, Danakil Depression, Eritrea - Duffield, Wendell A.; Bullen, Thomas D.; Clynne, Michael A.; Fournier, Robert O.; Janik, C.J.; Lanphere, Marvin A.; Lowenstern, Jacob B.; Smith, J. G.; Giorgis, Leake W.; Kahsai, Gabreab; Mariam, Kidane W.; Tesfai, Theoderos (Open-file report /, 1997)
openalex: W1492909132 mag: 1492909132
Keywords: openalex:import

Stepping Over the Color Line: African-American Students in White Suburban Schools. - Duncan, Garrett Albert; Wells, Amy Stuart; Crain, Robert J. (Journal of Negro Education, 1997)
Stepping Over the Color Line: African-American Students in White Suburban Schools, by Amy Stuart Wells and Robert J. Crain. New Haven, CT: Yale University Press, 1997. 380 pp. $35.00, cloth. Reviewed by Garrett Albert Duncan, Washington University (Saint Louis, MO). In Stepping Over the Color Line: African-American Students in White Suburban Schools, Amy Wells and Robert Crain present the findings from their five-year study of the St. Louis, Missouri, interdistrict school desegregation plan. unique character of St. Louis, a southern city with a northern exposure, and the voluntary nature of its school desegregation plan provide an excellent laboratory to conduct a case study on the politics of race and education. first author, Wells, is associate professor of educational policy at the University of California-Los Angeles Graduate School of Education and Information Studies. Her dissertation research was instrumental to the publication of Stepping Over the Color Line. second author, Crain, is a professor of sociology of education at Teachers College, Columbia University, and has written extensively on the politics of school desegregation. main objective of this work is to examine the processes and key players that contributed to the successes and the failures of the St. Louis desegregation plan. A case study research project, this book was produced using various methods including interviews with over 300 individuals, participant observations in classrooms and board meetings, and a review of numerous archives, newspapers, court documents, reports, and surveys. Though the authors seek to provide a balanced view of the state of the educational system for Black children and youth in St. Louis, they declare their allegiance to those people committed to the ideals of integration, stating at the outset that, [i]ndeed this book is written for and about them (p. 2). Stepping Over the Color Line is divided into three sections. Section 1, entitled The Politics of Race, is comprised of two chapters. Chapter 1 brings together disparate sources to demonstrate how urban and suburban jurisdictions are created through the activity of politically powerful people and thus are not the consequences of natural sorting-out processes, as might be claimed by those who refuse to acknowledge the effects of de facto segregation. Chapter 2 provides a more specific examination of activities at the grassroots level and in the courts that contributed directly to the present-day voluntary desegregation program, which includes the transfer of Black students from city schools to county and suburban schools, the transfer of White children and youth from the county and suburbs to urban magnet schools, and capital improvements for predominantly Black city schools. Section 2, The City, examines the St. Louis desegregation plan from the black side of the color line (p. 18). Chapter 3 traces the history of the St. Louis public school system, describing its transformation from a mainly White school system serving up to 110,000 students to a predominantly Black system serving 42,000 students. In chapter 4, the authors focus on the consumers of urban education, those Black students (and their families) who attend city schools. Chapter 5 draws upon interviews conducted with city-to-county transfer students and their families to explore the reasons Black youths from the city chose to participate in the desegregation program. This section closes with chapter 6, a portrayal of Black students who participated in the city-to-county transfer program but who then decided-or had it decided for them-to return to city schools. In some instances, these students ultimately left school altogether. concluding section 3, The Suburbs, presents the St. Louis desegregation plan from the perspective of White educators, parents, and students who live in the county and suburbs. Chapter 7 details the resistance of White educators and parents to the desegregation program. …
openalex: W2797841147 mag: 2797841147
Keywords: openalex:import

Education in an autonomous Palestine : Palestinian perspectives - Dyke, Blair Van (1997)
openalex: W2299010388 mag: 2299010388
Keywords: openalex:import

Promoting Education within the Context of a Neo-Patrimonial State : The Case of Nigeria - Edevbaro, Daniel (1997)
In the first two or three decades of independence, Nigeria, like the rest of Africa. placed heavy emphasis on expanding educational opportunities from primary school through university. This has resulted in a very impressive increase in the number of stu
openalex: W1520827614 mag: 1520827614
Keywords: openalex:import

Promoting Education within the Context of a Neo-Patrimonial State: The Case of Nigeria - Edevbaro, Daniel (RePEc: Research Papers in Economics, 1997)
In the first two of three decades of independence, Nigeria, like the rest of Africa, placed heavy emphasis on expanding educational opportunities from primary school through university. This has resulted in a very impressive increase in the number of students enrolled in institutions at all levels. In spite of this, education today, like other social sevices, is in deep cirsis. The population growth which greatly increases the number of children seeking access to scholls combined with the recent ecoomic decline has necessitated significant cutbacks in public spending on all social services.
openalex: W3152328055 mag: 3152328055
Keywords: openalex:import

Africa Comes to Northwest Elementary School - Edward, Jhon (Journal of General Music Education, 1997)
openalex: W2260106825 mag: 2260106825
Keywords: openalex:import

Computer aided training on the environmental impacts of agricultural development projects: an Egyptian case study - Edwards‐Jones, Gareth; Ibrahim, A. A. (1997)
A knowledge-based system was developed to help a multilateral agency train natural resource planners to be more aware of the full environmental impacts of agricultural development projects. This system, called ECOZONE, has been used successfully in training, but its generic nature limits its ability to capture the true complexity of any given development project. As such its use in training is constrained. A specific case study was developed which used the ECOZONE framework in order to provide a more in-depth representation of the impacts associated with a given development project. This paper describes the ECOZONE software and its uses, and then considers the development of a model of the North Sinai Agricultural Development Project, a large irrigation project in northeast Egypt. The use of this particular case study in training is described, and opportunities for further development of this concept are explored.
openalex: W185168553 mag: 185168553
Keywords: openalex:import

Mothers and Daughters: The Training of African Nurses by Missionary Nurses of the Swiss Mission in South Africa - Egli, Martina; Krayer, Denise (1997)
openalex: W1582745811 mag: 1582745811
Keywords: openalex:import

Impact of climate change on possible scenarios for Egyptian agriculture in the future - Elshaer, Hesham; Rosenzweig, Cynthia; Iglesias, Ana; Eid, Mai; Hillel, Daniel (Mitigation and Adaptation Strategies for Global Change, 1997)
openalex: W1991918350 mag: 1991918350
Keywords: openalex:import

War and Drought in Sudan: Essays on Population Displacement - Eltigani, Eltigani El Tahir (International Journal of African Historical Studies, 1997)
The plight of Sudan, where great numbers of people live and work under the chronic threats of famine, civil war and sickness, is a matter of humanitarian concern. Here, Sudanese scholars examine one aspect of these issues - the population displacement problem that affects one third of the nation.
openalex: W1981495091 mag: 1981495091
Keywords: openalex:import

The Gold Coast Nationalist Reaction to the Controversy over Higher Education in Anglophone West Africa and its Impact on Decision Making in the Colonial Office, 1945-47 - Emudong, C.P. (Journal of Negro Education, 1997)
It has been widely assumed that African nationalism had no significant impact on educational policy making by the British Colonial Office until very late inthe colonial period. present articla refutes this generalistic and rather Eucoventric assumption, deriving its evidence largely from declassified primary official records. It demonstrates that nationalist pressure, especially from the Gold Coast (Ghana), was the crucial force behind the Colonial Office's decision to further higher education in Anglophone West Africa. Moreover, it reveals that the issue of establishing universities in Afriva was conceded within a wider context of the evolving colonial policy of planned neocolonialism. INTRODUCTION Passionately advocated by pan-Africanists as early as the 1870s and increasingly after the first World War, proposed by the National Congress of British West Africa in 1920, and championed by such revolutionary nationalists as Nnamdi Azikiwe of Nigeria, the idea of a West African university was generally resisted by colonial governors, who saw an educated African elite as a threat to European control. Eventually, however, the upheavals of the late 1930s and World War II forced Britain, which was then led by the Conservative Party, to reconsider its alliances with supposedly traditional African authorities and turn instead to the task of creating a Western-oriented buffer class to which administrative and political power could be incrementally transferred. As a result, institutions of higher education in West Africa became a possibility and a reality only within a strategy of decolonization-or, as Kwame Nkrumah (1968) has called it, neocolonialism. Moreover, the divergent reports of the Colonial Office's (hereafter CO) Elliot Commission sparked an acute two-year controversy between 1945 and 1947 over the future of higher education in Anglophone West Africa. That Commission's Majority Report, backed by three African and five British commissioners, called for the establishment of university colleges at Ibadan in Nigeria and Achimota in the Gold Coast (the nation presently known as Ghana) and for the reorganization of Fourah Bay College in Sierra Leone. Commission's Minority Report, backed by the opposition Labour Party's colonial expert, Arthur Creech-Jones, and four other commissioners, proposed the establishment of a single university college at Ibadan, along with the creation of territorial colleges that would serve as extramural centers in Nigeria, the Gold Coast, and Sierra Leone. Nevertheless, as this article argues, the system of higher education that was eventually established in this region reflected, in important aspects, the wishes and interests of the West African elite, especially those of the Gold Coast. Historians of West African education have generally ignored the role of nationalist pressure upon colonial education policy and have tended to concetrate on other British universities, concentrates more on the phenomenon of educational adaptation fron one culture to another than on the political aspects of the subject. Hence, the relegates the nationalist events between 1945 and 1947 to a mere footnote. Other scholars illuminate the panAfricanist roots of the agitation for a West African university but neglect events between 1945 and 1947, when agitation became a matter of practical politics (King, 1971; Langley, 1973). Ajayi and Tamuno (1973) focus on the divelopment of the University of Ibadan after its founding in 1947, peripherizing the influence of the West African elite to a brief section titled The Anecedents. Eluwa's (1967) unpublished doctoral dissertatioin is closely related to the theme of the present study, but it does not go beyond 1930. Howard (1982) attempts to deal with the critical events between 1945 and 1947. He analyzes the impact of African educational models introduced by Africans returning from America, especially Nnamdi Azikiwe (1937-1969, 1961, 1970), whose radical journalism in the 1930s and 1940s sheds light on West African nationalism during its maturation stages. …
openalex: W1994008566 mag: 1994008566
Keywords: openalex:import

Teachers' perceptions of learning difficulties among students in Uganda - Enon, J.C. (1997)
openalex: W1495286669 mag: 1495286669
Keywords: openalex:import

Contemporary liberalism and civic education in South Africa - Enslin, Penny (Current Writing: Text And Reception in Southern Africa, 1997)
(1997). Contemporary liberalism and civic education in South Africa. Current Writing: Text and Reception in Southern Africa: Vol. 9, No. 2, pp. 77-90.
openalex: W2056571875 mag: 2056571875
Keywords: openalex:import

Reinfection of school children with schistosoma mansoni in the Finchaa Valley, Western Ethiopia - Erko, Berhanu; Gemetchu, T.; Medhin, Girmay; Birrie, Hailu (Ethiopian Journal of Health Development, 1997)
Abstract: Reinfection of school children with Schistosoma mansoni and factors thought to be responsible were studied in Finchaa Valley during 1993-95. A cohort of school children treated and cured of schistosome infection were followed for 12 months for reinfection studies. The annual reinfection rate and intensity were 26% and 374 EPG (eggs per gram of stool), respectively. Pretreatment intensity level was regained faster than pre-treatment prevalence 12 months posttreatment. Reinfection rate was associated with age, sex and seasonality of infection in snail hosts. Peak in snail population density and associated cercarial infection was observed in the dry season when high reinfection rate was found among school children. Rainfall appeared to have a pronounced effect in governing snail population density and cercarial infection. Detailed investigations involving all age groups on immunological response and water contact activities are necessary to assess the role of immunity and exposure on schistosome reinfection patterns. The implication of the findings to the control strategies are discussed. [Ethiop. J. Health Dev. 1997;11(3):269-274]
openalex: W2260152905 mag: 2260152905
Keywords: openalex:import

Water pollution in selected urban areas in the ESCWA region (case-studies of Damascus, Gaza and Jeddah). - Escwa, Un. (1997)
openalex: W3162964999 mag: 3162964999
Keywords: openalex:import

Multicultural Training Needs for Counselors of Gifted African American Children. - Evans, Kathy (Multicultural Education, 1997)
openalex: W2994107106 mag: 2994107106
Keywords: openalex:import

Empowering African American Students to Learn - Ewing, Kimberly D. (1997)
openalex: W601118144 mag: 601118144
Keywords: openalex:import

Higher Education and National Development Planning in Africa - Ewoh, Andrew I.E. (Journal of Public Management, 1997)
openalex: W1555037634 mag: 1555037634
Keywords: openalex:import

Of copper and fire : the Self-Help Action Plan for Education (SHAPE) in Zambia - Faccini, Benedict (1997)
openalex: W588895748 mag: 588895748
Keywords: openalex:import

The Effects of Gender and Education on Perceptions of Social Status and Power in Larteh, Ghana - Fallon, Kathleen M. (1997)
openalex: W1128015370 mag: 1128015370
Keywords: openalex:import

Is Math in the Classroom Neutral–or Dead? A View from Palestine. - Fasheh, Munir (for the learning of mathematics, 1997)
openalex: W2994109166 mag: 2994109166
Keywords: openalex:import

Quality of STD Care in Zambia. Impact of Training in STD Management - Faxelid, Elisabeth; Ahlberg, Beth Maina; Freudenthal, Solveig; Ndulos, J.; Krantz, Ingela (International Journal for Quality in Health Care, 1997)
Study Objective: To assess quality of care of sexually transmitted diseases (STDs) and evaluate interactive training methods aimed at improving provider‘s performance. Design and setting: This comparative study, with a baseline, intervention, and evaluation phases was conducted at two urban health centers in Zambia. The personnel at one health center were trained in STD management using interactive training methods. The other health center acted as a control. Subjects and methods: Two-hundred patients with STD were interviewed and their interaction with health care provides observed before and after the training. Another 200 interviews and observations were conducted at the control health center. Resubr: The proportion of patients being examined, given health education and informed about partner notification increased significantly after the intervention. The proportion of patients who had complaints about the health care did not decrease. Long waiting time and lack of time to discuss the disease were the main complaints. Conclusion: Tbe training solved some, but not all, problems of poor case management This indicates tbe need for a more process-oriented approach for improving quality of care. © 1997 E3sevier Science Ltd.
openalex: W1995843774 mag: 1995843774
Keywords: openalex:import

Yalla Baax Naa: AIDS Education, Women and Islam in Bambey, Senegal: Developing an Effective AIDS Education Model for Women - Fjeld, Karen J. (1997)
openalex: W1592480703 mag: 1592480703
Keywords: openalex:import

A study of the appraisal of mathematics teachers in Ghana - Fletcher, Jonathan A. (1997)
Teacher appraisal may provide opportunities for teachers to improve the quality of their teaching, thereby increasing the quality of pupil learning. Literature on teacher appraisal in Ghana indicates that the appraisal system is designed to serve both formative and summative purposes. The ability of the appraisal system to provide opportunities for mathematics teachers to develop professionally is the subject of this study. The study aims to: a) identify the nature and purposes of Teacher Appraisal in Ghana (TAG); b) examine the validity of existing methods of TAG specifically by: i ... examining the potential of the appraisal system to help mathematics teachers improve their teaching of mathematics; 11 ... finding which variables are significantly related to Ghanaian secondary mathematics teachers' views of teacher appraisal in Ghana and its ability to help them improve their teaching of mathematics c) identify the implications of any changes in the existing teacher appraisal systems for Ghana's educational policies. 441 secondary mathematics teachers participated. 193 of these teach the subject at the junior secondary level and 248 teach it at the senior secondary level. In addition, 44 Ghana Education Service officials (and 6 heads of secondary schools) who appraise mathematics teachers were sampled. Questionnaires and interviews were used to collect teachers' and appraisers' perceptions of the appraisal system. Additionally, some appraisers were observed while at work. The results of the study showed that many education officials in Ghana who appraise mathematics teachers, and who are required to 'help' mathematics teachers improve their work, have little or no training in secondary school mathematics teaching or its appraisal. Regarding mathematics teachers' perception of the appraisal system, highly significant negative correlations were found between their perceived professional support and rank and professional status at the senior secondary level; whereas relatively weak positive correlations were found between perceived support and last appraisal session and rank at the junior secondary level. Thus, the results indicated a dramatic difference between junior secondary and senior secondary mathematics teachers in their perceptions about the potential of the teacher appraisal system in Ghana to help them improve their teaching of mathematics. Senior secondary mathematics teachers were generally more pessimistic about the potential of the appraisal system to help them improve their work than their junior secondary counterparts. Putting the results at the junior secondary and senior secondary levels together, the study found professional status to be the single most important determinant of teachers' attitude to teacher appraisal in Ghana as a formative process. The above differences between junior secondary and senior secondary respondents thus reflected the differences in the two groups of teachers' academic and professional qualifications in mathematics. The findings of the study lead to the conclusion that the teacher appraisal system in Ghana cannot, in its present form, provide opportunities for mathematics teachers to develop professionally. The implications of the findings are discussed.
openalex: W1700603452 mag: 1700603452
Keywords: openalex:import

Karani, F.A. and J.O. Shiundu; "Education Systems in East Africa - Trends and Issues," in Thomas Mcdonald, and Thomas W. Scheidtweiler (eds.) Higher Education in East Africa. Proceedings of a KASEA Seminar 17 - 21 September 1997 Nairobi. Kenya. Katholisch - Florida, A Karani (1997)
openalex: W2597884351 mag: 2597884351
Keywords: openalex:import

Relevance of Higher Education in Africa in the 21st century - Florida, A Karani (1997)
openalex: W2566339301 mag: 2566339301
Keywords: openalex:import

An examination of the problems confronting effective teaching and learning of the Arabic language in Nigerian colleges of education - Folorunsho, Mikail Adebisi (1997)
openalex: W1505272532 mag: 1505272532
Keywords: openalex:import

Developments in the South African fitness industry : implications for education and training. - Forbes, Mary Jane. (1997)
openalex: W1604748112 mag: 1604748112
Keywords: openalex:import

African Portraits: Essays on Daily Life by Sierra Leonean Students - Foster, Leslie (1997)
openalex: W603013352 mag: 603013352
Keywords: openalex:import

Learning from South Africa - Fowler, Raymond D. (1997)
openalex: W4233019311
Keywords: openalex:import

"Sundiata, Lion King of Mali." Adapted by Kim Hines, Featuring Griot Alhaji Papa Susso, Cue Sheet for Students. - Freeman, A. (1997)
openalex: W2569638959 mag: 2569638959
Keywords: openalex:import

Linguistically and Culturally Diverse Students. Populations: African American & Hmong. Language Sample Analysis Companion Guide. - Freiberg, Christine (1997)
openalex: W117597716 mag: 117597716
Keywords: openalex:import

Telling Their Stories: African-American Parents Talk to White Teachers. - Frieman, Barry B.; Watson-Thompson, Ocie (1997)
African-American parents whose children attend twelve different Baltimore City Public Schools made it clear while participating in a focus group that white teachers have a lot to learn about teaching their children. They want teachers to come into the classroom with a belief that their children can learn. They also want teachers to understand African-American history and culture, as well as how best to teach their children. Finally these parents want teachers to see their children as unique people and know that parents are willing to be partners in the education
openalex: W100092000 mag: 100092000
Keywords: openalex:import

Their Highest Potential: An African American School Community in the Segregated South - Fultz, Michael; Walker, Vanessa Siddle; Irvine, Jacqueline Jordan; Foster, Michèle (History of Education Quarterly, 1997)
openalex: W2334140279 mag: 2334140279
Keywords: openalex:import

Conflicts in church and society in Uganda with special reference to culture, politics and education - Gaalimaka, Herbert I. (1997)
This thesis examines the conflicts which emerged from the way the Church in Uganda generally (and the Anglican Church of Uganda (ACU) in particular) interacted with die society on three key fronts: culturally, politically and educationally. The aim is to exhibit die historical development of the Church m light of those areas; and die impact that development has had on the society, and so pose a challenge for the present ACU to reflect on and act for a viable and more acceptable ministry in future free of conflict favouritism and domination. Chapter I covers the historical background from 1877-1962; it describes the coming of die CMS missionaries to Uganda following Muteesa I’s invitation to be followed later by the Roman Catholic missionaries. It describes how religious controversies between these two groups dominated Ugandan politics. The road leading to a Uganda protectorate and the developments initiated by both the missionaries and die colonial government including education, health services and economy, are also set out. Chapter 11 looks at the culture into which Christianity came and the nature of their clash leading to an age long conflict. It highlights the model operated by die missionaries, its weaknesses and strengths. It describes some alternative models from Africa and die Caribbean and lastly suggests die best way forward. Chapter III deals with the Church and Colonialism. then: invasion of the traditional political structure and the developments brought about by the two institions. The beginning of political parties following the political and economic dissatisfaction of die Ugandan society, so paving die way to independence, is discussed here. Featured also are the colonial policies answerable for the age long suffering in Uganda and the model responsible for church and state interdependence which reigns to this day. It cites alternative models and suggests which way to go. This chapter covers pre- independence, and post independence to die present day. Chapter IV looks at the traditional form of education and its values. It highlights die introduction of the missionary western form of education, its characteristics and goals which in many ways divorced the learner from his/her roots. It shows both the native society and die colonial government losing confidence in that system of education and seeking to replace it with a government-run system of education. This chapter also looks at other models from elsewhere and suggests a way forward.
openalex: W180949843 mag: 180949843
Keywords: openalex:import

History of Ghana since pre-history : a textbook for senior secondary schools - Gadzekpo, Seth Kordzo (1997)
openalex: W595197085 mag: 595197085
Keywords: openalex:import

Issues and strategies for primary and secondary education decentralisation in Tanzania - Galabawa, J.C.J. (Papers in Education and Development, 1997)
openalex: W297636551 mag: 297636551
Keywords: openalex:import

Motives and Objectives of Teaching Russian in South Africa - Garmashova, Irina (Language Matters, 1997)
Abstract In this article, using updated research information from 1995-1996, the author examines motives for learning and objectives of teaching Russian as a foreign language at university level in South Africa. This paper reveals new insights into previously determined objectives of learning Russian Language, Literature and Culture. The author identifies new tendencies in initial students' motives and demonstrates the necessity of creating an alternative comprehensive study model in terms of a proposed semesterisation and modularisation system of teaching foreign languages at UNISA. Based upon the research findings, recommendations are made to address students' motivation and expectations.
openalex: W2175242965 mag: 2175242965
Keywords: openalex:import

Climate changes in the African tropics over the last glacial/post-glacial period. What do lake sediments tell us? - Gasse, F.; Gibert, E. (1997)
openalex: W3148353589 mag: 3148353589
Keywords: openalex:import

Kenya Secondary School Christian Religious Education: quantitative and qualitative investigation of teachers and students attitudes-Phd. Thesis: - Gatumu, JC (1997)
openalex: W2257795200 mag: 2257795200
Keywords: openalex:import

Efficiency of primary education in Kenya: Situational analysis and implications for educational reform - George, Odipo; Abagi, Okwach (1997)
openalex: W1498241864 mag: 1498241864
Keywords: openalex:import

Education : a gender profile of the determinants and outcomes of schooling in the West Bank and Gaza Strip - Ghali, Mona (1997)
openalex: W598965593 mag: 598965593
Keywords: openalex:import

Are There Lessons That Sub-Saharan African Countries Could Learn From East Asia's Successful Development Experience? - Ghebreyesus, Ghirmay S. (Scandinavian journal of development alternatives, 1997)
openalex: W2258515553 mag: 2258515553
Keywords: openalex:import

Training Needs Perceptions of Kenyan Entrepreneurs. - Gichira, Robert; Nelson, Robert E. (Journal of Industrial Teacher Education, 1997)
Over the past 10 years, economic planners have realized the importance of the small enterprise sector in achieving economic development. Estimates are that 900,000 small enterprises in Kenya employ two million people (Dolman, 1994). While little evidence exists that these small firms grow into medium-size firms (employing 50 to 100 workers), many of these small firms have the potential to add one to five employees. In addition to its importance in creating jobs, the small enterprise sector contributes 33% ofthe value-added in manufacturing and the retail trade in Kenya (Onyango & Tomecko, 1995). Major constraints to expanding the small enterprise sector in Kenya appear to be lack of capital, infrastructure, and managerial skills. Government can provide leadership in developing a policy framework that will create a more positive environment within which small enterprises can operate. However, entrepreneurs must take the initiative to improve their small enterprises by improving their managerial skills through training. Individuals from different economic, social, and educational backgrounds become entrepreneurs in many different ways and under varying conditions, many without undergoing any training. Other people become entrepreneurs only after having been selected and trained. One question is whether they can develop these skills to expand their business operations through training or by merely engaging in entrepreneurial activities (Osirim, 1990; Rissal, 1988). A second question is whether training provides entrepreneurs with a
openalex: W295893816 mag: 295893816
Keywords: openalex:import

Management Structures in European and South African Higher Education Systems - Goedegebuure, Leo; Maassen, Peter (1997)
openalex: W2736677386 mag: 2736677386
Keywords: openalex:import

Facilitating education in rural areas of South Africa : the role of electricity and other sources of energy - Gordon, Adele (1997)
openalex: W407717517 mag: 407717517
Keywords: openalex:import

Environmental education and outcomes-based education in South Africa: A marriage made in heaven? - Grange, Lesley Le; Reddy, Chris (The Southern African Journal of Environmental Education, 1997)
The infusion of environmental education into a new South African curriculum marks a historic shift from the past where it was marginalised from mainstream, formal education. Through the Environmental Education Policy Initiative (EEPI), environmental education was included as a key principle in the most recent government white paper on education and training. This policy process provided a platform for the establishment of an Environmental Education Curriculum Initiative (EECI) to ensure that environmental concerns form part of the new outcomes based curriculum (OBE) for South Africa. Many members of the environmental education community have been actively involved in EECI activities and environmental education and OBE was one of the key features at the most recent conference of the Environmental Education Association of Southern Africa (EEASA). In this article we attempt to highlight the parallels between environmental education and OBE and raise a critical debate around the institutionalisation of environmental education in South Africa.
openalex: W2409769343 mag: 2409769343
Keywords: openalex:import

Three Strikes and They're Out: African American Boys and American Schools' Responses to Misbehavior - Gregory, James F. (International journal of adolescence and youth, 1997)
ABSTRACT This article examines summary data from a recent U.S. Office for Education civil rights survey of American schools in terms of three specific types of school responses to children's misbehaviors: corporal punishment, suspension from school, and placement in Special Education for the Behaviorally Disordered. Extremely large disparities in rates for African American boys versus those for girls and boys of other race/ethnicity groups were often found. The shear magnitude of the differences suggests that selectivity may be operating vis-a-vis punitive/exclusionary measures taken by schools when responding to children's behaviors. Speculations as to these dynamics are offered.
openalex: W2032781305 mag: 2032781305
Keywords: openalex:import

Differences in educational outcomes of African American students from different socioeconomic backgrounds - Grosset, Jane (Structural Equation Modeling: A Multidisciplinary Journal, 1997)
This research tested a structural equation model of educational outcomes for three socioeconomic status (SES) groups of African American students enrolled in a community college. The structural model, which was based on a variant of Tinto's (1987) model, contained two exogenous constructs, educational intentions/commitment and external commitments, and three endogenous constructs, academic integration, social integration, and educational outcomes. The study demonstrated that higher levels of academic and social engagement had positive direct effects on educational outcomes for all students regardless of SES background. Other paths that were supported included the positive direct effects of educational intentions/commitment on academic and social integration and the negative impact of external commitments on social integration. Significant structural differences were not present in the measurement of model constructs or the process of educational outcomes among lowest, lower to middle, and middle to upper SES groups.
openalex: W1989329790 mag: 1989329790
Keywords: openalex:import

Perception of head teachers regarding supervision of Swaziland school system - Gumbi, C.S.; Dlamini, B.M. (1997)
openalex: W110211963 mag: 110211963
Keywords: openalex:import

The learning of French by Algerian students : a socio-phonetical study - Hacini, Fatiha (1997)
openalex: W4392216299
Keywords: openalex:import

Proposition 16 and the access to higher education for college- bound African American student athletes - Hairston, Karla C. (1997)
openalex: W1149666324 mag: 1149666324
Keywords: openalex:import

Family influences on school achievement in low-income, African American children. - Halle, Tamara; Kurtz‐Costes, Beth; Mahoney, Joseph L. (Journal of educational psychology, 1997)
openalex: W4241848683
Keywords: openalex:import

The language of education in Africa: The key issues - Hameso, Seyoum (Language, Culture and Curriculum, 1997)
As a result of their colonial past, African children are still educated predominantly through the medium of a foreign language. The author explores the historical, political and socio‐economic background to this situation, and examines its advantages and disadvantages. Since the foreign languages (mainly English, French and Portuguese) are major international languages, they help in the transfer of science and technology. But they are foreign, and are therefore limited, as media of education, in their capacity to serve many of the personal, local and national objectives of the educational system. The position of the indigenous languages is examined and their potential as media of instruction. The case of Amharic in Ethiopia is examined in detail, and also that of Kiswahili in Kenya and Tanzania. The author discusses the necessary developments that will have to occur to provide full participation of the population in truly democratic institutions. He concludes that the revival of African languages and cultures is inextricably linked with rehabilitation of African political and economic institutions.
openalex: W2171702209 mag: 2171702209
Keywords: openalex:import

Kenya studies its schools to identify obstacles for girls. Education and gender. - Harel, K (PubMed, 1997)
Interviews were conducted with almost 800 adolescents and their parents in 3 districts representing the range of school experience in Kenya. Researchers also visited 36 primary schools attended by more than 80% of the adolescents sampled, holding interviews with teachers and students, documenting facilities, observing interactions, and compiling measures of performance. Boys were seen bullying girls outside of classrooms, teasing them and blocking their movements. In focus group discussions, boys and girls reported that boys routinely grab girls' breasts, while teachers ignore the abuse. Teachers described girls as stupid and lazy, with both male and female teachers who expressed a preference for teaching one sex or the other preferring boys. The teachers more often allocated menial chores to girls and teaching tasks to boys. Even in schools in which girls performed almost as well as boys on exams, teachers awarded twice as many prizes to boys. The teachers created a context in which girls perform poorly. When the girls do in fact fail to achieve, teachers' prejudices are simply reinforced. On the other hand, schools at which girls performed better on exams had more female teachers who presumably served as role models. Also, girls in schools with more female students scored higher on the final, nationwide exam.
openalex: W105459646 mag: 105459646
Keywords: openalex:import

The Diploma Disease in Egypt: learning, teaching and the monster of the secondary leaving certificate - Hargreaves, Eleanore (Assessment in education, 1997)
Abstract Eygpt's education system is dominated by the secondary leaving certificate, the thanaawiya aama examination. From the earliest primary years, schooling is characterised by examination orientation and ritualisation. These features, in addition to Egypt's relatively late drive towards modernisation accompanied by centralisation and newly forged social divisions, clearly categorise Egypt as a victim of the ‘diploma disease’. Attempts to reform the assessment system are being hampered by the continuing perception of current school qualifications as the means to success, whether in the public or private sector, within Egypt or abroad.
openalex: W1980743258 mag: 1980743258
Keywords: openalex:import

Media literacy and video technology: Educational and motivational tools to empower African-American males in special education - Harts, Melissa Lorraine (1997)
openalex: W613257612 mag: 613257612
Keywords: openalex:import

Prevalence and Some Determinants of Premenstrual Syndrome among a Group of Primary School Teachers in Alexandria, Egypt - Hassan, Mona (1997)
The present study was carried out aiming to study ttle prevalence of Premenstrual Syndrome [PMS] among a group of teachers in Alexandria and to find out the relation between some determinants and PMS. The study was conducted on a sample of 500 primary school teachers in Alexandria through a cross-sectional approach. A pre-structured pre-tested questionnaire was used to collect the data. The Menstrual Distress Questionnaire [MDQ] developed and revised by Moos in 1991 was used to identify the type and intensity of symptoms during the premenstrual phase. Role acceptance scale was used to measure the womans acceptance to her feminine role. The prevalence of PMS rangedfrom 10.6% for those having high score on pain scale to 20.6% for Ulose having high score on arousal scale. Symptoms scales were positively correlated across the three cycle phases with the highest correlation between premenstrual and menstrual phases on both arousal and impaired concentration scales. Positive correlation was also found among the symptom scales with the highest correlation between impaired concentration and each of behavioral change and negative affect scales. Using stepwise logistic regression analysis, the most important determinants contributing for the high scoring on MDQ scales were cycle length [<24 days and >32 days], caffeine consumption, nulliparity, and unpredictable menses. Role acceptance and intrauterine device use had a protective effect against PMS symptoms.
openalex: W3133280755 mag: 3133280755
Keywords: openalex:import

University Education and African Thought: Reflections on Underachievement Among Some UNISA Students - Heerden, Van; Eulalie, M. (South African Journal of Ethnology, 1997)
openalex: W2266730213 mag: 2266730213
Keywords: openalex:import

Social cognitive theory and career development in African-American and Euro-American college students - Hill, Mary (1997)
openalex: W2599315002 mag: 2599315002
Keywords: openalex:import

Annotated Selected Bibliography & Index for Teaching African-American Learners: Culturally Responsive Pedagogy Project. - Hilliard, Asa G. (1997)
openalex: W1091854901 mag: 1091854901
Keywords: openalex:import

Resources for Teaching about Sub-Saharan Africa. - Hinton, Samuel; Mowell, Barry; Brook, Diane L. (Social Education, 1997)
openalex: W211492804 mag: 211492804
Keywords: openalex:import

Large and small classes in Egyptian university classrooms: a cultural justification for curriculum change - Holliday, A. K. (1997)
openalex: W1919303780 mag: 1919303780
Keywords: openalex:import

Environmental management research and training in Coast Province, Kenya - Hoorweg, J.C. (1997)
The natural environment of the Kenyan coast is threatened in many ways. A study day was organized on August 7, 1996, by the School of Environmental Studies, Moi University, Eldoret, with presentations on the activities and research priorities of organizations concerned with coastal environment issues. This report contains presentations on district environment management by Henry Munga'sia; the Coast Development Authority by Bonfance Mwandotto; maritime research priorities for the Kenya Marine and Fisheries Research Institute, by Enock Wakwabi; the marine programmes of the Kenya Wildlife Service, by Nyawira Muthiga; the wetlands conservation project of the Kenya Wildlife Service, by Els Martens; small fisheries research in Kwale District, by Anthony King and Delphine Malleret-King; priorities in botanical research in coastal Kenya, by S. Ann Robertson; Kaya Forest conservation on the Kenya coast, by Anthony Githito; wasteland rehabilitation, by Sabine Baer; activities of the International Centre of Insect Physiology and Ecology, by Srinivasan Sithanantham & Z. Ngalo Otieno; activities of the Kenya Agricultural Research Institute, by Geoffrey Kamau; the Coral Reef Conservation Project, by Nyawira Muthiga and Tim McClanahan; and the training course on Fundamental and Applied Marine Ecology of the Free University of Brussels, by Nanette Daro
openalex: W1518684412 mag: 1518684412
Keywords: openalex:import

Achievement motivation and level of aspiration: adolescent Ethiopian immigrants in the Israeli education system. - Horowitz, Tamar; Mosher, Naftalie (PubMed, 1997)
This paper focuses on two questions: Are Ethiopian high school children who immigrated to Israel achievement motivated? To what extent does the presence or absence of certain components of the achievement construct in the indigenous value system of Ethiopian students affect progress at school? The study is based on pilot research conducted in Israel in 1987 for which the central research questions were: Are elements of motivation to be found in the indigenous value system of Ethiopian students? If so, what is their effect on progress at school? The research is based on a questionnaire administered to 88 Ethiopian students and 85 veteran Israeli students. The main findings of this research are: There are some elements in the socialization of Ethiopian students that can be looked upon as components of achievement motivation. These include a high level of aspiration, the ability to postpone gratification, and obedience. These elements help the Ethiopian children succeed at school. On the other hand, some elements in the socialization of Ethiopian children hinder their progress: conformity restraints on individual creativity and external locus of control.
openalex: W65788499 mag: 65788499
Keywords: openalex:import

Educational Resources on Traditional African Music: An Annotated Bibliography of Contemporary Offerings and Suggestions for Their Use in the Classroom - Horton, Christian D. J. (Journal of Negro Education, 1997)
Christian D. J. Horton, Fort Valley State University* In their eagerness to develop proposals for curriculum and instruction, contemporary researchers and developers of resources on traditional African music often fail to understand that available resource materials must be critiqued in terms of the schools and students for whom they are primarily intended. Toward that end, this annotated bibliography was compiled to combat both the dearth of musicological resources on traditional African music and teacher-educators' lack of knowledge about these resources. It examines significant works published between 1960 and 1991 that provide information and perspectives superseding previously available instructional resources. In Africa and elsewhere, educators have called for the development and use of educational resource materials on traditional African music as a means of preserving and perpetuating this vital art form. This call has become increasingly urgent in recent years as the breakdown in traditional systems of cultural transmission among modernizing nations on the continent of Africa has resulted in much of its traditional music being lost or severely misrepresented. Several resources on traditional African music have been published in the last three decades. Unfortunately, many of these works, particularly those published in the 1960s and before, fail to assess the enormity of the sociocultural and educational issues involved in the formal study, use, and performance of this music in the classroom. In their eagerness to develop proposals for curriculum and instruction, contemporary researchers and developers of resources on traditional African music often fail as well to understand that available resource materials must be critiqued in terms of the schools and students for whom they are primarily intended. Although many of the contemporary resources offer innovative suggestions for the inclusion of traditional African music in formal education, most continue to ignore the critical issues mentioned above. It is therefore incumbent that teachers and learners using these resources take these aspects into consideration to determine whether any adjustments in instructional strategies or perspective must be made. The authenticity of various traditional musical forms must also be interrogated to determine their relevance and importance to the cultures from which they spring. This bibliography was compiled to combat both the dearth of musicological resources on traditional African music and teacher-educators' lack of knowledge about these resources. It examines significant works published between 1960 and 1991 that provide information and perspectives superseding previously available instructional resources. In compiling it, sight was not lost of earlier bibliographic compilations, many of which are annotated and contain information relevant to this research (e.g., Aning, 1967; Gaskin, 1965; Gray, 1991; Lems-Dworkin, 1991; Merriam, 1951; Thieme, 1962; Varley, 1936). The most notable of these are described in this compilation. Nonetheless, there remains an urgent need for more ethnographic studies of traditional African music, especially those pertaining to song repertoire and musical instruments, that ensure the preservation and perpetuation of Africa's cultural heritage. Studies addressing these critical areas, and the resource materials that emerge from them, are essential to the continued study of this important musical legacy in classrooms around the world. Aduonum, Kwasi. (1981). A compilation, analysis, and adaptation of selected Ghanaian folktale songs for use in the elementary general music class. Doctoral dissertation in music education, University of Michigan-Ann Arbor, 1980 (UMI No. AAI 8017212). 492 pp. The teaching techniques recommended in this work, which provides notation for several traditional Ghanaian folk songs and a recounting of the folktales associated with them, are based on the assumption that exposure to and involvement with traditional African music forms will help fulfill the aesthetic needs of children and assist in raising the level of their intellectual and cultural experience (p. …
openalex: W2074417775 mag: 2074417775
Keywords: openalex:import

Mathematics and Science Performance in the Middle School Years in the Northern Cape Province of South Africa. The Performance of Students in the Northern Cape Province in the Third International Mathematics and Science Study (TIMSS). - Howie, Sarah J. (1997)
openalex: W1564474331 mag: 1564474331
Keywords: openalex:import

Psychosocial environment of agricultural science classrooms in Nigeria - Idiris, Suleiman; Fraser, Barry J. (International Journal of Science Education, 1997)
This article reports the first classroom environment study worldwide specifically in agricultural science classes and one of the few learning environment studies in Nigeria. The sample consisted of 1 175 students in 50 classes in 20 schools in eight states and the federal capital. First, Nigerian agricultural science classrooms were perceived by students to have particularly low levels of student centredness and negotiation. Second, a new classroom environment instrument displayed satisfactory internal consistency reliability and discriminant validity with both the individual student and the class mean as the unit of analysis; it also differentiated between the perceptions of students in different classrooms. Third, past research was replicated in that associations between student outcomes (attitudes and enquiry skills) and classroom environment were established.
openalex: W2029061011 mag: 2029061011
Keywords: openalex:import

Students' Deviance in Nigerian Tertiary Institutions: An Observation - Igbinovia, Patrick Edobor (International journal of adolescence and youth, 1997)
ABSTRACT The definition of deviant behaviour is elusive; but I will adopt a simple one; deviance is behaviour that violates the norms and expectations of a group. The first mention of the concept Sociology of deviant behaviour can be traced to Marshall B. Clinard, an American sociologist, who wrote a book of the same title about 37 years ago (1957). Indeed, Clinard's book was the first textbook in deviant behaviour and it provided the first codification of the deviant behaviour perspective. Consequently, in tackling the subject before us, emphasis throughout will be on the sociological understanding of the meaning, the process, and the control of deviant behaviour of students in institutions of higher learning in Nigeria.
openalex: W1989850857 mag: 1989850857
Keywords: openalex:import

Environmental problems associated with aquatic pollution: a focus on Nigeria - Imeh, O.; Akanbi; Oladimeji, C.T. (IFE Psychologia: An International Journal, 1997)
Environmental problems occur at all stages of pollution of the natural environment. In the marine environment the problem is more serious when the pollutants arc absorbed in the food web of marine system. They arc as a result of disturbance of the natural habitat which included; dumping of raw sewage directly into the marine waters, chemical and oil spills. The input of oil to the Atlantic waters of Nigeria have been identified as a major source of environmental problem in Nigeria's marine waters. This paper reveals that marine pollution have caused serious setback to the orderly progress, economic and social advancement of the territorial communities.
openalex: W2950691058 mag: 2950691058
Keywords: openalex:import

Crafted for prosperity; Pointers from Germany regarding the appropriate place and provision of Vocational Education and Training within the Educational Realm, and comparisons with South Africa - Inskip, Chris; Spargo, P. E. (1997)
openalex: W2623510110 mag: 2623510110
Keywords: openalex:import

High risk sexual behaviours for STD/HIV, pregnancies and contraception among high school students in a rural town, north western Ethiopia - Ismail, Shabbir; Bitsuamlak, Habteab; Alemu, Kahsu (Ethiopian Journal of Health Development, 1997)
Abstract: A cross-sectional study evaluated STD/HIV related sexual behaviours among 383 (90.8% of the required 422) secondary school students in Kolla Diba town of North Gondar Zone using a pre-tested self-reporting questionnaire. Additionally, the contraceptive utilization and occurrence of pregnancies among the 202 female students was evaluated. There were 122 (31.9%) sexually active students, of these 44 were females. Their mean age of sexual commencement was 16.4(± 2.3 SD) years. The total number of sexual partners in the past six months was around two. Ten (9.3%) had sex with commercial sex workers (CSWs) in the past six months. Only 45.9% had used condoms and half of them regularly. The most common sources of condoms were shops. Fourteen (11.5%) of the sexually active students had contracted a sexually transmitted disease (STD) in the past six months. Three hundred and forty nine (91%) of the students have heard about AIDS, 297 (85.1%) believe in its existence and 166 (47.6%) have seen an AIDS patient. Only 65 (18.6%) felt that they can acquire HIV infection. Of the 44 sexually active female students, 11 (25%) are using contraceptives at present. Oral contraceptive pill is the most commonly used method. The major reasons for the non-utilization of a reliable method of contraception among the non-users were fear of side effects, refusal by the partners and refusal by family. Half of all the sexually active female students were pregnant at least once. Seventy four percent of the female students would prefer to deliver at term if pregnant. Only 37 (18.1%) of the females favoured the legalization of abortion. A higher level of education was associated with contraceptive use (p<0.03). The implications of these results are discussed. Strengthening the present educational campaign on AIDS, promotion of family life education and making contraceptives accessible in schools are recommended. [Ethiop. J. Health Dev. 1997;11(1):29-36]
openalex: W2287309900 mag: 2287309900
Keywords: openalex:import

Reform of legal education in South Africa: Analysis of the new challenge of change* - Iya, Philip F. (The Law Teacher, 1997)
openalex: W2019155755 mag: 2019155755
Keywords: openalex:import

The Frequency and persistence of droughts in Eastern and Southern Africa - J, Ininda Mwalichi (1997)
openalex: W2298150353 mag: 2298150353
Keywords: openalex:import

Quinine-induced Hearing Loss in the Guinea Pig is Not Affected by the Ca^2+Channel Antagonist Verapamil - Jäger, Wanje; Idrizbegovic, Esma; Karlsson, K.; Alván, Gunnar (Acta Oto-Laryngologica, 1997)
It is well documented that quinine induces reversible hearing loss and tinnitus. The purpose in this study was to induce a quinine hearing loss and to investigate if verapamil, a Ca2+ channel antagonist of L-type might affect the response. Pigmented guinea pigs (n = 24) were anaesthetized by atropine. Hypnorm and midazolam but permitting spontaneous respiration. An electrode of platinum was placed on the round window and short (10 msec) tone pulses at 8 kHz were presented to the external ear. A typical deflection of the N1-wave was determined as the hearing threshold. Quinine hydrochloride 40 mg/kg and verapamil 1 mg/kg were given intravenously. Quinine induced a significant and reversible hearing loss (mean 16 dB). This hearing loss was not at all affected by verapamil given before or after quinine. Verapamil often caused acute cardiac arrest and particularly the combination verapamil followed by quinine-induced death to the animal. We conclude that verapamil and quinine had no in vivo interaction with regard to the hearing ability.
openalex: W1972414665 mag: 1972414665
Keywords: openalex:import

The Fula and Islamic Education in Freetown, Sierra Leone - Jalloh, Alusine (American journal of Islam and society, 1997)
This study examines the role of the Fula in Islamic education inFreetown, the capital city of Sierra Leone, from the colonial to the postcolonialperiod. The Fula educational initiative forges a partnershipbetween the Muslim private sector and local educators. Not only does itprovide a model for responding to the challenge of developing Islamiceducation in Sierra Leone, but it is a model that can be implementedthroughout Africa. It is especially important given the increasing multiethnicstudent population and limited government support for Islamiceducation in Sierra Leone and across the continent. The recent decline insupport from foreign Islamic countries for education in Africa addsurgency to the need for African Muslims, such as the Fula, to pursue alternative approaches to promotingIslamic education through broad-based cooperation among local educators, indigenous Muslim businesspersons, and the govemment.For over two centuries the Fula, a devout Muslim group inAfrica,' were pioneers in the spread of Islam not just in Freetownbut throughout Sierra Leone. In fact, the Fula ...
openalex: W1821815930 mag: 1821815930
Keywords: openalex:import

Contradictory Tensions in the Experiences of African Canadians in a Faculty of Education with an Access Program - James, Carl E. (Canadian Journal of Education, 1997)
In this article, I examine the experiences of a sample of African Canadian teacher candidates in a Faculty of Education with an access program, noting how their educational experiences are affected by the existence of the program; how they negotiate the learning environment, which does not welcome their presence; and what narratives they construct to explain the contradictions inherent in their presence in the institution. The experiences of these students indicate that the culture of the Faculty does not provide a productive learning environment. The narratives the students construct reveal that although they were disenchanted with being identified as access students, they remained determined to become teachers because they saw themselves as involved in a critical process to become role models, and advocates for educational change.
openalex: W338687097 mag: 338687097
Keywords: openalex:import

Early Childhood Education Opportunities in the Community of Ebuakwa (a community located in Ghana, West Africa) - James, Jennifer (1997)
openalex: W200109857 mag: 200109857
Keywords: openalex:import

Curriculum Development For A National Nutrition Training Programme: Republic Of South Africa. - Jansen, Jonathan D.; Omwega, AM (1997)
openalex: W2276117815 mag: 2276117815
Keywords: openalex:import

School science and the development of scientific culture: a review of contemporary science education in Africa - Jegede, Olugbemiro J. (International Journal of Science Education, 1997)
The significant role science plays in the development of an individual and a nation has led to its inclusion in the school curriculum since the early part of the nineteenth century. The values, ethos, practices and perspective of science for interpreting nature are a part of science education. However, in recent times due to a combination of factors, school science has been seen to promote a mythic text book science rather than present the true image of science and reflect the real nature and outcome of scientific enterprise. If current developments occurring around the world are anything to go by, globalization with its attendant economic, political, social and other spin‐offs, together with the phenomenal development in telecommunications, communications technology and computer technology will affect every person living on the globe in the twenty‐first century. To fully understand, appreciate and effectively use all these developments for meaningful learning, scientific culture must permeate the society and the every‐day thoughts and actions of ordinary people. For the developing countries of Africa dominated and governed by non‐western socio‐cultural factors, western science means an imposition of one culture over another. It means the replacement of the anthropomorphic worldview with a mechanistic one. This situation, amongst many others, would further militate against the race to development by African nations. This paper reviews the advent of science into Africa, the curret state of school science in Africa and discusses the possibilities for, and implications of, harnessing traditional African thought system and Western science to develop an effective culture for Africa of the twenty‐first century.
openalex: W2096445005 mag: 2096445005
Keywords: openalex:import

Intestinal helminth infections in school children in Adarkay District, Northwest Ethiopia, with special reference to Schistosomiasis mansoni - Jemaneh, L (Ethiopian Journal of Health Development, 1997)
Abstract: In a survey carried out in five schools of five rural towns in Adarkay district in Northwest Ethiopia, 519 children had their stool specimens examined for Schistosoma mansoni and other intestinal helminth infections of man by the Kato thick smear technique. Infection due to S. mansoni was the most prevalent (54.3%), ranging from 16.7% in Deb Bahir to 55.3% in Adarkay and Buya, 67.4% in Kerenejan and as high as 88.9% in Zarema, followed by Ascaris lumbricoides (43.0%) and hookworm spp (23.3%). The least prevalent was Trichuris trichiura infection (11.8%). Triple, double, and single infections were found in 49 (9.4%), 180 (34.7%) and 172 (33.1%) specimens respectively. Most of the double infections were a combination of S. mansoni and A. lumbricoides (90=17.3%). The highest prevalence for a single infection was recovered for S. mansoni (103=19.8%). Age specific analysis of prevalence due to S. mansoni, the hookworms and A. lumbricoides showed the presence of infection in all ages under consideration, but with no significant difference among the age groups. Neither was there any significant difference in infection rates between the sexes. The average egg counts were generally higher for S. mansoni and A. lumbricoides. Younger age groups appear to have higher average egg counts, particularly for the hookworms. Sex was not related to egg output. The high infection rate of intestinal helminth infestation observed in this study among school children signifies the need for prompt intervention measures. [Ethiop. J. Health Dev. 1997;11(3):289-294]
openalex: W2164804792 mag: 2164804792
Keywords: openalex:import

A case of adoption: distance education at the Mauritius - Jenkins, Janet (Open praxis: the bulletin of the International Council for Distance Education, 1997)
openalex: W1132829387 mag: 1132829387
Keywords: openalex:import

Nigerian guidelines for sexuality education introduced at ceremony in Lagos. - Jl, Shortridge (PubMed, 1997)
The 1996 publication of "The Guidelines for Comprehensive Sexuality Education in Nigeria," a result of collaboration between SIECUS and Nigerian organizations, is a major step toward incorporating sex education into current reproductive health and population initiatives. A National Task Force of 20 key Nigerian agencies and institutions working in the area of adolescent health, education, and development prepared the document with technical assistance from SIECUS. Days before the document's public release, a workshop was held for members of the mass media to increase their understanding of adolescent reproductive and sexual health in Nigeria. 70% of males and 50% of females attending secondary school are sexually active before the age of 20 years; by the time they leave school, one out of every five Nigerian girls has terminated an unwanted pregnancy. The Guidelines seek to help Nigerian youth to acquire knowledge and develop responsible behavior to reduce high rates of unwanted pregnancy, complications from unsafe abortion, sexually transmitted diseases, and acquired immunodeficiency syndrome.
openalex: W2253353570 mag: 2253353570
Keywords: openalex:import

The Multiple Hats of Identity: Addressing the Various Components of African American Identity in Student Development. - Johnson, Susan D. (The College Student Affairs Journal, 1997)
openalex: W58158952 mag: 58158952
Keywords: openalex:import

Factors Related To the Academic Achievement of African American Students In Two Northeastern Louisiana School Districts - Jones, Donna S. Washington (1997)
openalex: W1534719020 mag: 1534719020
Keywords: openalex:import

Aspiration and Preparation of African and Caucasian American High School Students Interested in Health Careers for the Years 1975, 1985 and 1995 - Jones, J. Raymond; Rzonca, Chet (Journal of Health Occupations Education, 1997)
openalex: W2913301768 mag: 2913301768
Keywords: openalex:import

An evaluation of the criteria and procedures used for selection of occupational therapy students at South African universities. - Joubert, Robin (1997)
The existing selection criteria and procedures applied at universities training occupational therapists in South Africa are not meeting the country's need for selecting students who adequately fulfill the demographic mix which represents the South African population. The aims of this research were: to investigate the existing criteria and procedures used for the selection of occupational therapy students; to establish recommendations with regard to how these criteria and procedures can be adapted to allow for more appropriate and equitable selection of students, and to obtain opinions from qualified therapists about those characteristics deemed most important for them to possess in the current South African Health System. A combination of quantitative and qualitative methodology was adopted. A survey was undertaken to obtain basic information and statistics about the numbers of applicants selected, and the existing selection criteria and procedures currently used to select occupational therapy students in South African universities. A series of two focus groups for each of the eight existing universities were carried out i.e. one incorporating the views of lecturers and clinicians and the other the views of students. The purpose of these groups was to obtain existing and emerging views of qualified therapists and students on current selection processes, what could be recommended to make selection fairer for disadvantaged applicants and what specific characteristics of qualified therapists would be most desirable in the current health system. The results indicate that the proportion of African students admitted into occupational therapy degrees is still far below numbers of other race groups, particularly white South Africans. That existing selection criteria and procedures are still dominated by eurocentric influence, particularly in the historically white universities, although there are definite attempts on the part of all occupational therapy training centres to overcome this, and that there are serious problems related to recruitment of African applicants which are partly the cause of the low numbers of African applicants. Characteristics deemed most desirable in qualified occupational therapists included many, most significant were: flexibility, particularly a special ability to be able to adjust to all types of people and cultures which included good communication and interpersonal skills; the ability to be assertive where appropriate; a life-Iong-Ieamer attitude including a visionary mentality/attitude; creativity and inriovative thinking; perseverance, determination and good management skills.
openalex: W1567020568 mag: 1567020568
Keywords: openalex:import

Theoretical underpinnings of a Student Mentoring Programme at an historically Black university in South Africa - Kagee, Ashraf; Naidoo, Tony; Mahatey, Nazeem (International Journal for the Advancement of Counselling, 1997)
openalex: W2070956523 mag: 2070956523
Keywords: openalex:import

Occurrence of stains on teeth amongst school children in Nairobi, Kenya. - Kaimenyi, J T (1997)
openalex: W2567056448 mag: 2567056448
Keywords: openalex:import

Towards an appropriate civic education in Kenya: an exploratory attempt; presented to the Institute for Education in democracy (IED). - Kamau, Mubuu (1997)
openalex: W2268536236 mag: 2268536236
Keywords: openalex:import

Acquisition of the English Article System by Francophone Students: The Case of Burkina Faso - Kambou, Moses Kwadwo (1997)
openalex: W2339183272 mag: 2339183272
Keywords: openalex:import

Language frontiers, language standardization, and mother tongue education: the Zaire-Zambia Border area with reference to the Bemba cluster - Kamwangamalu, Nkonko M. (South African Journal of African Languages, 1997)
It is often claimed that Africa has a myriad of mutually unintelligible languages, each of which is associated with presumably a distinct ethnic group or culture. Though no expert would question the claim that Africa is a multilingual continent, the question arises of the reality of the frontiers that have been drawn among some of her languages. This paper aims to address this question in the light of the language situation across the Zaire-Zambia border area, with a focus on the Bemba cluster (Lamba, Lima, Lala, Swaka, and Bemba). It is shown that though officially these are treated as separate languages they are, in reality, varieties of the same ‘mother’ language, Bemba. Phonological, lexical and syntactic evidence is presented which attests that the languages within this cluster are mutually intelligible. The implications of this intelligibility for language standardization and mother-tongue education are considered. It is concluded that ‘if the success of African education and development depends on the usage of African languages, then there is an urgent need for an update of the ethnolinguistic map of Africa, which would reflect more accurately the distribution of language clusters on the continent…’ (Prah 1995); and for a rethink of language planning in Africa, with a focus on mother-tongue education as the key to mass education and development on the continent.
openalex: W292689350 mag: 292689350
Keywords: openalex:import

Language frontiers, language standardization, and mother tongue education: the Zaire-Zambia Border area with reference to the Bemba cluster - Kamwangamalu, Nkonko M. (South African Journal of African Languages, 1997)
It is often claimed that Africa has a myriad of mutually unintelligible languages, each of which is associated with presumably a distinct ethnic group or culture. Though no expert would question the claim that Africa is a multilingual continent, the question arises of the reality of the frontiers that have been drawn among some of her languages. This paper aims to address this question in the light of the language situation across the Zaire-Zambia border area, with a focus on the Bemba cluster (Lamba, Lima, Lala, Swaka, and Bemba). It is shown that though officially these are treated as separate languages they are, in reality, varieties of the same ‘mother’ language, Bemba. Phonological, lexical and syntactic evidence is presented which attests that the languages within this cluster are mutually intelligible. The implications of this intelligibility for language standardization and mother-tongue education are considered. It is concluded that ‘if the success of African education and development depends on the usage of African languages, then there is an urgent need for an update of the ethnolinguistic map of Africa, which would reflect more accurately the distribution of language clusters on the continent…’ (Prah 1995); and for a rethink of language planning in Africa, with a focus on mother-tongue education as the key to mass education and development on the continent.
openalex: W292689350 mag: 292689350
Keywords: openalex:import

Multilingualism and Education Policy in Post-Apartheid South Africa - Kamwangamalu, Nkonko M. (Language Problems and Language Planning, 1997)
MU CIKOSO Miakulu ne Politike wa Tulasa kunyima kwa apateide mu Afrike wa Kwinshi Afrike wa Kwinshi pakadipikulaye ku bupika bwa apateide mu 1994, lukonko lunene luvwa pa moyo wa bamfumu ba ditunga luvwa lwa ne ncini civwabo ne bwa kwenza ne miakulu ya batoke bavwa bakwata ditunga ku bupika, Angele ne Afrikanse. Mu dibeji edi ndi ngakula bwa politike udi bamfumu ba ditunga benza bwa kwandamuna lukonko elu, ne nangananga politike wa kulongesha bana mu miakulu ya bankambwa. Ne ndeja ne bwa politike eu kupatula bipeta bimpe, bidi bikengela ne bamfumu ba ditunga bakudimuna cimfwani cibi civwa batoke bapeshe miakulu ya bankambwa mu matuku a bupika bwa apateide. Cianana baledi kabakwitaba bwa ne bana babo balongeshibwa mu miakulu eyi to. Ne ndeja mushindu udi bamfumu ba ditunga mwa kukudimuna cimfwani cibi cia miakulu eyi kabiyi bikengela kupepeja Angele ani Afrikanse. RESUMO Multlingvismo kaj eduka politiko en postapartisma Sudafriko Kiam Sudafriko liberigis sin el rasapartismo en aprilo 1994, unu el la tuj frontendaj problemoj estis decidi la sorton de la du lingvoj, angla kaj afrikansa, kiujn ĝi heredis el antaŭaj registaroj -la koloniaj kaj la apartismaj. La nuna referaĵo rekte esploras la respondon de Sudafriko al tiu ĉi problemo, nome la lastatempe akceptitan politikon de dek unu oficialaj lingvoj. Ĝi aparte fokusigas je la nuna debato pri edukado en la gepatra lingvo kontraŭ edukado en fremda lingvo, la angla aŭ la afrikansa. La aŭtoro argumentas ke, por ke la nova eduka politiko atingu sian celon, nome la apogon de edukado en la gepatra lingvo, necesos forigi la hontosignojn ligitajn al edukado en la gepatra lingvo dum la epoko de apartismo. La aŭtoro donas sugestojn pri kiel atingi tion sen subfosi la rolon kaj gravecon de la angla kaj la afrikansa en la klopodoj de la lando konstrui novaj kaj li egalecan nacion.
openalex: W1994032189 mag: 1994032189
Keywords: openalex:import

Teaching for excellence in the mathematics classroom: views from Namibian teachers - Kasanda, Choshi D. (Zimbabwe Journal of Educational Research, 1997)
openalex: W2259150541 mag: 2259150541
Keywords: openalex:import

Obstacles to high level agricultural manpower training in Ethiopia: evaluation of the post-graduate programme in agriculture - Kassa, Belay (1997)
openalex: W2286922672 mag: 2286922672
Keywords: openalex:import

Lifestyle, education, and prevalence of hypertension in populations of African origin - Kaufman, Jay S.; Tracy, Julie A.; Durazo‐Arvizu, Ramón; Cooper, Richard S. (Annals of epidemiology, 1997)
Lifestyle Incongruity has been shown to be associated with elevated blood pressure in various developing societies. We sought to test this model in an international collaborative study of hypertension in populations of African origin. Data were available for 4770 men and women, aged 25-74, from Africa, the Caribbean, and the United States. The main effects of lifestyle score (LSS) and education on hypertension prevalence were explored, as well as interactions predicted by the Lifestyle Incongruity model. Significant interactions were observed, but only the U.S. men conformed to the pattern predicted. For this group, adjusted ORs for LSS were 4.45 among low-education and 0.71 among high-education subgroups (risk OR = 0.16, 0.03-0.84 95% CI). The Lifestyle Incongruity model therefore received limited support. The model was designed to describe processes in societies experiencing modernization and opportunities for lifestyle differentiation, conditions that may not have been met in some sites.
openalex: W2032696879 mag: 2032696879
Keywords: openalex:import

Poverty, desertification and the impact of drought in Ethiopia - Kefialew, A (Desertification control bulletin, 1997)
openalex: W2258963730 mag: 2258963730
Keywords: openalex:import

An ethnographic description of the verbal and nonverbal communication of teachers and African American and white male students during the implementation of teacher expectations and student achievement (TESA) in three first grade reading classes - Kerman, Margie Hicks (1997)
openalex: W2253997384 mag: 2253997384
Keywords: openalex:import

Physical punishment of elementary school children in urban and rural communities in Ethiopia. - Ketsela, Tigest; Kebede, Derege (PubMed, 1997)
Severe corporeal punishment is known to hamper the physical, emotional and psychosocial development of children. This cross-sectional study was, thus, undertaken to make a quantified preliminary investigation on the occurrence of the problem. Six hundred and forty nine elementary schools' students were interviewed in selected urban and rural schools in Ethiopia. Eighty percent and 76% of the urban and rural children, respectively, admitted being subjected to physical punishment. Almost 21% of the urban and 64% of the rural children had skin bruises or body swelling as a result of the punishment. Only six children (three in each group) visited health facilities for the injury. Among urban students the proportion of those who had physical punishment increased with increasing paternal education and also with increasing maternal education. Among the rural students, on the other hand, physical punishment decreased with increasing age and grade. The public needs to be aware of the rights of children and every possibility should be worked out to secure their utmost emotional and physical development.
openalex: W1599970669 mag: 1599970669
Keywords: openalex:import

[Training in the use of animal traction for sustentable development: A world vision project in Tetre province, Mozambique 1994] - Keyserlingk, Alix von (1997)
openalex: W2767895475 mag: 2767895475
Keywords: openalex:import

What school, what university for tomorrow's Africa? - Khati, T.G. (1997)
openalex: W2231820815 mag: 2231820815
Keywords: openalex:import

An Analysis of the Content and Questions of the Physics Textbooks of the Basic Education Level (Ages 13-15) in Libya. - Khoja, Suleiman; Ventura, Frank (Mediterranean Journal of Educational Studies, 1997)
openalex: W305777771 mag: 305777771
Keywords: openalex:import

Gender, Education and Occupational Prestige in Kenya - Kibera, Lucy W. (1997)
openalex: W2565690602 mag: 2565690602
Keywords: openalex:import

The Influence of Ecology and Ethnicity on Educational Aspirations of Secondary School Students in Kenya - Kibera, Lucy W. (1997)
openalex: W2738986909 mag: 2738986909
Keywords: openalex:import

An Outcome Study of Graduates From the School of Social Work, Harare, Zimbabwe, 1988-1992 - Kiire, Ruth; Marlow, Christine; Kaseke, Edwin (Journal of Social Development in Africa, 1997)
openalex: W184069331 mag: 184069331
Keywords: openalex:import

Liberisation Policies and University Education in Uganda: An Assessment of the Cost-Sharing Policy - Kiiza, Julius (1997)
openalex: W102718341 mag: 102718341
Keywords: openalex:import

Factors influencing women enrolment in distance education: a case study of the Open University of Tanzania - Kilato, Niwael Simon (1997)
openalex: W3159050043 mag: 3159050043
Keywords: openalex:import

Applauding second-rate research: South African Association of Language Teachers Conference, Rand Afrikaans University, July 1996 - Kilfoil, Wendy R. (Scrutiny2, 1997)
"Applauding second-rate research: South African Association of Language Teachers Conference, Rand Afrikaans University, July 1996." , 2(1), pp. 62–63
openalex: W2090119909 mag: 2090119909
Keywords: openalex:import

Effects of physical education programme on the health of diploma teacher trainees in Kenya - Kinoti, J. W.; Njororai, W. W. S.; Kiganjo, G. M.; Asembo, J. M. (1997)
openalex: W2274919017 mag: 2274919017
Keywords: openalex:import

Effects of physical education programme on the health of diploma teacher trainees in Kenya - Kinoti, J. W.; Njororai, W. W. S.; Kiganjo, G. M.; Asembo, J. M. (1997)
openalex: W2274919017 mag: 2274919017
Keywords: openalex:import

Global Warming and Climate Impacts in Southern Africa: How Might Things Change? - Kinuthia, J. H. (Journal of African Studies, 1997)
openalex: W2283466705 mag: 2283466705
Keywords: openalex:import

The teaching of African languages to European students: the role of linguistic pragmatics illustrated by Swahili - Klein-Arendt, Reinhard (Journal of Humanities, 1997)
openalex: W2256722421 mag: 2256722421
Keywords: openalex:import

An investigation into the leadership roles of heads of department in science and mathematics in Botswana senior secondary schools - Kouwenhoven, Wim (Mosenodi, 1997)
openalex: W2259333290 mag: 2259333290
Keywords: openalex:import

School for all: a challenge to special needs education in Uganda: a brief country report - Kristensen, Kirsten (1997)
openalex: W2273393975 mag: 2273393975
Keywords: openalex:import

Intellectual Disability In Rural Black Children In The Bushbuckridge District Of South Africa - Kromberg, J. G. R.; Christianson, Arnold L.; Manga, Prashiela; Zwane, Mandisa; Rosen, Eric; Venter, André; Homer, Stephanie (Southern African journal of child and adolescent mental health, 1997)
Abstract The aim of this project was to investigate the prevalence and aetiology of intellectual disability in rural black children in the Bushbuckridge district. Children (aged 2–9 years) were screened by local trained field-workers who interviewed the caregivers with a simple questionnaire. Children who screened positive were examined by a paediatrician. Altogether 4581 children were screened, 541 had a paediatric assessment, and 152 (3,3%) were found to have an intellectual disability (IQ ≤ 80). The mild to severe disability ratio was 4:1, and 52% of affected children with an IQ ≤ 70 had associated disorders. The aetiology of the disability was congenital in 25% of cases, acquired in 11% and undetermined in 64%. The affected male to female ratio was 3:2. These findings have implications for the provision of appropriate special education, as well as health preventive services.
openalex: W2013752046 mag: 2013752046
Keywords: openalex:import

Strengthening technical and vocational teacher education and improving instruction effectiveness in Papua New Guinea (PNG) - Kuhena, Jerry (1997)
This paper seeks to draw together the development in six areas of design and delivery of technical and vocational education and training (TVET) in Papua New Guinea (PNG). The areas are: (1) the upgrading of skills and quality of teaching practice in PNG technical and business colleges; (2) the development of quality teaching aids and resources; (3) upgrading and enhancing skills, knowledge and practice in technical education quality management; (4) the development of national industry training standards; (5) technology transfer of best practice in industry training; and (6) intellectual capital transfer of competency based industry training and accreditation. The author argues that by developing a framework incorporating all the strands, it should be possible to meet wide-ranging TVET strategic goals.
openalex: W3185440120 mag: 3185440120
Keywords: openalex:import

Making Traditional Courses More Inclusive: Confessions of an African American Female Professor Who Attempted to Crash All the Barriers at Once - Kupenda, Angela Mae (1997)
openalex: W282829920 mag: 282829920
Keywords: openalex:import

The meaning of Beijing for higher education in Uganda - Kwesiga, Joy (Uganda Journal, 1997)
openalex: W1526163428 mag: 1526163428
Keywords: openalex:import

Motivation and Learning Preferences of High School Students Learning English as a Foreign Language in Morocco. - Kyriacou, Chris; Benmansour, Naima (Mediterranean Journal of Educational Studies, 1997)
openalex: W166131860 mag: 166131860
Keywords: openalex:import

Relationships between cognitive styles and written composition of African American ninth grade students in a metropolitan school district in Western Michigan - Large, Catherine W. (1997)
openalex: W1773993839 mag: 1773993839
Keywords: openalex:import

Non-traditional military training for Canadian peacekeepers : a study prepared for the Commission of Inquiry into the Deployment of Canadian Forces to Somalia - Larose-Edwards, Paul; Dangerfield, Jack; Weekes, Randy (1997)
openalex: W655309017 mag: 655309017
Keywords: openalex:import

Participatory learning materials for health promotion in Ghana–a case study - Laverack, Glenn; Sakyi, Barbara; Hubley, John (Health Promotion International, 1997)
This paper reports on operational research carried out by the Kumasi Health Education Project in Ghana to study the utilisation of participatory/empowerment learning methods for health promotion. The Project used community-based workshops to develop an extensive range of participatory materials on child health and followed these up with in-service training of 367 teachers and 157 public health workers (nurses and environmental health officers). A simple random sample of about half (262) of the participants was taken 6 months later and these personnel were asked to complete a self-reporting questionnaire to evaluate the format, content and usefulness of the materials. Results were compared with focus-group discussions with mothers attending well baby clinics, at home, in market-places and with pupils at school. The field agents reported a high degree of satisfaction with the training and claimed to be utilising the methods. However, this contrasted with the interviews with target groups who reported a low level of exposure to the materials. Those who had been exposed to materials reported a high level of satisfaction and recall of messages. Further focus-group discussions were carried out with field agents and their managers, and four sets of reasons for low utilisation emerged: the quality of participatory learning materials; personal attributes of the users and the impact of training; situational factors including the location and timing of educational sessions; and the support from peers/supervisors. The experiences in Kumasi are critically assessed and indicate that uptake of participatory/empowerment methods for health promotion depends on the quality of the materials and the selection, training and support provided to field staff.
openalex: W1978074947 mag: 1978074947
Keywords: openalex:import

Bridging Home and School Literacies: Models for Culturally Responsive Teaching, A Case for African American English: Research on Teaching the Communicative and Visual Arts - Lee, Carol D (1997)
openalex: W2737317964 mag: 2737317964
Keywords: openalex:import

School learning in Nigeria: roles, problems and prospects - Leleji, E.U. (Savanna: A Journal of the Environmental and Social Sciences, 1997)
openalex: W2277460613 mag: 2277460613
Keywords: openalex:import

Physical education and school sport within the post-apartheid educational dispensation of South Africa - Lion-Cachet, Susan (1997)
openalex: W256194358 mag: 256194358
Keywords: openalex:import

Sailing against the Wind. African Americans and Women in U.S. Education. SUNY Series, Frontiers in Education. - Lomotey, Kofi (1997)
openalex: W103376977 mag: 103376977
Keywords: openalex:import

Volcanology of the carbonatitic Gross Brukkaros volcanic field (Namibia) - Lorenz, Volker; Kurszlaukis, S.; Stachel, Thomas; Stanistreet, Ian G. (Geologiya I Geofizika, 1997)
openalex: W2937866973 mag: 2937866973
Keywords: openalex:import

Management Education: Needs of Business Practice A South African Perspective - Louw, Me L.; Bosch, J. K.; Plessis, A. P du; Louw, Lynette (Jurnal pengurusan, 1997)
One of the most distressing problems confronting South Africa is a structural shortage of core managerial competencies on the one hand, and an increasing oversupply of unskilled and semi-ckilled human resources on the other hand. It is often asserted that needs/requirements of business practice are totally at variance with the nature and content of Business Management syllabi. This assertion leads to the question of which subject disciplines, skills and characteristics graduates should possess to meet the requirements of business practice. The prime focus of this paper, which is a follow-up of pilot study, is on the findings of a national empirical survey (493 respondents) aimed at determining the knowledge and skills required by Business Management graduates in South Africa. The most outstanding findings were the importance of a wide variety of subject disciplines; the necessity of a broad skill-based education; and the need for a co-operative education system. ABSTRAK Salah satu masalah yang kritikal yang dihadapi Afrika Selatan ialah kekurangan kemahiran pengurusan dan pertambahan bekalan tenaga kerja yang kurang mahir dan separuh mahir. Keperluan amalan perniagaan kadang-kadang bertentangan secara total dengan kandungan silibus pengurusan perniagaan. Penekanan ini membawa kepada persoalan berhubung dengan disiplin subjek, kemahiran dun ciri-ciri para graduan yang manakah yang perlu ada bagi memenuhi keperluan amalan perniagaan. Fokus utama kertas ini adalah terhadap hasil kajian survei (493 respondens) yang bertujuan untuk menentukan pengetahuan dun kemahiran yang diperlukan oleh para graduan pengurusan perniagaan di Afrika Selatan. Antara penemuan utama kajian ini ialah pentingnya disiplin subjek yang luas dan pelbagai, keperluan pendidikan yang berasaskan kemahiran yang luas dan keperluan sistem pendidikan kooperatif.
openalex: W2170542877 mag: 2170542877
Keywords: openalex:import

Agrohydrological sensitivity analyses with regard to projected climate change in Southern Africa. - Lowe, Kerry Lynne. (1997)
openalex: W219602258 mag: 219602258
Keywords: openalex:import

Self-restraining and Condom Use Behaviours: The HIV/AIDS Prevention Challenges in Tanzanian Schools - Lugoe, Wycliffe L.; Biswalo, Paul M. (International journal of adolescence and youth, 1997)
ABSTRACT Of the 528 nonvirgin students, 61.5% had sexual partners at the time of the study. However, only 21.5% of the nonvirgins reported use of condoms at their most recent sexual experience. Those who perceived themselves vulnerable to HIV/AIDS and the females were unlikely to have restrained from sexual relationship. Brief periods of dating before intercourse and early sexual debut were not associated with increased condom use. Overall, involvement in sexual behaviour was linked to misconceptions about chances of being HIV infected, less value on one's religion, inadequate knowledge of a sexual partner and being a female student. Measures that prevent students from the consequences of being sexually active are advocated.
openalex: W2007710681 mag: 2007710681
Keywords: openalex:import

The distribution and education of pupils with albinism in Zimbabwe - Lund, Patricia (Transactions of the Zimbabwe Scientific Association, 1997)
openalex: W136120704 mag: 136120704
Keywords: openalex:import

Study to assess new and renewable sources of energy (NRSE) training in technical schools in Botswana: Final Report - Lungu, Edward M.; Jain, Pushpendra K. (1997)
openalex: W2936756403 mag: 2936756403
Keywords: openalex:import

Quality Assurance and Relevance of Engineering Education in Africa - Luti, F.M; Massaquoi, J.G.M. (1997)
openalex: W2233490827 mag: 2233490827
Keywords: openalex:import

AIDS education for youth through active learning: A school-based approach from Malawi - MacLachlan, Malcolm; Chimombo, Moira; Mpemba, Naomi (International Journal of Educational Development, 1997)
Health education programmes need to address local understandings of HIV/AIDS within the broader context of sexual behaviour. We report on a locally derived and community orientated questionnaire survey of HIV/AIDS and sexually related behaviour among 756 pupils from two government secondary schools in Malawi. On average, pupils gave the correct answers to more than 70% of the items on the survey. Seventy-two pupils from one of the schools subsequently participated in playing an educational board game about AIDS, once a week, over four weeks. The percentage of correct responses given while playing the board game significantly increased each time the board game was played, and a one-month follow-up questionnaire showed that a significant improvement had been maintained in comparison with the initial questionnaire survey. Pupils who attended the school where the board game was trialed, but who did not participate in the board game, scored slightly, but significantly, higher than pupils from the other ‘no-board game’ control school. This result was tentatively interpreted as a ‘trickle down’ effect. The benefits of introducing active learning methods into schools, of focusing on local understandings of health problems, and of establishing an accurate knowledge base for health promotion are discussed.
openalex: W2092203540 mag: 2092203540
Keywords: openalex:import

Childhood Incestuous Abuse Among High School Students in South Africa: Prevalence and Risk Factors - Madu, Teresa-Anne B.; Sylvester, N; Peltzer; Mashego, Karl (Journal of Psychology in Africa, 1997)
The authors investigated the prevalence and risk factors of childhood incestuous abuse in the Northern Province (South Africa). High School students in Standard 9 and 10 in representative High Schools in the province filled in a retrospective self-rating questionnaire in a classroom setting. Result shows that the overall prevalence is 15.2%. The risk factors are 'dwelling in a village', 'parents are unemployed or labourers', 'highest education of the father is below standard 6', 'natural biological mother was not living with participant until he/she was at least 16 years old', 'participant was leaving in a Group Home before he/she was 16 years old', 'participant did not feel loved or cared for by the parents/step/foster parents before he/she was 8 years old'. We recommend the above risk factors for' proper consideration while planning preventive strategies and campaign against childhood incestuous abuse, and therapy for victims in the province.
openalex: W2259376066 mag: 2259376066
Keywords: openalex:import

Competing gender ideologies: a conceptual framework for the analysis of education amongst Batswana of Botswana, c.1840-c.1994 - Mafela, Lily (Pula: Botswana Journal of African Studies, 1997)
In both precolonial and Westerm forms of schooling, education was a crucial medium of construction and articulation of ideas concerning the role and behaviour of women. Precolonial education reproduced and maintained sharp differentiation in the division of labour. Socialisation and women's own internalisation of their role and position in society, upheld dominant male ideology and subordination of women. Under colonialism, missionary and colonial education renegotiated but did not fundamentally change the role and position of women. However, it inadvertently also provided women with ways to move out of the household sphere into the wider labour market, albeit as unequal participants. Missionary education strictly separated the sexes and rested on the continued association of women with Victorian notions of 'domesticity'. The concept of ideology is used in this paper to tease out and highlight the dynamics which have influenced and directed education among Batswana. Introduction precolonial and missionary concepts of gender were at times congruent and at times conflicting in their perception of men and women's changing roles in society. Although the Tswana precolonial notions of were also based on a strict division of labour, in the homestead-based economy of communal precolonial Tswana society, women's work was not confined to a private and domestic sphere of the home. It included public duties outside the home such as agricultural production and the gathering of wild fruit and vegetables. This widened the scope of women's activities and increased their socio-economic worth in precolonial communities. The specific Victorian ideology had distinct educational objectives for Tswana men and women. Western schools taught different subjects to boys and girls and prepared them for distinct socio-economic roles. The narrowly perceived Victorian notion of domesticity which was engendered in this process, affected Batswana women's lives in important ways. To some extent, the Tswana socio-cultural structures overlapped with Victorian perceptions of women's work, mainly in the sense that women were in each of these societies, associated with maternal and homemaking roles. However, the residual effects of these structures mediated missionary and colonial education and sanctioned Batswana womenis schooling, ensuring that they did not get fully domesticated. Moreover, there were distinct differences as well. For example, Batswana women, like other African women, were not confined to the narrow sphere of the home, as they performed other duties outside the home, such as cultivation of masimo (lands), collection of wild foods and building materials such as bojang (grass). Just as Batswana had selectively appropriated Christianising and civilising symbols, so with education too, they exercised this selectivity .. During the colonial era, missionaries continued to be responsIble for the education of Batswana alongside merafe schools, which were sponsored and run by merafe themselves However, with the granting of minimal funding to the financially beleaguered mission societies, the colo~ial government ,increasin~ly gaine~ co~trol over curriculum policy, more significantly III the late 1920 sand 30 s. The rejectIOn of the
openalex: W1552020857 mag: 1552020857
Keywords: openalex:import

Characteristics of the heads of high schools in Swaziland and of the schools they manage - Magagula, Cisco M. (1997)
openalex: W2247068854 mag: 2247068854
Keywords: openalex:import

Interorganizational linkages and their effectiveness in the operation of provincial high schools in Papua New Guinea - Maha, Api Cazaly (1997)
openalex: W2896243919 mag: 2896243919
Keywords: openalex:import

The relationship between family background factors and scholastic achievement of children from single and two-parent families in the Mankweng Education Circuit of South Africa - Malehase, M. C. (1997)
openalex: W2979562719 mag: 2979562719
Keywords: openalex:import

Mortality and Morbidity Patterns Associated with the October 12, 1992 Egypt Earthquake - Malilay, Josephine; Elias, Ibrahim Fayez; Olson, David R.; Sinks, Thomas; Noji, Eric K. (Natural Disaster Reduction, 1997)
openalex: W3023641774 mag: 3023641774
Keywords: openalex:import

Contraception and Fertility in Zimbabwe: Family Planning Services and Education Make a Difference - Maluccio, John A.; Thomas, Duncan (1997)
Controlling for access to services, education is a powerful predictor of both fertility and contraceptive use, particularly among younger women, who have benefited from the large increase in education opportunities since independence.
openalex: W2980752006 mag: 2980752006
Keywords: openalex:import

The Role of the Christian Church in Curriculum Development in Kenya: A Case Study of Cisret and Create Inservice Teacher Education Programs - Malusu, Joseph (1997)
A thesis Submitted in Fulfillment of the Requirements for the Degree of Doctor of Philosophy in Education Kenyatta University, 1997. LB 1731.M35
openalex: W80925715 mag: 80925715
Keywords: openalex:import

Labour Supply, Returns to Education, and the Effect of Firm Size on Wages: the Case of Kenya - Manda, Damiano Kulundu (1997)
openalex: W1574493689 mag: 1574493689
Keywords: openalex:import

A Preliminary Survey of Environmental Awareness in Some Secondary School Pupils in Zimbabwe - Manjengwa, Jeanette (1997)
For sustainable development to be effective there must be appropriate environmental education strategies which provide people with the necessary knowledge and attitudes and skills. This paper is based on exploratory research to establish the level of environmental knowledge, attitudes towards environmental issues, environmental activities and problem-solving skills of secondary school pupils in determining appropriate strategies for sustainable development. The methods used to obtain information include a questionnaire, a review of secondary sources including policy documents and the various syllabuses which contain aspects of environmental education, and interviews with officials at the Ministry of Environment and Tourism, the Ministry of Education and the Ministry of Higher Education. The questionnaire was administered to 555 Form 1 and Form 4 secondary school pupils at 8 secondary schools, 4 rural schools in Chirumanzu District, Midlands Province, and 4 urban schools in Harare. The questionnaire was designed to ascertain the knowledge, attitudes, activities and problem solving skills of pupils as regards a wide range of environmental issues in Zimbabwe. The research attempted to identify differences, if any, between Form 1 pupils and Form 4 pupils, and between those living in a rural environment and those living in an urban environment. The results revealed that although there was a relatively high level of environmental knowledge amongst the pupils, understanding and analysis of this knowledge was considerably lower, as were skills of solving environmental problems. Environmental activities such as tree planting were quite widespread. Form 4s scored much higher than Form Is, and generally, rural pupils did better than urban pupils. The interviews confirmed that there is no official policy on environmental education in Zimbabwe. The research concludes with a series of recommendations to enhance the status of environmental education, especially in secondary schools, in Zimbabwe, and to ensure that future generations possess the necessary knowledge, attitudes and skills to enable them to participate effectively in the sustainable development of Zimbabwe's natural resources.
openalex: W2261993862 mag: 2261993862
Keywords: openalex:import

Namibian music and dance as ngoma in arts education. - Mans, Minette (1997)
openalex: W2298225493 mag: 2298225493
Keywords: openalex:import

Environmental Education and Nigerian Students' Knowledge, Attitudes and Practices (KAP): Implications for Curriculum Development. - Mansaray, Ayo; Ajiboye, Josiah O. (International Journal of Environmental Education and Information, 1997)
openalex: W71924213 mag: 71924213
Keywords: openalex:import

Multicultural Guidance and Counselling in Post-Apartheid South African Education - Maree, Jacobus G.; Sedibe, E. M. (Education and society (Melbourne), 1997)
openalex: W2326272744 mag: 2326272744
Keywords: openalex:import

Long live the fresh air! Long live! Teaching and truth-telling about the environment in South Africa, 1986-96 - Martín, Julia (Scrutiny2, 1997)
openalex: W1982393453 mag: 1982393453
Keywords: openalex:import

Women and Education in South Africa: Factors Influencing Women's Educational Progress and Their Entry into Traditionally Male-Dominated Fields - Martineau, Rowena (Journal of Negro Education, 1997)
Creating a system that provides quality education and training for all -young and old, regardless of race, class, or gender-is probably greatest developmental challenge facing South African government today. Women (and girls), particularly those of African origin, have been largely excluded from analyses of South African education. This article seeks to address this gap in literature by examining South Africa's educational progress generally and that of its women specifically, especially African women, along with a discussion of factors affecting education of women in South Africa and possibilities for future redress. INTRODUCTION Many in international community and in South Africa itself are still amazed by that country's transition from an apartheid regime to a multiparty, democratic state. Local and international leaders agree, however, that battle has only just begun. South African leaders currently face challenge of transforming their society into one in which all segments of population have truly equal access to resources and can fully participate in democratic process. Education is one of critical areas in need of change. Under apartheid regime, basic elementary and secondary education was not widely available to all. Indeed, with 19 redundant administrative structures, separate-but-unequal education was norm. As Republic of South Africa Department of Education (1995) notes in its first White Paper on Education and Training, post-democratic election period marks the first time in South Africa's history that government has mandate to plan development of education and training system for benefit of country as a whole and all its people (p. 2). Thus, it is not surprising that task of developing equitable educational policies is currently of primary significance. As South Africa's educators and educational policymakers wrestle with vestiges of a bureaucratically unwieldy and racially biased educational system, they must also strive to create a system that provides quality education and training for all South Africans-young and old, regardless of race, class, or gender. Indeed, redress of educational inequities is probably greatest developmental challenge facing South African government today. Gessler Nkondo, vice chancellor of historically Black University of Venda, has argued that process of empowerment for nation's African students should occur as a result of changing content of curricula, rather than on symbolic changes of structures. As he notes, [Only] having a few Africans in positions of power without changing rules of game would only guarantee frustration (quoted in Khosa, 1996, p. 5). A similar argument must be made for introduction of curricula that are gendersensitive, particularly in sciences, where presence of women' is minimal. In addition to inequities created by apartheid, gender-based discrimination has confronted Black women. This represents a trend that bears careful watching, given that it could easily lead to a system of gendered apartheid. To counter this trend, present article considers three broad areas of research on education for African women in South Africa: (a) primary and secondary education; (b) higher education; and (c) relationship between gender, education, and occupational opportunities. The available literature on first dimension is rather limited. Until recently, researchers practically excluded consideration of Black South Africans' early educational experiences, much less that of Black girls. The literature on higher education is more abundant, although likewise constrained by its focus on race and its near-exclusion of gender. In this area, several scholars have provided excellent critiques of inequities between South Africa's historically Black and historically White universities, but few have explored double jeopardy Black women have experienced in South African institutions of higher education. …
openalex: W2040965953 mag: 2040965953
Keywords: openalex:import

Socio-Economic Backgrounds and Beliefs of University Student in Ghana - Martinez, C. (1997)
Chapter 1: Introduction Chapter 2: Methodology of Research Chapter 3: Literature Review Chapter 4: Data Gathered from Interviews... Chapter 5: Discussion of Findings Recommendation and Conclusion
openalex: W2118172969 mag: 2118172969
Keywords: openalex:import

The impact of immigration on the anxiety, self-esteem and attitudes towards school and friends of South African immigrant children : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Mason, Lesleyanne (1997)
openalex: W41464449 mag: 41464449
Keywords: openalex:import

Participatory learning and action to reduce women's workloads in east Africa - Masoy, Aloysia; Pridmore, Pat (International Journal of Educational Development, 1997)
This paper examines the multiple roles which women perform in their daily lives and considers how their heavy workloads impact on their own health and that of their children. It draws on the findings of a study carried out in Kenya and Tanzania to identify attitudinal and structural barriers to the reduction of women's workloads. It briefly contrasts this with the situation of women in the U.K. The study also demonstrates that an approach known as participatory learning and action (PLA) can be effective not only in raising awareness of women's workloads but also in influencing positive change in attitudes and behaviours, so that men and boys take on a greater share of the household tasks.
openalex: W2015669631 mag: 2015669631
Keywords: openalex:import

Attrition of Low-Income, First Generation African-American Students at a Predominantly White, Urban University. - Masursky, Danielle (1997)
This paper describes a study in progress that is designed to examine the pressures that low-income, first generation African-American college students experience to leave college and the factors that help them stay in college, especially as the elements are related to Vincent Tinto's concept of social integration. It is planned to examine the experiences of 12 to 30 African-American students who originally enrolled at Temple University in Philadelphia, half of whom returned to school after their freshman year and half of whom did not return to Temple or any other educational institution. In-depth, focused interviews will be conducted with each participant. _The coding scheme is.expected to reflect the major concerns of the study–what background characteristics or activities have influenced students to attend, remain in, or leave college; what obligations outside the university environment are impacting students' college experience; and what elements of the college environment have positively or negatively influenced student persistence or attrition. (Contains 28 references.) (MDM) Reproductions supplied by EDRS are the best that can be made from the original document. Attrition of low-income, first generation African-American students at a predominantly white, urban university by Danielle Masursky PERMISSION TO REPRODUCE AND DISSEMINATE THIS MATERIAL HAS BEEN GRANTED BY
openalex: W191430798 mag: 191430798
Keywords: openalex:import

Critical issues in post primary education in Tanzania - Materu, Peter; Omari, I.M. (Papers in Education and Development, 1997)
openalex: W2287792842 mag: 2287792842
Keywords: openalex:import

Nutritional Status of school children and some associated factors in Rupahgwaha irrigated scheme (Chiredzi Zimbabwe) - Matsvimbo, N (1997)
openalex: W2275144120 mag: 2275144120
Keywords: openalex:import

The review and evaluation of maritime training and education systems in the light of new international convention in the United Republic of Tanzania - Mayagilo, Thomas Justine (1997)
openalex: W2979945692 mag: 2979945692
Keywords: openalex:import

The World Bank, the language question and the future of African education - Mazrui, Alamin (Race & Class, 1997)
L'enseignement en Afrique est traverse par une contestation portant sur l'anglais d'une part et les langues indigenes d'autre part. Les langues africaines ont ete marginalisees par la pression colonialiste creant ainsi une repartition inegale du pouvoir entre les personnes selon les langues apprises. Seuls quelques pays (Somalie, Soudan, Ethyopie, Tanzanie) ont reussi a etendre l'enseignement des langues indigenes au-dela de l'enseignement primaire. L'A. presente l'ampleur de la contestation et la place de la Banque Mondiale dans les debats
openalex: W2093751529 mag: 2093751529
Keywords: openalex:import

The Star-Spangled Dialectic: African Universities and the American Model of Higher Education - Mazrui, Alí A. (Journal of African Studies, 1997)
openalex: W2264452910 mag: 2264452910
Keywords: openalex:import

Evaluation Report of All African Council of Churches Communication Training Centre - Mbindyo, JM; Okigbo, C. (1997)
openalex: W2232183473 mag: 2232183473
Keywords: openalex:import

The musical legacy of Dorothy Love Coates : African American female gospel singer with implications for education and theater education - McAllister, Anita Bernadette (1997)
openalex: W635575208 mag: 635575208
Keywords: openalex:import

Newspapers in education programmes and South African youth: a survey of the relationship between South African school-goers and newspapers in Esikhawini, Kwazulu-Natal - McComb, Roslin Vanessa (1997)
openalex: W2791325849 mag: 2791325849
Keywords: openalex:import

Black Students, Black Colleges: An African American College Choice Model. - McDonough, Patricia M.; Antonio, Anthony Lising; Trent, James W. (Journal for a Just and Caring Education, 1997)
openalex: W39975040 mag: 39975040
Keywords: openalex:import

Bilingual Education in South Africa: English and Afrikaans. - McEachern, William Ross (Reading Improvement, 1997)
openalex: W31757516 mag: 31757516
Keywords: openalex:import

Education in Guinea-Bissau: Report on the Secondary and Tertiary Sectors in 1995 - McGuire, Harriet C. (1997)
openalex: W2268534701 mag: 2268534701
Keywords: openalex:import

African-American identity, the quality of school life and academic achievement - McIntire, Michael James (1997)
openalex: W2760756740 mag: 2760756740
Keywords: openalex:import

The Clash of Cultures: Learning Through English in Papua New Guinea - McLaughlin, Denis (Language, Culture and Curriculum, 1997)
When expatriate academics teach Papua New Guineans, there is often a cultural dynamic at play that is inconsistent with that operating in ‘Western’ universities. Insights into some of these issues, particularly language, may assist expatriates to restructure accepted assumptions about teaching and learning in English to more appropriately meet the needs of students from a different culture. This paper argues that language problems occur because students are educated in a language in which their teachers themselves lack facility. Moreover, in the Papua New Guinea context the learning problems with English are associated with a lack of equivalence between the concepts in the academic discourse and the students’ existing conceptual framework. Learning problems in English are more about concept acquisition than translation.
openalex: W2066928323 mag: 2066928323
Keywords: openalex:import

Disconnecting education: language as a determinant of the quality of education in Tanzania: a critical rejoinder - Mekacha, Rugatiri D.K. (Journal of Linguistics and Language in Education, 1997)
openalex: W2256027581 mag: 2256027581
Keywords: openalex:import

Correlates of effectiveness for white psychotherapists working with African American clients : multicultural competence, clinical experience, racial consciousness, multicultural training, and social experience - Menapace, Bruce (1997)
openalex: W397863756 mag: 397863756
Keywords: openalex:import

Attention Deficit/Hyperactivity Disorder Among North Sotho Speaking Primary School Children in South Africa: Prevalence and Sex Ratios - Meyer, Anneke (Journal of Psychology in Africa, 1997)
This study presents a first attempt to conduct an epidemiological survey of Attention Deficit Disorder (ADHD) among primary school children in the Northern Province of South Africa. The main purpose of the study is to establish the prevalence rate of this disorder in samples of primary school children. More than two thousand North Sotho speaking children from six primary schools participated in the survey. Teacher rating scales based on DSM-IV were used. The results obtained are consistent in many aspects with those from previously published research. The usual differences of age and sex were found. Overall, these findings suggest that the prevalence of ADHD and instrument used for its assessment 'are not affected by cultural variables.
openalex: W941544106 mag: 941544106
Keywords: openalex:import

Boundaries and quality : towards a national qualification framework for education, training and development practitioners in South Africa - Millar, Clive (1997)
openalex: W2612384859 mag: 2612384859
Keywords: openalex:import

Pollution and degradation of African aquatic environments and consequences for inland fisheries and aquaculture: the case of the Republic of Zaire - Mino-Kahozi, K.; Mbantshi, M. (1997)
openalex: W1905527064 mag: 1905527064
Keywords: openalex:import

The role of philosophy of education in teacher education in South Africa - Mkabela, Nokulunga Queeneth (1997)
Submitted to the Faculty of Education in fulfillment or partial fulfillment of the requirement for the degree of Doctor of Education In the Department of Philosophy of Education at the University of Zululand, 1997.
openalex: W1524028478 mag: 1524028478
Keywords: openalex:import

Drought tolerance in African common bean genotypes - Mkandawire, A.B.C.; Benati, S.; Pankomera, D.; Lupwayi, Newton Z. (African Crop Science Conference Proceedings, 1997)
openalex: W12329306 mag: 12329306
Keywords: openalex:import

Increasing access and equity in higher education-the role of open universities and distance education: the experience of the open university of Tanzania - Mmari, Geoffrey (1997)
Distance education can be defined as the means of bringing learning to students in their homes or localities which can overcome problems of geography and time. In this chapter the author examines other important aspects of distance education which include flexibility in terms of mimimum and maximum period of study before a qualification can be obtained as well as modularization of courses. Distance education institutions of higher learning fall into three main categories. Category one covers those devoted 100% to teaching by this method. These are called single mode institutions which cover open universities. Category two covers those using both approaches i.e. conventional and distance. These are called dual mode institutions. Category three covers those which allow students to do some of their courses by distance and others by conventional methods. These could be called the mixed mode. The title of this paper therefore is devoted to higher education by distance methods in institutions that are primarily single mode. Discussion which follows will indicate, however, that all three modes can be considered as part of the strategy of making higher education available to students by the distance approach.
openalex: W2262980083 mag: 2262980083
Keywords: openalex:import

Source and evolution history of some Mesozoic alkaline volcanics in the Eastern Desert of Egypt: inference from petrology and geochemistry - Moghazi, A.M.; Hassanen, M. A.; Mohamed, F.H. (Journal of African earth sciences (1994), 1997)
Geological and geochemical data on three occurrences of intraplate Mesozoic volcanics in the Eastern Desert of Egypt are presented. The rock types range from alkali olivine basalts to trachytes and mostly occur in the form of dykes and plugs. The basalts exhibit a phenocryst assemblage of olivine + clinopyroxene + plagioclase + titanomagnetite. Their normalised trace element patterns and elemental ratios (e.g. Th/Nb and Rb/Sr) are very similar to those of ocean-island basalts. Such trace element characteristics suggest that the asthenosphere is the main source of these rocks and their compositional variation can be attributed to limited crystal fractionation. The high LILE/HFSE ratios observed in these basalts are attributed to relatively low degrees of partial melting of their asthenospheric source. Based on their chemical composition, the basalts and trachytes are two distinct groups. However, the mineralogical composition and geochemical modelling suggest that the less evolved trachytic magma represents the product of 60–70% fractional crystallisation of an alkali olivine basaltic parent by the separation of olivine, clinopyroxene, plagioclase and FeTi-oxides. The generated trachytic melt evolved by fractional removal of clinopyroxene, plagioclase, K-feldspar and magnetite to produce the silicic members of the trachytic rocks. Des données géologiques et géochimiques de trois occurrences de roches volcaniques intraplaques mésozoiques en provenance du Désert Oriental de l'Egypte sont présentées. Les types de roche variant de basaltes alcalins à olivine à` des trachytes et, le plus souvent, se présentent sous forme de dykes et de pointements. Les phénocristaux des basaltes sont l'olivine, le clinopyroxène, le plagioclase et la titanomagnétite. Les allures des éléments en trace normalisés ainsi qua les rapports de certains éléments (p.ex. Th/Nb et Rb/Sr) de ces roches sont très similaires à celles des basaltes d'îles océaniques. De telles signatures géochimiques suggèrent que l'asthénosphère est la source principale de ces roches. La variation de composition peut être attribuée à une cristallisation fractionnée limitée. Les rapports LILE/HFSE élevés observés dans ces basaltes sont attribués à des taux relativement bas de fusion partielle de la source asthénosphérique. Du point de vue composition chimique, les basaltes et les trachytes montrent deux groupes différents. Toutefois, la composition minéralogique et la modélisation géochimique suggèrent qua le magma trachytique moins évolué correspond aux produits de cristallisation fractionnée à 60–70% d'un magma parental basaltique alcalin à olivine par séparation d'olivine, de clinopyroxène, de plagioclase et d'oxydes FeTi. Le liquide trachytique ainsi généré a évolué par separation fractionnée des cristaux de clinopyroxène, plagioclase, feldspath-K et magnétite pour donner les membees saturés des roches trachytiques.
openalex: W2042712847 mag: 2042712847
Keywords: openalex:import

Primary education officers and instructional leadership in Botswana - Moletsane, Nelson T.; Hopkin, A.G. (Mosenodi, 1997)
openalex: W197774678 mag: 197774678
Keywords: openalex:import

[Preliminary survey of a school health program implementation in Guinea]. - Montresor, Antonio; Urbani, CarloE; Camara, B.; Ab, Bha; Albonico, Marco; Savioli, Lorenzo (PubMed, 1997)
The Sectorial Adjustment Education Program implemented in Guinea by the Ministry of Pre-University Education in 1995 includes health-related measures. An important part is the fight against parasitosis and in particular against intestinal helminth infection which has been shown to impair cognitive function in school children. In order to obtain data for this purpose, a survey was carried out in 7 subprefectures across the country. A total of 1,649 children were examined to determine the prevalence in each school of macroscopic hematuria-related schistosomiasis and of various intestinal helminthiasis in stools. In 1468 of these children blood tests were also made to measure hemoglobin levels and detect malarial hematozoons. Overall prevalence rates were 60.0% for soil-transmitted nematodes, 9.1% for urinary schistosomiasis, 57.6% for blood plasmodium, and 57.0% for anemia. Hemoglobin levels were lower in children presenting plasmodium, multiple parasitic infection, and high ankylostoma burdens. Prevalence rates varied widely between regions indicating differences in therapeutic measures. In two villages more than 200 children not attending school who had been informed by school children were treated. This word-of-mouth effect shows that school health programs are also useful to reach children outside the school health system.
openalex: W2474329316 mag: 2474329316
Keywords: openalex:import

The challenge of providing appropriate technology education in the new South Africa - Morshuizen, Kaye Ter (The Journal of Design and Technology Education, 1997)
As South Africa moves forward with its educational reforms , the Techno l ogy 2005 Project , based i n Natal province, i s focus i ng on developing technology education for all pupils . Teacher training is one of the prime objectives of the project and the project deve l opers are working hard to create training programmes. This article outlines the background to the implementation of technology in the South African National Curriculum and shows a case study which is one example of the project's work to date.
openalex: W1933091351 mag: 1933091351
Keywords: openalex:import

Eritrea Education Sector Support Programme: Annual Sector Review Agreement - Mortensen, Knud; Vagnby, Bo (1997)
openalex: W104462405 mag: 104462405
Keywords: openalex:import

THE EFFECTS OF ECONOMIC INCENTIVES IN CONTROLLING POLLUTION IN THE SOUTH AFRICAN LEATHER INDUSTRY - Mowat, Shaun Phillip; Antrobus, G.G.; Fraser, Gavin (Agrekon, 1997)
Pollution of the environment is becoming an increasingly serious problem. A large contributor to this is industry which generates effluent as a by-product of its production process. Two methods of controlling the pollution generated by industry are the so-called “command and control” techniques and economic incentives. In theory, economic incentives promise a more economically efficient and equitable means of pollution control. This paper sets out to ascertain whether this would hold in practice by applying environmental economic theory to the practical problem of controlling the effluent generated by one particular industry, viz the South African leather industry. DIE UITWERKING VAN EKONOMIESE INSENTIEWE OP DIE BEHEER VAN BESOEDELING IN DIE SUID-AFRIKAANSE LEERBEDRYF Omgewingsbesoedeling word 'n toenemend ernstige probleem. Een groot bydraer is nywerhede wat afvalwater as 'n neweproduk van die produksieproses genereer. Twee metodes waardeur die besoedeling deur nywerhede gegenereer kan word is die sogenaamde beveel en beheer tegnieke en ekonomiese insentiewe. In teorie beloof ekonomiese insentiewe om ekonomies meer doeltreffend en ewewigtige metodes van besoedelingsbeheer te wees. Hierdie referaat poog om te bepaal of dit in die praktyk waar sal wees deur omgewings-ekonomie teorie toe te pas op die praktiese probleem van van die afvalwater wat deur een besondere bedryf, nl. die Suid-Afrikaanse leerbeeryf gegenereer word.
openalex: W2159423874 mag: 2159423874
Keywords: openalex:import

Perceptions of the Zimbabwe merit pay system for school teachers: an exploratory study - Mpofu, Elias (Zimbabwe Journal of Educational Research, 1997)
openalex: W2112742392 mag: 2112742392
Keywords: openalex:import

Learning African Languages Utilizing Digital Technologies - Mugane, John M. (Africa Today, 1997)
openalex: W2304090042 mag: 2304090042
Keywords: openalex:import

Learning African Languages With Evolving Digital Technologies - Mugane, John M. (Africa Today, 1997)
New digital technologies offer exciting possibilities for innovation in African language instruction. Teaching pedagogies-methods and approaches-evolve rather slowly when compared with technology. Indeed, there is a widening gap between content and the tools used to acquire it. Separation of the substance of language from technology prevents both instructors and students from fully appreciating the possibilities technology presents and the values that can be derived from it. The instrumental approach to technology proposed here, however, allows students to use computers with the supportive assistance of instructors as facilitators. The elaboration of language content offers especially promising opportunities for collaboration among Africanists and the realization of collective ambitions. Collaboration could lead to the emergence of multiple language databases that would articulate how Africans view themselves, Africa, and the rest of the world. Proceeding from a strong belief that technology should be nonintrusively present in the classroom, the Stanford Swahili project1 was begun with funding from the Consortium of Language Teaching and Learning. The project's main purpose is to develop technologically innovative materials (including rich browsing opportunities) that would be consonant with learning theory, build on student initiative and creativity, and satisfy both pedagogical and exploratory needs.
openalex: W163092212 mag: 163092212
Keywords: openalex:import

New technologies and the future of communication education in Africa - Muhammad, Bala A (1997)
openalex: W3088918871 mag: 3088918871
Keywords: openalex:import

The Zambia National Correspondence College :an evaluation of its role in the provision of secondary and vocational education to school-leavers and adults. - Mulenga, Freda Mutale Mupepa. (1997)
openalex: W2305575571 mag: 2305575571
Keywords: openalex:import

Evolving policy in higher education in South Africa with particular reference to quality assurance - Muller, Anne C. (1997)
openalex: W2606245176 mag: 2606245176
Keywords: openalex:import

The law relating to water pollution control in Kenya - Mumma, Albert O (1997)
openalex: W670858 mag: 670858
Keywords: openalex:import

A study of theological education in Africa inland church-Kenya: - Mumo, Peter Mutuku (1997)
openalex: W849334524 mag: 849334524
Keywords: openalex:import

The Prevalence Of Proteinuria, Haematuria, Other Urinary Abnormalities And Hypertension In Secondary School Students In Nairobi, Kenya - Muraguri, P W; Kayima, J K; McLigeyo, Seth O. (1997)
openalex: W25444895 mag: 25444895
Keywords: openalex:import

Students’ Dropout in Continuing Education: A Namibian Case Study - Murangi, Vekaama Heroldt (1997)
This study was undertaken in Namibia, to determme causes for student dropouts m continuing education face-to-face centers. The utilized sample in the study consisted of one hundred and seventy learners (including both current & non-continuing learners), and sixty tutors. In this context, dropout refers to those students enrolling for a course (Grade 10, Standard 10) at face-to-face centers and discontinuing their studies before completing the entire course. It is required from all learners to attend classes regularly before they can sit for the final external examination taking place annually in October or November. Chapter 1 of the study gives a general overview of the dropout problem as it occurs in many nonformal educational settings, and specifically to the context in Namibia. In addition, the chapter includes the research questions which guided the study, and defines a few terms consistently used in the study. Chapter 2 of the study gives a synopsis of the historical background of programs aimed at improving or supplementing the educational qualifications of students during the period preand post-independence, 1990. In dealing with the historical background literature specifically on the activities of the Namibian Extension Unit, the Council of Churches in Namibia, and the former and current government education systems is reviewed. Furthermore, the study reviews literature on the theoretical models on student attrition developed by other researchers. Chapter 3 of the study outlines the research process, emphasizing the data gathering instruments used in the study. Interviews, observation, and questionnaires were used in collecting
openalex: W947442651 mag: 947442651
Keywords: openalex:import

Influence of communication program on weekly iron supplementation in Tanzanian adolescent school girls - Muro, Grace S. (1997)
openalex: W3200411765 mag: 3200411765
Keywords: openalex:import

Opportunity-to-Learn Issues Common to South Africa and the United States - Murray, Gloria J. (Journal of Negro Education, 1997)
Among the many educational dilemmas the United States and South Africa share in common, this article highlights two: disparities in school funding and school dropout. The twist, however, is that in South Africa, the majority population has borne the brunt of educational segregation, discrimination, economic exploitation, and deprivation based on racial/ethnic differences; while in the US., minority groups suffered these inequities. Nonetheless, the author maintains that the similar challenges each nation faces to improve education can be addressed by identifying the important educational lessons both can learn from each other. Comparisons of student achievement in the United States with that of students in other economically advanced nations raise legitimate concerns for educators and politicians. For example, as early as 1983, educational policymakers in the U.S. were jolted with the issuance of the A Nation at Risk report, which underscored the poor performance of U.S. schoolchildren compared to the performances of children from other economically advantaged nations (National Commission for Excellence in Education, 1983). However, such comparisons, before and since, must be evaluated in light of both the social histories and the recent demographic changes that shaped and are rapidly reshaping the nature of the U.S. student population, their families, and society at large. Among developed nations, South Africa and the U.S. share many characteristics in common. The election of African National Congress (ANC) leader Nelson Mandela as president of South Africa in 1994 exposed to the world apartheid's deliberate and systematic denial of education to the majority of the South African population. Forty years earlier, the U.S. Supreme Court decision in Brown v. Board of Education of Topeka, Kansas (1954) uncovered and legally ended the then-accepted practices of racial segregation and discrimination in that nation's schools. Presently, similar issues confront both countries, including the fragmentation of their educational systems, low student achievement, disproportionate levels of child poverty, and multiple and often conflicting demands on a strained economy. These challenges are associated with other social problems and demand immediate attention, yet they manifest differently due to the racial mix evident in the two nations' populations. In South Africa, it is the majority that has suffered discrimination due to that country's apartheid system of rigidly enforced racial separation. In the U.S., the minority has suffered at the hands of Jim Crow systematic segregation and second-class citizenship. As a result, many of the decisions and concerns about education in both nations historically been racially motivated. In both, these decisions and concerns favored White students over disadvantaged Black students and other students of color. Race and class touched and polarized almost every aspect of the human experience in the U.S. and South Africa. Over time, the separate but unequal educational experiences wrought by both nations' discriminatory policies created a significant gap between the races and people of various ethnic groups as well as between rich and poor. Several U.S. and South African studies found that student achievement, and consequently employment readiness, are correlated, to some degree, with the serious disparities in the funds available to different school systems (Hanushek, 1994; Kozol, 1991; Nkabinde, 1997). The gap between educational haves and have nots has jeopardized the academic achievement and the future of all children in these two countries. In both, there is an urgent need to reconcile school funding policies that privilege one group of students to a better educational experience because they are members of a certain racial/ ethnic group or class or live in one area of a country. This is especially important when those advantages accrue at the expense of students who belong to other groups or classes or who live in other regions. …
openalex: W2093255069 mag: 2093255069
Keywords: openalex:import

What can we learn from the epjdemic of schizophrenia in African-Caribbeans in the UK? - Murray, Robin M.; Hutchinson, Gerard; McKenzie, Kwame; Os, Jim van (Schizophrenia research (Print), 1997)
openalex: W1971597784 mag: 1971597784
Keywords: openalex:import

African American Women and Education: Marita Bonner's Response to the "Talented Tenth." - Musser, Judith (Studies in short fiction, 1997)
Alain Locke's call for New Negro and W. E. B. Du Bois's classification of the Talented Tenth created a myriad of creative interpretations during Harlem Renaissance, especially by women writers. Marita Bonner's work responds to need for an examination of lives of characters who must cope with economic hardships, discrimination, deterioration of family relationships, illnesses that are particular to urban life, new religious communities, and multi-ethnic neighborhoods within urban settings. Her themes are unique in comparison to stories written by other African American women., She is only Harlem Renaissance woman to write short stories set in Chicago. Although she follows African American women's writing tradition in portraying women as her main characters, these women are not independently strong, not individualized and not triumphant. She avoids any autobiographical elements from her distinctive childhood. She adheres to a social-realist mode of writing about multi-ethnic Chicago, an environment that directs not only her themes, but her craft as well. Her stories present a unique perspective on struggles of those twentieth-century African Americans who live outside Mecca of art in Harlem, who do not live in all-African American rural communities, who must face a completely different set of Jim Crow laws from those of post-Civil War South, and whose daily existence depends on economic prosperity of Midwestern industry. In particular, several of Bonner's short stories reflect often overpowering barriers that African American women faced when they attempted to follow Harlem Renaissance's call for self-improvement through education. Locating Bonner in history of African American writing is essential to understanding both her short fiction and sociological map of Renaissance era. She lived during Harlem Renaissance, published in two of leading African American journals (Opportunity and The Crisis), participated in writing groups such as Georgia Douglas Johnson's S Street Salon,(1) and lived in three urban setting's (Boston, Washington, DC and Chicago) that were centers for vigorous African American reform activities. She was a contemporary of such well-known women Renaissance writers as Zora Neale Hurston,(2) Jessie Fauset, Nella Larsen, Alice Dunbar-Nelson, Gwendolyn Bennet, Dorothy West, and Ann Petry. She was most prolific woman short story writer for Opportunity, publishing seven short stories whereas average for other women writers was one to two stories. Compared to male short story writers, Bonner's total publication number for Opportunity was exceeded by only two–Henry B. Jones and John Frederick Matheus, who each published nine stories. Until at least 1987, Bonner was unknown to contemporary readers. With publication of her works in Beacon Press Black Women Writer's series,(3) her short stories have begun to appear in anthologies.(4) Not surprisingly, scholarship on Bonner has been slight. Cheryl Wall's more recent book Women of Harlem Renaissance discusses Bonner's essay On Being Young–A Woman–and Colored. Joyce Flynn's brief introduction to Bonner's works provides only summaries of her short stories. More has been written on her three plays–The Pot Maker: A Play to Be Read (published in Opportunity 5 [Feb. 1927]), The Purple Flower (published in The Crisis 35 [Jan. 1928]), and Exit, an Illusion: A One-Act Play (published in The Crisis 36 [Oct. 1929]). Bonner's pre-publication life is important when one considers her presentation of education in lives of her characters.(5) She does not incorporate her own family into her stories,(6) and she does not draw on her own early personal experiences for plots, settings and themes. The violence and poverty of inner-city life found in her stories are not part of her early life experiences. In fact, her childhood and education could be considered privileged. …
openalex: W147203140 mag: 147203140
Keywords: openalex:import

An evaluation of theological education by extension seminar discussions in selected Christian denominations in Kenya - Musyoka, Benjamin Mwange (1997)
openalex: W784774743 mag: 784774743
Keywords: openalex:import

How Tanzania secondary school teachers react to students' interlanguage: focus on the treatment of errors in written work - Mwaseba, Jackson Jairos Mbwani (1997)
Available in print form, East Africana Collection, Dr. Wilbert Chagula Library, (THS EAF LB1631.T3M8)
openalex: W3201751459 mag: 3201751459
Keywords: openalex:import

Diversity in Education; Respect for Language Minorities – the case for Kenyan sign Language as a medium of Instruction in schools for deaf in Kenya - Mweri, George Jefwa (1997)
openalex: W2306729303 mag: 2306729303
Keywords: openalex:import

Vocational Education and the African American Experience: An Historical and Philosophical Perspective. - Nall, Hiram (The Journal of Intergroup Relations, 1997)
openalex: W294012434 mag: 294012434
Keywords: openalex:import

Measuring Access to Family Planning Education and Services for Young Adults in Dakar, Senegal - Naré, Christine; Katz, Karen; Tolley, Elizabeth E. (1997)
openalex: W1026833831 mag: 1026833831
Keywords: openalex:import

The attitude of traditional 'ulama' to Muslim female education in Nigeria - Nasiru, W.O.A. (1997)
openalex: W1585479143 mag: 1585479143
Keywords: openalex:import

Creative Instability: The Case of the South African Higher Education System - Ndebele, Njabulo S. (Journal of Negro Education, 1997)
South Africa's historically disadvantaged institutions of higher education (HDIs), which collectively admit the largest number of Black South Africans in higher education, were major sites of student anti-apartheid revolts. Their administrative and academic functions became unintended victims of this struggle. Sustained political activity by student-worker alliances on many campuses resulted in fragile and unstable administrative systems. As this lecture presentation excerpt posits, these unstable conditions are not likely to disappear soon. Thus, the major challenge facing South African HDIs in a new democracy is that of developing the capacity to effect major institutional reform while successfully managing instability. Professor Charles Dlamini, Vice Chancellor of the University of Zululand, recently shared some literary memories at a gathering of vice chancellors of South African historically disadvantaged institutions (HDIs) of higher learning who were grappling with issues of strategic planning on their respective campuses. In his inimitable way, he reminded those of us in attendance of the opening paragraph of Charles Dickens's (1859/1952) novel, A Tale of Two Cities, which never loses its rhetorical appeal: It was the best of times; it was the worst of times, it was the age of wisdom, it was the age of foolishness, it was the season of Light, it was the season of Darkness, it was the spring of hope, it was the winter of despair. We had everything before us, we had nothing before us. We were all going direct to Heaven, we were all going direct the other way. (p. 21) Having drawn by analogy a picture of a bygone era he suggests is closely characteristic of our own times, Professor Dlamini rounded out his analogy with a reference to a wellknown African American spiritual: Nobody knows the troubles I've seen.... / Sometimes I'm up/Sometimes I'm down.. . Thus he concluded his comments about the life of a vice chancellor in these best and worst of times in South Africa. have unwittingly introduced the concept of historically disadvantaged institutions. They are, however, the specific subject of this lecture, as believe that the discussion of them-and the image we may have of them within the South African higher education system-must now no longer be defined by the limitations of their political history. In this we are called upon to make a special effort mind and imagination. say this knowing fully that any discussion of the contemporary situation in South Africa should always be informed by a knowledge of our history. These institutions are currently building bridges over rivers that are a continuously raging torrent of water. Often the rivers break free of their banks, threatening to wash away everything on shore. Moments of calm are few and far between, yet the bridges have to be built. All of us have to reach the other side. Yet, there are other institutions within the South African higher education environment that built their bridges long ago. Do they still remember what it was like to build those bridges, or have they forgotten some vital matters about which they may unwittingly choose to be silent? The words of the poet T. S. Eliot are worth remembering in full in this regard. To quote Eliot: I do not know much about gods, But think that the river is a strong brown god Sullen, untamed and intractable. Patient to some degree, at first recognised as a frontier; Then only a problem confronting the builder of bridges. The problem once solved, the brown god is almost forgotten By the dwellers of cities-ever, however, implacable, Keeping his seasons and rages, destroyer, reminder Of what men choose to forget. (p. 205) Forgetfulness may be an unintended result of achievement. That happens when achievement signals the end of experience, when the collective identity of successful societies becomes locked into the sense of their own achievement and it becomes almost impossible for them to see new possibilities beyond. …
openalex: W1967399243 mag: 1967399243
Keywords: openalex:import

Dental health awareness and practice among secondary school children in Enugu, Nigeria - Ndokwelu, Etisiobi (DOAJ (DOAJ: Directory of Open Access Journals), 1997)
openalex: W4389598825
Keywords: openalex:import

The Changing Attitudes to Primary School Christian Religion in Kenya - Ndungu, Nahasho W (1997)
openalex: W2567537604 mag: 2567537604
Keywords: openalex:import

An examination of the experiences and coping strategies of African students at predominantly White institutions of higher education in the United States - Nebedum-Ezeh, Georgina Chizoba (1997)
openalex: W93079905 mag: 93079905
Keywords: openalex:import

Entrepreneurship Education as a Strategic Approach to Economic Growth in Kenya. - Nelson, Robert E.; Johnson, Scott D. (Journal of Industrial Teacher Education, 1997)
For the past 10 years, small enterprise development has been identified as a priority area in development policy in general, and in Africa in particular. There is now considerable experience among international donor agencies with interventions aimed at the development of the small enterprise sector. Increasingly, small enterprise development is regarded as crucial to the achievement of broader objectives such as poverty alleviation, economic development, and the emergence of more democratic and pluralistic societies. The trend in recent years has been to target a greater proportion of international aid resources to small enterprise development (Working Group on Business Development Services, 1997). International donor agencies such as the World Bank, United Nations Development Program, and the African Development Bank have identified the small enterprise sector as a key to development in African countries and have financed a number of projects to encourage the section to grow. In addition, Sweden (SIDA), Germany (GTZ), Great Britain (ODA), and the United States (USAID) are supporting small enterprise development in African countries through their international aid programs. For example, the ODA's financial support of small enterprise development has increased in Africa from approximately $ .5 million in 1992-93 to $16.2 million in 1996-97. Within the United Nations system, the International Labor Organization (ILO) and the United Nations Industrial Development
openalex: W88997178 mag: 88997178
Keywords: openalex:import

The African American Education Data Book. Volume I: Higher and Adult Education. - Nettles, Michael T.; Perna, Laura W. (1997)
openalex: W1509477849 mag: 1509477849
Keywords: openalex:import

The African American Education Data Book. Volume I: Higher and Adult Education. Executive Summary. - Nettles, Michael T.; Perna, Laura W. (1997)
openalex: W7595736 mag: 7595736
Keywords: openalex:import

The African American Education Data Book. Volume II: Preschool through High School Education. Executive Summary. - Nettles, Michael T.; Perna, Laura W. (1997)
openalex: W145497491 mag: 145497491
Keywords: openalex:import

The African American Education Data Book. Volume III: The Transition from School to College and School to Work. Executive Summary. - Nettles, Michael T.; Perna, Laura W. (1997)
openalex: W140590667 mag: 140590667
Keywords: openalex:import

The Failure of Language Policy in Tanzanian Schools. - Ngonyani, Deo (Social Education, 1997)
openalex: W3518822 mag: 3518822
Keywords: openalex:import

The effects of policy marginalization on the implementation of a curriculum innovation: A case study of the implementation of education with production in Zimbabwe - Nhundu, Tichatonga J. (Journal of Curriculum Studies, 1997)
This paper reports the findings of a case study of the implementation of the education with production ewp curriculum reform 13years after it was first introduced in eight pilot schools in Zimbabwe. The findings of the study show that education with production was introduced as top-down curriculum reform and that a nongovernmental organization, set up to experiment with the innovation and spread the idea to other schools using a stepwise approach, lacked decisional power over personnel matters. The study also found that erratic in-service training, periodic staff transfers, lack of equipment and incentives, and lack of autonomy and independent power for the implementing organization further inhibited effective implementation. In addition, the policy of education with production became marginalized at the national education planning level because of changing socio-political priorities combined with negative dispositions of education planners. Finally, ewp found itself in unfair competition with the traditional academic curriculum because the economic rewards, societal values and attitudes and the examination system did not promote the implementation of education with production. The paper concludes by making several suggestions on the implementation of education with production in Zimbabwe.
openalex: W2037740432 mag: 2037740432
Keywords: openalex:import

Early, late and non-participants in sexual intercourse: A profile of black South African first-year university students - Nicholas, Lionel; Tredoux, Colin (International Journal for the Advancement of Counselling, 1997)
openalex: W2085177299 mag: 2085177299
Keywords: openalex:import

Factors influencing parents' choice and purchase of clothing for pre-schoolers in Kenya: implication for exercise - Njororai, Fletcher Injede; Njororai, W. W. S. (1997)
openalex: W2285058613 mag: 2285058613
Keywords: openalex:import

Sport facilities and equipment in primary schools in Kenya - Njororai, W. W. S.; Gathua, S. M. (1997)
openalex: W2284709276 mag: 2284709276
Keywords: openalex:import

Physical education and sport in primary schools in Kenya: the case of central province - Njororai, W. W. S.; Gathua, S. M.; Owiye, R. (1997)
openalex: W2287627747 mag: 2287627747
Keywords: openalex:import

The development of a prototype induction model for the teaching profession in Botswana - Nleya, Setoki; Paul, Tanusree; Maseko (Mosenodi, 1997)
This paper presents both a generalised model of induction and a prototype induction model specifically designed for the teaching profession in Botswana. During the two year probationary period, which is required of every teacher at all levels in Botswana, no structured procedures are laid down regarding their induction. Research has documented that teachers face many problems during these early years of teaching and that it is during this period that the Newly Qualified Teachers (NQTs), need support and guidance so as to gain confidence in the decision making processes and general professional matters. The proposed induction model is therefore intended to provide the necessary guidelines regarding the induction of NQTs in Botswana. The induction model was developed largely from a literature search on the induction of NQTs. Some piloting of the induction model items has been conducted and a validation study (pre-testing) of the model is in progress.
openalex: W2728973645 mag: 2728973645
Keywords: openalex:import

Sexual discourse in the context of AIDS: dominant themes on adolescent sexuality among primary school pupils in Magu district, Tanzania - Nnko, Soori; Pool, Robert (Health transition review, 1997)
School pupils in Tanzania have been identified as a risk group for HIV/AIDS, so a large part of TANESA's anthropological research is aimed at charting and understanding forms of sexual risk behaviour among adolescents with a view to influencing change. This study presents the dominant themes of sexual discourse among adolescent primary school pupils in Magu district along the south-eastern shores of Lake Victoria in Tanzania. The themes are: love and sex; sexual desire; money and rewards; and deception. The fear of pregnancy also emerges as a dominant theme. Because of the nature and extent of their sexual relationships, school pupils will be increasingly exposed to the risk of HIV and STD infection. This is exacerbated by the lack of condom availability and the proscribed nature of sex (and therefore condom use) among primary school pupils. Methods: role play Because it is difficulty to study sexual behaviour directly, we decided to use discourse analysis. We started by recruiting two ex- primary school pupils who in collaboration with us, interviewed their fellow pupils. During the preparatory phase the two 'peer' researchers visited all 1 1 primary schools in Kisesa ward, Mwanza town. Pupils from six schools near the workshop venue were selected for the narrative research. During the Christmas break we
openalex: W1909763326 mag: 1909763326
Keywords: openalex:import

Drought tolerant barley genotypes for rainfed areas in Egypt - Noaman, M. M.; Asaad, F. A.; El-Sayed, Ahmed A.; El-Bawab, A.M.O. (Egyptian Journal of Agricultural Research, 1997)
openalex: W2479509269 mag: 2479509269
Keywords: openalex:import

Some Effects of Culture-Referenced Topics on the Writing Performance of African American Students. - Norment, Nathaniel (Journal of Basic Writing, 1997)
openalex: W15554835 mag: 15554835
Keywords: openalex:import

The African Experience with Higher Education - Nwauwa, Apollos O.; Ajayi, J. F. Ade; Goma, Lameck K. H.; Johnson, G. Ampah (Canadian Journal of African Studies, 1997)
openalex: W2796804162 mag: 2796804162
Keywords: openalex:import

A study of leadership qualities of principals of good secondary schools in Imo State, Nigeria - Nwogwugwu, Emmanuel Chinonye (1997)
openalex: W1606748628 mag: 1606748628
Keywords: openalex:import

Education of the girl child with visual impairment in Kenya and Malawi integrated programmes - Nyaga, G (1997)
openalex: W2105913744 mag: 2105913744
Keywords: openalex:import

Soil erosion and sedimentation as agents of water pollution in western Kenya - Nyangaga, J. (1997)
openalex: W2743171430 mag: 2743171430
Keywords: openalex:import

Gardens in the Gambia: A Study on Women Gardens and School Gardens - Nystrom, Johanna; Åsman, Karolina (1997)
openalex: W2291817931 mag: 2291817931
Keywords: openalex:import

Dispositions Toward (Collective) Struggle and Educational Resilience in the Inner City: A Case Analysis of Six African-American High School Students - O’Connor, Carla (American Educational Research Journal, 1997)
For more than 20 years, researchers have shown that the recognition of a limited opportunity structure on the part of marginal youth circumscribes their optimism toward the future and hence increases their likelihood of disengaging from school. This article, however, focuses on six, low-income, African-American adolescents who expected to realize their ambitions and were high achieving, all the while articulating an acute recognition of how race and class (and, in two cases, gender) operated to constrain the life chances of people like themselves. These students’ familiarity with struggle, including collective struggle, was the only biographical factor which distinguished them from the other respondents in the larger project of which they were a part. Thus, in contrast to the findings of some, their knowledge of struggle did not curtail their academic success but may have contributed to their sense of human agency and facilitated their academic motivation. Because this knowledge derived from their interaction with significant others, this article also maintains that the meanings that arise from immediate experiences and discourses are essential for understanding the diverse ways by which marginal people interpret and respond to their subjugation.
openalex: W2158822126 mag: 2158822126
Keywords: openalex:import

Dispositions toward (Collective) Struggle and Educational Resilience in the Inner City: A Case Analysis of Six African-American High School Students - O’Connor, Carla (American Educational Research Journal, 1997)
For more than 20 years, researchers have shown that the recognition of a limited opportunity structure on the part of marginal youth circumscribes their optimism toward the future and hence increases their likelihood of disengaging from school. This article, however, focuses on six, low-income, African-American adolescents who expected to realize their ambitions and were high achieving, all the while articulating an acute recognition of how race and class (and, in two cases, gender) operated to constrain the life chances of people like themselves. These students’ familiarity with struggle, including collective struggle, was the only biographical factor which distinguished them from the other respondents in the larger project of which they were a part. Thus, in contrast to the findings of some, their knowledge of struggle did not curtail their academic success but may have contributed to their sense of human agency and facilitated their academic motivation. Because this knowledge derived from their interaction with significant others, this article also maintains that the meanings that arise from immediate experiences and discourses are essential for understanding the diverse ways by which marginal people interpret and respond to their subjugation.
openalex: W4243412764
Keywords: openalex:import

Detached harmonies : a study in/on developing social processes of environmental education in eastern southern Africa - O’Donoghue, Rob (1997)
Long-term social processes are explored to examine the shaping of environmental education in eastern southern Africa. The study opens with early Nguni social figurations when 'to conserve was to hunt.' It then examines colonial conservation on the frontiers of imperial expansion and developing struggles for and against wildlife preservation. These processes shaped an inversion of earlier harmonies as declining wildlife was protected in island sanctuaries of natural wilderness and 'to conserve was not to hunt.' Inside protected areas, conservation management struggles shaped new harmonies of interdependence in nature, enabling better steering choices in developing conservation science institutions. Here more reality congruent knowledge also revealed escalating risk which was linked to a lack of awareness amongst communities of 'others' outside. Within continuing conservation struggles, education in, about and for the environment emerged as new institutional processes of social control. The study examines wilderness experience, interpretation, extension, conservancies and the development of an environmental education field centre, a teacher education programme and a school curriculum. Naming and clarifying the emergent education game for reshaping the awareness and behaviour of others is examined within a developing figuration of environmental education specialists. Particular attention is given to academic and statutory processes shaping environmental education as a field of objective principles and rational processes within modernist continuities and discontinuities into the 1990's. An environmental education field centre, an earth-love curriculum and research on reserve neighbour interaction are examined as political sociologies developing within a declining power gradient and wide ranging socio-political change. Into the present, a final window on a local case of water pollution examines shifting relational dynamics revealing how environment and development education models of process may have little resonance amidst long-term socio-historical struggles and shifting controls over surroundings, others and self. A concluding review suggests that grounded critical processes engaging somewhat blind control over surroundings may yet reshape self-control and social control amongst others. The trajectories of these clarifying struggles must remain open-ended as sedimented myth and memory is reshaped within ongoing processes of escalating risk and global intermeshing.
openalex: W2890686325 mag: 2890686325
Keywords: openalex:import

Book Review: Mill Hill Fathers in West Cameroon: Education, Health, and Development, 1884–1970 - O’Neil, Robert J. (International bulletin of missionary research, 1997)
openalex: W2735726386 mag: 2735726386
Keywords: openalex:import

Effect of Crude Oil Pollution on a Freshwater Stream in Nigeria - Obire, O.; Okudo, I V (Discovery and Innovation, 1997)
openalex: W1190062905 mag: 1190062905
Keywords: openalex:import

Bilingual Education in Africa: An Overview - Obondo, Margaret (1997)
openalex: W1517850306 mag: 1517850306
Keywords: openalex:import

Air and odour pollution in the city of Nairobi, Kenya - Obudho, A.R. (1997)
openalex: W30288908 mag: 30288908
Keywords: openalex:import

School Mathematics in Nigeria. - Ochepa, Isa A. (Mathematics in School, 1997)
openalex: W113925065 mag: 113925065
Keywords: openalex:import

Student struggles in tertiary education in South Africa during the 1980s. - Odhav, Kiran (1997)
openalex: W43377399 mag: 43377399
Keywords: openalex:import

Access, Quality And Efficiency In Education In Kenya - Odipo, G; Abagi, O (1997)
openalex: W2285185189 mag: 2285185189
Keywords: openalex:import

HIV/AIDS Awareness among secondary school youths in Enugu Nigeria - Ofoegbu, EN (DOAJ (DOAJ: Directory of Open Access Journals), 1997)
openalex: W1534415841 mag: 1534415841
Keywords: openalex:import

Post-Impact Syndromes and Drought Response Strategies in Sub-Saharan Africa - Ogallo, Laban (Journal of African Studies, 1997)
openalex: W2294767222 mag: 2294767222
Keywords: openalex:import

Climate Change: An Ethical Perspective in Potential Impacts of Climate Change in Kenya - Ogutu, Gilbert E. M. (1997)
openalex: W2234787056 mag: 2234787056
Keywords: openalex:import

Students' Union Courts as Arbitral Tribunals in Nigerian Law: The Case of the University of Nigeria - Okafor, Obiora Chinedu (1997)
In a recent ruling, a Nigerian High Court ordered that proceedings brought before the court, by a student who was aggrieved by his impeachment from the position of President of the Students' Union of the, University of Nigeria, be stayed pending the determination of the dispute by the Judicial Council of the Union. This article considers the legal basis for this ruling and argues that the court has in effect determined that the student courts that operate in a number of Nigerian higher-institutions enjoy the status of arbitral tribunals under Nigerian law. 'The article also argues that, if the first argument is correct, one consequence would be that legal practitioners may be able to contribute to the decongestion of the regular courts by a more frequent use of the power of the High Court to stay its proceedings and thus encourage the use of student courts to settle intra-union disputes.
openalex: W3124453062 mag: 3124453062
Keywords: openalex:import

Students' Union Courts as Arbitral Tribunals in Nigerian Law:The Case of the University of Nigeria - Okafor, Obiora Chinedu (Social Science Research Network, 1997)
In a recent ruling, a Nigerian High Court ordered that proceedings brought before the court, by a student who was aggrieved by his impeachment from the position of President of the Students' Union of the, University of Nigeria, be stayed pending the determination of the dispute by the Judicial Council of the Union. This article considers the legal basis for this ruling and argues that the court has in effect determined that the student courts that operate in a number of Nigerian higher-institutions enjoy the status of arbitral tribunals under Nigerian law. 'The article also argues that, if the first argument is correct, one consequence would be that legal practitioners may be able to contribute to the decongestion of the regular courts by a more frequent use of the power of the High Court to stay its proceedings and thus encourage the use of student courts to settle intra-union disputes.
openalex: W2259906408 mag: 2259906408
Keywords: openalex:import

The need for university education for African priests - Okolo, Chukwueloka (AFER, 1997)
openalex: W1568120533 mag: 1568120533
Keywords: openalex:import

Evaluation Of The Status Of Teaching And Use Of African Languages In Higher Eduction Accra - Okombo, Dancan Okoth (1997)
openalex: W2748349934 mag: 2748349934
Keywords: openalex:import

Trends in Women Education: An Analysis of Primary, Secondary, and University Enrollment in Nigeria (1984-93) - Okoye, Asun C.F.; Baklit, C.O. (1997)
openalex: W2221945388 mag: 2221945388
Keywords: openalex:import

Short note on the teaching of cultural resources management at the University of Nigeria, Nsukka - Okpoko, Pat Uche (West African journal of archaeology, 1997)
openalex: W972413092 mag: 972413092
Keywords: openalex:import

Reproductive Knowledge, Attitudes and Behaviour of Secondary School Students in Akure, Nigeria - Oladapo, Margaret Moyosola; Brieger, William R. (International quarterly of community health education (Print), 1997)
Adolescents are subject to many life changes as their secondary sexual characteristics emerge. Contrary to parents' and society's wishes, these young people are more sexually active then previous generations and thus at greater risk of unwanted pregnancies, sexually transmitted diseases, and related problems. Adolescents enrolled in school have the potential opportunity to learn ways to prevent these reproductive and sexual health problems, but there is concern whether schools are living up to this challenge. Therefore, this study was designed to learn whether adolescents in secondary school in the Ondo State capital of Akure have reproductive health education and are practicing healthy sexual behaviors. The study was based on a sample of six of the twenty-eight secondary schools in Akure that fell under the jurisdiction of the Ondo State Post-Primary Schools' Management Board. Focus was placed on pupils in the final years of both Junior Secondary School (JSS 3) and Senior Secondary School (SSS 3). Overall, 30 percent of the young people reported having sexual intercourse: 21 percent of females and 38 percent of males. Also 39 percent in SSS 3 reported having had sex compared to 21 percent in JSS 3. Forty percent of students in coeducational school compared to 19 percent in boy's school and 8 percent in girl's school had sex. Respondents averaged only 11 points on a 33-point scale of reproductive health knowledge. Students in the senior classes and those in single sex schools scored higher. The mass media was stated to be the major source of reproductive health knowledge; only one-third reported that they had actually talked with someone about their reproductive health concerns. Attitudes toward pre-marital sex were more favorable among male students, pupils in mixed sex schools and those whose parents had lower levels of education. These findings suggest not only that the schools must take a more active role in providing reproductive health education, but that this should be done in the junior secondary years before most pupils become sexually active.
openalex: W2135599415 mag: 2135599415
Keywords: openalex:import

Governance of tertiary institutions: the case of the Lesotho National Teacher Training College - Oliphant, John (1997)
openalex: W2276484402 mag: 2276484402
Keywords: openalex:import

School-leavers' guide to tertiary education in South Africa - Olivier, Steve; Olivier, Amanda (1997)
openalex: W2951326301 mag: 2951326301
Keywords: openalex:import

Rewards for teaching excellence: practice in South African medical schools - Olmesdahl, P J (Medical Education, 1997)
Excellence in teaching through recruitment of good teachers, rewarding good teaching and the creation of staff development programmes are priorities in the mission statement of most universities. Often, reality belies intention. At many universities serious attempts to ensure maximum teacher effectiveness, overt recognition of teaching excellence, and specific development funding are lacking. This study examines the extrinsic (i.e. financial) reward systems which operate at the eight medical schools attached to South African universities and reports on the current situation. Replies indicated that a reward system of some type operates within the university at seven South African universities which have faculties of medicine and embraces all faculties. One university rewards medical school teachers specifically but, at another, no reward system exists at all. The monetary value of rewards varies greatly. Significant criticism of all systems was the inability to meet their design aims. There was criticism of the criteria, such as they are and where they exist, used to identify teaching excellence and to reward recipients. All replies indicated support for an impartial and equitable system of reward for effectiveness and excellence in teaching.
openalex: W1971715089 mag: 1971715089
Keywords: openalex:import

IDENTITY OVERLAP AND SITUATIONAL DIFFERENTIAL AMONG NIGERIAN STUDENTS - Olobatuyi, Moses E. (Social Behavior and Personality, 1997)
This study examines the notion that Nigerian students will identify with their ethnic group and their nation at the same time because they are members of different ethnic groups and citizens of the same country. It also examines whether their perception of their identity will change from situation to situation. Data were collected from 306 Nigerian students in the Washington DC metropolitan area through a proportional stratified sampling procedure. The results confirm the hypothesis that the Nigerian students will identify with their ethnic groups and nation at the same time. It is also confirmed that how the Nigerian students will perceive themselves in different situations depends on the situation in which they find themselves. This negates the primordial approach which claims that an individual will identify him/herself in terms of his/her ethnic group because of a strong bond of ethnic attachment. Implications of these findings for future research are discussed.
openalex: W2019577057 mag: 2019577057
Keywords: openalex:import

The Teaching of Reference in Nigerian Library Schools: A Case Study - Olorunsola, Richard (Journal of Education for Library and Information Science, 1997)
openalex: W258362331 mag: 258362331
Keywords: openalex:import

Appraisal Report - Vocational Education and Training Sub-sector in Tanzania: Confidential Report - Olsen, Willy (1997)
openalex: W2808973374 mag: 2808973374
Keywords: openalex:import

Towards ecoscience: environmental and sociocultural perspectives in science - some insights from Uganda, and implications for higher education - Oluka, Silas (1997)
openalex: W295222977 mag: 295222977
Keywords: openalex:import

Stress reactions of university students to Nigeria s socio-economic changes in a ten-year period - Omoluabi, Peter F. (Journal of Psychology in Africa, 1997)
openalex: W2265523967 mag: 2265523967
Keywords: openalex:import

Food And Nutrition Assessment In Drought-prone Areas Of Kenya - Omwega, AM (1997)
openalex: W2255291310 mag: 2255291310
Keywords: openalex:import

Africa 2000: Kenya's intiative on water pollution and human health - Omwenga, John Maurice (1997)
openalex: W427770615 mag: 427770615
Keywords: openalex:import

TRANSPORTATION-RELATED AIR POLLUTION MANAGEMENT IN METROPOLITAN LAGOS, NIGERIA - Oni, S. I. (XIIIth World meeting of the International Road FederationInternational Road Federation, 1997)
The dangerous rising tide of air pollution and environmental cost is resulting largely from road transportation vehicle emissions. An estimated 80% of the commuter transportation in Lagos is presently being done by road, and by private transportation. The amount of carbon monoxide, lead and suspended particulates in Lagos' air exceed internationally accepted levels in most areas. This paper shows the relevance of air quality monitoring, determines the existing impact of gaseous pollutants on the human population and socioeconomics, and compares the pollution level extent with the metropolitan standards resulting from poor enforcement. Geographic Information Systems techniques are suggested for efficient monitoring and providing a control base and management. Strict obedience to, and compliance with, air pollution guidelines would also ensure the desired environmental sustainability.
openalex: W622666082 mag: 622666082
Keywords: openalex:import

The ‘whole language’ approach to literacy education in the third world: The Nigerian experience - Onukaogu, Chukwuemeka Eze (Language, Culture and Curriculum, 1997)
This paper contends that most people of the Third World need functional and development‐oriented literacy (FDD if they are to contribute meaningfully to illiteracy eradication and the attainment of sustainable national development in their respective countries. Arguing that the current literacy instruction approaches in use in most Third World countries can not sustain FDL, it suggests the adoption of the Whole Language (WL) approach as a complement to or substitute for existing approaches. It also contends that WL can catalyse the love for literature, book writing and production in order to sustain the interests of new literates, and can also provide effective monitoring and enhancement of learners’ interests. The paper notes however, that the current economic depression which has sustained military rule in most Third World countries is bound to inhibit WL and not allow it to blossom. Some strategies which literacy facilitators can adopt in order to enhance FDL pending the robust and vibrant development of WL are suggested.
openalex: W1971185027 mag: 1971185027
Keywords: openalex:import

The effects of climate changes on river baseflow and aquifer storage in Central Africa. - Orange, Didier; Wesselink, A. J.; Mahé, Gil; Feizoure, C.T. (1997)
openalex: W2249830472 mag: 2249830472
Keywords: openalex:import

Gender Differentiation and the Role of Culture in Tertiary Level Education: Implications for employment Opportunities and Environmental Utilization by Women in Kenya - Otunga, Ruth N. (Ufahamu, 1997)
openalex: W1604688973 mag: 1604688973
Keywords: openalex:import

School Participation by Gender: Implications for Occupational Activities in Kenya - Otunga, Ruth N. (Africa Development: a Quarterly Journal of CODESRIA, 1997)
openalex: W1503908048 mag: 1503908048
Keywords: openalex:import

Black Ivy: An African-American Perspective on Law School - Owsley, Brian (Social Science Research Network, 1997)
This 1997 article discusses the experiences of the author as an African-American student at Columbia Law The author discusses the differing treatment he received from faculty and students during his legal studies, going into detail regarding particular courses and experiences that highlight the discrimination present in law schools. He parallels his own memorialization with Scott Turow’s One L: The Turbulent True Story of a First Year at Harvard Law School.
openalex: W1937875889 mag: 1937875889
Keywords: openalex:import

Perceptions of African-American Students Who Dropped Out of Decatur School District 61 - Palmer, Priscilla Marjorie (1997)
openalex: W2592830788 mag: 2592830788
Keywords: openalex:import

Learning to Be Men at a Teachers' College in Zimbabwe - Pattman, Rob (1997)
openalex: W137056862 mag: 137056862
Keywords: openalex:import

The African Experience with Higher Education - Peil, Margaret (African affairs (London), 1997)
Journal Article The African Experience with Higher Education Get access The African Experience with Higher Education, by J. F. Ade Ajayi, Lameck J. H. Boma & G. Ampah Johnson. AAU in Association with James Currey Ltd. and Ohio University Press, 1996. xii+275 pp. £35.00 hardback; £14.95 paperbak. ISBN (James Currey) 0-85255-734-5; paper 9-98255-733-7. MARGARET PEIL MARGARET PEIL University of Birmingham Search for other works by this author on: Oxford Academic Google Scholar African Affairs, Volume 96, Issue 382, January 1997, Pages 123–124, https://doi.org/10.1093/oxfordjournals.afraf.a007800 Published: 01 January 1997
openalex: W2318042962 mag: 2318042962
Keywords: openalex:import

Inclusivity and diversity in early childhood services in South Africa - Penn, Helen (International Journal of Inclusive Education, 1997)
There are unresolved tensions between achieving inclusivity and maintaining diversity in early childhood services in South Africa. While there have been substantial and impressive attempts to develop a comprehensive early childhood development policy as part of the new education planning in South Africa, there is a concern that indigenous traditions may be overlooked or lost in the process. Early childhood services, both governmental and those supported by non‐governmental organizations, have relied heavily,’ if not exclusively, on concepts and curricula drawn from Anglo‐American traditions. In order to illustrate these points this paper draws on material collected as part of a recent review of early childhood services in South Africa carried out for the Save the Children Fund.
openalex: W2041660647 mag: 2041660647
Keywords: openalex:import

Clay mineral associations in sulphide-bearing volcanic rocks and sediments from the Lihir Area, Papua New Guinea - Percival, John A.; Hannington, Mark D.; Herzig, Peter; Jonasson, I R (1997)
openalex: W2731320329 mag: 2731320329
Keywords: openalex:import

Perspectives on special needs education in Nigeria, Kenya, and Zimbabwe - Peresuh, M.; Adenigba, S.A.; Ogonda, Godfrey (1997)
openalex: W2273455138 mag: 2273455138
Keywords: openalex:import

[Influence of fruit bearing on the potential productivity and quality of grapes cv Ribier, under South African training system [Gable]] - Pérez, Daniela R.; Alonso, Gonzalo L. (1997)
openalex: W2566566477 mag: 2566566477
Keywords: openalex:import

Police-schools liaison and community policing: Empowering the South African school child - Pillay, Kris (Acta Criminologica: Southern African Journal of Criminology, 1997)
June 16, 1976 was a watershed year in the struggle for liberation and democracy in the history of South Africa. The country was plunged into anarchy and chaos, because of the unilateral decision of the apartheid regime to impose the Afrikaans language as a compulsory medium of instruction on the majority African student population.
openalex: W2738460669 mag: 2738460669
Keywords: openalex:import

Does Education Increase Agricultural Productivity in Africa - Pinckney, Thomas C. (RePEc: Research Papers in Economics, 1997)
Past published studies establishing a significant, positive link between education and agricultural productivity have used Asian data almost exclusively. With one exception, these studies have not checked to see if the positive impact of education comes about only by screening for ability. Using household level data from coffee regions of Kenya and Tanzania, this study finds that households in which the agricultural decision-maker is numerate and literate produce 30 percent more agricultural output, holding other variables constant. This estimate of the impact of education is markedly higher than those made using years of schooling as an independent variable. Increasing cognitive skills beyond basic numeracy and literacy has no additional impact on production. Evidence from Kenya (but not from Tanzania) suggests that reasoning ability and the presence of at least one educated person in the household also increase productivity substantially.
openalex: W587113136 mag: 587113136
Keywords: openalex:import

Does Education Increase Agricultural Productivity in Africa - Pinckney, Thomas C. (1997)
Past published studies establishing a significant, positive link between education and agricultural productivity have used Asian data almost exclusively. With one exception, these studies have not checked to see if the positive impact of education comes about only by screening for ability. Using household level data from coffee regions of Kenya and Tanzania, this study finds that households in which the agricultural decision-maker is numerate and literate produce 30 percent more agricultural output, holding other variables constant. This estimate of the impact of education is markedly higher than those made using years of schooling as an independent variable. Increasing cognitive skills beyond basic numeracy and literacy has no additional impact on production. Evidence from Kenya (but not from Tanzania) suggests that reasoning ability and the presence of at least one educated person in the household also increase productivity substantially.
openalex: W3124628188 mag: 3124628188
Keywords: openalex:import

New Hopes, New Horizons: The Challenges of Diversity in Education. Proceedings of the Biennial International Conference of the International Association of Special Education (5th, Capetown, South Africa, August 3-8, 1997). - Prater, Greg; Minner, Sam; Islam, Mohammad Tanjimul; Hawthorne, Deborrah (1997)
openalex: W1608795950 mag: 1608795950
Keywords: openalex:import

Combating racism toward and among African American females in public education administration through the use of networking. - Pressey, Doretha (1997)
openalex: W11443577 mag: 11443577
Keywords: openalex:import

The Role and Place of Language in Education and Society: The Case of Kiswahili and English in Tanzania - Qorro, Martha (Papers in Education and Development, 1997)
openalex: W2277529713 mag: 2277529713
Keywords: openalex:import

Involving traditional healers in AIDS education and counselling in sub-Saharan Africa: a review. - R, King; Homsy, Jaco (PubMed, 1997)
Traditional healers are the preferred and most accessible care providers in Africa. The AIDS epidemic in sub-Saharan Africa has stimulated interest on the part of modern biomedical health practitioners in collaboration with these traditional healers. The literature includes numerous studies of healers' perceptions of HIV/AIDS and other sexually transmitted diseases. On the basis of study findings, healers have been trained as educators and counselors to disseminate HIV/AIDS information and prevention practices among their peers and communities. This article reviews the initial outcomes and challenges of such new initiatives in Zambia, Uganda, Botswana, Malawi, Mozambique, South Africa, and Central African Republic. None of the projects has completed a comprehensive evaluation of the different approaches used and their real impact on the population served. Overall, however, the case studies indicate that traditional healers are capable of performing at least as well as their biomedical counterparts as AIDS educators and counselors. Of concern is the failure of many projects to provide systematic follow-up to healers after their initial training. Such follow-up is essential to support healers in dealing with unfamiliar issues such as condom use and death and dying.
openalex: W1708325289 mag: 1708325289
Keywords: openalex:import

The right to education in South Africa and Belgium: a comparative perspective - Raemdonck, Koen; Verheyde, Mieke (1997)
openalex: W2734054217 mag: 2734054217
Keywords: openalex:import

The Effects of a Computer Algebra System on the Learning of, and Attitudes towards Mathematics amongst Engineering Students in Papua New Guinea. - Raj, Leonard; Malone, John (1997)
openalex: W2554744636 mag: 2554744636
Keywords: openalex:import

Contextualising evaluation : a case for transition in art and design education in a contemporary South Africa context - Rankin, Jeffrey Stuart (1997)
openalex: W880888918 mag: 880888918
Keywords: openalex:import

Characterization of drought stress in the major maize production zones of Kenya - Ransom, J.K.; Njoroge, Kiarie; Wafula, B.M. (1997)
openalex: W2564804318 mag: 2564804318
Keywords: openalex:import

Teaching African literature in the Department of English, University of Botswana - Rasebotsa, Nobantu L. (Women’s Studies Quarterly, 1997)
Instructional approaches to and studies in African literature in the department of English at the University of Botswana (UB) should be considered within the context of sociopolitical changes in Botswana. The University of Botswana's educational programs have a history that is rooted in the British colonial system, a history that begins with the establishment of Pius XII College in 1945 after a decision was taken in 1938 by the Synod of Catholic Bishops in South Africa to provide African Catholic students with post-matriculation education coupled with religious guidance (National University of Lesotho [NUL] Calendar, 40). During its time (1945-1964) Pius XII College adopted the British curricula of the University of South Africa (UNISA) with which it was affiliated. Consequently, the department of English taught British literature; that is, the English tradition and heritage, from Beowulf to T. S. Eliot. In 1964, however, Pius XII College was replaced by an independent, nondenominational University of Basutoland [Lesotho], Bechuanaland Protectorate [Botswana] , and Swaziland with its own Charter granted by Her Majesty Queen Elizabeth (NUL Calendar, 41). Since its break from UNISA, the new University of Botswana, Lesotho, and Swaziland, from which the present University of Botswana has evolved, has set up its own curriculum highlighting developments in African literature, African history, and African theology and philosophy. This shift from colonial cultural traditions to African culture reflected the political mood that in the 1960s, characterized the achievement of independence from Europe of nearly all the African colonies. It is indeed the colonial legacy, the link with the British educational system, that some African intellectuals and academics strongly reacted against in the prelude to African independence. In the words of Ngugi wa Thiong'o, the colonial language and literature were taking us further and further from ourselves to other selves, from our world to other worlds (146). E. K. Braithwaite, the Caribbean intellectual, expresses similar sentiments about Eurocentric influence on the
openalex: W15465488 mag: 15465488
Keywords: openalex:import

Race on the Superhighway: How E-Mail Affects African American Student Writers. - Redd, Teresa M.; Massey, Victoria W. (JAC: A Journal of Composition Theory, 1997)
During the course of the semester we have sent several e-mail messages to the Montana students. . . . Although the language used was slightly different than the language i use with friends or relatives, i think my e mail messages were very close to my everyday speaking. . . . Even though i had never met or spoke to my Montana partner before, i felt completely uninhibited. i have often been characterized as shy, but when e-mailing i didn't feel that way. . . . Since the Montana students had never really had any real relationships with blacks, e-mailing provided a means by which to ask questions that they might have felt uncomfortable talking about face to with black people. Shonda1
openalex: W1483426987 mag: 1483426987
Keywords: openalex:import

African nonformal theological education research project - Regier, F.; Regier, S. (Africa Journal of Evangelical Theology, 1997)
openalex: W336387250 mag: 336387250
Keywords: openalex:import

GPS Constraints on Fault Slip Rates in the Arabia-Africa-Eurasia Plate Collision Zone: Implications for Earthquake Recurrence Times - Reilinger, Robert; Barka, Aykut (1997)
openalex: W2494380028 mag: 2494380028
Keywords: openalex:import

Perceptions of African-american Males Regarding Factors Supporting Doctoral Completion in Colleges of Education - Respress, William (1997)
PERCEPTIONS OF AFRICAN-AMERICAN MALES REGARDING FACTORS SUPPORTING DOCTORAL COMPLETION IN COLLEGES OF EDUCATION by William Respress The primary purpose of the study was to examine what institutional factors most influenced the decision of African-American male doctoral scholars to persist unto graduation. The literature review showed mentoring, institutional climate, race relations, and social adjustment as key factors in persistence of minorities in graduate studies. An objective specific to the study was to explore the cumulative outcomes that mentoring, social adjustment, institutional climate, and race relations have upon persistence. The population included scholars at both Predominantly White Colleges (PWIs) and Historically Black Colleges and Universities (HBCUs) throughout the United States in Colleges of Education. One hundred sixty-four scholars responded representing a return rate of 96%. The African-American Male Doctoral Scholar Survey was employed to collect data. Analyses of the data included ANOVA, independent sample t-tests, analysis of frequencies, percentages of responses, and Tukey’s Post-hoc analysis. Responses to open-ended questions were analyzed and cited from comments written by scholars. There were six major findings. Factors affecting scholars’ decision to persist unto graduation at PWIs differed from those who attended HBCUs when considering mentoring, social adjustment, race relations, and institutional climate. No significant differences were discovered between age groups upon the decision of scholars to persist. Employment classification affected persistence of scholars at both types of institutions. Institutional geographical location affected the decision of scholars to persist. Scholars’ classification status did not affect persistence at either type of institution. The number of scholars within the department significantly influenced persistence unto graduation. Recommendations were made for replication of the study and refinement of the instrument. A 13-point institutional plan of action was developed toward improving the persistence rate of scholars. A 12-point plan was developed to assist scholars in achieving a successful doctoral experience.
openalex: W2332014238 mag: 2332014238
Keywords: openalex:import

The Teaching of Afrocentric Values by African American Parents. - Richards, Harriet (Western journal of black studies, 1997)
openalex: W254600270 mag: 254600270
Keywords: openalex:import

Secondary teacher education in Ethiopia: ancient traditions and modern tensions - Ridley, Barbara; Bridges, David (1997)
openalex: W2229405925 mag: 2229405925
Keywords: openalex:import

Final report: groundwater management in drought-prone areas of Africa - Robins, N.S.; Calow, Roger; MacDonald, Alan; Macdonald, David; Gibbs, B.R.; Orpen, W. R. G.; Mtembezeka, P.; Andrews, Anita; Appiah, Samson Obed; Banda, Kawawa (1997)
openalex: W354600970 mag: 354600970
Keywords: openalex:import

African American College Students' Attitudes Toward Identity, Culture, and Curriculum - Rochon, Ronald (1997)
openalex: W2594627403 mag: 2594627403
Keywords: openalex:import

Perceptions of nontraditional African American baccalaureate nursing students of their persistence in or departure from an urban nursing program - Rodebaugh, Linda S. (1997)
openalex: W2582832631 mag: 2582832631
Keywords: openalex:import

Innovative Second Language Education in Southern Africa - Rodseth, J. Victor (1997)
openalex: W2161608152 mag: 2161608152
Keywords: openalex:import

Magnitude of schistosoma mansoni and intestinal helminthic infections among school children in Wondo-Genet Zuria, southern Ethiopia - Roma, Belay; Worku, Solomon (Ethiopian Journal of Health Development, 1997)
Abstract: A cross-sectional study was conducted in April, 1994 to determine the prevalence of S. mansoni and other intestinal helminths among students of Wondo-Genet Zuria Elementary and Junior Secondary Schools, Sidama Zone, Southern Ethiopia. A questionnaire was used to list each of the study subjects and Formol-ether concentration method was used to analyze stool samples collected. From a total of 520 students examined 465 (89.4%) were positive for different intestinal helminthiasis while 157 (30.2%) were positive for S. mansoni. The infection rate among the study group is discussed and possible recommendation is made for future action. [Ethiop. J. Health Dev. 1997;11(2):125-129]
openalex: W1568623253 mag: 1568623253
Keywords: openalex:import

The SADC (Southern African Development Community) Regional Early Warning System: Experiences Gained and Some Lessons Learned from the 1991-92 Southern African Drought - Rook, John M. (Journal of African Studies, 1997)
openalex: W2259423806 mag: 2259423806
Keywords: openalex:import

Education in the Development of Tanzania 1919-1990 - Roy-Campbell, Zaline M.; Buchert, Lene (International Journal of African Historical Studies, 1997)
openalex: W4298306898
Keywords: openalex:import

Language crisis in Tanzania : the myth of English versus education - Roy-Campbell, Zaline M.; Qorro, Martha (1997)
openalex: W607493616 mag: 607493616
Keywords: openalex:import

Disconnecting education: language as a determinant of the quality of education in Tanzania - Rubagumya, Casmir M. (Journal of Linguistics and Language in Education, 1997)
openalex: W2227052495 mag: 2227052495
Keywords: openalex:import

Requiem for the Sudan: War, Drought, and Disaster Relief on the Nile - Rue, George Michael La; Burr, James; Collins, Robert O. (International Journal of African Historical Studies, 1997)
openalex: W2795549536 mag: 2795549536
Keywords: openalex:import

Mapping (geomatics) related education trends and needs in Africa - Ruether, H. (1997)
openalex: W141719338 mag: 141719338
Keywords: openalex:import

Trends in reproductive health knowledge following a health education intervention among adolescents in Zimbabwe. - Rusakaniko, S; Mbizvo, Michael T.; Kasule, J.; Gupta, Vikram; Kinoti, S.N.; Mpanju-Shumbushu, W; Sebina-Zziwa, J; Mwateba, R; Padayachy, Jude (PubMed, 1997)
Unwanted teenage pregnancy, sexually transmitted infections and the attendant morbidity and mortality necessitate the need for understanding factors influencing adolescent sexuality and the implementation of programmes designed to improve their knowledge, reproductive behaviour, sexual and reproductive health.To determine the impact of an intervention package on knowledge levels of various reproductive health issues through trend analysis.Randomized controlled trial of a health education intervention in schools stratified for representativeness.Rural and urban secondary schools in Zimbabwe.1,689 students recruited from 11 secondary schools in Mashonaland Central.Knowledge level before and after intervention.The demographic characteristics of the pupils at baseline, five months and nine months were comparable between the two groups. There was an overall increase in knowledge on menstruation. Students from the intervention schools were more likely to have correct knowledge over time on aspects of reproductive biology. A significant linear trend (p = 0.017) was observed in the area of family planning and contraception. A linear decreasing trend (p = 0.001) was observed on pregnancy risk. Though not significantly linear, the general trend of knowledge levels in all the areas of reproductive health, pregnancy risk, STDs and HIV/AIDS showed an upward trend, from 20% to 96%. Worth noting was that in all the areas the intervention group had knowledge above that in the control group.The reproductive health education intervention had an impact on aspects of reproductive biology and contraception as measured by the increased scoring at follow up when comparing intervention and control schools. The overall findings point to the need for early school based reproductive health education programmes incooperating correct information on reproductive biology and the prevention of subsequent reproductive morbidity by imparting information on non-risk behaviour during the early developmental years.Evaluation of a secondary school-based reproductive health education intervention in Zimbabwe indicated that such a program should be introduced at the primary school level to have maximum impact. A total of 1689 rural and urban students (mean age, 13.5 years) from 11 secondary schools completed a baseline questionnaire. 1159 (68.7%) were randomly allocated to the intervention schools and 530 (31.3%) to control schools; evaluations were conducted after 5 and 9 months. At baseline, few students in either group had correct information on when a girl was likely to get pregnant during the menstrual cycle. Although follow-up revealed improved knowledge in this area, the intervention effect was significant only among the youngest students. Students in the intervention schools were more likely than controls to know that menarche is associated with the ability to become pregnant, but fewer were knowledgeable about the association between wet dreams in boys and the capability of making a girl pregnant. Attendance at family life education lectures had the most significant positive impact on both knowledge and use of contraception. Knowledge increases in other areas of reproductive health, sexually transmitted diseases, and AIDS increased to a greater extent among exposed than non-exposed youth (20-96% gains), but the trend was not significantly linear. The provision of information on reproductive biology and pregnancy prevention during an earlier developmental stage is recommended.
openalex: W1851567343 mag: 1851567343
Keywords: openalex:import

Primary school textbooks in Zimbabwe : an analysis in social context - Ryf, Andrea (1997)
This thesis is based on an examination of some of the variables that affect schooling in Zimbabwe, a Southern African country. The study consisted mainly of a content analysis of selected primary textbooks for language and gender related matters. It addressed the following questions: (1) Is the material presented as if the learners were first language speakers of English, the language of instruction? (2) How are girls and women portrayed verbally and pictorially? The selected grades 1, 4 and 7 English and science textbooks were first examined broadly for overall features such as visual readability and order of content. Subsequently, all textbooks and the corresponding syllabi were examined for awareness of and directions regarding preparation for the language needs of the science curriculum. A focus on science vocabulary and the portrayal of males and females in the science texts concluded the content analysis. Additional data on the actual use of texts and possible gender bias of teachers in the classroom were gathered through collaboration with graduate students at the University of Zimbabwe. Teachers' views on science education, the science texts, and boys and girls' abilities and performance were obtained. The results point to the existence of a good potential for improved access to the curriculum by coordinating the language needs of English and other subjects. Furthermore, more work needs to be done in Zimbabwe, as elsewhere, to portray males and females in less stereotypical roles.
openalex: W184419732 mag: 184419732
Keywords: openalex:import

The impact of intestinal parasitic infections on the nutritional status of primary school children in Alexandria, Egypt. - Sahn, F. F. El; Deghedi, B. M.; Mahdy, Nehad; Sahn, A. El (1997)
In order to investigate the relationship between intestinal parasitism and nutritional status, stool specimens obtained from 1674 school children aged 6-13 years, enrolled in primary governmental schools in the Eastern zone of Alexandria, Egypt were examined for helminth and protozoan parasites. The findings were collated with anthropometric data (weight and height) on the same children. The prevalence of parasitic infections was found to be 31.5%. The most common infections were found to be with Giardia lamblia (15.4%) and Ascaris lumbricoides (10.2%). Children infected with both helminths and protozoa showed an increased but insignificant risk of underweight relative to those without infections. The risk of stunting was found among all types of parasites as compared to children with no parasites. Also there was a higher non significant risk of wasting among those with protozoal infection especially Giardia lamblia. Children infected with three species or more of intestinal parasitic infections were significantly underweight than non infected children (OR = 4.68, 95% confidence limit = 1.04-18.03). Using stepwise logistic regression analysis, number of parasites appeared to be the most effective variable of the nutritional status of children indicated by weight for age Z score, followed by education of the mother.
openalex: W2401991346 mag: 2401991346
Keywords: openalex:import

Grazing Land Conservation and the Potential Role of Drought Insurance in the Sahel–Evidence from Burkina Faso - Sakurai, Takeshi (1997)
openalex: W405140009 mag: 405140009
Keywords: openalex:import

[The development of public health education: the Mauritius experience]. - Salamon, Roger; Lanièce, Christophe; Daby, Geeta; Lanièce, Isabelle; Mohith, Jagdish C.; Drevet, D; Julvez, J; Fareed, D.; Austin, Isabelle; Ducrey, Thomas; Beylot, J (PubMed, 1997)
A public course has been initiated in 1990 in Mauritius for covering the national growing needs of public health specialists. This training course was organized jointly by the Ministry of Health, the University of Bordeaux II and the French Cooperation. After 3 sessions dedicated specifically to the Mauritian physicians, the course has been re-designed for the needs of the other countries of the region. A feasibility study performed in 1994 in the countries of the Indian ocean region showed that during the past decade, the district level had become the focus point to integrate the health programs. This process has progressively transferred a wider and stronger part of the responsibilities from the central level to the district level and the survey showed that most of the health district managers were physicians that did not have the proper background for carrying such responsibilities. According to these results, a course curriculum was created by the Mauritian Ministry of Health and the University of Bordeaux II and submitted to various organisms supporting health program development in the region. This proposal was strongly supported by several agencies (the french Cooperation, Unicef, WHO, World Bank...) who agreed to sponsor candidates for that training course. The first session was organized in 1995, a second one in 1996. This training course is targeted to the medical doctors who are in charge of the management of health services at the district level. It is divided in two parts: A six-weeks intensive training course performed in Mauritius that include formal teaching and practical exercises in small groups for a total of 210 hours. The curriculum is mainly targeted on the various aspects of management as the management of health information (biostatistics epidemiology and computing), the management of human resources, financial resources and material resources. In addition to these main topics, there is an introduction to pedagogy, communication skills and applied research methodology. Following this six-weeks, training the students come back to work in their country and have 8 months to perform a thesis supervised by a local public health specialist. The subject of the thesis has to be closely related with one of the topic taught and should provide an obvious improvement for the public health situation in the district where this physician is acting. In 1995, 22 candidates attend to the course (13 from Madagascar, 4 from Mauritius, 3 from Comoros, 1 from Angola, 1 from Equatorial Guinea and 1 from Tchad), 19 had successively completed all the modules and got the diploma of public health delivered by the University of Bordeaux II. This diploma has been recognized as an equivalent to a master in public health in Mauritius. The evaluation of the courses-performed by the students, the teachers and the financial agencies gave a very positive results although the workload was considered as too important for a six-weeks training course. The recommendations of the 1995 session were included in the 1996 programs which is still on going for 23 candidates. The 97 session will probably extend the number of students up to 40, divided in 4 subgroups for practical exercises. In parallel to the course, a quarterly bulletin will be created and sent to the present and past candidates of this course in order to support a continuous medical education training program targeted to the district physicians.
openalex: W2415994666 mag: 2415994666
Keywords: openalex:import

The development of Public Health Training : experiences in Mauritius - Salamon, Roger; Lanièce, Christophe; Daby, Geeta; Lanièce, Isabelle; Mohith, Jagdish C.; Drevet, D; Julvez, J; Fareed, D.; Austin, Isabelle; Ducrey, Thomas; Beylot, J (Cahiers d'études et de recherches francophones / Santé, 1997)
A public course has been initiated in 1990 in Mauritius for covering the national growing needs of public health specialists. This training course was organized jointly by the Ministry of Health, the University of Bordeaux II and the French Cooperation. After 3 sessions dedicated specifically to the Mauritian physicians, the course has been re-designed for the needs of the other countries of the region. A feasibility study performed in 1994 in the countries of the Indian ocean region showed that during the past decade, the district level had become the focus point to integrate the health programs. This process has progressively transferred a wider and stronger part of the responsabilities from the central level to the district level and the survey showed that most of the health district managers were physicians that did not have the proper backgruund for carrying such responsabilities. According to these results, a course curriculum was created by the Mauritian Ministry of Health and the University of Bordeaux II and submitted to various organisms supporting health program development in the region. The proposal was strongly supported by several agencies (the french Cooperation, Unicef, WHO, World Bank...) who agreed to sponsor candidates for that training course. The first session was organized in 1995, a second one in 1996. This training course is targeted to the medical doctors who are in charge of the management of health services at the district level. It is divided in two parts : - A six-weeks intensive training course performed in Mauritius that include formal, teaching and practical exercises in small groups for a total of 210 hours. The curriculum is mainly targeted on the various aspects of management as the management of health information (biostatistics, epidemiology and computing), the management of human resources, financial resources and material resources. In addition to these main topics, there is an introduction to pedagogy, communication skills and applied research methodology. - Following this six-weeks training the students come back to work in their country and have 8 months to performe a thesis supervised by a local public health specialist. The subject of the thesis has to be closely related with one of the topic taught and should provide an obvious improvement for the public health situation in the district where this physician is acting. In 1995, 22 candidates attend to this course (13 from Madagascar, 4 font Mauritius, 3 from Comoros, 1 from Angola, 1 from Equatorial Guinea and l from Tchad). 19 had successively completed all the modules and got the diploma of public health delivered by the University of Bordeaux II. The diploma has been recognized as an equivalent to a master in public health in Mauritius. The evaluation of the courses performed by the students, the teachers and the financial agencies gave a very positive results although the workload was considered as too important for a six-weeks training course. The recommendation of the 1995 session were included in the 1996 programs which is still on going for 23 candidates. The 97 session will probably extend the number of students up to 40, divides in 4 subgroups for practical exercises. In parallel to the course, a quaterly bulletin will be created and sent to the present and past candidates of this course in order to support a continuous medical education training program targeted to the district physicians.
openalex: W2227322934 mag: 2227322934
Keywords: openalex:import

The Potential Role of Democratic Political Education in the African Context - Salih, M. A. Mohamed (Eastern Africa Social Science Research Review, 1997)
openalex: W1571244073 mag: 1571244073
Keywords: openalex:import

ALCOHOL USE, ETHNICITY, AND DISABILITY: A COMPARISON OF AFRICAN-AMERICAN AND CAUCASIAN GROUPS - Sample, Eddie B.; Li, Li; Moore, Dennis (Social Behavior and Personality, 1997)
Previous research has consistently reported that alcohol consumption among the general population varies across cultural groups. However, studies investigating risk factors and drinking patterns of African-Americans and Caucasians with disabilities have been limited. The current study explored the factors of alcohol use among African-Americans and Caucasians with disabilities who were seeking rehabilitation services in three mid-western states of the USA. Multivariate data analysis revealed that African-Americans were more likely to use alcohol than their Caucasian counterparts when other demographic and disability variables were controlled. Additionally, separate multiple-regression models differentiated patterns between African-Americans and Caucasians in selected variables on alcohol use. Cultural issues and implications for rehabilitation services are discussed.
openalex: W2066165397 mag: 2066165397
Keywords: openalex:import

Racial Identity Attitudes and School Performance among African American High School Students: An Exploratory Study. - Sandoval, Steve R.; Gutkin, Terry B.; Naumann, Wendy C. (Research in the Schools, 1997)
openalex: W275140929 mag: 275140929
Keywords: openalex:import

Training and policy guidelines for artisanal quarrying: report on field study research in the Nairobi region of Kenya. (ADD031). - Savery, S.P.A. (1997)
openalex: W432536767 mag: 432536767
Keywords: openalex:import

IMPROVING ROAD SAFETY EDUCATION IN DEVELOPING COUNTRIES; GHANA - Sayer, I A; Palmer, Colin J.; Murray, Gardner; Guy, Jon (1997)
Few schools in the developing world include Road Safety Education in their timetable, despite the fact that children represent a vulnerable group of road users. Two reasons for this were identified: a lack of teaching resources, and a lack of knowledge by teachers of how to teach road safety and what should be taught. This report discusses the design and evaluation of a Road Safety Education resource designed for teachers of 10 and 11 year old children and the development of good practice guidelines. The central educational theme of the resource, called 'Safe Ways', is that children learn best by active participation. 'Safe Ways' includes five lessons, each covering a different aspect of road safety. The evaluation took place in Ghana. An interviewer-administered questionaire was used to test 10 and 11 year old children's knowledge of three areas of pedestrian safety: knowledge of safe behaviour, knowledge of unsafe behaviour and knowledge of crossing behaviour. The groups of children who were exposed to the resource showed a significant increase in each of these three areas, compared with a control group. The report also includes a full copy of the 'Safe Ways' resource, and the Teacher Training notes which accompany it. (A)
openalex: W1481403357 mag: 1481403357
Keywords: openalex:import

Improving Road Safety Education in Developing Countries; Ghana. TRL Report 265. - Sayer, I A; Palmer, Colin J.; Murray, Gardner; Guy, Jon (1997)
openalex: W236935730 mag: 236935730
Keywords: openalex:import

Foreign education and indigenous reaction in late Ottoman Lebanon : students and teachers at the Syrian Protestant College in Beirut - Scholz, Norbert (1997)
openalex: W657739119 mag: 657739119
Keywords: openalex:import

Training Requirements in Agricultural Mechanisation and Machinery for Rural Women: An Empirical Study from Egypt - Schotte-Pfuhl, Jutta (Der Tropenlandwirt - Journal of Agriculture in the Tropics and Subtropics, 1997)
Training Requirements in Agricultural Mechanisation and Machinery for Rural Women: An Empirical Study from Egypt
openalex: W1596309209 mag: 1596309209
Keywords: openalex:import

Issues of inequity, health and water: reflections on the schools water action programmes in post-apartheid South Africa - Schreuder, Danie (Health Education Research, 1997)
This paper gives an account of some of the major developments in the field of low-cost educational water quality monitoring in South Africa as an approach to environmental education. The wide acceptance of this approach to education in schools as well as non-formal settings may be an indication of the many complex problems in a country plagued by problems regarding the availability of reliable supplies of clean, fresh water and sanitation. It reflects critically on some of the serious problems that have developed as a result of the non-availability of sufficient supplies of fresh, clean water to many disadvantaged communities. The non-availability of fresh running water and water-borne sanitation are causing serious health problems in many disadvantaged communities. The origin of many of these problems can be traced back to inadequate and inequitable legislation of the past. The problems facing the post-apartheid Government structures now are vast and challenging. Education, especially initiatives like the Schools Water Action Programme, is increasingly being looked upon to help develop wider understanding for the need for the sustainable and responsible utilization of our fresh-water resources, as well as the basic needs and rights of all people.
openalex: W2097547976 mag: 2097547976
Keywords: openalex:import

Link between the granitic and volcanic rocks of the Bushveld Complex, South Africa - Schweitzer, J. K.; Hatton, C. J.; Waal, S. A. de (Journal of African Earth Sciences, 1997)
Until recently, it was proposed that the Bushveld Complex, consisting of the extrusive Rooiberg Group and the intrusive Rashoop Granophyre, Rustenburg Layered and Lebowa Granite Suites, evolved over a long period of time, possibly exceeding 100 Ma. Most workers therefore considered that the various intrusive and extrusive episodes were unrelated. Recent findings suggest that the intrusive, mafic Rustenburg Layered Suite, siliceous Rashoop Granophyre Suite and the volcanic Rooiberg Group were synchronous, implying that the Bushveld igneous event was short-lived. Accepting the short-lived nature of the complex, the hypothesis that the granites are genetically unrelated to the other events of the Bushveld Complex can be reconsidered. Re-examination of the potential Rooiberg Group/Lebowa Granite Suite relationship suggests that the granites form part of the Bushveld event. Rhyolite lava, granite and granophyre melts originated from a source similar in composition to upper crustal rocks. This source is interpreted to have been melted by a thermal input associated with a mantle plume. Granite intruded after extrusion of the last Rooiberg rhyolite, or possibly overlapped in time with the formation of the youngest volcanic flows. Jusque récemment, il était proposé que le Complexe du Bushveld, comprenant le Groupe de Rooiberg extrusif ainsi qua les Suites intrusives du Granophyre de Rashoop, du Complexe Lité de Rustenburg et du Granite de Lebowa, s'est formé au cours d'une longue période de temps ayant pu durer plus de 100 Ma. Pour cette raison, la plupart des chercheurs considŕaient que les épisodes intrusifs divers et extrusif ne présentaient pas de relation entre eux. Des données récentes suggèrent que la Suite Litée de Rustenburg, intrusive et mafique, est synchrone de la Suite saturée du Granophyre de Rashoop et du Groupe volcanique de Rooiberg, impliquant que la mise en place de l'ensemble du Complexe du Bushveld s'est opérée en un bref laps de temps. Sur cette base, l'hypothèse des granites ne présentant pas de relation génétique avec les autres termes du Complexe du Bushveld doit être revue. La ré-examination des relations potentielles entre le Groupe de Rooiberg et la Suite des Granites de Lebowa suggère que ceux-ci appartiennent au Complexe du Bushveld. Pour les liquides des laves rhyolitiques, granites et granophyres, une source de composition similaire à celle de la croûte supérieure peut être envisagée. La fusion de celle-ci résulte du réchauffement attribués à un panache du manteau. Les granites se sont intrudés après ('extrusion des dernières rhyolites de Rooiberg ou éventuellement sont contemporains des coulées volcaniques terminales.
openalex: W1973095930 mag: 1973095930
Keywords: openalex:import

Empowering African-American males in special education to succeed: an exploratory study - Scott-Bowles, Leslie (1997)
SCHOOL OF SOCIAL WORK SCOTT-BOWLES, LESLIE B.S. SOUTHERN ILLINOIS UNIVERSITY -EDWARDSVILLE, 1995 EMPOWERING AFRICAN-AMERICAN MALES IN SPECIAL EDUCATION TO SUCCEED: AN EXPLORATORY STUDY Advisor: Melvin Williams, Ph.D. Thesis dated May 1997 This study explored the use of culture-based empowerment curricula in empowering a group of African-American male special education students to succeed. The Generalized Expectancy to Succeed Scale was used to measure the generalized expectancy to succeed among 8 severely emotionally disturbed adolescent males. The program outcomes assessed included increases and decreases in expectancy to succeed. The findings revealed that the students studied did not have a high expectancy to succeed and that the culture-based curriculum did not have an impact on their expectancy to succeed. Social work implications related to empowering African-American males are
openalex: W156960317 mag: 156960317
Keywords: openalex:import

Liberating the teaching of literature in a democratic South Africa: A pedagogy of reconstruction - Selepe, Thapelo (South African Journal of African Languages, 1997)
Literary study, like any other social process, is affected in one way or another by other related social processes. This article therefore investigates the possibilities of helping literary practice to remain in tune with other social processes.
openalex: W792253708 mag: 792253708
Keywords: openalex:import

Cultural Identity in an African Context: Indigenous Education and Curriculum in East Africa - Semali, Ladislaus M.; Stambach, Amy (1997)
[A]t present our pupils learn to despise even their own parents because they are old-fashioned and ignorant; there is nothing in our existing educational system which suggests to the pupil that he [she] can leam important things about farming from his [her] elders. The result is that he [she] absorbs beliefs about witchcraft before he [she] goes to school, but does not learn the properties of local grasses; he [she] absorbs the taboos from his [her] family but does not leam the methods of making nutritious traditional foods. And from school he [she] acquires knowledge unrelated to agricultural life. He [she] gets the worst of both systems! -Julius Nyerere, first president of Tanzania (1968:278)
openalex: W1148946588 mag: 1148946588
Keywords: openalex:import

Policy recommendations for a multicultural curriculum for all elementary schools in the Republic of South Africa - Setlhako, Motladi Angeline (1997)
openalex: W3133642982 mag: 3133642982
Keywords: openalex:import

An Assessment of the School Library Literature in Nigeria, with Emphasis on the Impact of School Libraries on Educational Performance. - Shaibu, Samaila (1997)
The school/library resource centre was popularized as an integral component of pre-tertiary education, particularly from the turn of the twentieth century. Many librarians and educators have conducted investigations into the relevance of the school library and the relationship between such an institution and learning generally. Most of these studies, however, were conducted in the developed countries. In Nigeria, few studies have investigated the place of the school library in education. This paper reiterates the invaluable educational role of the school library, and reviews the various attempts made to uncover the wide-ranging effects of the provision and use of collections of school learning resources. Only the literature considered highly significant has been reviewed.
openalex: W52111464 mag: 52111464
Keywords: openalex:import

A survey of Kenyan physical education teachers' understanding of heat illness and management of heat stress in athletes - Shehu, Jimoh; Wamukoya, Edwin K. (1997)
openalex: W2262006255 mag: 2262006255
Keywords: openalex:import

Directory of adult and nonformal education in Ethiopia. - Shenkut, M. K. (1997)
openalex: W2543712938 mag: 2543712938
Keywords: openalex:import

Government in Islam for Nigerian students - Sherif, Abu (1997)
openalex: W616951610 mag: 616951610
Keywords: openalex:import

Public Policy National Training Policy: The Case of Zimbabwe - Shora, Robinson M. (African Administrative Studies, 1997)
openalex: W2227390387 mag: 2227390387
Keywords: openalex:import

Beginning teachers' perceptions of a learner centered approach to teaching in Namibia - Sibuku, Cecilia Mwaka. (1997)
openalex: W2896146652 mag: 2896146652
Keywords: openalex:import

Education for democracy and human rights in African schools - Sifuna, Daniel N. (1997)
openalex: W344231480 mag: 344231480
Keywords: openalex:import

Performance of health workers after training in integrated management of childhood illness in Gondar, Ethiopia. - Simões, Eric A F; Desta, Teshome; Tessema, Tsegaw Muche; Gerbresellassie, T.; Dagnew, Mulat; Gove, Sandy (PubMed, 1997)
The performance of six primary health workers was evaluated after following a 9-day training course on integrated management of childhood illness (IMCI). The participants were selected from three primary health centres in the Gondar District, Ethiopia, and the course was focused on assessment, classification, and treatment of sick children (aged 2 months to 5 years) and on counselling of their mothers. Immediately following this training, a 3-week study was conducted in the primary health centres to determine how well these workers performed in assessing, classifying and treating the children and in counselling the mothers. A total of 449 sick children who presented at the three primary health centres during the study period were evaluated. Most of the complaints (87%) volunteered by the mothers (fever, cough, diarrhoea, and ear problems) were covered by the IMCI charts. The assessment of commonly seen signs (tachypnoea or ear pain) or easily identifiable signs (slow return after skin pinch, wasting, or pedal oedema) was good, with sensitivities of 67-91%, whereas the assessment of uncommonly seen signs (dry mouth, corneal clouding) or less easily quantifiable signs (eyelid pallor, absence of tears) had a fair or poor sensitivity of 20-45%. The classification of pneumonia, diarrhoea with signs of dehydration, and malnutrition showed sensitivities of 88%, 76%, and 85% and specificities of 87%, 98%, and 96%, respectively. However, the classification of febrile illnesses had a sensitivity of only 39% due to problems in using the draft algorithm in areas with a mixture of high, low, and no malaria risk, and due to confusion between axillary and rectal temperature thresholds. Of 39 children classified as having severe disease, 9 were misclassified, mostly by one nurse. Treatment of patients improved over the three weeks of observation, their completeness increasing from 69% to 88%. Health workers usually communicated appropriate advice to the mother. They learned to use checking questions but failed to adequately solve problems in the majority of cases. The mother's counselling card, which summarized recommendations on feeding and home fluids, and advice on when to return, was widely used to aid communication. The time taken to perform the complete management of children did not change significantly (20 to 19 minutes) during the study. Lessons from our findings have been incorporated into an improved version of the IMCI charts.6 outpatient clinic nurses selected from 3 primary health centers in the Gondar District of Ethiopia were trained over the course of 9 days in the integrated management of childhood illnesses (IMCI), after which their performance was evaluated. The training course focused upon the assessment, classification, and treatment of sick children aged 2 months to 5 years, and upon the counselling of their mothers. Immediately following the training, the trainees were observed working in the health centers for a 3-week period to determine how well they assessed, classified, and treated children, and counseled mothers. 449 children who presented at the centers during the study period were evaluated. 87% of the complaints noted by the mothers on fever, cough, diarrhea, and ear problems were covered by the IMCI charts. There was good assessment of commonly seen signs such as tachypnoea and ear pain, as well as of readily identifiable signs such as a slow return after skin pinch, wasting, and pedal oedema; sensitivities were 67-91%. However, sensitivities were only 20-45% for rarely seen signs such as dry mouth and corneal clouding and the more difficult to recognize signs of eyelid pallor and the absence of tears. The classification of pneumonia, diarrhea with signs of dehydration, and malnutrition had sensitivities of 88%, 76%, and 85%, and specificities of 87%, 98%, and 96%, respectively. The classification of febrile illnesses was 39% sensitive. 9 of 39 children with severe disease were misclassified, mostly by one nurse. Patient treatment improved over the 3 weeks of observation and health workers usually communicated appropriate advice to mothers.
openalex: W1748407125 mag: 1748407125
Keywords: openalex:import

The school improvement project of the Aga Khan Education Service, Uganda - Siraj‐Blatchford, Iram; Odada, Matthew; Omagor, Martin (1997)
openalex: W2201122069 mag: 2201122069
Keywords: openalex:import

Community Participation In Project Planning In ASAL, Areas Of Kenya, Emergency Drought Recovery Programme - Sitonik, W.K.; Biamah, E.K; Muketha, J.K (1997)
openalex: W2471234469 mag: 2471234469
Keywords: openalex:import

Implementing a new training approach: pilot test of ModCal in Zimbabwe. FCA-28. - Sj, Brechin; Hudspeth, L; Lacoste, M; Sullivan, Richard (1997)
Modified computer-assisted learning (ModCal [TM]) is JHPIEGOs newest option for implementing competency-based training in reproductive health. In May 1996 JHPIEGO an affiliate of Johns Hopkins University conducted a pilot test of ModCal at the Mpilo School of Midwifery in Bulawayo Zimbabwe to assess how participants with no prior computer experience responded to computer-based learning about IUDs. 38 participants (midwifery students tutors and practicing nurses) completed a 5-module prototype for IUD training. A comparison of pre- and post-test scores showed a significant increase (mean change = 24%; t = 13.9 p < 0.0001) in post-test scores. This successful pilot test helped alleviate doubts about the applicability of computer-assisted learning (CAL) in Africa. Prior computer use was not a factor in learning the content or in being able to maneuver through the program and participants praised the programs self-paced aspect–largely because they felt they controlled the pace of their learning and could pause or review sections or modules at any time. Key representatives from a variety of stakeholder organizations acknowledged that this pilot test succeeded in implementing CAL and in demonstrating that knowledge can be transferred using the CAL approach. By using computer technology to maximize training efficiency trainers can redirect their training time–which is scarce–to areas (such as skills practice) that depend upon intensive trainer-learner interaction. In a relatively sophisticated country like Zimbabwe the potential for institutionalizing ModCal is great.
openalex: W2738452861 mag: 2738452861
Keywords: openalex:import

Research and the training of physical science teachers in South Africa - Smit, Jan (AIP Conference Proceedings, 1997)
Physics departments in the RSA make serious attempts to improve the quality of physical science teaching. One of the most burning problems is the lack of well-qualified, experienced physical science teachers in the country. Physics department-based projects address this problem through research and development linked to the research. This paper gives an overview of the physics education research conducted in the RSA during the past few years. The focus is on research in the North West Province. Research findings on students’, prospective physical science teachers’ and practicing physical science teachers’ perceptions of time, space and models in physics will be dealt with. The research indicates that lack of development plays a more significant role than culture in students’ problems with time and space related concepts. Alternative conceptions on models restrict understanding of physics. The results of a study on the phenomenon of rote learning will be referred to. Insufficient attention to visualization proves to be a major cause of rote learning in physics. The future role of physics departments in research on problems with physical science teaching and the implementation of research results will in conclusion be indicated.
openalex: W1601650539 mag: 1601650539
Keywords: openalex:import

Language Policy and Education in South Africa - Smit, Ute (1997)
openalex: W86495277 mag: 86495277
Keywords: openalex:import

Environmental Pollution, dispute resolution and access to justice in Nigeria: Which way forward? - Smith, Ian (1997)
openalex: W1514301622 mag: 1514301622
Keywords: openalex:import

Knowledge of, attitudes toward, and barriers to cancer control and screening among primary care physicians in Egypt: the need for postgraduate medical education. - Soliman, Amr S.; Raouf, Ahmed A.; Chamberlain, Robert M. (PubMed, 1997)
openalex: W108518615 mag: 108518615
Keywords: openalex:import

Transformation and Outcomes-Based Education in South Africa: Opportunities and Challenges - Soudien, Crain; Baxen, Jean (Journal of Negro Education, 1997)
The difficulties of reconstruction and social renewal, as citizens of the Republic of South Africa are learning in their new democracy, are great and demand levels of commitment that challenge deep-seated and entrenched sensibilities about the nature of the world and its organization. During apartheid, education was used not only to achieve social separation but, insofar as it was built around a social philosophy, it was also the legitimating arena for White supremacy and for the complex system of racial and cultural ordering that evolved around it. Within the old order's traditional educational institutions, the hidden and explicit curricula were configured to produce, reproduce, and validate racial separation and hierarchy. Presumptions of European superiority and African inferiority within this canon were commonplace-indeed, they were established as modern truths about human progress and development. These truths provided the ideological foundations upon which apartheid education was built. According to Lotz (1996), within South African schools,
openalex: W2134001176 mag: 2134001176
Keywords: openalex:import

An exploration of youth offenders' subjective experiences of the rehabilitation programme at a South African reform school - Southgate, Benita (1997)
openalex: W3210609727 mag: 3210609727
Keywords: openalex:import

Type A behaviour and hostility in final-year South African students - Spangenberg, Judora J.; Shuda, Suzanne; Robbertze, U C (1997)
openalex: W2123634793 mag: 2123634793
Keywords: openalex:import

1946 and all that: the emergence of the University of South Africa as a teaching university - SPIES, S. B. (Kleio, 1997)
openalex: W2043778055 mag: 2043778055
Keywords: openalex:import

Private education in South Africa : the legal status and management of private schools - Squelch, Joan M (1997)
openalex: W835150243 mag: 835150243
Keywords: openalex:import

Preschool Education for Black South African Children: A Descriptive Study of 32 Educare Centers - Stevens, Floraline I. (Journal of Negro Education, 1997)
The education of young African children in South Africa was ignored during apartheid. In response, groups of African women, many lacking formal education or knowledge of early childhood education (ECE) practices, established private preschools called Educare centers in urban areas, townships, and rural homelands. In 1995, nongovernment organizations with assistance from USAID began training Educare teachers. An evaluation of 32 Educare facilities was conducted to assess the relationship of this training to improved ECE practices. Overall, the training was found to improve Educare teachers' ability to provide a healthy, safe environment and appropriate learning experiences for children. This article reports on that study, describing the deprived conditions found at most centers but also highlighting the incredible dedication of Educare teachers and staff. In most industrialized nations, the care and welfare of young children is seen as a basic social right (Lubeck, 1991). Throughout the industrialized world, preschool services are provided in a variety of settings including home-based care, public and private child care centers, worksite centers, and public schools. In new or developing nations, however, early childhood education-indeed, education generally-typically is provided to only a privileged few, not the masses. According to Pollitt (1984), explicit literacy-nurturing activities are not part of the early childhood experience of most poor children in developing countries. As these nations move toward more widespread empowerment of their populations, they usually experience the need to become more inclusive in their educational policies. At that point, policymakers in these nations, and the nations that support them, require information on how best, given limited resources, to implement and sustain educational programs for citizens ranging from the youngest toddlers to the oldest adult learners. One major educational policy issue facing new and developing nations involves early childhood education (ECE). As these nations move to establish stable social and economic environments, their policymakers must consider the impact of ECE on national progress. In effect, they must determine the educational as well as societal and economic benefits for the nation when very young children are afforded meaningful learning experiences. Myers (1991) cautions that the schools, families, and social institutions in nonindustrialized, Third World countries differ from those in industrialized, Western nations in significant ways. The causal mechanisms that seem to work in the United States or Europe, he notes, may or may not work in nations where large classes, an inadequate number of school places, scanty instructional resources, and minimally trained teachers are the norm. Nonetheless, research indicates that the quality of early schooling has a significant effect on poor children's primary school progress and performance (Haddad, 1979; Heyneman & Loxey, 1983; Schiefelbein & Farrell, 1978). For example, McKey, Condelli, Ganson, McConkey, and Plantz (1985) and Schweinhart, Barnes, and Weikert (1993) report that children attending Head Start, an ECE program for poor children in the United States, showed both immediate and continual improvement in their intellectual and socioemotional performance and health. Zill, Collins, West, and Hausken's (1995) research links attending Head Start, prekindergarten, or other centerbased preschool programs to higher emerging literacy scores. They further contend that the benefit of preschool attendance accrues to children from both high-risk and low-risk family backgrounds. Reporting empirical evidence about the effects of the School Readiness Language Development Program (SRLDP) for four-year-old African American and Hispanic children, Champagne (1987, 1988, 1989, 1990) notes that these preschool students' performance improved significantly on all subtests of the Cooperative Primary Preschool Inventory. …
openalex: W2048172490 mag: 2048172490
Keywords: openalex:import

The Comprehensive Role of Student Affairs in African-American Student Retention. - Stewart, Gregory; Russell, Ruth B.; Wright, Dianne Brown (Journal of College Admission, 1997)
openalex: W150855527 mag: 150855527
Keywords: openalex:import

Not out of Africa. How Afrocentrism Became an Excuse to Teach Myth as HistoryBlack Athena Revisited - Stray, Christopher; Lefkowitz, Mary R.; Rogers, Guy Mac Lean (1997)
openalex: W2046234064 mag: 2046234064
Keywords: openalex:import

Impact of Telikom Training Centre on economic development of Papua New Guinea - Sukthankar, Subhash (1997)
The UNESCO UNEVOC Regional Conference was held at the Royal Melbourne Institute of Technology from 11-14 November 1996. The theme of the conference was 'Policy development and implementation of technical and vocational education for economic development in Asia and the Pacific'. Delegates from almost all UNEVOC countries attended the conference. This paper outlines the two phases of the project and shows how the objectives of the project have been largely achieved.
openalex: W2991847356 mag: 2991847356
Keywords: openalex:import

Situated Math Skills Learning: 'Tiekie-Dice' Amongst Street Children in South Africa - Swart-Kruger, Jill (Journal of Psychology in Africa, 1997)
openalex: W1601711288 mag: 1601711288
Keywords: openalex:import

The persistence of difference in networked classrooms: Non-negotiable difference and the African American student body - Taylor, Tomaro (Computers and Composition, 1997)
This essay examines issues of diversity and literacy education primarily in terms of the concept of difference via a new term: non-negotiable difference. It argues that networked classrooms provide writing instructors with unique extra-linguistic cues (body language) that can help teachers and students become more responsive to racial difference. The essay discusses specifically the experiences of three African American students in a technical writing course and, on the basis of those experiences, concludes that scholars and critics should avoid universalizing so-called black experience.
openalex: W1979886671 mag: 1979886671
Keywords: openalex:import

EDUCATIONAL IMPACTS OF THE TRAINING AND VISIT EXTENSION SYSTEM ON SMALL FARMERS IN THE WEST PROVINCE OF CAMEROON - Tchouamo, Isaac Roger; Steele, Roger (Journal of International Agricultural and Extension Education, 1997)
openalex: W2334694901 mag: 2334694901
Keywords: openalex:import

The relevance of education to the socioeconomic development needs of rural people: the case of Kenya - Theuri, Emma Wanjiru (1997)
openalex: W638879858 mag: 638879858
Keywords: openalex:import

Music Education in South Africa - Striving for Unity and Diversity - Thorsén, Stig-Magnus (1997)
South Africa now finds itself in a state of dramatic change. Education based on segregation is to be replaced, this time by an implementation of the policy of the Rainbow Nation. To merge traditions from Africa, Europe, North America and Asia into a multicultural music education in a short space of time is indeed a vast and complicated mission.
openalex: W2187635200 mag: 2187635200
Keywords: openalex:import

Teacher-student ethnicity, suspension/expulsion, and referrals to special education: Implications for African-American males - Thrasher, James Frank (1997)
openalex: W3165602775 mag: 3165602775
Keywords: openalex:import

[Survey of leprosy disabilities in patients treated with multiple drug therapy in Ivory Coast]. - Tiendrébéogo, Alexandre; Ds, Djakeaux; Assé, Henri; Me, Eba; Sica, A. (PubMed, 1997)
Between 1990 and 1995, twenty thousand cases of leprosy were treated with WHO recommended multiple drug therapy (MDT) in Ivory Coast. A disability survey was conducted in April 1996 with a half-randomized sample of five hundred patients. This survey showed that 28.73% of the patients had got grade two disabilities in WHO scale. 12.9% of the non disabled patients at detection had developed leprosy impairments during or after treatment. Plantar ulcers (12.2% of the patients) appeared very frequent comparatively to the findings of a similar survey in Burkina Faso in 1995 (0.9% of plantar ulcers). With these results, the authors estimated the needs for disabilities care to enable the reinforcement of the prevention of disabilities and physical rehabilitation (POD and PR) in Ivory Coast.
openalex: W2403873045 mag: 2403873045
Keywords: openalex:import

Assessment of long-term air pollution impacts on soil properties in the vicinity of Arnot power station on the South African highveld - Tienhoven, Van; Mieke, Anne (1997)
openalex: W2944050616 mag: 2944050616
Keywords: openalex:import

Assessment of long-term air pollution impacts on soil properties in the vicinity of Arnot power station on the South African highveld - Tienhoven, Van; Mieke, Anne (1997)
openalex: W2944050616 mag: 2944050616
Keywords: openalex:import

Testing a Model of Degree Progress Among African-American Graduate Students - Toliver, Mary F. (1997)
openalex: W3026475767 mag: 3026475767
Keywords: openalex:import

Proceedings of a conference on Pollution Control and Environment Management in Developing Countries. Sponsored by The Commonwealth. Gaborone, Botswana - Totolo, Otlogetswe; Bogatsu, Yvonne Gotlop; Ekosse, Georges (1997)
openalex: W3157520828 mag: 3157520828
Keywords: openalex:import

Teaching Urban African American Students with Learning Disabilities in Inclusive Classrooms: Using Study Groups to Facilitate Change. - Trent, Stanley C. (Learning Disabilities Research and Practice, 1997)
openalex: W85147617 mag: 85147617
Keywords: openalex:import

The role of the environment in the sexual activity of school students in Tororo and Pallisa Districts of Uganda. - Twa-Twa, Jeremiahs (PubMed, 1997)
Several models of adolescent sexual activity have previously been published and most of them suggest two basic components, biological and sociological. This article highlights important environmental factors in shaping the sexual behaviour of the school-going youth in Uganda. Students in education levels Senior 1 to 6 participated in the study. Information was collected from self-response structured questionnaires, focus-group discussions, and discussions with teachers. Student respondents were randomly selected.Findings are reported from a cross-sectional study of the sexual behavior of randomly selected secondary school students in Tororo and Pallisa districts of Eastern Uganda. 322 males and 348 females from 14 secondary schools answered structured questionnaires while 50 additional students participated in focus group discussions. The survey respondents were aged 10-24 years, although approximately 70% were aged 15-19 years. 65% of the male and 32% of the female unmarried students reported having sexual experience. The mean ages at first sexual intercourse were 16.1 years for boys and 16.6 years for girls. Of those sexually active, 49% of the males and 25% of females had multiple sex partners. Parental care, peer influence, economic factors, and AIDS education are the main environmental factors which appear to have major influences in determining the nature of students' sexual activity in Uganda.
openalex: W1543964893 mag: 1543964893
Keywords: openalex:import

A feminist analysis of gender, education and development : the case of South Africa - Ulicki, Theresa (1997)
openalex: W2598908726 mag: 2598908726
Keywords: openalex:import

From quantum fluctuations to cosmological structures : proceedings of the First Moroccan School of Astrophysics, Casablanca, Morocco, 1-10 December 1996 - Valls–Gabaud, D.; Hendry, M.; Molaro, P.; Chamcham, Khalil (1997)
openalex: W1608511547 mag: 1608511547
Keywords: openalex:import

A Water Resources Planning Response to Climate Change in the Senegal River Basin - Venema, Henry David; Schiller, Eric J.; Adamowski, Kaz; Thizy, Jean-Michel (Journal of Environmental Management, 1997)
No abstract
openalex: W2032554314 mag: 2032554314
Keywords: openalex:import

Philosophy of Education in a new South Africa - Venter, Elza (South African journal of higher education, 1997)
In the last few years many changes have taken place in South Afrrca. The creation of a nonracial. non-sexist. democratic South Africa presents a challenge to everybody in the country. The heterogeneous population structure. with a plurality of Value systems. makes teacher educacation and training very qomplex. Teachers are significant change agents in a diverse society. such as South Africa. Teachers need to learn to accommodate different value systems and to place them within a framework of common human values. to educate their own students to respect differences. whilst recognising similarities. South Africa needs an open. critical education philosophy which encourages enquiry. discussion. debate and Iffelong leaming. Philosophy of Education has tha imports'nt role of providing perspective in a complex, demanding world. By critically studying different metatheories. as well 8S several education theo es and by being exposed to divergent ways of thinking, students might be better prepared to accommodate children from different cultures and backgrounds in the practical classroom situation.
openalex: W3027137770 mag: 3027137770
Keywords: openalex:import

Women at Work: Career Histories of Primary School Teachers in Botswana - Veur, van der; Shirley, Maurice (1997)
openalex: W2293057415 mag: 2293057415
Keywords: openalex:import

A task–based syllabus for English in South African primary schools - Villiers, De; Uvalde, Suzette (1997)
openalex: W757966421 mag: 757966421
Keywords: openalex:import

Teachers' attitutdes and perceptions towards poetry teaching and learning in Lesotho high schools - Wagana, J. (1997)
openalex: W1548174144 mag: 1548174144
Keywords: openalex:import

Student financial aid at South African universities and technikons - Wakeford, Jeremy J. (1997)
openalex: W2278969059 mag: 2278969059
Keywords: openalex:import

Agricultural education at the crossroads: Present dilemmas and possible options for the future in sub-Saharan Africa - Wallace, Ian (International Journal of Educational Development, 1997)
Agricultural Education and Training (AET) in sub-Saharan Africa (SSA) needs to respond to the many changes in the socio-economic and political environments within which it exists. In addition to these, there are marked changes in the concept of ‘agriculture’ itself, which is increasingly seen in terms of broader notions of renewable natural resource management, with increasing emphasis on integrated systems and sustainable production. Traditional forms of AET are also challenged by new ideas about the process of teaching and learning, including soft-systems thinking, participatory rural appraisal and farmer-to-farmer extension; as well as the emergence of new modes of learning (including distance learning). Current moves towards privatisation also mean that there is increasing prominence given to new and more flexible providers such as NGOs, parastatal bodies and agribusinesses. All these factors are leading to calls for adaptation, innovation and diversification in systems which have been marked by their lack of responsiveness in the past. Dilemmas which now face the AET sector include changing patterns of donor support, the emergence of new training needs and new types of audiences. The paper examines a range of issues, including the lack of labour market and training needs identification studies, the need for more relevant and responsive curricula, the key role of staff development in creating ‘learning organisations’, the need for a strategy of developing linkages and learning webs or networks and for far more sustainable donor interventions. Finally there is a lack of a coherent policy framework for AET in most countries in the region. A number of options are discussed, such as rationalisation, including achieving a better balance between public and private sector provision, the adoption of new aims and learning styles at all levels, catering for the needs of new target audiences and enhancing innovation and relevance in curriculum. Some important prerequisites for such changes are highlighted and include political will and commitment, consensus and popular support, entrepreneurial leadership, a balance between responsiveness and stability and the targeting of financial and other forms of support to enable sustainable models of innovation to emerge.
openalex: W1989746802 mag: 1989746802
Keywords: openalex:import

English as a Language of Learning in South Africa: Whose English? Whose Culture? - Walt, Christa van der (Language Awareness, 1997)
It is commonly accepted that a language reflects a particular culture and that learners should be made aware of the implicit values and beliefs of that culture in contrast to their own. However, in countries where English is used as a language of wider communication the users of English increasingly imbue that language with the accent, lexical items and value systems of their first language, particularly when English is also taught by non‐native speakers. One has to ask to what extent such teachers are aware not only of the cultural aspects of English language teaching, but also of the first‐language cultural values reflected in their teaching and use of English. This paper would like to argue that critical awareness of the role and function of the emergent South African English is dependent upon (1) the acknowledgement of the first languages of learners to prevent loss or down‐grading of first‐language cultures, and (2) the development of techniques by which learners’ first languages can be used more explicitly in classrooms where English is used as a language of learning and instruction.
openalex: W2033148868 mag: 2033148868
Keywords: openalex:import

Samora Machel School of Veterinary Medicine Library, University of Zambia - Walusiku, Likukela (1997)
The COllection currently stands at approximately 4 000 titles. including a textbook collection. Unfortunately. the book budget has been dwindling through the years to an eltent that we now rely more on dOnaIions than out' own resources. To this extent, the Japanese and British governments have been a great source of suppon through their JICA and aDA programmes. The University of Pretoria has been of great assistance to us and has so far given us two dOtWions tOtalling 112 titles . We are really very grateful at this gesrure .
openalex: W1570033667 mag: 1570033667
Keywords: openalex:import

Aims and objectives of secondary school, physical education in Kenya - Wamukoya, Edwin K. (1997)
openalex: W2264113397 mag: 2264113397
Keywords: openalex:import

Capacity building and institutional development in higher education in Kenya - Wandiga, SO (1997)
openalex: W2562767053 mag: 2562767053
Keywords: openalex:import

The role of physical education in the promotion of sport for all in Kenya - Wasonga, Teresa A. (1997)
openalex: W2279905693 mag: 2279905693
Keywords: openalex:import

Factors Associated with African American Grandparents' Interest in Grandparent Education - Watson, Jeffrey A. (Journal of Negro Education, 1997)
As educators begin to pioneer various types of grandparent education programs, little is known about what types of grandparents are interested in such training. To help answer this question, 427 grandparents from 15 churches in the Washington, D.C. area completed the Grandparent Strengths and Needs Inventory. A series of statistical comparisons across 23 variables revealed 10 significant differences between grandparents who expressed interest in taking a grandparenting class and those who did not. Greater interest in such courses was found among younger African American grandparents with fewer economic resources, who co-resided with their grandchild(ren), felt strongly about their role as a family teacher, and desired more information about their grandchildren. The implications of these findings are discussed and additional research recommended. INTRODUCTION Since 1900, African Americans have gained more than 30 years in life expectancy, European Americans more than 20 (Kain, 1993). Together, these trends have tripled the proportion of Americans who are 65 years of age or older in the United States (Sprey & Matthews, 1982). With this advantage of expanded longevity, the U.S. presently boasts over 60 million grandparents (Kornhaber, 1996), several million of whom serve as surrogate parents (Kornhaber, 1993; Minkler, Roe, & Driver, 1992; Strom & Strom, 1993b; Woodworth, 1995). Indeed, one of the most central family roles in the African American community is the grandmother, who commonly serves as a source of security and strength for the children of that community (Boyd-Franklin, 1989). The relationship between African American grandparents and their grandchildren often illustrates two of the strengths found in families of color: active networks of extended kin and flexible roles among the generations (Fine, Schwebel, & James-Myers, 1987; Kivett, 1985, 1991, 1993; Lyles & Carter, 1982). In the early history of grandparent research, many studies seemed to suggest that grandparenting was the same for everyone. Accordingly, the grandparent role was often discussed in a one-dimensional way, regardless of potential complexities resulting from the grandparent's gender, race/ ethnicity, class, age, or family involvement (Crawford, 1981). Commonly, after studying middle-class European American grandmothers of any age, some early researchers generalized about grandparents at large (Gladstone, 1988). As a result, several important questions were left unanswered. Among these questions are the following: Do these reports clarify or cloud the role of grandfathers? Are their results relevant for grandparents of color? Do the findings accurately represent lessaffluent grandparents? Do the conclusions drawn by the researchers reliably depict grandparents who enter the role at different ages or stages in life? As grandparent research continued, family scholars discovered that men and women seemed to view grandparenthood differently (Strom, Collinsworth, Strom, Griswold, & Strom, 1992; Strom, Ewing, & Strom, 1996; Strom & Strom, 1989). For instance, after interviewing 70 pairs of middle-class grandparents, Neugarten and Weinstein (1964) found that grandmothers were more likely to define the grandparenting role as significant and more likely to serve as surrogate parents than were grandfathers. Their reported gender differences were similar to those of other investigators, who described grandmothers as being more involved in child care (Bengtson, 1985; Cohler & Grunebaum, 1981; Cunningham-Burley, 1984) and as more satisfied in their grandparenting than grandfathers (Thomas, 1982, 1986a, 1986b). Findings such as these suggest the need to investigate whether a person's interest in attending a grandparent education seminar might be a function of grandparent gender. As the interest in grandparent research grew, other studies identified apparent role differences between grandparents of African heritage and those of European descent (Strom, Collinsworth, Strom, & Griswold, 1992, 1993; Strom, Collinsworth, Strom, Griswold, & Strom, 1992; Strom, Strom, Strom, Collinsworth, & Griswold, 1996). …
openalex: W2092522765 mag: 2092522765
Keywords: openalex:import

University of Pennsylvania School of Veterinary Medicine Travels to Turkana, Kenya - Weber, Scott (Bellwether Magazine, 1997)
openalex: W47059743 mag: 47059743
Keywords: openalex:import

Geography: Optional Test and Task Materials KS3 Consistency in Teacher Assessment: Unit 4: Comparing Development: Wales and The Gambia - Weeden, Paul; Tidmarsh, C (1997)
openalex: W1548933553 mag: 1548933553
Keywords: openalex:import

Late Third Millennium Abrupt Climate Change and Social Collapse in West Asia and Egypt - Weiss, Harvey (1997)
openalex: W59763712 mag: 59763712
Keywords: openalex:import

Environmental Priorities for Africa: Linkages between Climate Change and Basic Human Needs - White, Rodney R. (Canadian journal of African studies, 1997)
The changing implications of the use of the term in the context of economic growth and development in Africa and other regions of the Third World is important in understanding current approaches to and development, as used by the United Nations Commission for Environment and Development, for example (World Commission 1987). In the 1970s, it was widely assumed especially among economists that the environment was somehow external or secondary to economic development. In some cases, it was assumed that the preservation of the environment was antithetical to economic development. This attitude was widespread in both the market economies and central planned economies (White 1993). Environmental concerns were dismissed as the preoccupation of special interest groups, such as conservationists, that did not understand the imperatives of the world. Traces of this attitude still linger. However, in the 1980s, more people became aware that neglect of the physical life systems on which we depend the environment, including clean air and water carried very real costs, to both rich people and poor people. Whereas development economists had considered environmental standards as an unaffordable luxury for low-income countries, attitudes began to change by the late 1980s, as the costs of environmental neglect could be seen for the human population and the economy, as well as for the landscape. The energy used by households to boil unclean water became a measurable component of Gross Domestic Product (World Bank 1992, 5). As people became more broadly aware of the significance of these life support systems and the need to maintain them, they also had to come to terms with
openalex: W1488429082 mag: 1488429082
Keywords: openalex:import

Environmental Priorities for Africa: Linkages between Climate Change and Basic Human Needs - White, Rodney R. (Canadian Journal of African Studies, 1997)
openalex: W4246958860
Keywords: openalex:import

Career Preferences of Female Students at Ahfad Medical School in Sudan: a Pilot Study - Wiefferink, Carin H.; Essink, J.M.G.; Leeman, Yvonne (Education and Health, 1997)
openalex: W1531792125 mag: 1531792125
Keywords: openalex:import

Child Mental Handicap: Related Policies In The New South Africa - Wigton, Alyssa; Adnams, Colleen M.; King, Maylene Shung (Southern African journal of child and adolescent mental health, 1997)
openalex: W2075448732 mag: 2075448732
Keywords: openalex:import

Social Support, Self-Efficacy and Their Relationship to the Academic Performance of African-American Students Attending an Historically Black University - Wilson, Tremika LeShan (1997)
openalex: W3027137333 mag: 3027137333
Keywords: openalex:import

Villagers as forest managers and governments "learning to let go": the case of Duru-Haitemba & Mgori forests in Tanzania - Wily, Liz Alden (1997)
openalex: W617436811 mag: 617436811
Keywords: openalex:import

"Bible, Bath, and Broom": Nannie Helen Burroughs's National Training School and African-American Racial Uplift - Wolcott, Victoria W. (Journal of Women's History, 1997)
"Bible, Bath, and Broom": Nannie Helen Burroughs's National Training School and African-American Racial Uplift Victoria W. Wolcott In a promotional booklet, "Making Their Mark," school president and founder Nannie H. Burroughs looked back on the accompUshments of the National Training School for Women and Girls by relating the story of former student Bettie B. Reed. When a white famüy hired Reed to accompany them to their summer home in Maine, there was only one bathtub in the home which the famüy refused to let Reed use. Reed would not accept the job unless the family acquiesced and "it became a question as to whether they would give up their prejudice or the prospects of having a trained household assistant during the summer." The family finally agreed to Reed's demands, and when they returned in the fall Burroughs quoted them as saying, "We are begging her to go back with us next season. We want to tell you that she is a great deal cleaner than we are and just as refined. We are sorry we mentioned the bath tub [sic]. Our objection was based on mere hearsay about colored people."1 For Burroughs this anecdote exemplified the work of the National Training School in negating images of African-American working women as "unclean" and "unrefined."2 In the first 4 decades of the twentieth century the National Training School prepared young African-American women both to "uplift the race" and earn a livelihood. By incorporating industrial education with training in morality, religion, and cleanliness, school founder Nannie Helen Burroughs and her staff attempted to resolve a conflict central to the lives of African-American women: their role as wage laborers in ghettoized service occupations, and their role as guardians of the community and models for "the race." Burroughs and her staff combined a variety of ideological strands to resolve this conflict with the overall goal of training female students for service to their race. They focused on economic improvement, religious piety, and community pride—ideas that crossed a domestic ideology of femininity and a racial ideology of African-American autonomy. By adapting a complex set of ideals that resonated with African-American women across the country, the National Training School chaUenged the dominant culture's image of immoral African-American women, trained young AfricanAmerican women to be community activists as well as efficient wage © 1997 JOURNAL OF WOMEN'S HISTORY, VOL. 9 NO. 1 (SPRING) 1997 Victoria W. Wolcott 89 workers, and reinforced the gendered ideals of sexual purity and respectability as central to racial uplift. Some scholars have viewed racial uplift as a middle-class strategy of reform that chaUenged white racism while furthering class stratification within the African-American community.3 Other scholars have viewed uplift ideology as a project of racial advancement based on community consensus and inter-class cooperation.4 As seen in the case of the National Training School particular aspects of racial uplift resonated strongly with working-class women because these values were already part of their worldview. Notions of moratity, respectability, cleanliness, and reUgiosity were not ideological gifts of the middle class handed down to the poor, but rather part of a pre-existing working-class culture. There did exist, however, class-based tensions in the early twentieth century over appropriate wage work for African-American women and the role female migrants would play in new urban African-American communities. These tensions were reflected in the pedagogy of the National Training School, and the interaction of students with Burroughs and her staff. The many letters received by Burroughs from working-class women seeking to place their daughters, nieces, and granddaughters in the school also reveal that efforts to control the sexuality of young African-American women was a priority not only for middle-class women. Thus, the ideology promoted by the National Training School wove together common concerns of African Americans who sought to improve the material Uves of a generation of young women. Racial Uplift Ideology and the National Training School Racial pride, respectabiUty, and the work ethic were central components both in the training offered by the National Training School and racial uplift ideology. Burroughs and...
openalex: W2054968414 mag: 2054968414
Keywords: openalex:import

El Nino and Drought Early Warning in Ethiopia - Wolde–Georgis, Tsegay (Journal of African Studies, 1997)
El Nino (EN) is the increase in the surface temperatures (SST) in the central and eastern equatorial Pacific Ocean. EN results from changes in the pattern and direction of winds and ocean currents in the region, which have potentially catastrophic effects. Many researchers now believe that the occurrence of various droughts in Africa, especially in Southern Africa and the Horn, are caused by physical processes related to the occurrence of ENSO events thousands of miles away. If valid and reliable information about the linkages between these occurrences becomes available, it could help to forecast Sub-Saharan African droughts. ENSO-based drought early warning could send a wake-up call to governments to prepare for national food shortages. With such information, policies that reduce the impact of drought could be introduced. An early warning with many months of lead time, such as could be provided by ENSO information, would eliminate the excuse of national governments who claim to be unaware of the advent of drought. When drought causes famine, and a reliable drought early warning was available, it becomes a man-made disaster.
openalex: W3123781303 mag: 3123781303
Keywords: openalex:import

Desiderata in South African higher education studies' window on the outside world - Wolhuter, Charl C. (South African journal of higher education, 1997)
This article is aimed at evaluating the interaction . of South African higher education studies with ... research undertaken abroad. During the past . decade a constant stream of publications dealing . with South African higher education appeared in subject journals in other c~ntries . Likewise. a . steady flow of articles deahng ;ith the ·higher educational experience abroad appeared in local journals. In both instances. however. there is a · lack of a full . comparatiVe perspective. The · following focal points evidenced in higher education . studies abroad are absent in local higher education research: gender issues in higher education; higher education output (i e the graduate in the labour situation); ethical issues with reference to · higher education; a'ca- . demical autonomy. freedom and accountability; and the rectorate.
openalex: W2468783078 mag: 2468783078
Keywords: openalex:import

Gender Equity in Education: A Report by the Gender Equity Task Team, Department of Education, South Africa - Wolpe, AnnMarie; Quinlan, Orla; Martinez, Lyn (1997)
openalex: W2247893438 mag: 2247893438
Keywords: openalex:import

The Intercultural Culture of Schools: Problems and Challenges for a Post-Apartheid South Africa - Wyk, Jerome-Alexander Van (Journal of Negro Education, 1997)
To achieve optimal balance between cultural integration, differentiation, equity, and development, this article argues that an culture must be established in South Africa's public schools. This will demand critical awareness of and informed commitment by educators and learners to prevent schools, especially the formerly White schools, from continuing to embody skewed values and practices that, in a new political dispensation, enshrine rather than redress inequity. It will also require stakeholders to summon the political and educational will to transform schools through changing and strengthening their institutional cultures and not viewing efforts to promote as optional add-ons. INTERCULTURALISM AND INSTITUTIONS Institutions are living, breathing entities within which people exchange and share ideas and values as well as ways of acting, seeing, and understanding. Creating an appropriate institutional framework for the transformation of South Africa's schools will be critical, especially insofar as achieving clearer understandings of diversity and among students, teachers, administrators, and parents is concerned. Institutional weakness has been a major factor in failed or delayed attempts at transformation, and unless an effective institutional framework is created, the nation stands in danger of maintaining and strengthening the inequities of the apartheid system of education. The present article posits two questions: What role can accelerated school organizational development play in a post-apartheid transformation program? What kind of institutional redress and development will be needed to increase understanding among all of the stakeholders in South African education? The terms intercultural and interculturalism are preferred to multicultural and multiculturalism because the former seem to more accurately suggest the action of connecting or communicating issues, notions, beliefs, values, and understandings among and between different cultures. In this context, South African White men are seen as often viewing and valuing procedures within organizations differently than do Black men. Similarly, women are perceived as viewing and valuing these aspects differently than do their male counterparts. This article further argues that questions about institutions and organizational development are inseparable from those about the need for transformation and attempts to consciously pursue greater understandings. Several principles guide this perspective: (1) Institutional transformation programs cannot be viewed as optional, extras, or addons. Rather, they must be seen as essential and non-negotiable components of any strategy to promote educational equity and accelerated development. (2) Inequities and negatively perceived differences among constituencies need to be taken into account when developing understandings, which, by design, were ignored during the apartheid era. If this is not done, the inequities will be reproduced in the present era and no sustainable basis for the transformation of institutions will be created. It is also likely that the sociopolitical consequences of large-scale polarization will continue to entrench intolerance throughout the land. (3) Institutional transformation programs cannot be based on the unrealistic expectations of previously excluded and therefore weaker parties. Unless all parties can expect concrete benefits, the political will to sustain transformation will be lacking. (4) Institutional transformation programs must establish both cooperative and integrated efforts aimed at helping South Africans realize the benefits of closer interracial/ interethnic relations. (5) The success of institutional transformation programs depends on their ability to promote negotiation and cooperation among various constituencies to encourage the unlearning of prejudices, and as a result, release resources for the development of democracy, productivity, and diversity. …
openalex: W2091428320 mag: 2091428320
Keywords: openalex:import

Health education for family planning, schooling as family planning: contrasing perspectives on fertility and girls' education in Niger - Wynd, Shona (1997)
openalex: W2616683633 mag: 2616683633
Keywords: openalex:import

A survey study on the status of school health service in Ethiopia - Yohannes, Gebremedhin (1997)
openalex: W172062078 mag: 172062078
Keywords: openalex:import

The causes, processes and consequences of student drop-out from Junior Secondary School (JSS) in Ghana: the case of Komenda-Edina-Eguafo-Abrem (K.E.E.A.) district. - Yokozeki, Yumiko (1997)
Despite open access to both primary and junior secondary school (JSS), non-enrolment and dropout have been countrywide problems in Ghana. This thesis investigates the nature of student dropout from JSS in one district in the country, through four main questions. What is the relationship between drop-out rates and school characteristics of JSS in K.E.E.A. district? What are the factors causing students to drop out? What are the processes of dropping out? What are the consequences of dropping out? The thesis investigates the above questions in two phases: the first on a macro level, by means of a school survey of all 39 schools in the district; and the second on a micro level, by means of an in-depth study of drop-outs from four schools. In the school survey, among the school factors included in the current study, few showed significant association with the drop-out rates. (However, in subsequent in-depth study, the school characteristics were found to exert some influence; for example, the schools with low drop-out rates had stronger teacher commitment). In the school survey, drop-out rates were clearly associated with gender. The in-depth study of 32 drop-outs from four schools suggested that the cause of drop-out was predominantly finance for males and pregnancy for females. In a comparison of 32 drop-outs and 32 stay-ins, where age, gender, academic achievement and economic status were matched, few differences were found in family composition and school experience. In the examination of matched pairs, drop-outs tended to display particular characteristics, such as belonging to a minority language/ethnic group, or having a slight physical handicap. Parental divorce was common among both drop-outs and stay-ins. The investigation of the process of leaving school revealed that the problem was more complicated than the surface cause might suggest; there were often multiple causes leading drop-outs to abandon their education. When problems such as parents' divorce, belonging to a minority language/ethnic group, or having a slight physical handicap were coupled with poverty, the combination of these factors could cause students to leave school. Although a cause might not be serious enough to effect drop-out by itself, many students were already on the verge of dropping out; thus very little pressure was necessary to cause them to discontinue their schooling. Girls were more vulnerable than boys. Girls in general showed fewer risk factors yet more girls than boys dropped out. In some cases girls would not have dropped out if they had not become pregnant. After leaving school, most drop-outs engaged in economic activities. Only a few drop-outs wished to go back to school, and almost all wished to undertake an apprenticeship to lead to selfemployment. The occupational skills learned in apprenticeship were gender-specific, and women had fewer choices. Inequality was evident at every step; girls were disadvantaged in enrolment, retention, examination results, and in economic activities after leaving school. Education can be an effective tool for empowering the disadvantaged population. However, schooling in rural Ghana was not always meeting the strategic needs of the disadvantaged. Drop-outs, therefore, searched for other alternatives in which they could be successful, such as self-employment in microenterprises.
openalex: W12085575 mag: 12085575
Keywords: openalex:import

The children of the Nile : the Community Schools Project in Upper Egypt - Zaalouk, Malak (1997)
openalex: W610809632 mag: 610809632
Keywords: openalex:import

Self-Help Secondary Education in Kenya - Zamberia, Agustino M. (1997)
AbstractDiverse viewpoints on the role of education in the development of Third World countries have spawned a variety of theories of Third World education. Some scholars contend that Third World states are too weak and “fragile” to implement development programs for education, health, and other social services. This paper examines secondary education in Kenya with regard to issues of educational inequality and quality of education, emphasizing the role of civil society in the provision of education. The role of the state as a major actor in the provision of education, and additionally as a determinant of who gets the benefits from educational efforts of both the state and the civil society, is also discussed in detail. It is argued that despite the major expansion of secondary education, the overall provision of education remains inadequate in relation to equity considerations. Although impressive quantitative expansion has occurred, access to educational opportunities in Kenya is still not evenly distributed with respect to gender and region. With regard to regional inequalities in the provision of education, it clearly emerges from this analysis that educational benefits are distributed in favor of the economically and politically dominant districts and provinces in the country. It is argued that, despite the state's ceding of most of its influence on the educational arena to the civil society, educational outcomes are still largely determined, directly or indirectly, by structures instituted, or supported, by the state. The paper demonstrates how an intricate interplay of social, political, and economic factors has worked against the efforts of the state and the civil society to improve the quality of education and eradicate inequality in the provision of education in Kenya.
openalex: W4236793090
Keywords: openalex:import

AIDS Education in Cameroon: Assessing the Impact of "Teach English, Prevent AIDS" - Zibas, Crystal L. (1997)
openalex: W1488185608 mag: 1488185608
Keywords: openalex:import

Non-Formal Environmental Education: The Utilization of Solar Energy for Cooking in a Rural Area in Sudan. - Zubeir, Z. El (International Journal of Environmental Education and Information, 1997)
openalex: W277826286 mag: 277826286
Keywords: openalex:import